Closing the gap: Solving complex medically relevant genes at scale. - Mahmoud, Medhat; Harting, John; Corbitt, Holly; Chen, Xiao; Jhangiani, Shalini N; Harshavardhan Doddapaneni; Meng, Qingchang; Han, Tina; Lambert, Christine; Zhang, Siyuan; Baybayan, Primo; Henno, Geoff; et al. (medRxiv, 2024)
Comprehending the mechanism behind human diseases with an established heritable component represents the forefront of personalized medicine. Nevertheless, numerous medically important genes are inaccurately represented in short-read sequencing data analysis due to their complexity and repetitiveness or the so-called 'dark regions' of the human genome. The advent of PacBio as a long-read platform has provided new insights, yet HiFi whole-genome sequencing (WGS) cost remains frequently prohibitive. We introduce a targeted sequencing and analysis framework, Twist Alliance Dark Genes Panel (TADGP), designed to offer phased variants across 389 medically important yet complex autosomal genes. We highlight TADGP accuracy across eleven control samples and compare it to WGS. This demonstrates that TADGP achieves variant calling accuracy comparable to HiFi-WGS data, but at a fraction of the cost. Thus, enabling scalability and broad applicability for studying rare diseases or complementing previously sequenced samples to gain insights into these complex genes. TADGP revealed several candidate variants across all cases and provided insight into diversity when tested on samples from rare disease and cardiovascular disease cohorts. In both cohorts, we identified novel variants affecting individual disease-associated genes (e.g., ). Nevertheless, the annotation of the variants across these 389 medically important genes remains challenging due to their underrepresentation in ClinVar and gnomAD. Consequently, we also offer an annotation resource to enhance the evaluation and prioritization of these variants. Overall, we can demonstrate that TADGP offers a cost-efficient and scalable approach to routinely assess the dark regions of the human genome with clinical relevance.

Genetic sex validation for sample tracking in next-generation sequencing clinical testing. - Jianhong Hu; Korchina, Viktoriya; Zouk, Hana; Harden, Maegan V; Murdock, David; Macbeth, Alyssa; Harrison, Steven M; Lennon, Niall; Kovar, Christie; Balasubramanian, Adithya; Zhang, Lan; Chandanavelli, Gauthami; et al. (BMC Res Notes, 2024)
OBJECTIVE: Data from DNA genotyping via a 96-SNP panel in a study of 25,015 clinical samples were utilized for quality control and tracking of sample identity in a clinical sequencing network. The study aimed to demonstrate the value of both the precise SNP tracking and the utility of the panel for predicting the sex-by-genotype of the participants, to identify possible sample mix-ups. RESULTS: Precise SNP tracking showed no sample swap errors within the clinical testing laboratories. In contrast, when comparing predicted sex-by-genotype to the provided sex on the test requisition, we identified 110 inconsistencies from 25,015 clinical samples (0.44%), that had occurred during sample collection or accessioning. The genetic sex predictions were confirmed using additional SNP sites in the sequencing data or high-density genotyping arrays. It was determined that discrepancies resulted from clerical errors (49.09%), samples from transgender participants (3.64%) and stem cell or bone marrow transplant patients (7.27%) along with undetermined sample mix-ups (40%) for which sample swaps occurred prior to arrival at genome centers, however the exact cause of the events at the sampling sites resulting in the mix-ups were not able to be determined.
Keywords: Bone Marrow Transplantation; Clinical Laboratory Services; Genotype; High-Throughput Nucleotide Sequencing; Humans; Laboratories

Germline Genetic Testing and Survival Outcomes Among Children With Rhabdomyosarcoma: A Report From the Children's Oncology Group. - Martin-Giacalone, Bailey A; Li, He; Scheurer, Michael E; Casey, Dana L; Dugan-Perez, Shannon; Marquez-Do, Deborah A; Donna M Muzny; Richard A Gibbs; Barkauskas, Donald A; Hall, David; Stewart, Douglas R; Schiffman, Joshua D; et al. (JAMA Netw Open, 2024)
IMPORTANCE: Determining the impact of germline cancer-predisposition variants (CPVs) on outcomes could inform novel approaches to testing and treating children with rhabdomyosarcoma. OBJECTIVE: To assess whether CPVs are associated with outcome among children with rhabdomyosarcoma. DESIGN, SETTING, AND PARTICIPANTS: In this cohort study, data were obtained for individuals, aged 0.01-23.23 years, newly diagnosed with rhabdomyosarcoma who were treated across 171 Children's Oncology Group sites from March 15, 1999, to December 8, 2017. Data analysis was performed from June 16, 2021, to May 15, 2023. EXPOSURE: The presence of a CPV in 24 rhabdomyosarcoma-associated cancer-predisposition genes (CPGs) or an expanded set of 63 autosomal-dominant CPGs. MAIN OUTCOMES AND MEASURES: Overall survival (OS) and event-free survival (EFS) were the main outcomes, using the Kaplan-Meier estimator to assess survival probabilities and the Cox proportional hazards regression model to adjust for clinical covariates. Analyses were stratified by tumor histology and the fusion status of PAX3 or PAX7 to the FOXO1 gene. RESULTS: In this study of 580 individuals with rhabdomyosarcoma, the median patient age was 5.9 years (range, 0.01-23.23 years), and the male-to-female ratio was 1.5 to 1 (351 [60.5%] male). For patients with CPVs in rhabdomyosarcoma-associated CPGs, EFS was 48.4% compared with 57.8% for patients without a CPV (P = .10), and OS was 53.7% compared with 65.3% for patients without a CPV (P = .06). After adjustment, patients with CPVs had significantly worse OS (adjusted hazard ratio [AHR], 2.49 [95% CI, 1.39-4.45]; P = .002), and the outcomes were not better among patients with embryonal histology (EFS: AHR, 2.25 [95% CI, 1.25-4.06]; P = .007]; OS: AHR, 2.83 [95% CI, 1.47-5.43]; P = .002]). These associations were not due to the development of a second malignant neoplasm, and importantly, patients with fusion-negative rhabdomyosarcoma who harbored a CPV had similarly inferior outcomes as patients with fusion-positive rhabdomyosarcoma without CPVs (EFS: AHR, 1.35 [95% CI, 0.71-2.59]; P = .37; OS: AHR, 1.71 [95% CI, 0.84-3.47]; P = .14). There were no significant differences in outcome by CPV status of the 63 CPG set. CONCLUSIONS AND RELEVANCE: This cohort study identified a group of patients with embryonal rhabdomyosarcoma who had a particularly poor outcome. Other important clinical findings included that individuals with TP53 had poor outcomes independent of second malignant neoplasms and that patients with fusion-negative rhabdomyosarcoma who harbored a CPV had outcomes comparable to patients with fusion-positive rhabdomyosarcoma. These findings suggest that germline CPV testing may aid in clinical prognosis and should be considered in prospective risk-based clinical trials.
Keywords: Child; Cohort Studies; Female; Genetic Testing; Germ Cells; Humans; Male; Neoplasms, Second Primary; Prospective Studies; Rhabdomyosarcoma

HMZDupFinder: a robust computational approach for detecting intragenic homozygous duplications from exome sequencing data. - Du, Haowei; Dardas, Zain; Jolly, Angad; Grochowski, Christopher M; Jhangiani, Shalini N; Li, He; Donna M Muzny; Fatih, Jawid M; Yesil, Gozde; Elcioglu, Nursel H; Gezdirici, Alper; Marafi, Dana; et al. (Nucleic Acids Res, 2024)
Homozygous duplications contribute to genetic disease by altering gene dosage or disrupting gene regulation and can be more deleterious to organismal biology than heterozygous duplications. Intragenic exonic duplications can result in loss-of-function (LoF) or gain-of-function (GoF) alleles that when homozygosed, i.e. brought to homozygous state at a locus by identity by descent or state, could potentially result in autosomal recessive (AR) rare disease traits. However, the detection and functional interpretation of homozygous duplications from exome sequencing data remains a challenge. We developed a framework algorithm, HMZDupFinder, that is designed to detect exonic homozygous duplications from exome sequencing (ES) data. The HMZDupFinder algorithm can efficiently process large datasets and accurately identifies small intragenic duplications, including those associated with rare disease traits. HMZDupFinder called 965 homozygous duplications with three or less exons from 8,707 ES with a recall rate of 70.9% and a precision of 16.1%. We experimentally confirmed 8/10 rare homozygous duplications. Pathogenicity assessment of these copy number variant alleles allowed clinical genomics contextualization for three homozygous duplications alleles, including two affecting known OMIM disease genes EDAR (MIM# 224900), TNNT1(MIM# 605355), and one variant in a novel candidate disease gene: PAAF1.
Keywords: Adaptor Proteins, Signal Transducing; DNA Copy Number Variations; Exome Sequencing; Homozygote; Humans; Rare Diseases; Software

Inter and intra-host diversity of RSV in hematopoietic stem cell transplant adults with normal and delayed viral clearance. - Avadhanula, Vasanthi; Agustinho, Daniel Paiva; Menon, Vipin Kumar; Chemaly, Roy F; Shah, Dimpy P; Qin, Xiang; Surathu, Anil; Harshavardhan Doddapaneni; Donna M Muzny; Ginger A Metcalf; Cregeen, Sara Javornik; Richard A Gibbs; et al. (Virus Evol, 2024)
Respiratory syncytial virus (RSV) infection in immunocompromised individuals often leads to prolonged illness, progression to severe lower respiratory tract infection, and even death. How the host immune environment of the hematopoietic stem cell transplant (HCT) adults can affect viral genetic variation during an acute infection is not understood well. In the present study, we performed whole genome sequencing of RSV/A or RSV/B from samples collected longitudinally from HCT adults with normal (<14 days) and delayed (≥14 days) RSV clearance who were enrolled in a ribavirin trial. We determined the inter-host and intra-host genetic variation of RSV and the effect of mutations on putative glycosylation sites. The inter-host variation of RSV is centered in the attachment (G) and fusion (F) glycoprotein genes followed by polymerase (L) and matrix (M) genes. Interestingly, the overall genetic variation was constant between normal and delayed clearance groups for both RSV/A and RSV/B. Intra-host variation primarily occurred in the G gene followed by non-structural protein (NS1) and L genes; however, gain or loss of stop codons and frameshift mutations appeared only in the G gene and only in the delayed viral clearance group. Potential gain or loss of O-linked glycosylation sites in the G gene occurred both in RSV/A and RSV/B isolates. For RSV F gene, loss of N-linked glycosylation site occurred in three RSV/B isolates within an antigenic epitope. Both oral and aerosolized ribavirin did not cause any mutations in the L gene. In summary, prolonged viral shedding and immune deficiency resulted in RSV variation, especially in structural mutations in the G gene, possibly associated with immune evasion. Therefore, sequencing and monitoring of RSV isolates from immunocompromised patients are crucial as they can create escape mutants that can impact the effectiveness of upcoming vaccines and treatments.

NODAL variants are associated with a continuum of laterality defects from simple D-transposition of the great arteries to heterotaxy. - Dardas, Zain; Fatih, Jawid M; Jolly, Angad; Dawood, Moez; Du, Haowei; Grochowski, Christopher M; Jones, Edward G; Jhangiani, Shalini N; Wehrens, Xander H T; Liu, Pengfei; Bi, Weimin; Eric Boerwinkle; et al. (Genome Med, 2024)
BACKGROUND: NODAL signaling plays a critical role in embryonic patterning and heart development in vertebrates. Genetic variants resulting in perturbations of the TGF-β/NODAL signaling pathway have reproducibly been shown to cause laterality defects in humans. To further explore this association and improve genetic diagnosis, the study aims to identify and characterize a broader range of NODAL variants in a large number of individuals with laterality defects. METHODS: We re-analyzed a cohort of 321 proband-only exomes of individuals with clinically diagnosed laterality congenital heart disease (CHD) using family-based, rare variant genomic analyses. To this cohort we added 12 affected subjects with known NODAL variants and CHD from institutional research and clinical cohorts to investigate an allelic series. For those with candidate contributory variants, variant allele confirmation and segregation analysis were studied by Sanger sequencing in available family members. Array comparative genomic hybridization and droplet digital PCR were utilized for copy number variants (CNV) validation and characterization. We performed Human Phenotype Ontology (HPO)-based quantitative phenotypic analyses to dissect allele-specific phenotypic differences. RESULTS: Missense, nonsense, splice site, indels, and/or structural variants of NODAL were identified as potential causes of heterotaxy and other laterality defects in 33 CHD cases. We describe a recurrent complex indel variant for which the nucleic acid secondary structure predictions implicate secondary structure mutagenesis as a possible mechanism for formation. We identified two CNV deletion alleles spanning NODAL in two unrelated CHD cases. Furthermore, 17 CHD individuals were found (16/17 with known Hispanic ancestry) to have the c.778G > A:p.G260R NODAL missense variant which we propose reclassification from variant of uncertain significance (VUS) to likely pathogenic. Quantitative HPO-based analyses of the observed clinical phenotype for all cases with p.G260R variation, including heterozygous, homozygous, and compound heterozygous cases, reveal clustering of individuals with biallelic variation. This finding provides evidence for a genotypic-phenotypic correlation and an allele-specific gene dosage model. CONCLUSION: Our data further support a role for rare deleterious variants in NODAL as a cause for sporadic human laterality defects, expand the repertoire of observed anatomical complexity of potential cardiovascular anomalies, and implicate an allele specific gene dosage model.
Keywords: Animals; Arteries; Comparative Genomic Hybridization; Heart Defects, Congenital; Heterotaxy Syndrome; Humans; Phenotype; Transposition of Great Vessels

Somatic mutations of esophageal adenocarcinoma: a comparison between Black and White patients. - Lim, Hyeyeun; Marie-Claude Gingras; Zhao, Jing; Byun, Jinyoung; Castro, Patricia D; Tsavachidis, Spiridon; Jianhong Hu; Harshavardhan Doddapaneni; Yi Han; Donna M Muzny; Richard A Gibbs; Amos, Christopher I; et al. (Sci Rep, 2024)
Esophageal adenocarcinoma is the most common histological subtype of esophageal cancer in Western countries and shows poor prognosis with rapid growth. EAC is characterized by a strong male predominance and racial disparity. EAC is up to fivefold more common among Whites than Blacks, yet Black patients with EAC have poorer survival rates. The racial disparity remains largely unknown, and there is limited knowledge of mutations in EAC regarding racial disparities. We used whole-exome sequencing to show somatic mutation profiles derived from tumor samples from 18 EAC male patients. We identified three molecular subgroups based on the pre-defined esophageal cancer-specific mutational signatures. Group 1 is associated with age and NTHL1 deficiency-related signatures. Group 2 occurs primarily in Black patients and is associated with signatures related to DNA damage from oxidative stress and NTHL1 deficiency-related signatures. Group 3 is associated with defective homologous recombination-based DNA often caused by BRCA mutation in White patients. We observed significantly mutated race related genes (LCE2B in Black, SDR39U1 in White) were (q-value < 0.1). Our findings underscore the possibility of distinct molecular mutation patterns in EAC among different races. Further studies are needed to validate our findings, which could contribute to precision medicine in EAC.
Keywords: Adenocarcinoma; Black or African American; Esophageal Neoplasms; Exome Sequencing; Female; Humans; Male; Mutation; White

A biallelic frameshift indel in PPP1R35 as a cause of primary microcephaly. - Dawood, Moez; Akay, Gulsen; Mitani, Tadahiro; Marafi, Dana; Fatih, Jawid M; Gezdirici, Alper; Najmabadi, Hossein; Kahrizi, Kimia; Punetha, Jaya; Grochowski, Christopher M; Du, Haowei; Jolly, Angad; et al. (Am J Med Genet A, 2023)
Protein phosphatase 1 regulatory subunit 35 (PPP1R35) encodes a centrosomal protein required for recruiting microtubule-binding elongation machinery. Several proteins in this centriole biogenesis pathway correspond to established primary microcephaly (MCPH) genes, and multiple model organism studies hypothesize PPP1R35 as a candidate MCPH gene. Here, using exome sequencing (ES) and family-based rare variant analyses, we report a homozygous, frameshifting indel deleting the canonical stop codon in the last exon of PPP1R35 [Chr7: c.753_*3delGGAAGCGTAGACCinsCG (p.Trp251Cysfs*22)]; the variant allele maps in a 3.7 Mb block of absence of heterozygosity (AOH) in a proband with severe MCPH (-4.3 SD at birth, -6.1 SD by 42 months), pachygyria, and global developmental delay from a consanguineous Turkish kindred. Droplet digital PCR (ddPCR) confirmed mutant mRNA expression in fibroblasts. In silico prediction of the translation of mutant PPP1R35 is expected to be elongated by 18 amino acids before encountering a downstream stop codon. This complex indel allele is absent in public databases (ClinVar, gnomAD, ARIC, 1000 genomes) and our in-house database of 14,000+ exomes including 1800+ Turkish exomes supporting predicted pathogenicity. Comprehensive literature searches for PPP1R35 variants yielded two probands affected with severe microcephaly (-15 SD and -12 SD) with the same homozygous indel from a single, consanguineous, Iranian family from a cohort of 404 predominantly Iranian families. The lack of heterozygous cases in two large cohorts representative of the genetic background of these two families decreased our suspicion of a founder allele and supports the contention of a recurrent mutation. We propose two potential secondary structure mutagenesis models for the origin of this variant allele mediated by hairpin formation between complementary GC rich segments flanking the stop codon via secondary structure mutagenesis.
Keywords: Codon, Terminator; Frameshift Mutation; Humans; Infant, Newborn; Iran; Microcephaly; Microtubule-Associated Proteins; Pedigree

Circulating tumor DNA sequencing of pediatric solid and brain tumor patients: An institutional feasibility study. - Mangum, Ross; Reuther, Jacquelyn; Sen Baksi, Koel; Gandhi, Ilavarasi; Zabriskie, Ryan C; Recinos, Alva; Raesz-Martinez, Robin; Lin, Frank Y; Potter, Samara L; Sher, Andrew C; Kralik, Stephen F; Mohila, Carrie A; et al. (Pediatr Hematol Oncol, 2023)
The potential of circulating tumor DNA (ctDNA) analysis to serve as a real-time "liquid biopsy" for children with central nervous system (CNS) and non-CNS solid tumors remains to be fully elucidated. We conducted a study to investigate the feasibility and potential clinical utility of ctDNA sequencing in pediatric patients enrolled on an institutional clinical genomics trial. A total of 240 patients had tumor DNA profiling performed during the study period. Plasma samples were collected at study enrollment from 217 patients and then longitudinally from a subset of patients. Successful cell-free DNA extraction and quantification occurred in 216 of 217 (99.5%) of these initial samples. Twenty-four patients were identified whose tumors harbored 30 unique variants that were potentially detectable on a commercially-available ctDNA panel. Twenty of these 30 mutations (67%) were successfully detected by next-generation sequencing in the ctDNA from at least one plasma sample. The rate of ctDNA mutation detection was higher in patients with non-CNS solid tumors (7/9, 78%) compared to those with CNS tumors (9/15, 60%). A higher ctDNA mutation detection rate was also observed in patients with metastatic disease (9/10, 90%) compared to non-metastatic disease (7/14, 50%), although tumor-specific variants were detected in a few patients in the absence of radiographic evidence of disease. This study illustrates the feasibility of incorporating longitudinal ctDNA analysis into the management of relapsed or refractory patients with childhood CNS or non-CNS solid tumors.
Keywords: Biomarkers, Tumor; Brain Neoplasms; Child; Circulating Tumor DNA; Feasibility Studies; High-Throughput Nucleotide Sequencing; Humans; Mutation

Exome-wide assessment of isolated biliary atresia: A report from the National Birth Defects Prevention Study using child-parent trios and a case-control design to identify novel rare variants. - Sok, Pagna; Aniko Sabo; Almli, Lynn M; Jenkins, Mary M; Nembhard, Wendy N; Agopian, A J; Bamshad, Michael J; Blue, Elizabeth E; Brody, Lawrence C; Brown, Austin L; Browne, Marilyn L; Canfield, Mark A; et al. (Am J Med Genet A, 2023)
The etiology of biliary atresia (BA) is unknown, but recent studies suggest a role for rare protein-altering variants (PAVs). Exome sequencing data from the National Birth Defects Prevention Study on 54 child-parent trios, one child-mother duo, and 1513 parents of children with other birth defects were analyzed. Most (91%) cases were isolated BA. We performed (1) a trio-based analysis to identify rare de novo, homozygous, and compound heterozygous PAVs and (2) a case-control analysis using a sequence kernel-based association test to identify genes enriched with rare PAVs. While we replicated previous findings on PKD1L1, our results do not suggest that recurrent de novo PAVs play important roles in BA susceptibility. In fact, our finding in NOTCH2, a disease gene associated with Alagille syndrome, highlights the difficulty in BA diagnosis. Notably, IFRD2 has been implicated in other gastrointestinal conditions and warrants additional study. Overall, our findings strengthen the hypothesis that the etiology of BA is complex.
Keywords: Biliary Atresia; Case-Control Studies; Exome; Homozygote; Humans; Membrane Proteins; Parents

Genetic Sex Validation for Sample Tracking in Clinical Testing. - Jianhong Hu; Korchina, Viktoriya; Zouk, Hana; Harden, Maegan V; Murdock, David; Macbeth, Alyssa; Harrison, Steven M; Lennon, Niall; Kovar, Christie; Balasubramanian, Adithya; Zhang, Lan; Chandanavelli, Gauthami; et al. (Res Sq, 2023)
OBJECTIVE: Data from DNA genotyping via a 96-SNP panel in a study of 25,015 clinical samples were utilized for quality control and tracking of sample identity in a clinical sequencing network. The study aimed to demonstrate the value of both the precise SNP tracking and the utility of the panel for predicting the sex-by-genotype of the participants, to identify possible sample mix-ups. RESULTS: Precise SNP tracking showed no sample swap errors within the clinical testing laboratories. In contrast, when comparing predicted sex-by-genotype to the provided sex on the test requisition, we identified 110 inconsistencies from 25,015 clinical samples (0.44%), that had occurred during sample collection or accessioning. The genetic sex predictions were confirmed using additional SNP sites in the sequencing data or high-density genotyping arrays. It was determined that discrepancies resulted from clerical errors, samples from transgender participants and stem cell or bone marrow transplant patients along with undetermined sample mix-ups.

The genomic landscape of familial glioma. - Choi, Dong-Joo; Armstrong, Georgina; Lozzi, Brittney; Vijayaraghavan, Prashanth; Plon, Sharon E; Wong, Terence C; Eric Boerwinkle; Donna M Muzny; Chen, Hsiao-Chi; Richard A Gibbs; Ostrom, Quinn T; Melin, Beatrice; et al. (Sci Adv, 2023)
Glioma is a rare brain tumor with a poor prognosis. Familial glioma is a subset of glioma with a strong genetic predisposition that accounts for approximately 5% of glioma cases. We performed whole-genome sequencing on an exploratory cohort of 203 individuals from 189 families with a history of familial glioma and an additional validation cohort of 122 individuals from 115 families. We found significant enrichment of rare deleterious variants of seven genes in both cohorts, and the most significantly enriched gene was ( = 0.0006). Furthermore, we identified rare noncoding variants in both cohorts that were predicted to affect transcription factor binding sites or cause cryptic splicing. Last, we selected a subset of discovered genes for validation by CRISPR knockdown screening and found that , have profound impacts on proliferation. This study performs comprehensive surveillance of the genomic landscape of familial glioma.
Keywords: Brain Neoplasms; Calcium-Binding Proteins; DNA-Binding Proteins; Genetic Predisposition to Disease; Genomics; Glioma; Humans; Tumor Suppressor Proteins; Whole Genome Sequencing

Identification of allele-specific KIV-2 repeats and impact on Lp(a) measurements for cardiovascular disease risk. - Behera, S; Belyeu, J R; Chen, X; Paulin, L F; Nguyen, N Q H; Newman, E; Mahmoud, M; Menon, V K; Qi, Q; Joshi, P; Marcovina, S; Rossi, M; et al. (bioRxiv, 2023)
The abundance of Lp(a) protein holds significant implications for the risk of cardiovascular disease (CVD), which is directly impacted by the copy number (CN) of KIV-2, a 5.5 kbp sub-region. KIV-2 is highly polymorphic in the population and accurate analysis is challenging. In this study, we present the DRAGEN KIV-2 CN caller, which utilizes short reads. Data across 166 WGS show that the caller has high accuracy, compared to optical mapping and can further phase ~50% of the samples. We compared KIV-2 CN numbers to 24 previously postulated KIV-2 relevant SNVs, revealing that many are ineffective predictors of KIV-2 copy number. Population studies, including USA-based cohorts, showed distinct KIV-2 CN, distributions for European-, African-, and Hispanic-American populations and further underscored the limitations of SNV predictors. We demonstrate that the CN estimates correlate significantly with the available Lp(a) protein levels and that phasing is highly important.

Identification of USP9X as a leukemia susceptibility gene. - Sisoudiya, Saumya Dushyant; Mishra, Pamela; Li, He; Schraw, Jeremy M; Scheurer, Michael E; Salvi, Sejal; Harshavardhan Doddapaneni; Donna M Muzny; Mitchell, Danielle; Taylor, Olga; Aniko Sabo; Lupo, Philip J; et al. (Blood Adv, 2023)
We recently reported that children with multiple birth defects have a significantly higher risk of childhood cancer. We performed whole-genome sequencing on a cohort of probands from this study with birth defects and cancer and their parents. Structural variant analysis identified a novel 5 kb de novo heterozygous inframe deletion overlapping the catalytic domain of USP9X in a female proband with multiple birth defects, developmental delay, and B-cell acute lymphoblastic leukemia (B-ALL). Her phenotype was consistent with female-restricted X-linked syndromic intellectual developmental disorder-99 (MRXS99F). Genotype-phenotype analysis including previously reported female probands (n = 42) demonstrated that MRXS99F probands with B-ALL (n = 3) clustered with subjects with loss-of-function (LoF) USP9X variants and multiple anomalies. The cumulative incidence of B-ALL among these female probands (7.1%) was significantly higher than an age- and sex-matched cohort (0.003%) from the Surveillance, Epidemiology, and End Results database (P < .0001, log-rank test). There are no reports of LoF variants in males. Males with hypomorphic missense variants have neurodevelopmental disorders without birth defects or leukemia risk. In contrast, in sporadic B-ALL, somatic LoF USP9X mutations occur in both males and females, and expression levels are comparable in leukemia samples from both sexes (P = .54), with the highest expressors being female patients with extra copies of the X-chromosome. Overall, we describe USP9X as a novel female-specific leukemia predisposition gene associated with multiple congenital, neurodevelopmental anomalies, and B-ALL risk. In contrast, USP9X serves as a tumor suppressor in sporadic pediatric B-ALL in both sexes, with low expression associated with poorer survival in patients with high-risk B-ALL.
Keywords: Female; Humans; Intellectual Disability; Leukemia; Loss of Function Mutation; Male; Mutation, Missense; Phenotype; Ubiquitin Thiolesterase

Longitudinal host transcriptional responses to SARS-CoV-2 infection in adults with extremely high viral load. - Avadhanula, Vasanthi; Creighton, Chad J; Ferlic-Stark, Laura; Sucgang, Richard; Zhang, Yiqun; Nagaraj, Divya; Nicholson, Erin G; Rajan, Anubama; Menon, Vipin Kumar; Harshavardhan Doddapaneni; Donna M Muzny; Ginger A Metcalf; et al. (bioRxiv, 2023)
Current understanding of viral dynamics of SARS-CoV-2 and host responses driving the pathogenic mechanisms in COVID-19 is rapidly evolving. Here, we conducted a longitudinal study to investigate gene expression patterns during acute SARS-CoV-2 illness. Cases included SARS-CoV-2 infected individuals with extremely high viral loads early in their illness, individuals having low SARS-CoV-2 viral loads early in their infection, and individuals testing negative for SARS-CoV-2. We could identify widespread transcriptional host responses to SARS-CoV-2 infection that were initially most strongly manifested in patients with extremely high initial viral loads, then attenuating within the patient over time as viral loads decreased. Genes correlated with SARS-CoV-2 viral load over time were similarly differentially expressed across independent datasets of SARS-CoV-2 infected lung and upper airway cells, from both in vitro systems and patient samples. We also generated expression data on the human nose organoid model during SARS-CoV-2 infection. The human nose organoid-generated host transcriptional response captured many aspects of responses observed in the above patient samples, while suggesting the existence of distinct host responses to SARS-CoV-2 depending on the cellular context, involving both epithelial and cellular immune responses. Our findings provide a catalog of SARS-CoV-2 host response genes changing over time.

Rare variant enrichment analysis supports as a contributory driver gene in the etiology of Mayer-Rokitansky-Küster-Hauser syndrome. - Jolly, Angad; Du, Haowei; Borel, Christelle; Chen, Na; Zhao, Sen; Grochowski, Christopher M; Duan, Ruizhi; Fatih, Jawid M; Dawood, Moez; Salvi, Sejal; Jhangiani, Shalini N; Donna M Muzny; et al. (HGG Adv, 2023)
Mayer-Rokitansky-Küster-Hauser (MRKH) syndrome is characterized by aplasia of the female reproductive tract; the syndrome can include renal anomalies, absence or dysgenesis, and skeletal anomalies. While functional models have elucidated several candidate genes, only (MIM: 603490) variants have been definitively associated with a subtype of MRKH with hyperandrogenism (MIM: 158330). DNA from 148 clinically diagnosed MRKH probands across 144 unrelated families and available family members from North America, Europe, and South America were exome sequenced (ES) and by family-based genomics analyzed for rare likely deleterious variants. A replication cohort consisting of 442 Han Chinese individuals with MRKH was used to further reproduce findings in diverse genetic backgrounds. Proband and OMIM phenotypes annotated using the Human Phenotype Ontology were analyzed to quantitatively delineate the phenotypic spectrum associated with variant alleles found in our MRKH cohort and those previously published. This study reports 18 novel variant alleles, 16 within a multiethnic MRKH cohort and two within a congenital scoliosis cohort. Cohort-wide analyses for a burden of rare variants within a single gene identified likely damaging variants in (MIM: 617782), a known disease gene for renal hypoplasia and uterine abnormalities (MIM: 617805), in 16 of 590 MRKH probands. variant alleles, including a CNV null allele, were found in 8 MRKH type 1 probands and 8 MRKH type II probands. This study used quantitative phenotypic analyses in a worldwide multiethnic cohort to identify and strengthen the association of to isolated uterine agenesis (MRKH type I) and syndromic MRKH type II.
Keywords: 46, XX Disorders of Sex Development; Female; Humans; Urogenital Abnormalities; Uterus

Author Correction: Comparative and demographic analysis of orang-utan genomes. - Locke, Devin P; Hillier, LaDeana W; Warren, Wesley C; Kim C Worley; Nazareth, Lynne V; Donna M Muzny; Yang, Shiaw-Pyng; Wang, Zhengyuan; Chinwalla, Asif T; Minx, Pat; Mitreva, Makedonka; Cook, Lisa; et al. (Nature, 2022)

Clinical and molecular features of pediatric cancer patients with Lynch syndrome. - Scollon, Sarah; Eldomery, Mohammad K; Reuther, Jacquelyn; Lin, Frank Y; Potter, Samara L; Desrosiers, Lauren; McClain, Kenneth L; Smith, Valeria; Su, Jack Meng-Fen; Venkatramani, Rajkumar; Jianhong Hu; Korchina, Viktoriya; et al. (Pediatr Blood Cancer, 2022)
BACKGROUND: The association of childhood cancer with Lynch syndrome is not established compared with the significant pediatric cancer risk in recessive constitutional mismatch repair deficiency syndrome (CMMRD). PROCEDURE: We describe the clinical features, germline analysis, and tumor genomic profiling of patients with Lynch syndrome among patients enrolled in pediatric cancer genomic studies. RESULTS: There were six of 773 (0.8%) pediatric patients with solid tumors identified with Lynch syndrome, defined as a germline heterozygous pathogenic variant in one of the mismatch repair (MMR) genes (three with MSH6, two with MLH1, and one with MSH2). Tumor analysis demonstrated evidence for somatic second hits and/or increased tumor mutation burden in three of four patients with available tumor with potential implications for therapy and identification of at-risk family members. Only one patient met current guidelines for pediatric cancer genetics evaluation at the time of tumor diagnosis. CONCLUSION: Approximately 1% of children with cancer have Lynch syndrome, which is missed with current referral guidelines, suggesting the importance of adding MMR genes to tumor and hereditary pediatric cancer panels. Tumor analysis may provide the first suggestion of an underlying cancer predisposition syndrome and is useful in distinguishing between Lynch syndrome and CMMRD.
Keywords: Brain Neoplasms; Child; Colorectal Neoplasms; Colorectal Neoplasms, Hereditary Nonpolyposis; DNA Mismatch Repair; DNA-Binding Proteins; Germ-Line Mutation; Humans; MutL Protein Homolog 1; MutS Homolog 2 Protein; Neoplastic Syndromes, Hereditary

Construction of a new chromosome-scale, long-read reference genome assembly for the Syrian hamster, Mesocricetus auratus. - R. Alan Harris; Raveendran, Muthuswamy; Lyfoung, Dustin T; Fritz J Sedlazeck; Mahmoud, Medhat; Prall, Trent M; Karl, Julie A; Harshavardhan Doddapaneni; Meng, Qingchang; Yi Han; Donna M Muzny; Wiseman, Roger W; et al. (Gigascience, 2022)
BACKGROUND: The Syrian hamster (Mesocricetus auratus) has been suggested as a useful mammalian model for a variety of diseases and infections, including infection with respiratory viruses such as SARS-CoV-2. The MesAur1.0 genome assembly was generated in 2013 using whole-genome shotgun sequencing with short-read sequence data. Current more advanced sequencing technologies and assembly methods now permit the generation of near-complete genome assemblies with higher quality and greater continuity. FINDINGS: Here, we report an improved assembly of the M. auratus genome (BCM_Maur_2.0) using Oxford Nanopore Technologies long-read sequencing to produce a chromosome-scale assembly. The total length of the new assembly is 2.46 Gb, similar to the 2.50-Gb length of a previous assembly of this genome, MesAur1.0. BCM_Maur_2.0 exhibits significantly improved continuity, with a scaffold N50 that is 6.7 times greater than MesAur1.0. Furthermore, 21,616 protein-coding genes and 10,459 noncoding genes are annotated in BCM_Maur_2.0 compared to 20,495 protein-coding genes and 4,168 noncoding genes in MesAur1.0. This new assembly also improves the unresolved regions as measured by nucleotide ambiguities, where ∼17.11% of bases in MesAur1.0 were unresolved compared to BCM_Maur_2.0, in which the number of unresolved bases is reduced to 3.00%. CONCLUSIONS: Access to a more complete reference genome with improved accuracy and continuity will facilitate more detailed, comprehensive, and meaningful research results for a wide variety of future studies using Syrian hamsters as models.
Keywords: Animals; Chromosomes, Mammalian; Genome; High-Throughput Nucleotide Sequencing; Mesocricetus; Whole Genome Sequencing

Distinct somatic DICER1 hotspot mutations in three metachronous ovarian Sertoli-Leydig cell tumors in a patient with DICER1 syndrome. - Garcia, Annie; Desrosiers, Lauren; Scollon, Sarah; Gruner, Stephanie; Reuther, Jacquelyn; Gandhi, Ilavarasi; Patil, Ninad; Fuller, Maren Y; Dai, Hongzheng; Donna M Muzny; Richard A Gibbs; Bercaw-Pratt, Jennifer L; et al. (Cancer Genet, 2022)
Keywords: DEAD-box RNA Helicases; Female; Humans; Mutation; Ovarian Neoplasms; Ribonuclease III; Sertoli-Leydig Cell Tumor

Fully resolved assembly of Cryptosporidium parvum. - Vipin Menon; Okhuysen, Pablo C; Chappell, Cynthia L; Mahmoud, Medhat; Mahmoud, Medhat; Meng, Qingchang; Harshavardhan Doddapaneni; Vee, Vanesa; Yi Han; Salvi, Sejal; Bhamidipati, Sravya; Kottapalli, Kavya; et al. (Gigascience, 2022)
BACKGROUND: Cryptosporidium parvum is an apicomplexan parasite commonly found across many host species with a global infection prevalence in human populations of 7.6%. Understanding its diversity and genomic makeup can help in fighting established infections and prohibiting further transmission. The basis of every genomic study is a high-quality reference genome that has continuity and completeness, thus enabling comprehensive comparative studies. FINDINGS: Here, we provide a highly accurate and complete reference genome of Cryptosporidium parvum. The assembly is based on Oxford Nanopore reads and was improved using Illumina reads for error correction. We also outline how to evaluate and choose from different assembly methods based on 2 main approaches that can be applied to other Cryptosporidium species. The assembly encompasses 8 chromosomes and includes 13 telomeres that were resolved. Overall, the assembly shows a high completion rate with 98.4% single-copy BUSCO genes. CONCLUSIONS: This high-quality reference genome of a zoonotic IIaA17G2R1 C. parvum subtype isolate provides the basis for subsequent comparative genomic studies across the Cryptosporidium clade. This will enable improved understanding of diversity, functional, and association studies.
Keywords: Cryptosporidiosis; Cryptosporidium; Cryptosporidium parvum; Genome; Genomics; Humans

Genetic errors of immunity distinguish pediatric nonmalignant lymphoproliferative disorders. - Forbes, Lisa R; Eckstein, Olive S; Gulati, Nitya; Peckham-Gregory, Erin C; Ozuah, Nmazuo W; Lubega, Joseph; El-Mallawany, Nader K; Agrusa, Jennifer E; Poli, M Cecilia; Vogel, Tiphanie P; Chaimowitz, Natalia S; Rider, Nicholas L; et al. (J Allergy Clin Immunol, 2022)
BACKGROUND: Pediatric nonmalignant lymphoproliferative disorders (PLPDs) are clinically and genetically heterogeneous. Long-standing immune dysregulation and lymphoproliferation in children may be life-threatening, and a paucity of data exists to guide evaluation and treatment of children with PLPD. OBJECTIVE: The primary objective of this study was to ascertain the spectrum of genomic immunologic defects in PLPD. Secondary objectives included characterization of clinical outcomes and associations between genetic diagnoses and those outcomes. METHODS: PLPD was defined by persistent lymphadenopathy, lymph organ involvement, or lymphocytic infiltration for more than 3 months, with or without chronic or significant Epstein-Barr virus (EBV) infection. Fifty-one subjects from 47 different families with PLPD were analyzed using whole exome sequencing. RESULTS: Whole exome sequencing identified likely genetic errors of immunity in 51% to 62% of families (53% to 65% of affected children). Presence of a genetic etiology was associated with younger age and hemophagocytic lymphohistiocytosis. Ten-year survival for the cohort was 72.4%, and patients with viable genetic diagnoses had a higher survival rate (82%) compared to children without a genetic explanation (48%, P = .03). Survival outcomes for individuals with EBV-associated disease and no genetic explanation were particularly worse than outcomes for subjects with EBV-associated disease and a genetic explanation (17% vs 90%; P = .002). Ascertainment of a molecular diagnosis provided targetable treatment options for up to 18 individuals and led to active management changes for 12 patients. CONCLUSIONS: PLPD defines children at high risk for mortality, and whole exome sequencing informs clinical risks and therapeutic opportunities for this diagnosis.
Keywords: Adolescent; Autoimmunity; Child; Child, Preschool; Exome Sequencing; Female; Genetic Association Studies; Genetic Testing; Herpesvirus 4, Human; Humans; Immunity; Infant; Lymphoproliferative Disorders; Male; Young Adult

Genome Sequencing in the Parkinson Disease Clinic. - Hill, Emily J; Robak, Laurie A; Al-Ouran, Rami; Deger, Jennifer; Fong, Jamie C; Vandeventer, Paul Jerrod; Schulman, Emily; Rao, Sindhu; Saade, Hiba; Savitt, Joseph M; von Coelln, Rainer; Desai, Neeja; et al. (Neurol Genet, 2022)
BACKGROUND AND OBJECTIVES: Genetic variants affect both Parkinson disease (PD) risk and manifestations. Although genetic information is of potential interest to patients and clinicians, genetic testing is rarely performed during routine PD clinical care. The goal of this study was to examine interest in comprehensive genetic testing among patients with PD and document reactions to possible findings from genome sequencing in 2 academic movement disorder clinics. METHODS: In 203 subjects with PD (age = 63 years, 67% male), genome sequencing was performed and filtered using a custom panel, including 49 genes associated with PD, parkinsonism, or related disorders, as well as a 90-variant PD genetic risk score. Based on the results, 231 patients (age = 67 years, 63% male) were surveyed on interest in genetic testing and responses to vignettes covering (1) familial risk of PD (); (2) risk of PD dementia (); (3) PD genetic risk score; and (4) secondary, medically actionable variants (). RESULTS: Genome sequencing revealed a variant in 3% and a risk variant in 10% of our clinical sample. The genetic risk score was normally distributed, identifying 41 subjects with a high risk of PD. Medically actionable findings were discovered in 2 subjects (1%). In our survey, the majority (82%) responded that they would share a variant with relatives. Most registered unchanged or increased interest in testing when confronted with a potential risk for dementia or medically actionable findings, and most (75%) expressed interest in learning their PD genetic risk score. DISCUSSION: Our results highlight broad interest in comprehensive genetic testing among patients with PD and may facilitate integration of genome sequencing in clinical practice.

Implementation of preemptive DNA sequence-based pharmacogenomics testing across a large academic medical center: The Mayo-Baylor RIGHT 10K Study. - Wang, Liewei; Steven E Scherer; Bielinski, Suzette J; Donna M Muzny; Jones, Leila A; Black, John Logan; Moyer, Ann M; Giri, Jyothsna; Sharp, Richard R; Matey, Eric T; Wright, Jessica A; Oyen, Lance J; et al. (Genet Med, 2022)
PURPOSE: The Mayo-Baylor RIGHT 10K Study enabled preemptive, sequence-based pharmacogenomics (PGx)-driven drug prescribing practices in routine clinical care within a large cohort. We also generated the tools and resources necessary for clinical PGx implementation and identified challenges that need to be overcome. Furthermore, we measured the frequency of both common genetic variation for which clinical guidelines already exist and rare variation that could be detected by DNA sequencing, rather than genotyping. METHODS: Targeted oligonucleotide-capture sequencing of 77 pharmacogenes was performed using DNA from 10,077 consented Mayo Clinic Biobank volunteers. The resulting predicted drug response-related phenotypes for 13 genes, including CYP2D6 and HLA, affecting 21 drug-gene pairs, were deposited preemptively in the Mayo electronic health record. RESULTS: For the 13 pharmacogenes of interest, the genomes of 79% of participants carried clinically actionable variants in 3 or more genes, and DNA sequencing identified an average of 3.3 additional conservatively predicted deleterious variants that would not have been evident using genotyping. CONCLUSION: Implementation of preemptive rather than reactive and sequence-based rather than genotype-based PGx prescribing revealed nearly universal patient applicability and required integrated institution-wide resources to fully realize individualized drug therapy and to show more efficient use of health care resources.
Keywords: Academic Medical Centers; Base Sequence; Cytochrome P-450 CYP2D6; Genotype; Humans; Pharmacogenetics

Long read sequencing and expression studies of AHDC1 deletions in Xia-Gibbs syndrome reveal a novel genetic regulatory mechanism. - Chander, Varuna; Mahmoud, Medhat; Jianhong Hu; Dardas, Zain; Grochowski, Christopher M; Dawood, Moez; Khayat, Michael M; Li, He; Li, Shoudong; Jhangiani, Shalini; Korchina, Viktoriya; Shen, Hua; et al. (Hum Mutat, 2022)
Xia-Gibbs syndrome (XGS; MIM# 615829) is a rare mendelian disorder characterized by Development Delay (DD), intellectual disability (ID), and hypotonia. Individuals with XGS typically harbor de novo protein-truncating mutations in the AT-Hook DNA binding motif containing 1 (AHDC1) gene, although some missense mutations can also cause XGS. Large de novo heterozygous deletions that encompass the AHDC1 gene have also been ascribed as diagnostic for the disorder, without substantial evidence to support their pathogenicity. We analyzed 19 individuals with large contiguous deletions involving AHDC1, along with other genes. One individual bore the smallest known contiguous AHDC1 deletion (∼350 Kb), encompassing eight other genes within chr1p36.11 (Feline Gardner-Rasheed, IFI6, FAM76A, STX12, PPP1R8, THEMIS2, RPA2, SMPDL3B) and terminating within the first intron of AHDC1. The breakpoint junctions and phase of the deletion were identified using both short and long read sequencing (Oxford Nanopore). Quantification of RNA expression patterns in whole blood revealed that AHDC1 exhibited a mono-allelic expression pattern with no deficiency in overall AHDC1 expression levels, in contrast to the other deleted genes, which exhibited a 50% reduction in mRNA expression. These results suggest that AHDC1 expression in this individual is compensated by a novel regulatory mechanism and advances understanding of mutational and regulatory mechanisms in neurodevelopmental disorders.
Keywords: Abnormalities, Multiple; DNA-Binding Proteins; Endoribonucleases; Humans; Intellectual Disability; Musculoskeletal Abnormalities; Neurodevelopmental Disorders; Phosphoprotein Phosphatases; Qa-SNARE Proteins; RNA-Binding Proteins; Sphingomyelin Phosphodiesterase

The multiple de novo copy number variant (MdnCNV) phenomenon presents with peri-zygotic DNA mutational signatures and multilocus pathogenic variation. - Du, Haowei; Jolly, Angad; Grochowski, Christopher M; Bo Yuan; Dawood, Moez; Jhangiani, Shalini N; Li, He; Donna M Muzny; Fatih, Jawid M; Coban-Akdemir, Zeynep; Carlin, Mary Esther; Scheuerle, Angela E; et al. (Genome Med, 2022)
BACKGROUND: The multiple de novo copy number variant (MdnCNV) phenotype is described by having four or more constitutional de novo CNVs (dnCNVs) arising independently throughout the human genome within one generation. It is a rare peri-zygotic mutational event, previously reported to be seen once in every 12,000 individuals referred for genome-wide chromosomal microarray analysis due to congenital abnormalities. These rare families provide a unique opportunity to understand the genetic factors of peri-zygotic genome instability and the impact of dnCNV on human diseases. METHODS: Chromosomal microarray analysis (CMA), array-based comparative genomic hybridization, short- and long-read genome sequencing (GS) were performed on the newly identified MdnCNV family to identify de novo mutations including dnCNVs, de novo single-nucleotide variants (dnSNVs), and indels. Short-read GS was performed on four previously published MdnCNV families for dnSNV analysis. Trio-based rare variant analysis was performed on the newly identified individual and four previously published MdnCNV families to identify potential genetic etiologies contributing to the peri-zygotic genomic instability. Lin semantic similarity scores informed quantitative human phenotype ontology analysis on three MdnCNV families to identify gene(s) driving or contributing to the clinical phenotype. RESULTS: In the newly identified MdnCNV case, we revealed eight de novo tandem duplications, each ~ 1 Mb, with microhomology at 6/8 breakpoint junctions. Enrichment of de novo single-nucleotide variants (SNV; 6/79) and de novo indels (1/12) was found within 4 Mb of the dnCNV genomic regions. An elevated post-zygotic SNV mutation rate was observed in MdnCNV families. Maternal rare variant analyses identified three genes in distinct families that may contribute to the MdnCNV phenomenon. Phenotype analysis suggests that gene(s) within dnCNV regions contribute to the observed proband phenotype in 3/3 cases. CNVs in two cases, a contiguous gene duplication encompassing PMP22 and RAI1 and another duplication affecting NSD1 and SMARCC2, contribute to the clinically observed phenotypic manifestations. CONCLUSIONS: Characteristic features of dnCNVs reported here are consistent with a microhomology-mediated break-induced replication (MMBIR)-driven mechanism during the peri-zygotic period. Maternal genetic variants in DNA repair genes potentially contribute to peri-zygotic genomic instability. Variable phenotypic features were observed across a cohort of three MdnCNV probands, and computational quantitative phenotyping revealed that two out of three had evidence for the contribution of more than one genetic locus to the proband's phenotype supporting the hypothesis of de novo multilocus pathogenic variation (MPV) in those families.
Keywords: Comparative Genomic Hybridization; DNA; DNA Copy Number Variations; DNA-Binding Proteins; Genomic Instability; Humans; Mutation; Nucleotides; Transcription Factors

Novel pathogenic variants and quantitative phenotypic analyses of Robinow syndrome: WNT signaling perturbation and phenotypic variability. - Zhang, Chaofan; Jolly, Angad; Shayota, Brian J; Mazzeu, Juliana F; Du, Haowei; Dawood, Moez; Soper, Patricia Celestino; Ramalho de Lima, Ariadne; Ferreira, Barbara Merfort; Coban-Akdemir, Zeynep; White, Janson; Shears, Deborah; et al. (HGG Adv, 2022)
Robinow syndrome (RS) is a genetically heterogeneous disorder with six genes that converge on the WNT/planar cell polarity (PCP) signaling pathway implicated (, , , , , and ). RS is characterized by skeletal dysplasia and distinctive facial and physical characteristics. To further explore the genetic heterogeneity, paralog contribution, and phenotypic variability of RS, we investigated a cohort of 22 individuals clinically diagnosed with RS from 18 unrelated families. Pathogenic or likely pathogenic variants in genes associated with RS or RS phenocopies were identified in all 22 individuals, including the first variant to be reported in . We retrospectively collected medical records of 16 individuals from this cohort and extracted clinical descriptions from 52 previously published cases. We performed Human Phenotype Ontology (HPO) based quantitative phenotypic analyses to dissect allele-specific phenotypic differences. Individuals with variants clustered into two groups with demonstrable phenotypic differences between those with missense and truncating alleles. Probands with biallelic variants clustered together with the majority of probands carrying , , and variants, demonstrating no phenotypic distinction between the -autosomal recessive and dominant forms of RS. While phenotypically similar diseases on the RS differential matched through HPO analysis, clustering using phenotype similarity score placed RS-associated phenotypes in a unique cluster containing , , and apart from non-RS-associated paralogs. Through human phenotype analyses of this RS cohort and OMIM clinical synopses of Mendelian disease, this study begins to tease apart specific biologic roles for non-canonical WNT-pathway proteins.

Phenotypic and mutational spectrum of ROR2-related Robinow syndrome. - Lima, Ariadne R; Ferreira, Barbara M; Zhang, Chaofan; Jolly, Angad; Du, Haowei; White, Janson J; Dawood, Moez; Lins, Tulio C; Chiabai, Marcela A; van Beusekom, Ellen; Cordoba, Mara S; Caldas Rosa, Erica C C; et al. (Hum Mutat, 2022)
Robinow syndrome is characterized by a triad of craniofacial dysmorphisms, disproportionate-limb short stature, and genital hypoplasia. A significant degree of phenotypic variability seems to correlate with different genes/loci. Disturbances of the noncanonical WNT-pathway have been identified as the main cause of the syndrome. Biallelic variants in ROR2 cause an autosomal recessive form of the syndrome with distinctive skeletal findings. Twenty-two patients with a clinical diagnosis of autosomal recessive Robinow syndrome were screened for variants in ROR2 using multiple molecular approaches. We identified 25 putatively pathogenic ROR2 variants, 16 novel, including single nucleotide variants and exonic deletions. Detailed phenotypic analyses revealed that all subjects presented with a prominent forehead, hypertelorism, short nose, abnormality of the nasal tip, brachydactyly, mesomelic limb shortening, short stature, and genital hypoplasia in male patients. A total of 19 clinical features were present in more than 75% of the subjects, thus pointing to an overall uniformity of the phenotype. Disease-causing variants in ROR2, contribute to a clinically recognizable autosomal recessive trait phenotype with multiple skeletal defects. A comprehensive quantitative clinical evaluation of this cohort delineated the phenotypic spectrum of ROR2-related Robinow syndrome. The identification of exonic deletion variant alleles further supports the contention of a loss-of-function mechanism in the etiology of the syndrome.
Keywords: Craniofacial Abnormalities; Dwarfism; Genes, Recessive; Humans; Limb Deformities, Congenital; Male; Phenotype; Receptor Tyrosine Kinase-like Orphan Receptors; Urogenital Abnormalities

Polygenic transcriptome risk scores for COPD and lung function improve cross-ethnic portability of prediction in the NHLBI TOPMed program. - Hu, Xiaowei; Qiao, Dandi; Kim, Wonji; Moll, Matthew; Balte, Pallavi P; Lange, Leslie A; Bartz, Traci M; Kumar, Rajesh; Li, Xingnan; Yu, Bing; Cade, Brian E; Laurie, Cecelia A; et al. (Am J Hum Genet, 2022)
While polygenic risk scores (PRSs) enable early identification of genetic risk for chronic obstructive pulmonary disease (COPD), predictive performance is limited when the discovery and target populations are not well matched. Hypothesizing that the biological mechanisms of disease are shared across ancestry groups, we introduce a PrediXcan-derived polygenic transcriptome risk score (PTRS) to improve cross-ethnic portability of risk prediction. We constructed the PTRS using summary statistics from application of PrediXcan on large-scale GWASs of lung function (forced expiratory volume in 1 s [FEV] and its ratio to forced vital capacity [FEV/FVC]) in the UK Biobank. We examined prediction performance and cross-ethnic portability of PTRS through smoking-stratified analyses both on 29,381 multi-ethnic participants from TOPMed population/family-based cohorts and on 11,771 multi-ethnic participants from TOPMed COPD-enriched studies. Analyses were carried out for two dichotomous COPD traits (moderate-to-severe and severe COPD) and two quantitative lung function traits (FEV and FEV/FVC). While the proposed PTRS showed weaker associations with disease than PRS for European ancestry, the PTRS showed stronger association with COPD than PRS for African Americans (e.g., odds ratio [OR] = 1.24 [95% confidence interval [CI]: 1.08-1.43] for PTRS versus 1.10 [0.96-1.26] for PRS among heavy smokers with ≥ 40 pack-years of smoking) for moderate-to-severe COPD. Cross-ethnic portability of the PTRS was significantly higher than the PRS (paired t test p < 2.2 × 10 with portability gains ranging from 5% to 28%) for both dichotomous COPD traits and across all smoking strata. Our study demonstrates the value of PTRS for improved cross-ethnic portability compared to PRS in predicting COPD risk.
Keywords: Humans; Lung; National Heart, Lung, and Blood Institute (U.S.); Pulmonary Disease, Chronic Obstructive; Risk Factors; Transcriptome; United States

Proteogenomic Markers of Chemotherapy Resistance and Response in Triple-Negative Breast Cancer. - Anurag, Meenakshi; Jaehnig, Eric J; Krug, Karsten; Lei, Jonathan T; Bergstrom, Erik J; Kim, Beom-Jun; Vashist, Tanmayi D; Huynh, Anh Minh Tran; Dou, Yongchao; Gou, Xuxu; Huang, Chen; Shi, Zhiao; et al. (Cancer Discov, 2022)
UNLABELLED: Microscaled proteogenomics was deployed to probe the molecular basis for differential response to neoadjuvant carboplatin and docetaxel combination chemotherapy for triple-negative breast cancer (TNBC). Proteomic analyses of pretreatment patient biopsies uniquely revealed metabolic pathways, including oxidative phosphorylation, adipogenesis, and fatty acid metabolism, that were associated with resistance. Both proteomics and transcriptomics revealed that sensitivity was marked by elevation of DNA repair, E2F targets, G2-M checkpoint, interferon-gamma signaling, and immune-checkpoint components. Proteogenomic analyses of somatic copy-number aberrations identified a resistance-associated 19q13.31-33 deletion where LIG1, POLD1, and XRCC1 are located. In orthogonal datasets, LIG1 (DNA ligase I) gene deletion and/or low mRNA expression levels were associated with lack of pathologic complete response, higher chromosomal instability index (CIN), and poor prognosis in TNBC, as well as carboplatin-selective resistance in TNBC preclinical models. Hemizygous loss of LIG1 was also associated with higher CIN and poor prognosis in other cancer types, demonstrating broader clinical implications. SIGNIFICANCE: Proteogenomic analysis of triple-negative breast tumors revealed a complex landscape of chemotherapy response associations, including a 19q13.31-33 somatic deletion encoding genes serving lagging-strand DNA synthesis (LIG1, POLD1, and XRCC1), that correlate with lack of pathologic response, carboplatin-selective resistance, and, in pan-cancer studies, poor prognosis and CIN. This article is highlighted in the In This Issue feature, p. 2483.
Keywords: Antineoplastic Combined Chemotherapy Protocols; Carboplatin; Humans; Neoadjuvant Therapy; Proteogenomics; Proteomics; Triple Negative Breast Neoplasms; X-ray Repair Cross Complementing Protein 1

Rare coding variants in 35 genes associate with circulating lipid levels-A multi-ancestry analysis of 170,000 exomes. - Hindy, George; Dornbos, Peter; Chaffin, Mark D; Liu, Dajiang J; Wang, Minxian; Selvaraj, Margaret Sunitha; Zhang, David; Park, Joseph; Aguilar-Salinas, Carlos A; Antonacci-Fulton, Lucinda; Ardissino, Diego; Arnett, Donna K; et al. (Am J Hum Genet, 2022)
Large-scale gene sequencing studies for complex traits have the potential to identify causal genes with therapeutic implications. We performed gene-based association testing of blood lipid levels with rare (minor allele frequency < 1%) predicted damaging coding variation by using sequence data from >170,000 individuals from multiple ancestries: 97,493 European, 30,025 South Asian, 16,507 African, 16,440 Hispanic/Latino, 10,420 East Asian, and 1,182 Samoan. We identified 35 genes associated with circulating lipid levels; some of these genes have not been previously associated with lipid levels when using rare coding variation from population-based samples. We prioritize 32 genes in array-based genome-wide association study (GWAS) loci based on aggregations of rare coding variants; three (EVI5, SH2B3, and PLIN1) had no prior association of rare coding variants with lipid levels. Most of our associated genes showed evidence of association among multiple ancestries. Finally, we observed an enrichment of gene-based associations for low-density lipoprotein cholesterol drug target genes and for genes closest to GWAS index single-nucleotide polymorphisms (SNPs). Our results demonstrate that gene-based associations can be beneficial for drug target development and provide evidence that the gene closest to the array-based GWAS index SNP is often the functional gene for blood lipid levels.
Keywords: Alleles; Blood Glucose; Case-Control Studies; Computational Biology; Databases, Genetic; Diabetes Mellitus, Type 2; Exome; Genetic Predisposition to Disease; Genetic Variation; Genetics, Population; Genome-Wide Association Study; Humans; Lipid Metabolism; Lipids; Liver; Molecular Sequence Annotation; Multifactorial Inheritance; Open Reading Frames; Phenotype; Polymorphism, Single Nucleotide

Whole-exome sequencing of 14 389 individuals from the ESP and CHARGE consortia identifies novel rare variation associated with hemostatic factors. - Pankratz, Nathan; Wei, Peng; Brody, Jennifer A; Chen, Ming-Huei; de Vries, Paul S; Huffman, Jennifer E; Stimson, Mary Rachel; Auer, Paul L; Eric Boerwinkle; Cushman, Mary; de Maat, Moniek P M; Folsom, Aaron R; et al. (Hum Mol Genet, 2022)
Plasma levels of fibrinogen, coagulation factors VII and VIII and von Willebrand factor (vWF) are four intermediate phenotypes that are heritable and have been associated with the risk of clinical thrombotic events. To identify rare and low-frequency variants associated with these hemostatic factors, we conducted whole-exome sequencing in 10 860 individuals of European ancestry (EA) and 3529 African Americans (AAs) from the Cohorts for Heart and Aging Research in Genomic Epidemiology Consortium and the National Heart, Lung and Blood Institute's Exome Sequencing Project. Gene-based tests demonstrated significant associations with rare variation (minor allele frequency < 5%) in fibrinogen gamma chain (FGG) (with fibrinogen, P = 9.1 × 10-13), coagulation factor VII (F7) (with factor VII, P = 1.3 × 10-72; seven novel variants) and VWF (with factor VIII and vWF; P = 3.2 × 10-14; one novel variant). These eight novel rare variant associations were independent of the known common variants at these loci and tended to have much larger effect sizes. In addition, one of the rare novel variants in F7 was significantly associated with an increased risk of venous thromboembolism in AAs (Ile200Ser; rs141219108; P = 4.2 × 10-5). After restricting gene-based analyses to only loss-of-function variants, a novel significant association was detected and replicated between factor VIII levels and a stop-gain mutation exclusive to AAs (rs3211938) in CD36 molecule (CD36). This variant has previously been linked to dyslipidemia but not with the levels of a hemostatic factor. These efforts represent the largest integration of whole-exome sequence data from two national projects to identify genetic variation associated with plasma hemostatic factors.
Keywords: Exome Sequencing; Factor VII; Factor VIII; Fibrinogen; Hemostatics; Humans; Polymorphism, Single Nucleotide; von Willebrand Factor

Whole-genome sequencing as an investigational device for return of hereditary disease risk and pharmacogenomic results as part of the All of Us Research Program. - Eric Venner; Donna M Muzny; Smith, Joshua D; Kimberly Walker; Neben, Cynthia L; Lockwood, Christina M; Empey, Phillip E; Ginger A Metcalf; Kachulis, Chris; Mian, Sana; Musick, Anjene; Rehm, Heidi L; et al. (Genome Med, 2022)
BACKGROUND: The All of Us Research Program (AoURP, "the program") is an initiative, sponsored by the National Institutes of Health (NIH), that aims to enroll one million people (or more) across the USA. Through repeated engagement of participants, a research resource is being created to enable a variety of future observational and interventional studies. The program has also committed to genomic data generation and returning important health-related information to participants. METHODS: Whole-genome sequencing (WGS), variant calling processes, data interpretation, and return-of-results procedures had to be created and receive an Investigational Device Exemption (IDE) from the United States Food and Drug Administration (FDA). The performance of the entire workflow was assessed through the largest known cross-center, WGS-based, validation activity that was refined iteratively through interactions with the FDA over many months. RESULTS: The accuracy and precision of the WGS process as a device for the return of certain health-related genomic results was determined to be sufficient, and an IDE was granted. CONCLUSIONS: We present here both the process of navigating the IDE application process with the FDA and the results of the validation study as a guide to future projects which may need to follow a similar path. Changes to the program in the future will be covered in supplementary submissions to the IDE and will support additional variant classes, sample types, and any expansion to the reportable regions.
Keywords: Genomics; Humans; Pharmacogenetics; Population Health; United States; Whole Genome Sequencing

xAtlas: scalable small variant calling across heterogeneous next-generation sequencing experiments. - Farek, Jesse; Hughes, Daniel; Salerno, William; Zhu, Yiming; Pisupati, Aishwarya; Mansfield, Adam; Krasheninina, Olga; English, Adam C; Ginger A Metcalf; Eric Boerwinkle; Donna M Muzny; Richard A Gibbs; et al. (Gigascience, 2022)
BACKGROUND: The growing volume and heterogeneity of next-generation sequencing (NGS) data complicate the further optimization of identifying DNA variation, especially considering that curated high-confidence variant call sets frequently used to validate these methods are generally developed from the analysis of comparatively small and homogeneous sample sets. FINDINGS: We have developed xAtlas, a single-sample variant caller for single-nucleotide variants (SNVs) and small insertions and deletions (indels) in NGS data. xAtlas features rapid runtimes, support for CRAM and gVCF file formats, and retraining capabilities. xAtlas reports SNVs with 99.11% recall and 98.43% precision across a reference HG002 sample at 60× whole-genome coverage in less than 2 CPU hours. Applying xAtlas to 3,202 samples at 30× whole-genome coverage from the 1000 Genomes Project achieves an average runtime of 1.7 hours per sample and a clear separation of the individual populations in principal component analysis across called SNVs. CONCLUSIONS: xAtlas is a fast, lightweight, and accurate SNV and small indel calling method. Source code for xAtlas is available under a BSD 3-clause license at https://github.com/jfarek/xatlas.
Keywords: Algorithms; Genome; High-Throughput Nucleotide Sequencing; INDEL Mutation; Polymorphism, Single Nucleotide; Software

Author Correction: High-depth African genomes inform human migration and health. - Choudhury, Ananyo; Aron, Shaun; Botigué, Laura R; Sengupta, Dhriti; Botha, Gerrit; Bensellak, Taoufik; Wells, Gordon; Kumuthini, Judit; Shriner, Daniel; Fakim, Yasmina J; Ghoorah, Anisah W; Dareng, Eileen; et al. (Nature, 2021)

Chromosome Xq23 is associated with lower atherogenic lipid concentrations and favorable cardiometabolic indices. - Natarajan, Pradeep; Pampana, Akhil; Graham, Sarah E; Ruotsalainen, Sanni E; Perry, James A; de Vries, Paul S; Broome, Jai G; Pirruccello, James P; Honigberg, Michael C; Aragam, Krishna; Wolford, Brooke; Brody, Jennifer A; et al. (Nat Commun, 2021)
Autosomal genetic analyses of blood lipids have yielded key insights for coronary heart disease (CHD). However, X chromosome genetic variation is understudied for blood lipids in large sample sizes. We now analyze genetic and blood lipid data in a high-coverage whole X chromosome sequencing study of 65,322 multi-ancestry participants and perform replication among 456,893 European participants. Common alleles on chromosome Xq23 are strongly associated with reduced total cholesterol, LDL cholesterol, and triglycerides (min P = 8.5 × 10), with similar effects for males and females. Chromosome Xq23 lipid-lowering alleles are associated with reduced odds for CHD among 42,545 cases and 591,247 controls (P = 1.7 × 10), and reduced odds for diabetes mellitus type 2 among 54,095 cases and 573,885 controls (P = 1.4 × 10). Although we observe an association with increased BMI, waist-to-hip ratio adjusted for BMI is reduced, bioimpedance analyses indicate increased gluteofemoral fat, and abdominal MRI analyses indicate reduced visceral adiposity. Co-localization analyses strongly correlate increased CHRDL1 gene expression, particularly in adipose tissue, with reduced concentrations of blood lipids.
Keywords: Cardiometabolic Risk Factors; Chromosomes, Human, X; Eye Proteins; Female; Gene Expression Regulation; Genetic Association Studies; Genetic Loci; Genetic Predisposition to Disease; Genotype; Humans; Lipids; Male; Middle Aged; Nerve Tissue Proteins; Phenomics; Polymorphism, Single Nucleotide; Subcutaneous Tissue; Whole Genome Sequencing

Comparative genomic analysis of sifakas () reveals selection for folivory and high heterozygosity despite endangered status. - Guevara, Elaine E; Webster, Timothy H; Lawler, Richard R; Bradley, Brenda J; Greene, Lydia K; Ranaivonasy, Jeannin; Ratsirarson, Joelisoa; R. Alan Harris; Liu, Yue; Murali, Shwetha; Raveendran, Muthuswamy; Hughes, Daniel S T; et al. (Sci Adv, 2021)
Sifakas (genus ) are critically endangered, large-bodied diurnal lemurs that eat leaf-based diets and show corresponding anatomical and microbial adaptations to folivory. We report on the genome assembly of Coquerel's sifaka () and the resequenced genomes of Verreaux's (), the golden-crowned (), and the diademed () sifakas. We find high heterozygosity in all sifakas compared with other primates and endangered mammals. Demographic reconstructions nevertheless suggest declines in effective population size beginning before human arrival on Madagascar. Comparative genomic analyses indicate pervasive accelerated evolution in the ancestral sifaka lineage affecting genes in several complementary pathways relevant to folivory, including nutrient absorption and xenobiotic and fatty acid metabolism. Sifakas show convergent evolution at the level of the pathway, gene family, gene, and amino acid substitution with other folivores. Although sifakas have relatively generalized diets, the physiological challenges of habitual folivory likely led to strong selection.

COPB2 loss of function causes a coatopathy with osteoporosis and developmental delay. - Marom, Ronit; Burrage, Lindsay C; Venditti, Rossella; Clément, Aurélie; Blanco-Sánchez, Bernardo; Jain, Mahim; Scott, Daryl A; Rosenfeld, Jill A; Sutton, V Reid; Shinawi, Marwan; Mirzaa, Ghayda; DeVile, Catherine; et al. (Am J Hum Genet, 2021)
Coatomer complexes function in the sorting and trafficking of proteins between subcellular organelles. Pathogenic variants in coatomer subunits or associated factors have been reported in multi-systemic disorders, i.e., coatopathies, that can affect the skeletal and central nervous systems. We have identified loss-of-function variants in COPB2, a component of the coatomer complex I (COPI), in individuals presenting with osteoporosis, fractures, and developmental delay of variable severity. Electron microscopy of COPB2-deficient subjects' fibroblasts showed dilated endoplasmic reticulum (ER) with granular material, prominent rough ER, and vacuoles, consistent with an intracellular trafficking defect. We studied the effect of COPB2 deficiency on collagen trafficking because of the critical role of collagen secretion in bone biology. COPB2 siRNA-treated fibroblasts showed delayed collagen secretion with retention of type I collagen in the ER and Golgi and altered distribution of Golgi markers. copb2-null zebrafish embryos showed retention of type II collagen, disorganization of the ER and Golgi, and early larval lethality. Copb2 mice exhibited low bone mass, and consistent with the findings in human cells and zebrafish, studies in Copb2 mouse fibroblasts suggest ER stress and a Golgi defect. Interestingly, ascorbic acid treatment partially rescued the zebrafish developmental phenotype and the cellular phenotype in Copb2 mouse fibroblasts. This work identifies a form of coatopathy due to COPB2 haploinsufficiency, explores a potential therapeutic approach for this disorder, and highlights the role of the COPI complex as a regulator of skeletal homeostasis.
Keywords: Animals; Ascorbic Acid; Bone and Bones; Brain; Child; Child, Preschool; Coat Protein Complex I; Coatomer Protein; Collagen Type I; Developmental Disabilities; Embryo, Nonmammalian; Endoplasmic Reticulum; Female; Fibroblasts; Gene Expression Regulation, Developmental; Golgi Apparatus; Haploinsufficiency; Humans; Intellectual Disability; Male; Mice; Osteoporosis; RNA, Small Interfering; Severity of Illness Index; Zebrafish

Cross-oncopanel study reveals high sensitivity and accuracy with overall analytical performance depending on genomic regions. - Gong, Binsheng; Li, Dan; Kusko, Rebecca; Novoradovskaya, Natalia; Zhang, Yifan; Wang, Shangzi; Pabón-Peña, Carlos; Zhang, Zhihong; Lai, Kevin; Cai, Wanshi; LoCoco, Jennifer S; Lader, Eric; et al. (Genome Biol, 2021)
BACKGROUND: Targeted sequencing using oncopanels requires comprehensive assessments of accuracy and detection sensitivity to ensure analytical validity. By employing reference materials characterized by the U.S. Food and Drug Administration-led SEquence Quality Control project phase2 (SEQC2) effort, we perform a cross-platform multi-lab evaluation of eight Pan-Cancer panels to assess best practices for oncopanel sequencing. RESULTS: All panels demonstrate high sensitivity across targeted high-confidence coding regions and variant types for the variants previously verified to have variant allele frequency (VAF) in the 5-20% range. Sensitivity is reduced by utilizing VAF thresholds due to inherent variability in VAF measurements. Enforcing a VAF threshold for reporting has a positive impact on reducing false positive calls. Importantly, the false positive rate is found to be significantly higher outside the high-confidence coding regions, resulting in lower reproducibility. Thus, region restriction and VAF thresholds lead to low relative technical variability in estimating promising biomarkers and tumor mutational burden. CONCLUSION: This comprehensive study provides actionable guidelines for oncopanel sequencing and clear evidence that supports a simplified approach to assess the analytical performance of oncopanels. It will facilitate the rapid implementation, validation, and quality control of oncopanels in clinical use.
Keywords: Biomarkers, Tumor; DNA Copy Number Variations; Genetic Testing; Genomics; Humans; Molecular Diagnostic Techniques; Mutation; Neoplasms; Oncogenes; Polymorphism, Single Nucleotide; Reproducibility of Results; Sensitivity and Specificity

DNA methylation patterns identify subgroups of pancreatic neuroendocrine tumors with clinical association. - Lakis, Vanessa; Lawlor, Rita T; Newell, Felicity; Patch, Ann-Marie; Mafficini, Andrea; Sadanandam, Anguraj; Koufariotis, Lambros T; Johnston, Rebecca L; Leonard, Conrad; Wood, Scott; Rusev, Borislav; Corbo, Vincenzo; et al. (Commun Biol, 2021)
Here we report the DNA methylation profile of 84 sporadic pancreatic neuroendocrine tumors (PanNETs) with associated clinical and genomic information. We identified three subgroups of PanNETs, termed T1, T2 and T3, with distinct patterns of methylation. The T1 subgroup was enriched for functional tumors and ATRX, DAXX and MEN1 wild-type genotypes. The T2 subgroup contained tumors with mutations in ATRX, DAXX and MEN1 and recurrent patterns of chromosomal losses in half of the genome with no association between regions with recurrent loss and methylation levels. T2 tumors were larger and had lower methylation in the MGMT gene body, which showed positive correlation with gene expression. The T3 subgroup harboured mutations in MEN1 with recurrent loss of chromosome 11, was enriched for grade G1 tumors and showed histological parameters associated with better prognosis. Our results suggest a role for methylation in both driving tumorigenesis and potentially stratifying prognosis in PanNETs.
Keywords: Biomarkers, Tumor; Carcinoma, Neuroendocrine; DNA Methylation; Epigenesis, Genetic; Epigenome; Epigenomics; Genetic Predisposition to Disease; Humans; Neoplasm Grading; Pancreatic Neoplasms; Phenotype; Tumor Burden

Durable Response to Larotrectinib in a Child With Histologic Diagnosis of Recurrent Disseminated Ependymoma Discovered to Harbor an Fusion: The Impact of Integrated Genomic Profiling. - Mangum, Ross; Reuther, Jacquelyn; Bertrand, Kelsey C; Chandramohan, Raghu; Kukreja, Marcia K; Paulino, Arnold C; Donna M Muzny; Jianhong Hu; Richard A Gibbs; Curry, Daniel J; Malbari, Fatema; Chintagumpala, Murali M; et al. (JCO Precis Oncol, 2021)
Keywords: Brain Neoplasms; Child; Ependymoma; Gene Expression Profiling; Humans; Male; Membrane Glycoproteins; Neoplasm Recurrence, Local; Pyrazoles; Pyrimidines; Receptor, trkB

Exome sequencing in children with clinically suspected maturity-onset diabetes of the young. - Tosur, Mustafa; Soler-Alfonso, Claudia; Chan, Katie M; Khayat, Michael M; Jhangiani, Shalini N; Meng, Qingchang; Refaey, Ahmad; Donna M Muzny; Richard A Gibbs; David R Murdock; Posey, Jennifer E; Balasubramanyam, Ashok; et al. (Pediatr Diabetes, 2021)
OBJECTIVE: Commercial gene panels identify pathogenic variants in as low as 27% of patients suspected to have MODY, suggesting the role of yet unidentified pathogenic variants. We sought to identify novel gene variants associated with MODY. RESEARCH DESIGN AND METHODS: We recruited 10 children with a clinical suspicion of MODY but non-diagnostic commercial MODY gene panels. We performed exome sequencing (ES) in them and their parents. RESULTS: Mean age at diabetes diagnosis was 10 (± 3.8) years. Six were females; 4 were non-Hispanic white, 5 Hispanic, and 1 Asian. Our variant prioritization analysis identified a pathogenic, de novo variant in INS (c.94G > A, p.Gly32Ser), confirmed by Sanger sequencing, in a proband who was previously diagnosed with "autoantibody-negative type 1 diabetes (T1D)" at 3 y/o. This rare variant, absent in the general population (gnomAD database), has been reported previously in neonatal diabetes. We also identified a frameshift deletion (c.2650delC, p.Gln884AsnfsTer57) in RFX6 in a child with a previous diagnosis of "autoantibody-negative T1D" at 12 y/o. The variant was inherited from the mother, who was diagnosed with "thin type 2 diabetes" at 25 y/o. Heterozygous protein-truncating variants in RFX6 gene have been recently reported in individuals with MODY. CONCLUSIONS: We diagnosed two patients with MODY using ES in children initially classified as "T1D". One has a likely pathogenic novel gene variant not previously associated with MODY. We demonstrate the clinical utility of ES in patients with clinical suspicion of MODY.
Keywords: Adolescent; Autoantibodies; Child; Diabetes Mellitus, Type 1; Diabetes Mellitus, Type 2; Diagnosis, Differential; Exome Sequencing; Female; Frameshift Mutation; Genetic Variation; Humans; Islets of Langerhans; Male; Mutation, Missense; Pedigree

Genetic testing in ambulatory cardiology clinics reveals high rate of findings with clinical management implications. - David R Murdock; Eric Venner; Donna M Muzny; Ginger A Metcalf; Mullai Murugan; Hadley, Trevor D; Chander, Varuna; de Vries, Paul S; Jia, Xiaoming; Hussain, Aliza; Agha, Ali M; Aniko Sabo; et al. (Genet Med, 2021)
PURPOSE: Cardiovascular disease (CVD) is the leading cause of death in adults in the United States, yet the benefits of genetic testing are not universally accepted. METHODS: We developed the "HeartCare" panel of genes associated with CVD, evaluating high-penetrance Mendelian conditions, coronary artery disease (CAD) polygenic risk, LPA gene polymorphisms, and specific pharmacogenetic (PGx) variants. We enrolled 709 individuals from cardiology clinics at Baylor College of Medicine, and samples were analyzed in a CAP/CLIA-certified laboratory. Results were returned to the ordering physician and uploaded to the electronic medical record. RESULTS: Notably, 32% of patients had a genetic finding with clinical management implications, even after excluding PGx results, including 9% who were molecularly diagnosed with a Mendelian condition. Among surveyed physicians, 84% reported medical management changes based on these results, including specialist referrals, cardiac tests, and medication changes. LPA polymorphisms and high polygenic risk of CAD were found in 20% and 9% of patients, respectively, leading to diet, lifestyle, and other changes. Warfarin and simvastatin pharmacogenetic variants were present in roughly half of the cohort. CONCLUSION: Our results support the use of genetic information in routine cardiovascular health management and provide a roadmap for accompanying research.
Keywords: Adult; Cardiology; Cardiovascular Diseases; Genetic Testing; Humans; Pharmacogenetics; Pharmacogenomic Testing; United States

Germline Cancer Predisposition Variants in Pediatric Rhabdomyosarcoma: A Report From the Children's Oncology Group. - Li, He; Sisoudiya, Saumya D; Martin-Giacalone, Bailey A; Khayat, Michael M; Dugan-Perez, Shannon; Marquez-Do, Deborah A; Scheurer, Michael E; Donna M Muzny; Eric Boerwinkle; Richard A Gibbs; Chi, Yueh-Yun; Barkauskas, Donald A; et al. (J Natl Cancer Inst, 2021)
BACKGROUND: Several cancer-susceptibility syndromes are reported to underlie pediatric rhabdomyosarcoma (RMS); however, to our knowledge there have been no systematic efforts to characterize the heterogeneous genetic etiologies of this often-fatal malignancy. METHODS: We performed exome-sequencing on germline DNA from 615 patients with newly diagnosed RMS consented through the Children's Oncology Group. We compared the prevalence of cancer predisposition variants in 63 autosomal-dominant cancer predisposition genes in these patients with population controls (n = 9963). All statistical tests were 2-sided. RESULTS: We identified germline cancer predisposition variants in 45 RMS patients (7.3%; all FOXO1 fusion negative) across 15 autosomal dominant genes, which was statistically significantly enriched compared with controls (1.4%, P = 1.3 × 10-22). Specifically, 73.3% of the predisposition variants were found in predisposition syndrome genes previously associated with pediatric RMS risk, such as Li-Fraumeni syndrome (TP53) and neurofibromatosis type I (NF1). Notably, 5 patients had well-described oncogenic missense variants in HRAS (p.G12V and p.G12S) associated with Costello syndrome. Also, genetic etiology differed with histology, as germline variants were more frequent in embryonal vs alveolar RMS patients (10.0% vs 3.0%, P = .02). Although patients with a cancer predisposition variant tended to be younger at diagnosis (P = 9.9 × 10-4), 40.0% of germline variants were identified in those older than 3 years of age, which is in contrast to current genetic testing recommendations based on early age at diagnosis. CONCLUSIONS: These findings demonstrate that genetic risk of RMS results from germline predisposition variants associated with a wide spectrum of cancer susceptibility syndromes. Germline genetic testing for children with RMS should be informed by RMS subtypes and not be limited to only young patients.
Keywords: Child; Genetic Predisposition to Disease; Germ Cells; Germ-Line Mutation; Humans; Li-Fraumeni Syndrome; Rhabdomyosarcoma

Germline mutation in : a heterogeneous, multi-systemic developmental disorder characterized by transcriptional dysregulation. - Hansen, Adam W; Arora, Payal; Khayat, Michael M; Smith, Leah J; Lewis, Andrea M; Rossetti, Linda Z; Jayaseelan, Joy; Cristian, Ingrid; Haynes, Devon; DiTroia, Stephanie; Meeks, Naomi; Delgado, Mauricio R; et al. (HGG Adv, 2021)
germline variation in was recently reported to associate with a neurodevelopmental disorder. We report twelve individuals harboring putatively pathogenic or inherited variants in , detail their phenotypes, and map all known variants to the domain structure of and crystal structure of RNA polymerase II. Affected individuals were ascertained from a local data lake, pediatric genetics clinic, and an online community of families of affected individuals. These include six affected by missense variants (including one previously reported individual), four clinical laboratory samples affected by missense variation with unknown inheritance-with yeast functional assays further supporting altered function-one affected by a in-frame deletion, and one affected by a C-terminal frameshift variant inherited from a largely asymptomatic mother. Recurrently observed phenotypes include ataxia, joint hypermobility, short stature, skin abnormalities, congenital cardiac abnormalities, immune system abnormalities, hip dysplasia, and short Achilles tendons. We report a significantly higher occurrence of epilepsy (8/12, 66.7%) than previously reported (3/15, 20%) (p value = 0.014196; chi-square test) and a lower occurrence of hypotonia (8/12, 66.7%) than previously reported (14/15, 93.3%) (p value = 0.076309). -related developmental disorders likely represent a spectrum of related, multi-systemic developmental disorders, driven by distinct mechanisms, converging at a single locus.

High prevalence of multilocus pathogenic variation in neurodevelopmental disorders in the Turkish population. - Mitani, Tadahiro; Isikay, Sedat; Gezdirici, Alper; Gulec, Elif Yilmaz; Punetha, Jaya; Fatih, Jawid M; Herman, Isabella; Akay, Gulsen; Du, Haowei; Calame, Daniel G; Ayaz, Akif; Tos, Tulay; et al. (Am J Hum Genet, 2021)
Neurodevelopmental disorders (NDDs) are clinically and genetically heterogenous; many such disorders are secondary to perturbation in brain development and/or function. The prevalence of NDDs is > 3%, resulting in significant sociocultural and economic challenges to society. With recent advances in family-based genomics, rare-variant analyses, and further exploration of the Clan Genomics hypothesis, there has been a logarithmic explosion in neurogenetic "disease-associated genes" molecular etiology and biology of NDDs; however, the majority of NDDs remain molecularly undiagnosed. We applied genome-wide screening technologies, including exome sequencing (ES) and whole-genome sequencing (WGS), to identify the molecular etiology of 234 newly enrolled subjects and 20 previously unsolved Turkish NDD families. In 176 of the 234 studied families (75.2%), a plausible and genetically parsimonious molecular etiology was identified. Out of 176 solved families, deleterious variants were identified in 218 distinct genes, further documenting the enormous genetic heterogeneity and diverse perturbations in human biology underlying NDDs. We propose 86 candidate disease-trait-associated genes for an NDD phenotype. Importantly, on the basis of objective and internally established variant prioritization criteria, we identified 51 families (51/176 = 28.9%) with multilocus pathogenic variation (MPV), mostly driven by runs of homozygosity (ROHs) - reflecting genomic segments/haplotypes that are identical-by-descent. Furthermore, with the use of additional bioinformatic tools and expansion of ES to additional family members, we established a molecular diagnosis in 5 out of 20 families (25%) who remained undiagnosed in our previously studied NDD cohort emanating from Turkey.
Keywords: Adolescent; Adult; Child; Child, Preschool; Cohort Studies; Exome Sequencing; Female; Genomics; Humans; Infant; Infant, Newborn; Male; Middle Aged; Mutation; Neurodevelopmental Disorders; Pedigree; Phenotype; Prevalence; Turkey; Young Adult

Molecular Features of Cancers Exhibiting Exceptional Responses to Treatment. - David A Wheeler; Takebe, Naoko; Hinoue, Toshinori; Hoadley, Katherine A; Cardenas, Maria F; Hamilton, Alina M; Laird, Peter W; Wang, Linghua; Johnson, Adrienne; Dewal, Ninad; Miller, Vincent; Piñeyro, David; et al. (Cancer Cell, 2021)
A small fraction of cancer patients with advanced disease survive significantly longer than patients with clinically comparable tumors. Molecular mechanisms for exceptional responses to therapy have been identified by genomic analysis of tumor biopsies from individual patients. Here, we analyzed tumor biopsies from an unbiased cohort of 111 exceptional responder patients using multiple platforms to profile genetic and epigenetic aberrations as well as the tumor microenvironment. Integrative analysis uncovered plausible mechanisms for the therapeutic response in nearly a quarter of the patients. The mechanisms were assigned to four broad categories-DNA damage response, intracellular signaling, immune engagement, and genetic alterations characteristic of favorable prognosis-with many tumors falling into multiple categories. These analyses revealed synthetic lethal relationships that may be exploited therapeutically and rare genetic lesions that favor therapeutic success, while also providing a wealth of testable hypotheses regarding oncogenic mechanisms that may influence the response to cancer therapy.
Keywords: Antineoplastic Agents; Biopsy; Epigenesis, Genetic; Female; Gene Regulatory Networks; Genetic Variation; Genomics; Humans; Male; Neoplasms; Prognosis; Survival Analysis; Treatment Outcome; Tumor Microenvironment

Neptune: an environment for the delivery of genomic medicine. - Eric Venner; Yi, Victoria; David R Murdock; Sara E Kalla; Wu, Tsung-Jung; Aniko Sabo; Li, Shoudong; Meng, Qingchang; Tian, Xia; Mullai Murugan; Cohen, Michelle; Kovar, Christie; et al. (Genet Med, 2021)
PURPOSE: Genomic medicine holds great promise for improving health care, but integrating searchable and actionable genetic data into electronic health records (EHRs) remains a challenge. Here we describe Neptune, a system for managing the interaction between a clinical laboratory and an EHR system during the clinical reporting process. METHODS: We developed Neptune and applied it to two clinical sequencing projects that required report customization, variant reanalysis, and EHR integration. RESULTS: Neptune has been applied for the generation and delivery of over 15,000 clinical genomic reports. This work spans two clinical tests based on targeted gene panels that contain 68 and 153 genes respectively. These projects demanded customizable clinical reports that contained a variety of genetic data types including single-nucleotide variants (SNVs), copy-number variants (CNVs), pharmacogenomics, and polygenic risk scores. Two variant reanalysis activities were also supported, highlighting this important workflow. CONCLUSION: Methods are needed for delivering structured genetic data to EHRs. This need extends beyond developing data formats to providing infrastructure that manages the reporting process itself. Neptune was successfully applied on two high-throughput clinical sequencing projects to build and deliver clinical reports to EHR systems. The software is open source and available at https://gitlab.com/bcm-hgsc/neptune .
Keywords: Electronic Health Records; Genomics; High-Throughput Nucleotide Sequencing; Humans; Neptune; Software

Novel pathogenic genomic variants leading to autosomal dominant and recessive Robinow syndrome. - Zhang, Chaofan; Mazzeu, Juliana F; Eisfeldt, Jesper; Grochowski, Christopher M; White, Janson; Akdemir, Zeynep C; Jhangiani, Shalini N; Donna M Muzny; Richard A Gibbs; Lindstrand, Anna; James R Lupski; Sutton, V Reid; et al. (Am J Med Genet A, 2021)
Robinow syndrome (RS) is a genetically heterogeneous disorder characterized by skeletal dysplasia and a distinctive facial appearance. Previous studies have revealed locus heterogeneity with rare variants in DVL1, DVL3, FZD2, NXN, ROR2, and WNT5A underlying the etiology of RS. The aforementioned "Robinow-associated genes" and their gene products all play a role in the WNT/planar cell polarity signaling pathway. We performed gene-targeted Sanger sequencing, exome sequencing, genome sequencing, and array comparative genomic hybridization on four subjects with a clinical diagnosis of RS who had not had prior DNA testing. Individuals in our cohort were found to carry pathogenic or likely pathogenic variants in three RS related genes: DVL1, ROR2, and NXN. One subject was found to have a nonsense variant (c.817C > T [p.Gln273*]) in NXN in trans with an ~1 Mb telomeric deletion on chromosome 17p containing NXN, which supports our contention that biallelic NXN variant alleles are responsible for a novel autosomal recessive RS locus. These findings provide increased understanding of the role of WNT signaling in skeletal development and maintenance. These data further support the hypothesis that dysregulation of the noncanonical WNT pathway in humans gives rise to RS.
Keywords: Chromosomes, Human, Pair 17; Comparative Genomic Hybridization; Craniofacial Abnormalities; Dishevelled Proteins; Dwarfism; Exome Sequencing; Female; Genes, Dominant; Genes, Recessive; Genetic Heterogeneity; Genetic Predisposition to Disease; Genomic Structural Variation; Humans; Limb Deformities, Congenital; Male; Oxidoreductases; Receptor Tyrosine Kinase-like Orphan Receptors; Urogenital Abnormalities; Whole Genome Sequencing; Wnt Signaling Pathway

Oligonucleotide capture sequencing of the SARS-CoV-2 genome and subgenomic fragments from COVID-19 individuals. - Harshavardhan Doddapaneni; Cregeen, Sara Javornik; Sucgang, Richard; Meng, Qingchang; Xiang Qin; Avadhanula, Vasanthi; Chao, Hsu; Menon, Vipin; Nicholson, Erin; Henke, David; Piedra, Felipe-Andres; Rajan, Anubama; et al. (PLoS One, 2021)
The newly emerged and rapidly spreading SARS-CoV-2 causes coronavirus disease 2019 (COVID-19). To facilitate a deeper understanding of the viral biology we developed a capture sequencing methodology to generate SARS-CoV-2 genomic and transcriptome sequences from infected patients. We utilized an oligonucleotide probe-set representing the full-length genome to obtain both genomic and transcriptome (subgenomic open reading frames [ORFs]) sequences from 45 SARS-CoV-2 clinical samples with varying viral titers. For samples with higher viral loads (cycle threshold value under 33, based on the CDC qPCR assay) complete genomes were generated. Analysis of junction reads revealed regions of differential transcriptional activity among samples. Mixed allelic frequencies along the 20kb ORF1ab gene in one sample, suggested the presence of a defective viral RNA species subpopulation maintained in mixture with functional RNA in one sample. The associated workflow is straightforward, and hybridization-based capture offers an effective and scalable approach for sequencing SARS-CoV-2 from patient samples.
Keywords: COVID-19; DNA, Complementary; Gene Frequency; Genetic Variation; Genome, Viral; Humans; Open Reading Frames; Real-Time Polymerase Chain Reaction; RNA, Viral; SARS-CoV-2; Sequence Analysis, DNA; Viral Load

Sequencing of a central nervous system tumor demonstrates cancer transmission in an organ transplant. - Marie-Claude Gingras; Aniko Sabo; Cardenas, Maria; Rana, Abbas; Dhingra, Sadhna; Meng, Qingchang; Jianhong Hu; Donna M Muzny; Harshavardhan Doddapaneni; Perez, Lesette; Korchina, Viktoriya; Nessner, Caitlin; et al. (Life Sci Alliance, 2021)
Four organ transplant recipients from an organ donor diagnosed with anaplastic pleomorphic xanthoastrocytoma developed fatal malignancies for which the origin could not be confirmed by standard methods. We identified the somatic mutational profiles of the neoplasms using next-generation sequencing technologies and tracked the relationship between the different samples. The data were consistent with the presence of an aggressive clonal entity in the donor and the subsequent proliferation of descendent tumors in each recipient. Deleterious mutations in , , , , and , and a chromosomal deletion spanning the genes, were shared between the recipients' lesions. In addition to demonstrating that DNA sequencing tracked a donor/recipient cancer transmission, this study established that the genetic profile of a donor tumor and its potential aggressive phenotype could have been determined before transplantation was considered. As the genetic correlates of tumor invasion and metastases become better known, adding genetic profiling by DNA sequencing to the data considered for transplant safety should be considered.
Keywords: Adolescent; Adult; Biomarkers, Tumor; Biopsy; Central Nervous System Neoplasms; DNA Mutational Analysis; Exome Sequencing; Female; Humans; INDEL Mutation; Male; Middle Aged; Mutation; Organ Transplantation; Prognosis; Sequence Analysis, DNA; Tissue Donors; Transplant Recipients; Transplants; Young Adult

Transmission event of SARS-CoV-2 Delta variant reveals multiple vaccine breakthrough infections. - Farinholt, Timothy; Harshavardhan Doddapaneni; Xiang Qin; Menon, Vipin; Meng, Qingchang; Ginger A Metcalf; Chao, Hsu; Marie-Claude Gingras; Farinholt, Paige; Agrawal, Charu; Donna M Muzny; Piedra, Pedro A; et al. (medRxiv, 2021)
IMPORTANCE: Vaccine breakthrough by an emergent SARS-CoV-2 variant poses a great risk to global public health. OBJECTIVE: To determine the SARS-CoV-2 variant responsible for 6 cases of vaccine breakthrough. DESIGN: Nasopharyngeal swabs from suspected vaccine breakthrough cases were tested for SARS-CoV-2 by qPCR for Wuhan-Hu1 and Alpha variant. Positive samples were then sequenced by Swift Normalase Amplicon Panels to determine the causal variant. SETTING: Transmission event occurred at events surrounding a wedding outside of Houston, TX. Two patients from India, likely transmitted the Delta variant to other guests. PARTICIPANTS: Following a positive SARS-CoV-2 qPCR test at a third-party site, six fully vaccinated patients were investigated. Three males and three females ranged from 53 to 69 years old. One patient suffered from diabetes while three others were classified as overweight. No significant other comorbidities were identified. None of the patients had a history of failed vaccination. KEY POINTS: Which SARS-CoV-2 variant is responsible for 6 cases of vaccine breakthrough, one interventional monoclonal antibody treatment, and one death? Viral sequencing revealed 6 vaccinated patients were infected with the Delta SARS-CoV-2 variant. With no histories of vaccine breakthrough, this suggests Delta variant may possess immune evasion in patients that received the Pfizer BNT162b2, Moderna mRNA-1273, and Covaxin BBV152. Delta variant may pose the highest risk out of any currently circulating SARS-CoV-2 variants, with increased transmissibility over Alpha variant and possible vaccine breakthrough.

Transmission event of SARS-CoV-2 delta variant reveals multiple vaccine breakthrough infections. - Farinholt, Timothy; Harshavardhan Doddapaneni; Xiang Qin; Menon, Vipin; Meng, Qingchang; Ginger A Metcalf; Chao, Hsu; Marie-Claude Gingras; Avadhanula, Vasanthi; Farinholt, Paige; Agrawal, Charu; Donna M Muzny; et al. (BMC Med, 2021)
BACKGROUND: This study aims to identify the causative strain of SARS-CoV-2 in a cluster of vaccine breakthroughs. Vaccine breakthrough by a highly transmissible SARS-CoV-2 strain is a risk to global public health. METHODS: Nasopharyngeal swabs from suspected vaccine breakthrough cases were tested for SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2) by qPCR (quantitative polymerase chain reaction) for Wuhan-Hu1 and alpha variant. Positive samples were then sequenced by Swift Normalase Amplicon Panels to determine the causal variant. GATK (genome analysis toolkit) variants were filtered with allele fraction ≥80 and min read depth 30x. RESULTS: Viral sequencing revealed an infection cluster of 6 vaccinated patients infected with the delta (B.1.617.2) SARS-CoV-2 variant. With no history of vaccine breakthrough, this suggests the delta variant may possess immune evasion in patients that received the Pfizer BNT162b2, Moderna mRNA-1273, and Covaxin BBV152. CONCLUSIONS: Delta variant may pose the highest risk out of any currently circulating SARS-CoV-2 variants, with previously described increased transmissibility over alpha variant and now, possible vaccine breakthrough. FUNDING: Parts of this work was supported by the National Institute of Allergy and Infectious Diseases (1U19AI144297) and Baylor College of Medicine internal funding.
Keywords: BNT162 Vaccine; COVID-19; COVID-19 Vaccines; Humans; Immune Evasion; SARS-CoV-2

Allelic Heterogeneity at the CRP Locus Identified by Whole-Genome Sequencing in Multi-ancestry Cohorts. - Raffield, Laura M; Iyengar, Apoorva K; Wang, Biqi; Gaynor, Sheila M; Spracklen, Cassandra N; Zhong, Xue; Kowalski, Madeline H; Salimi, Shabnam; Polfus, Linda M; Benjamin, Emelia J; Bis, Joshua C; Bowler, Russell; et al. (Am J Hum Genet, 2020)
Whole-genome sequencing (WGS) can improve assessment of low-frequency and rare variants, particularly in non-European populations that have been underrepresented in existing genomic studies. The genetic determinants of C-reactive protein (CRP), a biomarker of chronic inflammation, have been extensively studied, with existing genome-wide association studies (GWASs) conducted in >200,000 individuals of European ancestry. In order to discover novel loci associated with CRP levels, we examined a multi-ancestry population (n = 23,279) with WGS (∼38× coverage) from the Trans-Omics for Precision Medicine (TOPMed) program. We found evidence for eight distinct associations at the CRP locus, including two variants that have not been identified previously (rs11265259 and rs181704186), both of which are non-coding and more common in individuals of African ancestry (∼10% and ∼1% minor allele frequency, respectively, and rare or monomorphic in 1000 Genomes populations of East Asian, South Asian, and European ancestry). We show that the minor (G) allele of rs181704186 is associated with lower CRP levels and decreased transcriptional activity and protein binding in vitro, providing a plausible molecular mechanism for this African ancestry-specific signal. The individuals homozygous for rs181704186-G have a mean CRP level of 0.23 mg/L, in contrast to individuals heterozygous for rs181704186 with mean CRP of 2.97 mg/L and major allele homozygotes with mean CRP of 4.11 mg/L. This study demonstrates the utility of WGS in multi-ethnic populations to drive discovery of complex trait associations of large effect and to identify functional alleles in noncoding regulatory regions.
Keywords: Asian People; Black People; C-Reactive Protein; Cohort Studies; Gene Frequency; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Linkage Disequilibrium; Polymorphism, Single Nucleotide; White People; Whole Genome Sequencing

Brown marmorated stink bug, Halyomorpha halys (Stål), genome: putative underpinnings of polyphagy, insecticide resistance potential and biology of a top worldwide pest. - Sparks, Michael E; Bansal, Raman; Benoit, Joshua B; Blackburn, Michael B; Chao, Hsu; Chen, Mengyao; Cheng, Sammy; Childers, Christopher; Dinh, Huyen; Harshavardhan Doddapaneni; Dugan, Shannon; Elpidina, Elena N; et al. (BMC Genomics, 2020)
BACKGROUND: Halyomorpha halys (Stål), the brown marmorated stink bug, is a highly invasive insect species due in part to its exceptionally high levels of polyphagy. This species is also a nuisance due to overwintering in human-made structures. It has caused significant agricultural losses in recent years along the Atlantic seaboard of North America and in continental Europe. Genomic resources will assist with determining the molecular basis for this species' feeding and habitat traits, defining potential targets for pest management strategies. RESULTS: Analysis of the 1.15-Gb draft genome assembly has identified a wide variety of genetic elements underpinning the biological characteristics of this formidable pest species, encompassing the roles of sensory functions, digestion, immunity, detoxification and development, all of which likely support H. halys' capacity for invasiveness. Many of the genes identified herein have potential for biomolecular pesticide applications. CONCLUSIONS: Availability of the H. halys genome sequence will be useful for the development of environmentally friendly biomolecular pesticides to be applied in concert with more traditional, synthetic chemical-based controls.
Keywords: Animals; Ecosystem; Gene Transfer, Horizontal; Genome Size; Heteroptera; Insect Proteins; Insecticide Resistance; Introduced Species; Phylogeny; Whole Genome Sequencing

CNVs cause autosomal recessive genetic diseases with or without involvement of SNV/indels. - Bo Yuan; Wang, Lei; Liu, Pengfei; Shaw, Chad; Dai, Hongzheng; Cooper, Lance; Zhu, Wenmiao; Anderson, Stephanie A; Meng, Linyan; Wang, Xia; Wang, Yue; Xia, Fan; et al. (Genet Med, 2020)
PURPOSE: Improved resolution of molecular diagnostic technologies enabled detection of smaller sized exonic level copy-number variants (CNVs). The contribution of CNVs to autosomal recessive (AR) conditions may be better recognized using a large clinical cohort. METHODS: We retrospectively investigated the CNVs' contribution to AR conditions in cases subjected to chromosomal microarray analysis (CMA, N = ~70,000) and/or clinical exome sequencing (ES, N = ~12,000) at Baylor Genetics; most had pediatric onset neurodevelopmental disorders. RESULTS: CNVs contributed to biallelic variations in 87 cases, including 81 singletons and three affected sibling pairs. Seventy cases had CNVs affecting both alleles, and 17 had a CNV and a single-nucleotide variant (SNV)/indel in trans. In total, 94.3% of AR-CNVs affected one gene; among these 41.4% were single-exon and 35.0% were multiexon partial-gene events. Sixty-nine percent of homozygous AR-CNVs were embedded in homozygous genomic intervals. Five cases had large deletions unmasking an SNV/indel on the intact allele for a recessive condition, resulting in multiple molecular diagnoses. CONCLUSIONS: AR-CNVs are often smaller in size, transmitted through generations, and underrecognized due to limitations in clinical CNV detection methods. Our findings from a large clinical cohort emphasized integrated CNV and SNV/indel analyses for precise clinical and molecular diagnosis especially in the context of genomic disorders.
Keywords: Child; DNA Copy Number Variations; Exome Sequencing; Exons; Humans; INDEL Mutation; Retrospective Studies

Cohort Profile: The Right Drug, Right Dose, Right Time: Using Genomic Data to Individualize Treatment Protocol (RIGHT Protocol). - Bielinski, Suzette J; St Sauver, Jennifer L; Olson, Janet E; Larson, Nicholas B; Black, John L; Steven E Scherer; Bernard, Matthew E; Eric Boerwinkle; Borah, Bijan J; Caraballo, Pedro J; Curry, Timothy B; Harshavardhan Doddapaneni; et al. (Int J Epidemiol, 2020)
Keywords: Clinical Protocols; Cohort Studies; Female; Genomics; Humans; Male; Pharmacogenetics; Precision Medicine

Community-based recruitment and exome sequencing indicates high diagnostic yield in adults with intellectual disability. - Aniko Sabo; David R Murdock; Dugan, Shannon; Meng, Qingchang; Marie-Claude Gingras; Jianhong Hu; Donna M Muzny; Richard A Gibbs (Mol Genet Genomic Med, 2020)
BACKGROUND: Establishing a genetic diagnosis for individuals with intellectual disability (ID) benefits patients and their families as it may inform the prognosis, lead to appropriate therapy, and facilitate access to medical and supportive services. Exome sequencing has been successfully applied in a diagnostic setting, but most clinical exome referrals are pediatric patients, with many adults with ID lacking a comprehensive genetic evaluation. METHODS: Our unique recruitment strategy involved partnering with service and education providers for individuals with ID. We performed exome sequencing and analysis, and clinical variant interpretation for each recruited family. RESULTS: All five families enrolled in the study opted-in for the return of genetic results. In three out of five families exome sequencing analysis identified pathogenic or likely pathogenic variants in KANSL1, TUSC3, and MED13L genes. Families discussed the results and any potential medical follow-up in an appointment with a board certified clinical geneticist. CONCLUSION: Our study suggests high yield of exome sequencing as a diagnostic tool in adult patients with ID who have not undergone comprehensive sequencing-based genetic testing. Research studies including an option of return of results through a genetic clinic could help minimize the disparity in exome diagnostic testing between pediatric and adult patients with ID.
Keywords: Adult; Exome Sequencing; Female; Genetic Testing; Humans; Independent Living; Intellectual Disability; Male; Mediator Complex; Membrane Proteins; Nuclear Proteins; Patient Selection; Sensitivity and Specificity; Tumor Suppressor Proteins

Correction to: Genome-enabled insights into the biology of thrips as crop pests. - Rotenberg, Dorith; Baumann, Aaron A; Ben-Mahmoud, Sulley; Christiaens, Olivier; Dermauw, Wannes; Ioannidis, Panagiotis; Jacobs, Chris G C; Vargas Jentzsch, Iris M; Oliver, Jonathan E; Poelchau, Monica F; Rajarapu, Swapna Priya; Schneweis, Derek J; et al. (BMC Biol, 2020)
An amendment to this paper has been published and can be accessed via the original article.

Correction: Whole exome sequencing study identifies novel rare and common Alzheimer's-Associated variants involved in immune response and transcriptional regulation. - Bis, Joshua C; Jian, Xueqiu; Kunkle, Brian W; Chen, Yuning; Hamilton-Nelson, Kara L; Bush, William S; Salerno, William J; Lancour, Daniel; Ma, Yiyi; Renton, Alan E; Marcora, Edoardo; Farrell, John J; et al. (Mol Psychiatry, 2020)
A correction to this paper has been published and can be accessed via a link at the top of the paper.

A diagnostic ceiling for exome sequencing in cerebellar ataxia and related neurological disorders. - Ngo, Kathie J; Rexach, Jessica E; Lee, Hane; Petty, Lauren E; Perlman, Susan; Valera, Juliana M; Deignan, Joshua L; Mao, Yuanming; Aker, Mamdouh; Posey, Jennifer E; Jhangiani, Shalini N; Coban-Akdemir, Zeynep H; et al. (Hum Mutat, 2020)
Genetic ataxias are associated with mutations in hundreds of genes with high phenotypic overlap complicating the clinical diagnosis. Whole-exome sequencing (WES) has increased the overall diagnostic rate considerably. However, the upper limit of this method remains ill-defined, hindering efforts to address the remaining diagnostic gap. To further assess the role of rare coding variation in ataxic disorders, we reanalyzed our previously published exome cohort of 76 predominantly adult and sporadic-onset patients, expanded the total number of cases to 260, and introduced analyses for copy number variation and repeat expansion in a representative subset. For new cases (n = 184), our resulting clinically relevant detection rate remained stable at 47% with 24% classified as pathogenic. Reanalysis of the previously sequenced 76 patients modestly improved the pathogenic rate by 7%. For the combined cohort (n = 260), the total observed clinical detection rate was 52% with 25% classified as pathogenic. Published studies of similar neurological phenotypes report comparable rates. This consistency across multiple cohorts suggests that, despite continued technical and analytical advancements, an approximately 50% diagnostic rate marks a relative ceiling for current WES-based methods and a more comprehensive genome-wide assessment is needed to identify the missing causative genetic etiologies for cerebellar ataxia and related neurodegenerative diseases.
Keywords: Cerebellar Ataxia; DNA Copy Number Variations; Exome; Exome Sequencing; Genetic Association Studies; Genetic Linkage; Genetic Predisposition to Disease; Humans; Microsatellite Repeats; Nervous System Diseases

Disease-associated CTNNBL1 mutation impairs somatic hypermutation by decreasing nuclear AID. - Kuhny, Marcel; Forbes, Lisa R; Çakan, Elif; Vega-Loza, Andrea; Kostiuk, Valentyna; Dinesh, Ravi K; Glauzy, Salomé; Stray-Pedersen, Asbjorg; Pezzi, Ashley E; Hanson, I Celine; Vargas-Hernandez, Alexander; Xu, Mina LuQuing; et al. (J Clin Invest, 2020)
Patients with common variable immunodeficiency associated with autoimmune cytopenia (CVID+AIC) generate few isotype-switched B cells with severely decreased frequencies of somatic hypermutations (SHMs), but their underlying molecular defects remain poorly characterized. We identified a CVID+AIC patient who displays a rare homozygous missense M466V mutation in β-catenin-like protein 1 (CTNNBL1). Because CTNNBL1 binds activation-induced cytidine deaminase (AID) that catalyzes SHM, we tested AID interactions with the CTNNBL1 M466V variant. We found that the M466V mutation interfered with the association of CTNNBL1 with AID, resulting in decreased AID in the nuclei of patient EBV-transformed B cell lines and of CTNNBL1 466V/V Ramos B cells engineered to express only CTNNBL1 M466V using CRISPR/Cas9 technology. As a consequence, the scarce IgG+ memory B cells from the CTNNBL1 466V/V patient showed a low SHM frequency that averaged 6.7 mutations compared with about 18 mutations per clone in healthy-donor counterparts. In addition, CTNNBL1 466V/V Ramos B cells displayed a decreased incidence of SHM that was reduced by half compared with parental WT Ramos B cells, demonstrating that the CTNNBL1 M466V mutation is responsible for defective SHM induction. We conclude that CTNNBL1 plays an important role in regulating AID-dependent antibody diversification in humans.
Keywords: Amino Acid Substitution; Apoptosis Regulatory Proteins; B-Lymphocytes; Cell Line; Child, Preschool; Common Variable Immunodeficiency; Cytidine Deaminase; Female; Homozygote; Humans; Immunologic Memory; Mutation, Missense; Nuclear Proteins; Somatic Hypermutation, Immunoglobulin

Gene content evolution in the arthropods. - Thomas, Gregg W C; Dohmen, Elias; Hughes, Daniel S T; Murali, Shwetha C; Poelchau, Monica; Glastad, Karl; Anstead, Clare A; Ayoub, Nadia A; Batterham, Phillip; Bellair, Michelle; Binford, Greta J; Chao, Hsu; et al. (Genome Biol, 2020)
BACKGROUND: Arthropods comprise the largest and most diverse phylum on Earth and play vital roles in nearly every ecosystem. Their diversity stems in part from variations on a conserved body plan, resulting from and recorded in adaptive changes in the genome. Dissection of the genomic record of sequence change enables broad questions regarding genome evolution to be addressed, even across hyper-diverse taxa within arthropods. RESULTS: Using 76 whole genome sequences representing 21 orders spanning more than 500 million years of arthropod evolution, we document changes in gene and protein domain content and provide temporal and phylogenetic context for interpreting these innovations. We identify many novel gene families that arose early in the evolution of arthropods and during the diversification of insects into modern orders. We reveal unexpected variation in patterns of DNA methylation across arthropods and examples of gene family and protein domain evolution coincident with the appearance of notable phenotypic and physiological adaptations such as flight, metamorphosis, sociality, and chemoperception. CONCLUSIONS: These analyses demonstrate how large-scale comparative genomics can provide broad new insights into the genotype to phenotype map and generate testable hypotheses about the evolution of animal diversity.
Keywords: Animals; Arthropods; DNA Methylation; Evolution, Molecular; Genetic Speciation; Genetic Variation; Phylogeny

Genetic Burden Contributing to Extremely Low or High Bone Mineral Density in a Senior Male Population From the Osteoporotic Fractures in Men Study (MrOS). - Chen, Shan; Jain, Mahim; Jhangiani, Shalini; Akdemir, Zeynep C; Campeau, Philippe M; Klein, Robert F; Nielson, Carrie; Dai, Hongzheng; Donna M Muzny; Eric Boerwinkle; Richard A Gibbs; Orwoll, Eric S; et al. (JBMR Plus, 2020)
Worldwide, one in five men aged over 50 years will experience osteoporosis or a clinical bone fracture, with a greater fracture-related mortality rate than women. However, the genetic etiology of osteoporosis in men is still poorly understood. We aimed to identify the genetic variants and candidate genes associated with extremely low or high BMD for a better understanding of the biology underlying low bone density that may point to potential therapeutic targets for increasing bone mass. Subjects from the Osteoporotic Fractures in Men Study (MrOS) cohort were evaluated by age and BMI-adjusted total hip BMD. Those with BMD values 3 SDs away from the mean were selected and the remaining individuals whose adjusted BMD ranked at the highest or lowest 100 were included. Men with the lowest adjusted BMD ( = 98) and highest adjusted BMD ( = 110) were chosen for exome sequencing. Controls ( = 82) were men of Northern and Western European descent from the US Utah population of the 1000 Genomes Project. Fisher's exact test was performed to compare low- or high-BMD subjects with controls for single-gene associations. Additionally, sets of candidate genes causative of heritable disorders of connective tissue, including osteogenesis imperfecta (OI) and Ehlers-Danlos syndrome (EDS), were grouped for multigene and mutation burden analyses. No single-gene associations with rare variants were found for either the low BMD group (33 genes) or high BMD group (18 genes). In the group of OI genes, we detected a significant threefold increased accumulation of rare variants in low-BMD subjects compared with controls ( = 0.009). Additionally, genes associated with EDS had a twofold increased frequency in low-BMD subjects compared with controls ( = 0.03). These findings reveal a rare variant burden in OI and EDS disease genes at low BMD, which suggests a potential gene-panel approach to screen for multivariant associations in larger cohorts. © 2019 The Authors. published by Wiley Periodicals, Inc. on behalf of American Society for Bone and Mineral Research.

Genetics of schizophrenia in the South African Xhosa. - Gulsuner, S; Stein, D J; Susser, E S; Sibeko, G; Pretorius, A; Walsh, T; Majara, L; Mndini, M M; Mqulwana, S G; Ntola, O A; Casadei, S; Ngqengelele, L L; et al. (Science, 2020)
Africa, the ancestral home of all modern humans, is the most informative continent for understanding the human genome and its contribution to complex disease. To better understand the genetics of schizophrenia, we studied the illness in the Xhosa population of South Africa, recruiting 909 cases and 917 age-, gender-, and residence-matched controls. Individuals with schizophrenia were significantly more likely than controls to harbor private, severely damaging mutations in genes that are critical to synaptic function, including neural circuitry mediated by the neurotransmitters glutamine, γ-aminobutyric acid, and dopamine. Schizophrenia is genetically highly heterogeneous, involving severe ultrarare mutations in genes that are critical to synaptic plasticity. The depth of genetic variation in Africa revealed this relationship with a moderate sample size and informed our understanding of the genetics of schizophrenia worldwide.
Keywords: Age Factors; Autistic Disorder; Bipolar Disorder; Dopamine; Female; gamma-Aminobutyric Acid; Genetic Variation; Glutamine; Humans; Male; Mutation; Neural Pathways; Schizophrenia; Sex Factors; South Africa; Synapses; Synaptic Transmission

Genome-enabled insights into the biology of thrips as crop pests. - Rotenberg, Dorith; Baumann, Aaron A; Ben-Mahmoud, Sulley; Christiaens, Olivier; Dermauw, Wannes; Ioannidis, Panagiotis; Jacobs, Chris G C; Vargas Jentzsch, Iris M; Oliver, Jonathan E; Poelchau, Monica F; Rajarapu, Swapna Priya; Schneweis, Derek J; et al. (BMC Biol, 2020)
BACKGROUND: The western flower thrips, Frankliniella occidentalis (Pergande), is a globally invasive pest and plant virus vector on a wide array of food, fiber, and ornamental crops. The underlying genetic mechanisms of the processes governing thrips pest and vector biology, feeding behaviors, ecology, and insecticide resistance are largely unknown. To address this gap, we present the F. occidentalis draft genome assembly and official gene set. RESULTS: We report on the first genome sequence for any member of the insect order Thysanoptera. Benchmarking Universal Single-Copy Ortholog (BUSCO) assessments of the genome assembly (size = 415.8 Mb, scaffold N50 = 948.9 kb) revealed a relatively complete and well-annotated assembly in comparison to other insect genomes. The genome is unusually GC-rich (50%) compared to other insect genomes to date. The official gene set (OGS v1.0) contains 16,859 genes, of which ~ 10% were manually verified and corrected by our consortium. We focused on manual annotation, phylogenetic, and expression evidence analyses for gene sets centered on primary themes in the life histories and activities of plant-colonizing insects. Highlights include the following: (1) divergent clades and large expansions in genes associated with environmental sensing (chemosensory receptors) and detoxification (CYP4, CYP6, and CCE enzymes) of substances encountered in agricultural environments; (2) a comprehensive set of salivary gland genes supported by enriched expression; (3) apparent absence of members of the IMD innate immune defense pathway; and (4) developmental- and sex-specific expression analyses of genes associated with progression from larvae to adulthood through neometaboly, a distinct form of maturation differing from either incomplete or complete metamorphosis in the Insecta. CONCLUSIONS: Analysis of the F. occidentalis genome offers insights into the polyphagous behavior of this insect pest that finds, colonizes, and survives on a widely diverse array of plants. The genomic resources presented here enable a more complete analysis of insect evolution and biology, providing a missing taxon for contemporary insect genomics-based analyses. Our study also offers a genomic benchmark for molecular and evolutionary investigations of other Thysanoptera species.
Keywords: Animals; Crops, Agricultural; Feeding Behavior; Food Chain; Genome, Insect; Immunity, Innate; Life History Traits; Perception; Phylogeny; Reproduction; Thysanoptera; Transcriptome

HEM1 deficiency disrupts mTORC2 and F-actin control in inherited immunodysregulatory disease. - Cook, Sarah A; Comrie, William A; Poli, M Cecilia; Similuk, Morgan; Oler, Andrew J; Faruqi, Aiman J; Kuhns, Douglas B; Yang, Sheng; Vargas-Hernandez, Alexander; Carisey, Alexandre F; Fournier, Benjamin; Anderson, D Eric; et al. (Science, 2020)
Immunodeficiency often coincides with hyperactive immune disorders such as autoimmunity, lymphoproliferation, or atopy, but this coincidence is rarely understood on a molecular level. We describe five patients from four families with immunodeficiency coupled with atopy, lymphoproliferation, and cytokine overproduction harboring mutations in , which encodes the hematopoietic-specific HEM1 protein. These mutations cause the loss of the HEM1 protein and the WAVE regulatory complex (WRC) or disrupt binding to the WRC regulator, Arf1, thereby impairing actin polymerization, synapse formation, and immune cell migration. Diminished cortical actin networks caused by WRC loss led to uncontrolled cytokine release and immune hyperresponsiveness. HEM1 loss also blocked mechanistic target of rapamycin complex 2 (mTORC2)-dependent AKT phosphorylation, T cell proliferation, and selected effector functions, leading to immunodeficiency. Thus, the evolutionarily conserved HEM1 protein simultaneously regulates filamentous actin (F-actin) and mTORC2 signaling to achieve equipoise in immune responses.
Keywords: Actins; ADP-Ribosylation Factor 1; CD4-Positive T-Lymphocytes; Cell Proliferation; Cytokines; Humans; Immunologic Deficiency Syndromes; Lymphoproliferative Disorders; Mechanistic Target of Rapamycin Complex 2; Membrane Proteins; Pedigree; Phosphorylation; Wiskott-Aldrich Syndrome Protein Family

High-depth African genomes inform human migration and health. - Choudhury, Ananyo; Aron, Shaun; Botigué, Laura R; Sengupta, Dhriti; Botha, Gerrit; Bensellak, Taoufik; Wells, Gordon; Kumuthini, Judit; Shriner, Daniel; Fakim, Yasmina J; Ghoorah, Anisah W; Dareng, Eileen; et al. (Nature, 2020)
The African continent is regarded as the cradle of modern humans and African genomes contain more genetic variation than those from any other continent, yet only a fraction of the genetic diversity among African individuals has been surveyed. Here we performed whole-genome sequencing analyses of 426 individuals-comprising 50 ethnolinguistic groups, including previously unsampled populations-to explore the breadth of genomic diversity across Africa. We uncovered more than 3 million previously undescribed variants, most of which were found among individuals from newly sampled ethnolinguistic groups, as well as 62 previously unreported loci that are under strong selection, which were predominantly found in genes that are involved in viral immunity, DNA repair and metabolism. We observed complex patterns of ancestral admixture and putative-damaging and novel variation, both within and between populations, alongside evidence that Zambia was a likely intermediate site along the routes of expansion of Bantu-speaking populations. Pathogenic variants in genes that are currently characterized as medically relevant were uncommon-but in other genes, variants denoted as 'likely pathogenic' in the ClinVar database were commonly observed. Collectively, these findings refine our current understanding of continental migration, identify gene flow and the response to human disease as strong drivers of genome-level population variation, and underscore the scientific imperative for a broader characterization of the genomic diversity of African individuals to understand human ancestry and improve health.
Keywords: Africa; Datasets as Topic; DNA Repair; Female; Gene Flow; Genetic Variation; Genetics, Medical; Genetics, Population; Genome, Human; Genomics; Health; History, Ancient; Human Migration; Humans; Immunity; Language; Male; Metabolism; Selection, Genetic; Whole Genome Sequencing

Human NK cell deficiency as a result of biallelic mutations in MCM10. - Mace, Emily M; Paust, Silke; Conte, Matilde I; Baxley, Ryan M; Schmit, Megan M; Patil, Sagar L; Guilz, Nicole C; Mukherjee, Malini; Pezzi, Ashley E; Chmielowiec, Jolanta; Tatineni, Swetha; Chinn, Ivan K; et al. (J Clin Invest, 2020)
Human natural killer cell deficiency (NKD) arises from inborn errors of immunity that lead to impaired NK cell development, function, or both. Through the understanding of the biological perturbations in individuals with NKD, requirements for the generation of terminally mature functional innate effector cells can be elucidated. Here, we report a cause of NKD resulting from compound heterozygous mutations in minichromosomal maintenance complex member 10 (MCM10) that impaired NK cell maturation in a child with fatal susceptibility to CMV. MCM10 has not been previously associated with monogenic disease and plays a critical role in the activation and function of the eukaryotic DNA replisome. Through evaluation of patient primary fibroblasts, modeling patient mutations in fibroblast cell lines, and MCM10 knockdown in human NK cell lines, we have shown that loss of MCM10 function leads to impaired cell cycle progression and induction of DNA damage-response pathways. By modeling MCM10 deficiency in primary NK cell precursors, including patient-derived induced pluripotent stem cells, we further demonstrated that MCM10 is required for NK cell terminal maturation and acquisition of immunological system function. Together, these data define MCM10 as an NKD gene and provide biological insight into the requirement for the DNA replisome in human NK cell maturation and function.
Keywords: Alleles; Cell Cycle Checkpoints; Cell Differentiation; Cell Line; Codon, Nonsense; DNA Damage; Fatal Outcome; Female; Gene Knockdown Techniques; Heterozygote; Humans; Induced Pluripotent Stem Cells; Infant; Killer Cells, Natural; Male; Minichromosome Maintenance Proteins; Models, Immunological; Mutation; Mutation, Missense; Pedigree; Primary Immunodeficiency Diseases

Integrated sequencing and array comparative genomic hybridization in familial Parkinson disease. - Robak, Laurie A; Du, Renqian; Bo Yuan; Gu, Shen; Alfradique-Dunham, Isabel; Kondapalli, Vismaya; Hinojosa, Evelyn; Stillwell, Amanda; Young, Emily; Zhang, Chaofan; Song, Xiaofei; Du, Haowei; et al. (Neurol Genet, 2020)
OBJECTIVE: To determine how single nucleotide variants (SNVs) and copy number variants (CNVs) contribute to molecular diagnosis in familial Parkinson disease (PD), we integrated exome sequencing (ES) and genome-wide array-based comparative genomic hybridization (aCGH) and further probed CNV structure to reveal mutational mechanisms. METHODS: We performed ES on 110 subjects with PD and a positive family history; 99 subjects were also evaluated using genome-wide aCGH. We interrogated ES and aCGH data for pathogenic SNVs and CNVs at Mendelian PD gene loci. We confirmed SNVs via Sanger sequencing and further characterized CNVs with custom-designed high-density aCGH, droplet digital PCR, and breakpoint sequencing. RESULTS: Using ES, we discovered individuals with known pathogenic SNVs in (p.Glu365Lys, p.Thr408Met, p.Asn409Ser, and p.Leu483Pro) and (p.Arg1441Gly and p.Gly2019Ser). Two subjects were each double heterozygotes for variants in and . Based on aCGH, we additionally discovered cases with an duplication and heterozygous intragenic deletion. Five additional subjects harbored both SNVs (p.Asn52Metfs*29, p.Thr240Met, p.Pro437Leu, and p.Trp453*) and likely disrupting CNVs at the locus, consistent with compound heterozygosity. In nearly all cases, breakpoint sequencing revealed microhomology, a mutational signature consistent with CNV formation due to DNA replication errors. CONCLUSIONS: Integrated ES and aCGH yielded a genetic diagnosis in 19.3% of our familial PD cohort. Our analyses highlight potential mechanisms for and CNV formation, uncover multilocus pathogenic variation, and identify novel SNVs and CNVs for further investigation as potential PD risk alleles.

Low-level parental somatic mosaic SNVs in exomes from a large cohort of trios with diverse suspected Mendelian conditions. - Gambin, Tomasz; Liu, Qian; Karolak, Justyna A; Grochowski, Christopher M; Xie, Nina G; Wu, Lucia R; Yan, Yan Helen; Cao, Ye; Coban Akdemir, Zeynep H; Wilson, Theresa A; Jhangiani, Shalini N; Chen, Ed; et al. (Genet Med, 2020)
PURPOSE: The goal of this study was to assess the scale of low-level parental mosaicism in exome sequencing (ES) databases. METHODS: We analyzed approximately 2000 family trio ES data sets from the Baylor-Hopkins Center for Mendelian Genomics (BHCMG) and Baylor Genetics (BG). Among apparent de novo single-nucleotide variants identified in the affected probands, we selected rare unique variants with variant allele fraction (VAF) between 30% and 70% in the probands and lower than 10% in one of the parents. RESULTS: Of 102 candidate mosaic variants validated using amplicon-based next-generation sequencing, droplet digital polymerase chain reaction, or blocker displacement amplification, 27 (26.4%) were confirmed to be low- (VAF between 1% and 10%) or very low (VAF <1%) level mosaic. Detection precision in parental samples with two or more alternate reads was 63.6% (BHCMG) and 43.6% (BG). In nine investigated individuals, we observed variability of mosaic ratios among blood, saliva, fibroblast, buccal, hair, and urine samples. CONCLUSION: Our computational pipeline enables robust discrimination between true and false positive candidate mosaic variants and efficient detection of low-level mosaicism in ES samples. We confirm that the presence of two or more alternate reads in the parental sample is a reliable predictor of low-level parental somatic mosaicism.
Keywords: Exome; Exome Sequencing; High-Throughput Nucleotide Sequencing; Humans; Mosaicism; Parents

Mapping and characterization of structural variation in 17,795 human genomes. - Abel, Haley J; Larson, David E; Regier, Allison A; Chiang, Colby; Das, Indraniel; Kanchi, Krishna L; Layer, Ryan M; Neale, Benjamin M; Salerno, William J; Reeves, Catherine; Buyske, Steven; Matise, Tara C; et al. (Nature, 2020)
A key goal of whole-genome sequencing for studies of human genetics is to interrogate all forms of variation, including single-nucleotide variants, small insertion or deletion (indel) variants and structural variants. However, tools and resources for the study of structural variants have lagged behind those for smaller variants. Here we used a scalable pipeline to map and characterize structural variants in 17,795 deeply sequenced human genomes. We publicly release site-frequency data to create the largest, to our knowledge, whole-genome-sequencing-based structural variant resource so far. On average, individuals carry 2.9 rare structural variants that alter coding regions; these variants affect the dosage or structure of 4.2 genes and account for 4.0-11.2% of rare high-impact coding alleles. Using a computational model, we estimate that structural variants account for 17.2% of rare alleles genome-wide, with predicted deleterious effects that are equivalent to loss-of-function coding alleles; approximately 90% of such structural variants are noncoding deletions (mean 19.1 per genome). We report 158,991 ultra-rare structural variants and show that 2% of individuals carry ultra-rare megabase-scale structural variants, nearly half of which are balanced or complex rearrangements. Finally, we infer the dosage sensitivity of genes and noncoding elements, and reveal trends that relate to element class and conservation. This work will help to guide the analysis and interpretation of structural variants in the era of whole-genome sequencing.
Keywords: Alleles; Case-Control Studies; Epigenesis, Genetic; Female; Gene Dosage; Genetic Variation; Genetics, Population; Genome, Human; High-Throughput Nucleotide Sequencing; Humans; Male; Molecular Sequence Annotation; Quantitative Trait Loci; Racial Groups; Software; Whole Genome Sequencing

Next Generation Sequencing of 134 Children with Autism Spectrum Disorder and Regression. - Yin, Jiani; Chun, Chun-An; Zavadenko, Nikolay N; Pechatnikova, Natalia L; Naumova, Oxana Yu; Harshavardhan Doddapaneni; Jianhong Hu; Donna M Muzny; Schaaf, Christian P; Grigorenko, Elena L (Genes (Basel), 2020)
Approximately 30% of individuals with autism spectrum disorder (ASD) experience developmental regression, the etiology of which remains largely unknown. We performed a complete literature search and identified 47 genes that had been implicated in such cases. We sequenced these genes in a preselected cohort of 134 individuals with regressive autism. In total, 16 variants in 12 genes with evidence supportive of pathogenicity were identified. They were classified as variants of uncertain significance based on ACMG standards and guidelines. Among these were recurring variants in and , variants in genes that were linked to syndromic forms of ASD (, , , , , and ), and variants in the form of oligogenic heterozygosity (, , and ).
Keywords: Autism Spectrum Disorder; Child; Child, Preschool; Cohort Studies; Disease Progression; Female; Gene Expression Regulation; Genetic Markers; Genetic Predisposition to Disease; High-Throughput Nucleotide Sequencing; Humans; Infant; Male; Mutation

Oligonucleotide capture sequencing of the SARS-CoV-2 genome and subgenomic fragments from COVID-19 individuals. - Harshavardhan Doddapaneni; Cregeen, Sara Javornik; Sucgang, Richard; Meng, Qingchang; Xiang Qin; Avadhanula, Vasanthi; Chao, Hsu; Menon, Vipin; Nicholson, Erin; Henke, David; Piedra, Felipe-Andres; Rajan, Anubama; et al. (bioRxiv, 2020)
The newly emerged and rapidly spreading SARS-CoV-2 causes coronavirus disease 2019 (COVID-19). To facilitate a deeper understanding of the viral biology we developed a capture sequencing methodology to generate SARS-CoV-2 genomic and transcriptome sequences from infected patients. We utilized an oligonucleotide probe-set representing the full-length genome to obtain both genomic and transcriptome (subgenomic open reading frames [ORFs]) sequences from 45 SARS-CoV-2 clinical samples with varying viral titers. For samples with higher viral loads (cycle threshold value under 33, based on the CDC qPCR assay) complete genomes were generated. Analysis of junction reads revealed regions of differential transcriptional activity and provided evidence of expression of ORF10. Heterogeneous allelic frequencies along the 20kb ORF1ab gene suggested the presence of a defective interfering viral RNA species subpopulation in one sample. The associated workflow is straightforward, and hybridization-based capture offers an effective and scalable approach for sequencing SARS-CoV-2 from patient samples.

Oligonucleotide Capture Sequencing of the SARS-CoV-2 Genome and Subgenomic Fragments from COVID-19 Individuals. - Harshavardhan Doddapaneni; Cregeen, Sara Javornik; Sucgang, Richard; Meng, Qingchang; Xiang Qin; Avadhanula, Vasanthi; Chao, Hsu; Menon, Vipin; Nicholson, Erin; Henke, David; Piedra, Felipe-Andres; Rajan, Anubama; et al. (bioRxiv, 2020)
The newly emerged and rapidly spreading SARS-CoV-2 causes coronavirus disease 2019 (COVID-19). To facilitate a deeper understanding of the viral biology we developed a capture sequencing methodology to generate SARS-CoV-2 genomic and transcriptome sequences from infected patients. We utilized an oligonucleotide probe-set representing the full-length genome to obtain both genomic and transcriptome (subgenomic open reading frames [ORFs]) sequences from 45 SARS-CoV-2 clinical samples with varying viral titers. For samples with higher viral loads (cycle threshold value under 33, based on the CDC qPCR assay) complete genomes were generated. Analysis of junction reads revealed regions of differential transcriptional activity and provided evidence of expression of ORF10. Heterogeneous allelic frequencies along the 20kb ORF1ab gene suggested the presence of a defective interfering viral RNA species subpopulation in one sample. The associated workflow is straightforward, and hybridization-based capture offers an effective and scalable approach for sequencing SARS-CoV-2 from patient samples.

Paternal age in rhesus macaques is positively associated with germline mutation accumulation but not with measures of offspring sociability. - Wang, Richard J; Thomas, Gregg W C; Raveendran, Muthuswamy; R. Alan Harris; Harshavardhan Doddapaneni; Donna M Muzny; Capitanio, John P; Radivojac, Predrag; Jeffrey Rogers; Hahn, Matthew W (Genome Res, 2020)
Mutation is the ultimate source of all genetic novelty and the cause of heritable genetic disorders. Mutational burden has been linked to complex disease, including neurodevelopmental disorders such as schizophrenia and autism. The rate of mutation is a fundamental genomic parameter and direct estimates of this parameter have been enabled by accurate comparisons of whole-genome sequences between parents and offspring. Studies in humans have revealed that the paternal age at conception explains most of the variation in mutation rate: Each additional year of paternal age in humans leads to approximately 1.5 additional inherited mutations. Here, we present an estimate of the de novo mutation rate in the rhesus macaque () using whole-genome sequence data from 32 individuals in four large pedigrees. We estimated an average mutation rate of 0.58 × 10 per base pair per generation (at an average parental age of 7.5 yr), much lower than found in direct estimates from great apes. As in humans, older macaque fathers transmit more mutations to their offspring, increasing the per generation mutation rate by 4.27 × 10 per base pair per year. We found that the rate of mutation accumulation after puberty is similar between macaques and humans, but that a smaller number of mutations accumulate before puberty in macaques. We additionally investigated the role of paternal age on offspring sociability, a proxy for normal neurodevelopment, by studying 203 male macaques in large social groups.
Keywords: Age Factors; Animals; Behavior, Animal; Female; Germ-Line Mutation; Humans; Macaca mulatta; Male; Mutation Accumulation; Mutation Rate; Paternal Age; Pregnancy; Prenatal Exposure Delayed Effects; Social Skills; Species Specificity

PCM1 is necessary for focal ciliary integrity and is a candidate for severe schizophrenia. - Monroe, Tanner O; Garrett, Melanie E; Kousi, Maria; Rodriguiz, Ramona M; Moon, Sungjin; Bai, Yushi; Brodar, Steven C; Soldano, Karen L; Savage, Jeremiah; Hansen, Thomas F; Donna M Muzny; Richard A Gibbs; et al. (Nat Commun, 2020)
The neuronal primary cilium and centriolar satellites have functions in neurogenesis, but little is known about their roles in the postnatal brain. We show that ablation of pericentriolar material 1 in the mouse leads to progressive ciliary, anatomical, psychomotor, and cognitive abnormalities. RNAseq reveals changes in amine- and G-protein coupled receptor pathways. The physiological relevance of this phenotype is supported by decreased available dopamine D2 receptor (D2R) levels and the failure of antipsychotic drugs to rescue adult behavioral defects. Immunoprecipitations show an association with Pcm1 and D2Rs. Finally, we sequence PCM1 in two human cohorts with severe schizophrenia. Systematic modeling of all discovered rare alleles by zebrafish in vivo complementation reveals an enrichment for pathogenic alleles. Our data emphasize a role for the pericentriolar material in the postnatal brain, with progressive degenerative ciliary and behavioral phenotypes; and they support a contributory role for PCM1 in some individuals diagnosed with schizophrenia.
Keywords: Adult; Aged; Alleles; Amines; Animals; Antipsychotic Agents; Brain; Cell Cycle Proteins; Cilia; Drug Resistance; Genetic Predisposition to Disease; Humans; Mice; Mice, Knockout; Middle Aged; Mutation; Phenotype; Receptors, Dopamine D2; Receptors, G-Protein-Coupled; Schizophrenia; Signal Transduction; Young Adult; Zebrafish

Phenotypic expansion in KIF1A-related dominant disorders: A description of novel variants and review of published cases. - Montenegro-Garreaud, Ximena; Hansen, Adam W; Khayat, Michael M; Chander, Varuna; Grochowski, Christopher M; Jiang, Yunyun; Li, He; Mitani, Tadahiro; Kessler, Elena; Jayaseelan, Joy; Shen, Hua; Gezdirici, Alper; et al. (Hum Mutat, 2020)
KIF1A is a molecular motor for membrane-bound cargo important to the development and survival of sensory neurons. KIF1A dysfunction has been associated with several Mendelian disorders with a spectrum of overlapping phenotypes, ranging from spastic paraplegia to intellectual disability. We present a novel pathogenic in-frame deletion in the KIF1A molecular motor domain inherited by two affected siblings from an unaffected mother with apparent germline mosaicism. We identified eight additional cases with heterozygous, pathogenic KIF1A variants ascertained from a local data lake. Our data provide evidence for the expansion of KIF1A-associated phenotypes to include hip subluxation and dystonia as well as phenotypes observed in only a single case: gelastic cataplexy, coxa valga, and double collecting system. We review the literature and suggest that KIF1A dysfunction is better understood as a single neuromuscular disorder with variable involvement of other organ systems than a set of discrete disorders converging at a single locus.
Keywords: Child; Child, Preschool; Family; Female; Genes, Dominant; Genetic Predisposition to Disease; Humans; Kinesins; Male; Mutation; Pedigree; Peru; Phenotype

Primate phylogenomics uncovers multiple rapid radiations and ancient interspecific introgression. - Vanderpool, Dan; Minh, Bui Quang; Lanfear, Robert; Hughes, Daniel; Murali, Shwetha; R. Alan Harris; Raveendran, Muthuswamy; Donna M Muzny; Hibbins, Mark S; Williamson, Robert J; Richard A Gibbs; Kim C Worley; et al. (PLoS Biol, 2020)
Our understanding of the evolutionary history of primates is undergoing continual revision due to ongoing genome sequencing efforts. Bolstered by growing fossil evidence, these data have led to increased acceptance of once controversial hypotheses regarding phylogenetic relationships, hybridization and introgression, and the biogeographical history of primate groups. Among these findings is a pattern of recent introgression between species within all major primate groups examined to date, though little is known about introgression deeper in time. To address this and other phylogenetic questions, here, we present new reference genome assemblies for 3 Old World monkey (OWM) species: Colobus angolensis ssp. palliatus (the black and white colobus), Macaca nemestrina (southern pig-tailed macaque), and Mandrillus leucophaeus (the drill). We combine these data with 23 additional primate genomes to estimate both the species tree and individual gene trees using thousands of loci. While our species tree is largely consistent with previous phylogenetic hypotheses, the gene trees reveal high levels of genealogical discordance associated with multiple primate radiations. We use strongly asymmetric patterns of gene tree discordance around specific branches to identify multiple instances of introgression between ancestral primate lineages. In addition, we exploit recent fossil evidence to perform fossil-calibrated molecular dating analyses across the tree. Taken together, our genome-wide data help to resolve multiple contentious sets of relationships among primates, while also providing insight into the biological processes and technical artifacts that led to the disagreements in the first place.
Keywords: Animals; Biological Evolution; Cercopithecidae; Computational Biology; Databases, Genetic; Fossils; Gene Flow; Genetic Introgression; Genome; Models, Genetic; Phylogeny; Primates; Sequence Analysis, DNA

Sawfly Genomes Reveal Evolutionary Acquisitions That Fostered the Mega-Radiation of Parasitoid and Eusocial Hymenoptera. - Oeyen, Jan Philip; Baa-Puyoulet, Patrice; Benoit, Joshua B; Beukeboom, Leo W; Bornberg-Bauer, Erich; Buttstedt, Anja; Calevro, Federica; Cash, Elizabeth I; Chao, Hsu; Charles, Hubert; Chen, Mei-Ju May; Childers, Christopher; et al. (Genome Biol Evol, 2020)
The tremendous diversity of Hymenoptera is commonly attributed to the evolution of parasitoidism in the last common ancestor of parasitoid sawflies (Orussidae) and wasp-waisted Hymenoptera (Apocrita). However, Apocrita and Orussidae differ dramatically in their species richness, indicating that the diversification of Apocrita was promoted by additional traits. These traits have remained elusive due to a paucity of sawfly genome sequences, in particular those of parasitoid sawflies. Here, we present comparative analyses of draft genomes of the primarily phytophagous sawfly Athalia rosae and the parasitoid sawfly Orussus abietinus. Our analyses revealed that the ancestral hymenopteran genome exhibited traits that were previously considered unique to eusocial Apocrita (e.g., low transposable element content and activity) and a wider gene repertoire than previously thought (e.g., genes for CO2 detection). Moreover, we discovered that Apocrita evolved a significantly larger array of odorant receptors than sawflies, which could be relevant to the remarkable diversification of Apocrita by enabling efficient detection and reliable identification of hosts.
Keywords: Amino Acid Sequence; Animals; Conserved Sequence; DNA Transposable Elements; Female; Gene Dosage; Genetic Speciation; Genome, Insect; Glycoproteins; Herbivory; Host-Parasite Interactions; Hymenoptera; Immunity; Insect Proteins; Male; Multigene Family; Receptors, Odorant; Social Behavior; Vision, Ocular

Sequence analysis in reveals pervasiveness of X-Y arms races in mammalian lineages. - Hughes, Jennifer F; Skaletsky, Helen; Pyntikova, Tatyana; Koutseva, Natalia; Raudsepp, Terje; Brown, Laura G; Bellott, Daniel W; Cho, Ting-Jan; Dugan-Rocha, Shannon; Ziad Khan; Kremitzki, Colin; Fronick, Catrina; et al. (Genome Res, 2020)
Studies of Y Chromosome evolution have focused primarily on gene decay, a consequence of suppression of crossing-over with the X Chromosome. Here, we provide evidence that suppression of X-Y crossing-over unleashed a second dynamic: selfish X-Y arms races that reshaped the sex chromosomes in mammals as different as cattle, mice, and men. Using super-resolution sequencing, we explore the Y Chromosome of (bull) and find it to be dominated by massive, lineage-specific amplification of testis-expressed gene families, making it the most gene-dense Y Chromosome sequenced to date. As in mice, an X-linked homolog of a bull Y-amplified gene has become testis-specific and amplified. This evolutionary convergence implies that lineage-specific X-Y coevolution through gene amplification, and the selfish forces underlying this phenomenon, were dominatingly powerful among diverse mammalian lineages. Together with Y gene decay, X-Y arms races molded mammalian sex chromosomes and influenced the course of mammalian evolution.
Keywords: Animals; Cattle; Cell Lineage; Crossing Over, Genetic; Evolution, Molecular; Female; Gene Amplification; Humans; Male; Mice; Organ Specificity; Sequence Analysis, DNA; Testis; X Chromosome; Y Chromosome

Whole exome sequencing study identifies novel rare and common Alzheimer's-Associated variants involved in immune response and transcriptional regulation. - Bis, Joshua C; Jian, Xueqiu; Kunkle, Brian W; Chen, Yuning; Hamilton-Nelson, Kara L; Bush, William S; Salerno, William J; Lancour, Daniel; Ma, Yiyi; Renton, Alan E; Marcora, Edoardo; Farrell, John J; et al. (Mol Psychiatry, 2020)
The Alzheimer's Disease Sequencing Project (ADSP) undertook whole exome sequencing in 5,740 late-onset Alzheimer disease (AD) cases and 5,096 cognitively normal controls primarily of European ancestry (EA), among whom 218 cases and 177 controls were Caribbean Hispanic (CH). An age-, sex- and APOE based risk score and family history were used to select cases most likely to harbor novel AD risk variants and controls least likely to develop AD by age 85 years. We tested ~1.5 million single nucleotide variants (SNVs) and 50,000 insertion-deletion polymorphisms (indels) for association to AD, using multiple models considering individual variants as well as gene-based tests aggregating rare, predicted functional, and loss of function variants. Sixteen single variants and 19 genes that met criteria for significant or suggestive associations after multiple-testing correction were evaluated for replication in four independent samples; three with whole exome sequencing (2,778 cases, 7,262 controls) and one with genome-wide genotyping imputed to the Haplotype Reference Consortium panel (9,343 cases, 11,527 controls). The top findings in the discovery sample were also followed-up in the ADSP whole-genome sequenced family-based dataset (197 members of 42 EA families and 501 members of 157 CH families). We identified novel and predicted functional genetic variants in genes previously associated with AD. We also detected associations in three novel genes: IGHG3 (p = 9.8 × 10), an immunoglobulin gene whose antibodies interact with β-amyloid, a long non-coding RNA AC099552.4 (p = 1.2 × 10), and a zinc-finger protein ZNF655 (gene-based p = 5.0 × 10). The latter two suggest an important role for transcriptional regulation in AD pathogenesis.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Apolipoproteins E; Exome Sequencing; Female; Gene Expression Regulation; Haplotypes; Humans; Immunity; Immunoglobulin G; Kruppel-Like Transcription Factors; Male; Polymorphism, Genetic; RNA, Long Noncoding; Transcription, Genetic

Whole genome sequence analysis of pulmonary function and COPD in 19,996 multi-ethnic participants. - Zhao, Xutong; Qiao, Dandi; Yang, Chaojie; Kasela, Silva; Kim, Wonji; Ma, Yanlin; Shrine, Nick; Batini, Chiara; Sofer, Tamar; Taliun, Sarah A Gagliano; Sakornsakolpat, Phuwanat; Balte, Pallavi P; et al. (Nat Commun, 2020)
Chronic obstructive pulmonary disease (COPD), diagnosed by reduced lung function, is a leading cause of morbidity and mortality. We performed whole genome sequence (WGS) analysis of lung function and COPD in a multi-ethnic sample of 11,497 participants from population- and family-based studies, and 8499 individuals from COPD-enriched studies in the NHLBI Trans-Omics for Precision Medicine (TOPMed) Program. We identify at genome-wide significance 10 known GWAS loci and 22 distinct, previously unreported loci, including two common variant signals from stratified analysis of African Americans. Four novel common variants within the regions of PIAS1, RGN (two variants) and FTO show evidence of replication in the UK Biobank (European ancestry n ~ 320,000), while colocalization analyses leveraging multi-omic data from GTEx and TOPMed identify potential molecular mechanisms underlying four of the 22 novel loci. Our study demonstrates the value of performing WGS analyses and multi-omic follow-up in cohorts of diverse ancestry.
Keywords: Adult; Aged; Aged, 80 and over; Alpha-Ketoglutarate-Dependent Dioxygenase FTO; Black or African American; Calcium-Binding Proteins; Feasibility Studies; Female; Follow-Up Studies; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Intracellular Signaling Peptides and Proteins; Lung; Male; Middle Aged; Polymorphism, Single Nucleotide; Protein Inhibitors of Activated STAT; Pulmonary Disease, Chronic Obstructive; Respiratory Physiological Phenomena; Small Ubiquitin-Related Modifier Proteins; Whole Genome Sequencing

Wolff-Parkinson-White syndrome: De novo variants and evidence for mutational burden in genes associated with atrial fibrillation. - Coban-Akdemir, Zeynep H; Charng, Wu-Lin; Azamian, Mahshid; Paine, Ingrid S; Punetha, Jaya; Grochowski, Christopher M; Gambin, Tomasz; Valdes, Santiago O; Cannon, Bryan; Zapata, Gladys; Hernandez, Patricia P; Jhangiani, Shalini; et al. (Am J Med Genet A, 2020)
BACKGROUND: Wolff-Parkinson-White (WPW) syndrome is a relatively common arrhythmia affecting ~1-3/1,000 individuals. Mutations in PRKAG2 have been described in rare patients in association with cardiomyopathy. However, the genetic basis of WPW in individuals with a structurally normal heart remains poorly understood. Sudden death due to atrial fibrillation (AF) can also occur in these individuals. Several studies have indicated that despite ablation of an accessory pathway, the risk of AF remains high in patients compared to general population. METHODS: We applied exome sequencing in 305 subjects, including 65 trios, 80 singletons, and 6 multiple affected families. We used de novo analysis, candidate gene approach, and burden testing to explore the genetic contributions to WPW. RESULTS: A heterozygous deleterious variant in PRKAG2 was identified in one subject, accounting for 0.6% (1/151) of the genetic basis of WPW in this study. Another individual with WPW and left ventricular hypertrophy carried a known pathogenic variant in MYH7. We found rare de novo variants in genes associated with arrhythmia and cardiomyopathy (ANK2, NEBL, PITX2, and PRDM16) in this cohort. There was an increased burden of rare deleterious variants (MAF ≤ 0.005) with CADD score ≥ 25 in genes linked to AF in cases compared to controls (P = .0023). CONCLUSIONS: Our findings show an increased burden of rare deleterious variants in genes linked to AF in WPW syndrome, suggesting that genetic factors that determine the development of accessory pathways may be linked to an increased susceptibility of atrial muscle to AF in a subset of patients.
Keywords: Adolescent; Adult; AMP-Activated Protein Kinases; Ankyrins; Atrial Fibrillation; Carrier Proteins; Child; Cohort Studies; Cytoskeletal Proteins; DNA-Binding Proteins; Exome Sequencing; Female; Genetic Association Studies; Genetic Predisposition to Disease; Heart Atria; Homeodomain Proteins; Humans; LIM Domain Proteins; Male; Mutation; Transcription Factors; Wolff-Parkinson-White Syndrome; Young Adult

Atlas-CNV: a validated approach to call single-exon CNVs in the eMERGESeq gene panel. - Chiang, Theodore; Liu, Xiuping; Wu, Tsung-Jung; Jianhong Hu; Fritz J Sedlazeck; White, Simon; Schaid, Daniel; Andrade, Mariza de; Jarvik, Gail P; Crosslin, David; Stanaway, Ian; Carrell, David S; et al. (Genet Med, 2019)
PURPOSE: To provide a validated method to confidently identify exon-containing copy-number variants (CNVs), with a low false discovery rate (FDR), in targeted sequencing data from a clinical laboratory with particular focus on single-exon CNVs. METHODS: DNA sequence coverage data are normalized within each sample and subsequently exonic CNVs are identified in a batch of samples, when the target log ratio of the sample to the batch median exceeds defined thresholds. The quality of exonic CNV calls is assessed by C-scores (Z-like scores) using thresholds derived from gold standard samples and simulation studies. We integrate an ExonQC threshold to lower FDR and compare performance with alternate software (VisCap). RESULTS: Thirteen CNVs were used as a truth set to validate Atlas-CNV and compared with VisCap. We demonstrated FDR reduction in validation, simulation, and 10,926 eMERGESeq samples without sensitivity loss. Sixty-four multiexon and 29 single-exon CNVs with high C-scores were assessed by Multiplex Ligation-dependent Probe Amplification (MLPA). CONCLUSION: Atlas-CNV is validated as a method to identify exonic CNVs in targeted sequencing data generated in the clinical laboratory. The ExonQC and C-score assignment can reduce FDR (identification of targets with high variance) and improve calling accuracy of single-exon CNVs respectively. We propose guidelines and criteria to identify high confidence single-exon CNVs.
Keywords: DNA Copy Number Variations; Exons; Genome, Human; High-Throughput Nucleotide Sequencing; Humans; Sequence Analysis, DNA; Software

Bi-allelic Variants in TONSL Cause SPONASTRIME Dysplasia and a Spectrum of Skeletal Dysplasia Phenotypes. - Burrage, Lindsay C; Reynolds, John J; Baratang, Nissan Vida; Phillips, Jennifer B; Wegner, Jeremy; McFarquhar, Ashley; Higgs, Martin R; Christiansen, Audrey E; Lanza, Denise G; Seavitt, John R; Jain, Mahim; Li, Xiaohui; et al. (Am J Hum Genet, 2019)
SPONASTRIME dysplasia is an autosomal-recessive spondyloepimetaphyseal dysplasia characterized by spine (spondylar) abnormalities, midface hypoplasia with a depressed nasal bridge, metaphyseal striations, and disproportionate short stature. Scoliosis, coxa vara, childhood cataracts, short dental roots, and hypogammaglobulinemia have also been reported in this disorder. Although an autosomal-recessive inheritance pattern has been hypothesized, pathogenic variants in a specific gene have not been discovered in individuals with SPONASTRIME dysplasia. Here, we identified bi-allelic variants in TONSL, which encodes the Tonsoku-like DNA repair protein, in nine subjects (from eight families) with SPONASTRIME dysplasia, and four subjects (from three families) with short stature of varied severity and spondylometaphyseal dysplasia with or without immunologic and hematologic abnormalities, but no definitive metaphyseal striations at diagnosis. The finding of early embryonic lethality in a Tonsl murine model and the discovery of reduced length, spinal abnormalities, reduced numbers of neutrophils, and early lethality in a tonsl zebrafish model both support the hypomorphic nature of the identified TONSL variants. Moreover, functional studies revealed increased amounts of spontaneous replication fork stalling and chromosomal aberrations, as well as fewer camptothecin (CPT)-induced RAD51 foci in subject-derived cell lines. Importantly, these cellular defects were rescued upon re-expression of wild-type (WT) TONSL; this rescue is consistent with the hypothesis that hypomorphic TONSL variants are pathogenic. Overall, our studies in humans, mice, zebrafish, and subject-derived cell lines confirm that pathogenic variants in TONSL impair DNA replication and homologous recombination-dependent repair processes, and they lead to a spectrum of skeletal dysplasia phenotypes with numerous extra-skeletal manifestations.
Keywords: Adolescent; Adult; Alleles; Animals; Cells, Cultured; Child; Child, Preschool; Chromosomal Instability; DNA Damage; Exome Sequencing; Female; Fibroblasts; Genetic Association Studies; Genetic Variation; Humans; Mice; Mice, Knockout; Musculoskeletal Abnormalities; NF-kappa B; Osteochondrodysplasias; Young Adult; Zebrafish

The comparative genomics and complex population history of baboons. - Jeffrey Rogers; Raveendran, Muthuswamy; R. Alan Harris; Mailund, Thomas; Leppälä, Kalle; Athanasiadis, Georgios; Schierup, Mikkel Heide; Cheng, Jade; Munch, Kasper; Walker, Jerilyn A; Konkel, Miriam K; Jordan, Vallmer; et al. (Sci Adv, 2019)
Recent studies suggest that closely related species can accumulate substantial genetic and phenotypic differences despite ongoing gene flow, thus challenging traditional ideas regarding the genetics of speciation. Baboons (genus ) are Old World monkeys consisting of six readily distinguishable species. Baboon species hybridize in the wild, and prior data imply a complex history of differentiation and introgression. We produced a reference genome assembly for the olive baboon () and whole-genome sequence data for all six extant species. We document multiple episodes of admixture and introgression during the radiation of baboons, thus demonstrating their value as a model of complex evolutionary divergence, hybridization, and reticulation. These results help inform our understanding of similar cases, including modern humans, Neanderthals, Denisovans, and other ancient hominins.
Keywords: Animals; Base Sequence; Biological Evolution; Female; Gene Flow; Genomics; Haplotypes; Humans; Hybridization, Genetic; Male; Papio; Phylogeny; Polymorphism, Genetic; Whole Genome Sequencing

Copy number variant and runs of homozygosity detection by microarrays enabled more precise molecular diagnoses in 11,020 clinical exome cases. - Dharmadhikari, Avinash V; Ghosh, Rajarshi; Bo Yuan; Liu, Pengfei; Dai, Hongzheng; Al Masri, Sami; Scull, Jennifer; Posey, Jennifer E; Jiang, Allen H; He, Weimin; Vetrini, Francesco; Braxton, Alicia A; et al. (Genome Med, 2019)
BACKGROUND: Exome sequencing (ES) has been successfully applied in clinical detection of single nucleotide variants (SNVs) and small indels. However, identification of copy number variants (CNVs) using ES data remains challenging. The purpose of this study is to understand the contribution of CNVs and copy neutral runs of homozygosity (ROH) in molecular diagnosis of patients referred for ES. METHODS: In a cohort of 11,020 consecutive ES patients, an Illumina SNP array analysis interrogating mostly coding SNPs was performed as a quality control (QC) measurement and for CNV/ROH detection. Among these patients, clinical chromosomal microarray analysis (CMA) was performed at Baylor Genetics (BG) on 3229 patients, either before, concurrently, or after ES. We retrospectively analyzed the findings from CMA and the QC array. RESULTS: The QC array can detect ~ 70% of pathogenic/likely pathogenic CNVs (PCNVs) detectable by CMA. Out of the 11,020 ES cases, the QC array identified PCNVs in 327 patients and uniparental disomy (UPD) disorder-related ROH in 10 patients. The overall PCNV/UPD detection rate was 5.9% in the 3229 ES patients who also had CMA at BG; PCNV/UPD detection rate was higher in concurrent ES and CMA than in ES with prior CMA (7.2% vs 4.6%). The PCNVs/UPD contributed to the molecular diagnoses in 17.4% (189/1089) of molecularly diagnosed ES cases with CMA and were estimated to contribute in 10.6% of all molecularly diagnosed ES cases. Dual diagnoses with both PCNVs and SNVs were detected in 38 patients. PCNVs affecting single recessive disorder genes in a compound heterozygous state with SNVs were detected in 4 patients, and homozygous deletions (mostly exonic deletions) were detected in 17 patients. A higher PCNV detection rate was observed for patients with syndromic phenotypes and/or cardiovascular abnormalities. CONCLUSIONS: Our clinical genomics study demonstrates that detection of PCNV/UPD through the QC array or CMA increases ES diagnostic rate, provides more precise molecular diagnosis for dominant as well as recessive traits, and enables more complete genetic diagnoses in patients with dual or multiple molecular diagnoses. Concurrent ES and CMA using an array with exonic coverage for disease genes enables most effective detection of both CNVs and SNVs and therefore is recommended especially in time-sensitive clinical situations.
Keywords: Chromosome Aberrations; DNA Copy Number Variations; Exome Sequencing; Female; Genetic Testing; Homozygote; Humans; Limit of Detection; Male; Microarray Analysis

Correction to: De novo and inherited TCF20 pathogenic variants are associated with intellectual disability, dysmorphic features, hypotonia, and neurological impairments with similarities to Smith-Magenis syndrome. - Vetrini, Francesco; McKee, Shane; Rosenfeld, Jill A; Suri, Mohnish; Lewis, Andrea M; Nugent, Kimberly Margaret; Roeder, Elizabeth; Littlejohn, Rebecca O; Holder, Sue; Zhu, Wenmiao; Alaimo, Joseph T; Graham, Brett; et al. (Genome Med, 2019)
It was highlighted that the original article [1] contained a typographical error in the Results section. Subject 17 was incorrectly cited as Subject 1. This Correction article shows the revised statement. The original article has been updated.

De novo and inherited TCF20 pathogenic variants are associated with intellectual disability, dysmorphic features, hypotonia, and neurological impairments with similarities to Smith-Magenis syndrome. - Vetrini, Francesco; McKee, Shane; Rosenfeld, Jill A; Suri, Mohnish; Lewis, Andrea M; Nugent, Kimberly Margaret; Roeder, Elizabeth; Littlejohn, Rebecca O; Holder, Sue; Zhu, Wenmiao; Alaimo, Joseph T; Graham, Brett; et al. (Genome Med, 2019)
BACKGROUND: Neurodevelopmental disorders are genetically and phenotypically heterogeneous encompassing developmental delay (DD), intellectual disability (ID), autism spectrum disorders (ASDs), structural brain abnormalities, and neurological manifestations with variants in a large number of genes (hundreds) associated. To date, a few de novo mutations potentially disrupting TCF20 function in patients with ID, ASD, and hypotonia have been reported. TCF20 encodes a transcriptional co-regulator structurally related to RAI1, the dosage-sensitive gene responsible for Smith-Magenis syndrome (deletion/haploinsufficiency) and Potocki-Lupski syndrome (duplication/triplosensitivity). METHODS: Genome-wide analyses by exome sequencing (ES) and chromosomal microarray analysis (CMA) identified individuals with heterozygous, likely damaging, loss-of-function alleles in TCF20. We implemented further molecular and clinical analyses to determine the inheritance of the pathogenic variant alleles and studied the spectrum of phenotypes. RESULTS: We report 25 unique inactivating single nucleotide variants/indels (1 missense, 1 canonical splice-site variant, 18 frameshift, and 5 nonsense) and 4 deletions of TCF20. The pathogenic variants were detected in 32 patients and 4 affected parents from 31 unrelated families. Among cases with available parental samples, the variants were de novo in 20 instances and inherited from 4 symptomatic parents in 5, including in one set of monozygotic twins. Two pathogenic loss-of-function variants were recurrent in unrelated families. Patients presented with a phenotype characterized by developmental delay, intellectual disability, hypotonia, variable dysmorphic features, movement disorders, and sleep disturbances. CONCLUSIONS: TCF20 pathogenic variants are associated with a novel syndrome manifesting clinical characteristics similar to those observed in Smith-Magenis syndrome. Together with previously described cases, the clinical entity of TCF20-associated neurodevelopmental disorders (TAND) emerges from a genotype-driven perspective.
Keywords: Adolescent; Child; Child, Preschool; Craniofacial Abnormalities; Developmental Disabilities; Female; Humans; INDEL Mutation; Infant; Intellectual Disability; Male; Muscle Hypotonia; Smith-Magenis Syndrome; Transcription Factors; Young Adult

Exome sequencing of 457 autism families recruited online provides evidence for autism risk genes. - Feliciano, Pamela; Zhou, Xueya; Astrovskaya, Irina; Turner, Tychele N; Wang, Tianyun; Brueggeman, Leo; Barnard, Rebecca; Hsieh, Alexander; Snyder, LeeAnne Green; Donna M Muzny; Aniko Sabo; Richard A Gibbs; et al. (NPJ Genom Med, 2019)
Autism spectrum disorder (ASD) is a genetically heterogeneous condition, caused by a combination of rare de novo and inherited variants as well as common variants in at least several hundred genes. However, significantly larger sample sizes are needed to identify the complete set of genetic risk factors. We conducted a pilot study for SPARK (SPARKForAutism.org) of 457 families with ASD, all consented online. Whole exome sequencing (WES) and genotyping data were generated for each family using DNA from saliva. We identified variants in genes and loci that are clinically recognized causes or significant contributors to ASD in 10.4% of families without previous genetic findings. In addition, we identified variants that are possibly associated with ASD in an additional 3.4% of families. A meta-analysis using the TADA framework at a false discovery rate (FDR) of 0.1 provides statistical support for 26 ASD risk genes. While most of these genes are already known ASD risk genes, has the strongest statistical support and reaches genome-wide significance as a risk gene for ASD (-value = 2.3e-06). Future studies leveraging the thousands of individuals with ASD who have enrolled in SPARK are likely to further clarify the genetic risk factors associated with ASD as well as allow accelerate ASD research that incorporates genetic etiology.

Exome Sequencing of a Primary Ovarian Insufficiency Cohort Reveals Common Molecular Etiologies for a Spectrum of Disease. - Jolly, Angad; Bayram, Yavuz; Turan, Serap; Aycan, Zehra; Tos, Tulay; Abali, Zehra Yavas; Hacihamdioglu, Bulent; Coban Akdemir, Zeynep Hande; Hijazi, Hadia; Bas, Serpil; Atay, Zeynep; Guran, Tulay; et al. (J Clin Endocrinol Metab, 2019)
CONTEXT: Primary ovarian insufficiency (POI) encompasses a spectrum of premature menopause, including both primary and secondary amenorrhea. For 75% to 90% of individuals with hypergonadotropic hypogonadism presenting as POI, the molecular etiology is unknown. Common etiologies include chromosomal abnormalities, environmental factors, and congenital disorders affecting ovarian development and function, as well as syndromic and nonsyndromic single gene disorders suggesting POI represents a complex trait. OBJECTIVE: To characterize the contribution of known disease genes to POI and identify molecular etiologies and biological underpinnings of POI. DESIGN, SETTING, AND PARTICIPANTS: We applied exome sequencing (ES) and family-based genomics to 42 affected female individuals from 36 unrelated Turkish families, including 31 with reported parental consanguinity. RESULTS: This analysis identified likely damaging, potentially contributing variants and molecular diagnoses in 16 families (44%), including 11 families with likely damaging variants in known genes and five families with predicted deleterious variants in disease genes (IGSF10, MND1, MRPS22, and SOHLH1) not previously associated with POI. Of the 16 families, 2 (13%) had evidence for potentially pathogenic variants at more than one locus. Absence of heterozygosity consistent with identity-by-descent mediated recessive disease burden contributes to molecular diagnosis in 15 of 16 (94%) families. GeneMatcher allowed identification of additional families from diverse genetic backgrounds. CONCLUSIONS: ES analysis of a POI cohort further characterized locus heterogeneity, reaffirmed the association of genes integral to meiotic recombination, demonstrated the likely contribution of genes involved in hypothalamic development, and documented multilocus pathogenic variation suggesting the potential for oligogenic inheritance contributing to the development of POI.
Keywords: Cell Cycle Proteins; Cohort Studies; DNA Helicases; DNA-Binding Proteins; Exome Sequencing; Female; Gene Frequency; Humans; Hypogonadism; Immunoglobulins; Minichromosome Maintenance Proteins; Primary Ovarian Insufficiency

Genetic architecture of laterality defects revealed by whole exome sequencing. - Li, Alexander H; Hanchard, Neil A; Azamian, Mahshid; D'Alessandro, Lisa C A; Coban-Akdemir, Zeynep; Lopez, Keila N; Hall, Nancy J; Dickerson, Heather; Nicosia, Annarita; Fernbach, Susan; Boone, Philip M; Gambin, Tomaz; et al. (Eur J Hum Genet, 2019)
Aberrant left-right patterning in the developing human embryo can lead to a broad spectrum of congenital malformations. The causes of most laterality defects are not known, with variants in established genes accounting for <20% of cases. We sought to characterize the genetic spectrum of these conditions by performing whole-exome sequencing of 323 unrelated laterality cases. We investigated the role of rare, predicted-damaging variation in 1726 putative laterality candidate genes derived from model organisms, pathway analyses, and human phenotypes. We also evaluated the contribution of homo/hemizygous exon deletions and gene-based burden of rare variation. A total of 28 candidate variants (26 rare predicted-damaging variants and 2 hemizygous deletions) were identified, including variants in genes known to cause heterotaxy and primary ciliary dyskinesia (ACVR2B, NODAL, ZIC3, DNAI1, DNAH5, HYDIN, MMP21), and genes without a human phenotype association, but with prior evidence for a role in embryonic laterality or cardiac development. Sanger validation of the latter variants in probands and their parents revealed no de novo variants, but apparent transmitted heterozygous (ROCK2, ISL1, SMAD2), and hemizygous (RAI2, RIPPLY1) variant patterns. Collectively, these variants account for 7.1% of our study subjects. We also observe evidence for an excess burden of rare, predicted loss-of-function variation in PXDNL and BMS1- two genes relevant to the broader laterality phenotype. These findings highlight potential new genes in the development of laterality defects, and suggest extensive locus heterogeneity and complex genetic models in this class of birth defects.
Keywords: Animals; Body Patterning; Embryonic Development; Exome Sequencing; Female; Genetic Association Studies; Genome, Human; Genomics; GTP Phosphohydrolases; Heart Defects, Congenital; Heterotaxy Syndrome; Humans; Male; Peroxidases; Zebrafish; Zebrafish Proteins

A Genocentric Approach to Discovery of Mendelian Disorders. - Hansen, Adam W; Mullai Murugan; Li, He; Khayat, Michael M; Wang, Liwen; Rosenfeld, Jill; B. Kim Andrews; Jhangiani, Shalini N; Coban Akdemir, Zeynep H; Fritz J Sedlazeck; Ashley-Koch, Allison E; Liu, Pengfei; et al. (Am J Hum Genet, 2019)
The advent of inexpensive, clinical exome sequencing (ES) has led to the accumulation of genetic data from thousands of samples from individuals affected with a wide range of diseases, but for whom the underlying genetic and molecular etiology of their clinical phenotype remains unknown. In many cases, detailed phenotypes are unavailable or poorly recorded and there is little family history to guide study. To accelerate discovery, we integrated ES data from 18,696 individuals referred for suspected Mendelian disease, together with relatives, in an Apache Hadoop data lake (Hadoop Architecture Lake of Exomes [HARLEE]) and implemented a genocentric analysis that rapidly identified 154 genes harboring variants suspected to cause Mendelian disorders. The approach did not rely on case-specific phenotypic classifications but was driven by optimization of gene- and variant-level filter parameters utilizing historical Mendelian disease-gene association discovery data. Variants in 19 of the 154 candidate genes were subsequently reported as causative of a Mendelian trait and additional data support the association of all other candidate genes with disease endpoints.
Keywords: Databases, Genetic; Exome; Exome Sequencing; Genetic Diseases, Inborn; Genetic Predisposition to Disease; Genetic Variation; Genomics; Humans; Pedigree; Phenotype

The Genomics of Arthrogryposis, a Complex Trait: Candidate Genes and Further Evidence for Oligogenic Inheritance. - Pehlivan, Davut; Bayram, Yavuz; Gunes, Nilay; Coban Akdemir, Zeynep; Shukla, Anju; Bierhals, Tatjana; Tabakci, Burcu; Sahin, Yavuz; Gezdirici, Alper; Fatih, Jawid M; Gulec, Elif Yilmaz; Yesil, Gozde; et al. (Am J Hum Genet, 2019)
Arthrogryposis is a clinical finding that is present either as a feature of a neuromuscular condition or as part of a systemic disease in over 400 Mendelian conditions. The underlying molecular etiology remains largely unknown because of genetic and phenotypic heterogeneity. We applied exome sequencing (ES) in a cohort of 89 families with the clinical sign of arthrogryposis. Additional molecular techniques including array comparative genomic hybridization (aCGH) and Droplet Digital PCR (ddPCR) were performed on individuals who were found to have pathogenic copy number variants (CNVs) and mosaicism, respectively. A molecular diagnosis was established in 65.2% (58/89) of families. Eleven out of 58 families (19.0%) showed evidence for potential involvement of pathogenic variation at more than one locus, probably driven by absence of heterozygosity (AOH) burden due to identity-by-descent (IBD). RYR3, MYOM2, ERGIC1, SPTBN4, and ABCA7 represent genes, identified in two or more families, for which mutations are probably causative for arthrogryposis. We also provide evidence for the involvement of CNVs in the etiology of arthrogryposis and for the idea that both mono-allelic and bi-allelic variants in the same gene cause either similar or distinct syndromes. We were able to identify the molecular etiology in nine out of 20 families who underwent reanalysis. In summary, our data from family-based ES further delineate the molecular etiology of arthrogryposis, yielded several candidate disease-associated genes, and provide evidence for mutational burden in a biological pathway or network. Our study also highlights the importance of reanalysis of individuals with unsolved diagnoses in conjunction with sequencing extended family members.
Keywords: Adolescent; Adult; Arthrogryposis; Child; Child, Preschool; Cohort Studies; Connectin; DNA Copy Number Variations; Exome Sequencing; Female; Genetic Markers; Genomics; Gestational Age; Humans; Infant; Infant, Newborn; Male; Mosaicism; Multifactorial Inheritance; Mutation; Pedigree; Ryanodine Receptor Calcium Release Channel; Vesicular Transport Proteins; Young Adult

Identification of Polycystic Kidney Disease 1 Like 1 Gene Variants in Children With Biliary Atresia Splenic Malformation Syndrome. - Berauer, John-Paul; Mezina, Anya I; Okou, David T; Aniko Sabo; Donna M Muzny; Richard A Gibbs; Hegde, Madhuri R; Chopra, Pankaj; Cutler, David J; Perlmutter, David H; Bull, Laura N; Thompson, Richard J; et al. (Hepatology, 2019)
Biliary atresia (BA) is the most common cause of end-stage liver disease in children and the primary indication for pediatric liver transplantation, yet underlying etiologies remain unknown. Approximately 10% of infants affected by BA exhibit various laterality defects (heterotaxy) including splenic abnormalities and complex cardiac malformations-a distinctive subgroup commonly referred to as the biliary atresia splenic malformation (BASM) syndrome. We hypothesized that genetic factors linking laterality features with the etiopathogenesis of BA in BASM patients could be identified through whole-exome sequencing (WES) of an affected cohort. DNA specimens from 67 BASM subjects, including 58 patient-parent trios, from the National Institute of Diabetes and Digestive and Kidney Diseases-supported Childhood Liver Disease Research Network (ChiLDReN) underwent WES. Candidate gene variants derived from a prespecified set of 2,016 genes associated with ciliary dysgenesis and/or dysfunction or cholestasis were prioritized according to pathogenicity, population frequency, and mode of inheritance. Five BASM subjects harbored rare and potentially deleterious biallelic variants in polycystic kidney disease 1 like 1 (PKD1L1), a gene associated with ciliary calcium signaling and embryonic laterality determination in fish, mice, and humans. Heterozygous PKD1L1 variants were found in 3 additional subjects. Immunohistochemical analysis of liver from the one BASM subject available revealed decreased PKD1L1 expression in bile duct epithelium when compared to normal livers and livers affected by other noncholestatic diseases. Conclusion: WES identified biallelic and heterozygous PKD1L1 variants of interest in 8 BASM subjects from the ChiLDReN data set; the dual roles for PKD1L1 in laterality determination and ciliary function suggest that PKD1L1 is a biologically plausible, cholangiocyte-expressed candidate gene for the BASM syndrome.
Keywords: Abnormalities, Multiple; Biliary Atresia; Child; Databases, Factual; Exome Sequencing; Female; Gene Expression Regulation, Developmental; Genetic Variation; Humans; Infant; Infant, Newborn; Male; Membrane Proteins; Polycystic Kidney Diseases; Retrospective Studies; Spleen; Syndrome

Insights into genetics, human biology and disease gleaned from family based genomic studies. - Posey, Jennifer E; O'Donnell-Luria, Anne H; Chong, Jessica X; Harel, Tamar; Jhangiani, Shalini N; Coban Akdemir, Zeynep H; Buyske, Steven; Pehlivan, Davut; Carvalho, Claudia M B; Baxter, Samantha; Sobreira, Nara; Liu, Pengfei; et al. (Genet Med, 2019)
Identifying genes and variants contributing to rare disease phenotypes and Mendelian conditions informs biology and medicine, yet potential phenotypic consequences for variation of >75% of the ~20,000 annotated genes in the human genome are lacking. Technical advances to assess rare variation genome-wide, particularly exome sequencing (ES), enabled establishment in the United States of the National Institutes of Health (NIH)-supported Centers for Mendelian Genomics (CMGs) and have facilitated collaborative studies resulting in novel "disease gene" discoveries. Pedigree-based genomic studies and rare variant analyses in families with suspected Mendelian conditions have led to the elucidation of hundreds of novel disease genes and highlighted the impact of de novo mutational events, somatic variation underlying nononcologic traits, incompletely penetrant alleles, phenotypes with high locus heterogeneity, and multilocus pathogenic variation. Herein, we highlight CMG collaborative discoveries that have contributed to understanding both rare and common diseases and discuss opportunities for future discovery in single-locus Mendelian disorder genomics. Phenotypic annotation of all human genes; development of bioinformatic tools and analytic methods; exploration of non-Mendelian modes of inheritance including reduced penetrance, multilocus variation, and oligogenic inheritance; construction of allelic series at a locus; enhanced data sharing worldwide; and integration with clinical genomics are explored. Realizing the full contribution of rare disease research to functional annotation of the human genome, and further illuminating human biology and health, will lay the foundation for the Precision Medicine Initiative.
Keywords: Databases, Genetic; Exome Sequencing; Genetic Diseases, Inborn; Genetic Heterogeneity; Genetic Predisposition to Disease; Genome, Human; Genomics; Humans; National Institutes of Health (U.S.); Pedigree; United States

Interchromosomal template-switching as a novel molecular mechanism for imprinting perturbations associated with Temple syndrome. - Carvalho, Claudia M B; Coban-Akdemir, Zeynep; Hijazi, Hadia; Bo Yuan; Pendleton, Matthew; Harrington, Eoghan; Beaulaurier, John; Juul, Sissel; Turner, Daniel J; Kanchi, Rupa S; Jhangiani, Shalini N; Donna M Muzny; et al. (Genome Med, 2019)
BACKGROUND: Intrachromosomal triplications (TRP) can contribute to disease etiology via gene dosage effects, gene disruption, position effects, or fusion gene formation. Recently, post-zygotic de novo triplications adjacent to copy-number neutral genomic intervals with runs of homozygosity (ROH) have been shown to result in uniparental isodisomy (UPD). The genomic structure of these complex genomic rearrangements (CGRs) shows a consistent pattern of an inverted triplication flanked by duplications (DUP-TRP/INV-DUP) formed by an iterative DNA replisome template-switching mechanism during replicative repair of a single-ended, double-stranded DNA (seDNA), the ROH results from an interhomolog or nonsister chromatid template switch. It has been postulated that these CGRs may lead to genetic abnormalities in carriers due to dosage-sensitive genes mapping within the copy-number variant regions, homozygosity for alleles at a locus causing an autosomal recessive (AR) disease trait within the ROH region, or imprinting-associated diseases. METHODS: Here, we report a family wherein the affected subject carries a de novo 2.2-Mb TRP followed by 42.2 Mb of ROH and manifests clinical features overlapping with those observed in association with chromosome 14 maternal UPD (UPD(14)mat). UPD(14)mat can cause clinical phenotypic features enabling a diagnosis of Temple syndrome. This CGR was then molecularly characterized by high-density custom aCGH, genome-wide single-nucleotide polymorphism (SNP) and methylation arrays, exome sequencing (ES), and the Oxford Nanopore long-read sequencing technology. RESULTS: We confirmed the postulated DUP-TRP/INV-DUP structure by multiple orthogonal genomic technologies in the proband. The methylation status of known differentially methylated regions (DMRs) on chromosome 14 revealed that the subject shows the typical methylation pattern of UPD(14)mat. Consistent with these molecular findings, the clinical features overlap with those observed in Temple syndrome, including speech delay. CONCLUSIONS: These data provide experimental evidence that, in humans, triplication can lead to segmental UPD and imprinting disease. Importantly, genotype/phenotype analyses further reveal how a post-zygotically generated complex structural variant, resulting from a replication-based mutational mechanism, contributes to expanding the clinical phenotype of known genetic syndromes. Mechanistically, such events can distort transmission genetics resulting in homozygosity at a locus for which only one parent is a carrier as well as cause imprinting diseases.
Keywords: Chromosome Aberrations; Chromosome Disorders; Chromosomes, Human, Pair 14; DNA Methylation; DNA Replication; Genomic Imprinting; Humans; Male; Pedigree; Phenotype; Polymorphism, Single Nucleotide; Young Adult

Leveraging Human Microbiome Features to Diagnose and Stratify Children with Irritable Bowel Syndrome. - Hollister, Emily B; Oezguen, Numan; Chumpitazi, Bruno P; Luna, Ruth Ann; Weidler, Erica M; Rubio-Gonzales, Michelle; Dahdouli, Mahmoud; Cope, Julia L; Mistretta, Toni-Ann; Raza, Sabeen; Ginger A Metcalf; Donna M Muzny; et al. (J Mol Diagn, 2019)
Accurate diagnosis and stratification of children with irritable bowel syndrome (IBS) remain challenging. Given the central role of recurrent abdominal pain in IBS, we evaluated the relationships of pediatric IBS and abdominal pain with intestinal microbes and fecal metabolites using a comprehensive clinical characterization and multiomics strategy. Using rigorous clinical phenotyping, we identified preadolescent children (aged 7 to 12 years) with Rome III IBS (n = 23) and healthy controls (n = 22) and characterized their fecal microbial communities using whole-genome shotgun metagenomics and global unbiased fecal metabolomic profiling. Correlation-based approaches and machine learning algorithms identified associations between microbes, metabolites, and abdominal pain. IBS cases differed from controls with respect to key bacterial taxa (eg, Flavonifractor plautii and Lachnospiraceae bacterium 7_1_58FAA), metagenomic functions (eg, carbohydrate metabolism and amino acid metabolism), and higher-order metabolites (eg, secondary bile acids, sterols, and steroid-like compounds). Significant associations between abdominal pain frequency and severity and intestinal microbial features were identified. A random forest classifier built on metagenomic and metabolic markers successfully distinguished IBS cases from controls (area under the curve, 0.93). Leveraging multiple lines of evidence, intestinal microbes, genes/pathways, and metabolites were associated with IBS, and these features were capable of distinguishing children with IBS from healthy children. These multi-omics features, and their links to childhood IBS coupled with nutritional interventions, may lead to new microbiome-guided diagnostic and therapeutic strategies.
Keywords: Abdominal Pain; Bacteria; Case-Control Studies; Child; Feces; Female; Gastrointestinal Tract; Genomics; Humans; Irritable Bowel Syndrome; Male; Metabolome; Microbiota; Multivariate Analysis; Principal Component Analysis; Statistics, Nonparametric

Megabase Length Hypermutation Accompanies Human Structural Variation at 17p11.2. - Beck, Christine R; Carvalho, Claudia M B; Akdemir, Zeynep C; Fritz J Sedlazeck; Song, Xiaofei; Meng, Qingchang; Jianhong Hu; Harshavardhan Doddapaneni; Chong, Zechen; Chen, Edward S; Thornton, Philip C; Liu, Pengfei; et al. (Cell, 2019)
DNA rearrangements resulting in human genome structural variants (SVs) are caused by diverse mutational mechanisms. We used long- and short-read sequencing technologies to investigate end products of de novo chromosome 17p11.2 rearrangements and query the molecular mechanisms underlying both recurrent and non-recurrent events. Evidence for an increased rate of clustered single-nucleotide variant (SNV) mutation in cis with non-recurrent rearrangements was found. Indel and SNV formation are associated with both copy-number gains and losses of 17p11.2, occur up to ∼1 Mb away from the breakpoint junctions, and favor C > G transversion substitutions; results suggest that single-stranded DNA is formed during the genesis of the SV and provide compelling support for a microhomology-mediated break-induced replication (MMBIR) mechanism for SV formation. Our data show an additional mutational burden of MMBIR consisting of hypermutation confined to the locus and manifesting as SNVs and indels predominantly within genes.
Keywords: Abnormalities, Multiple; Chromosome Breakpoints; Chromosome Disorders; Chromosome Duplication; Chromosomes, Human, Pair 17; DNA Copy Number Variations; DNA Repair; DNA Replication; Gene Rearrangement; Genome, Human; Genomic Structural Variation; Humans; INDEL Mutation; Models, Genetic; Mutation; Polymorphism, Single Nucleotide; Recombination, Genetic; Sequence Analysis, DNA; Smith-Magenis Syndrome

MHC genotyping from rhesus macaque exome sequences. - Caskey, John R; Wiseman, Roger W; Karl, Julie A; Baker, David A; Lee, Taylor; Maddox, Robert J; Raveendran, Muthuswamy; R. Alan Harris; Jianhong Hu; Donna M Muzny; Jeffrey Rogers; O'Connor, David H (Immunogenetics, 2019)
Indian rhesus macaque major histocompatibility complex (MHC) variation can influence the outcomes of transplantation and infectious disease studies. Frequently, rhesus macaques are MHC genotyped to identify variants that could account for unexpected results. Since the MHC is only one region in the genome where variation could impact experimental outcomes, strategies for simultaneously profiling variation in the macaque MHC and the remainder of the protein coding genome would be useful. Here we determine MHC class I and class II genotypes using target-capture probes enriched for MHC sequences, a method we term macaque exome sequence (MES) genotyping. For a cohort of 27 Indian rhesus macaques, we describe two methods for obtaining MHC genotypes from MES data and demonstrate that the MHC class I and class II genotyping results obtained with these methods are 98.1% and 98.7% concordant, respectively, with expected MHC genotypes. In contrast, conventional MHC genotyping results obtained by deep sequencing of short multiplex PCR amplicons were only 92.6% concordant with expectations for this cohort.
Keywords: Animals; Exome; Exome Sequencing; Haplotypes; Histocompatibility Antigens Class I; Histocompatibility Antigens Class II; Macaca mulatta; Polymorphism, Genetic

Molecular evolutionary trends and feeding ecology diversification in the Hemiptera, anchored by the milkweed bug genome. - Panfilio, Kristen A; Vargas Jentzsch, Iris M; Benoit, Joshua B; Erezyilmaz, Deniz; Suzuki, Yuichiro; Colella, Stefano; Robertson, Hugh M; Poelchau, Monica F; Waterhouse, Robert M; Ioannidis, Panagiotis; Weirauch, Matthew T; Hughes, Daniel S T; et al. (Genome Biol, 2019)
BACKGROUND: The Hemiptera (aphids, cicadas, and true bugs) are a key insect order, with high diversity for feeding ecology and excellent experimental tractability for molecular genetics. Building upon recent sequencing of hemipteran pests such as phloem-feeding aphids and blood-feeding bed bugs, we present the genome sequence and comparative analyses centered on the milkweed bug Oncopeltus fasciatus, a seed feeder of the family Lygaeidae. RESULTS: The 926-Mb Oncopeltus genome is well represented by the current assembly and official gene set. We use our genomic and RNA-seq data not only to characterize the protein-coding gene repertoire and perform isoform-specific RNAi, but also to elucidate patterns of molecular evolution and physiology. We find ongoing, lineage-specific expansion and diversification of repressive C2H2 zinc finger proteins. The discovery of intron gain and turnover specific to the Hemiptera also prompted the evaluation of lineage and genome size as predictors of gene structure evolution. Furthermore, we identify enzymatic gains and losses that correlate with feeding biology, particularly for reductions associated with derived, fluid nutrition feeding. CONCLUSIONS: With the milkweed bug, we now have a critical mass of sequenced species for a hemimetabolous insect order and close outgroup to the Holometabola, substantially improving the diversity of insect genomics. We thereby define commonalities among the Hemiptera and delve into how hemipteran genomes reflect distinct feeding ecologies. Given Oncopeltus's strength as an experimental model, these new sequence resources bolster the foundation for molecular research and highlight technical considerations for the analysis of medium-sized invertebrate genomes.
Keywords: Amino Acid Sequence; Animals; CYS2-HIS2 Zinc Fingers; Evolution, Molecular; Feeding Behavior; Gene Dosage; Gene Expression Profiling; Gene Transfer, Horizontal; Genes, Homeobox; Genome, Insect; Hemiptera; Pigmentation; Smell; Transcription Factors

Molecular profiling predicts meningioma recurrence and reveals loss of DREAM complex repression in aggressive tumors. - Patel, Akash J; Wan, Ying-Wooi; Al-Ouran, Rami; Revelli, Jean-Pierre; Cardenas, Maria F; Oneissi, Mazen; Xi, Liu; Jalali, Ali; Magnotti, John F; Donna M Muzny; Harshavardhan Doddapaneni; Sebastian, Sherly; et al. (Proc Natl Acad Sci U S A, 2019)
Meningiomas account for one-third of all primary brain tumors. Although typically benign, about 20% of meningiomas are aggressive, and despite the rigor of the current histopathological classification system there remains considerable uncertainty in predicting tumor behavior. Here, we analyzed 160 tumors from all 3 World Health Organization (WHO) grades (I through III) using clinical, gene expression, and sequencing data. Unsupervised clustering analysis identified 3 molecular types (A, B, and C) that reliably predicted recurrence. These groups did not directly correlate with the WHO grading system, which classifies more than half of the tumors in the most aggressive molecular type as benign. Transcriptional and biochemical analyses revealed that aggressive meningiomas involve loss of the repressor function of the DREAM complex, which results in cell-cycle activation; only tumors in this category tend to recur after full resection. These findings should improve our ability to predict recurrence and develop targeted treatments for these clinically challenging tumors.
Keywords: Adult; Aged; Aged, 80 and over; Cell Cycle; Cell Line; Disease Progression; DNA Copy Number Variations; Female; Gene Expression Profiling; Humans; Kv Channel-Interacting Proteins; Male; Meningeal Neoplasms; Meningioma; Middle Aged; Neoplasm Recurrence, Local; Prognosis; Repressor Proteins; Young Adult

A novel disorder involving dyshematopoiesis, inflammation, and HLH due to aberrant CDC42 function. - Lam, Michael T; Coppola, Simona; Krumbach, Oliver H F; Prencipe, Giusi; Insalaco, Antonella; Cifaldi, Cristina; Brigida, Immacolata; Zara, Erika; Scala, Serena; Di Cesare, Silvia; Martinelli, Simone; Di Rocco, Martina; et al. (J Exp Med, 2019)
Hemophagocytic lymphohistiocytosis (HLH) is characterized by immune dysregulation due to inadequate restraint of overactivated immune cells and is associated with a variable clinical spectrum having overlap with more common pathophysiologies. HLH is difficult to diagnose and can be part of inflammatory syndromes. Here, we identify a novel hematological/autoinflammatory condition (NOCARH syndrome) in four unrelated patients with superimposable features, including neonatal-onset cytopenia with dyshematopoiesis, autoinflammation, rash, and HLH. Patients shared the same de novo mutation (Chr1:22417990C>T, p.R186C) and altered hematopoietic compartment, immune dysregulation, and inflammation. mutations had been associated with syndromic neurodevelopmental disorders. In vitro and in vivo assays documented unique effects of p.R186C on CDC42 localization and function, correlating with the distinctiveness of the trait. Emapalumab was critical to the survival of one patient, who underwent successful bone marrow transplantation. Early recognition of the disorder and establishment of treatment followed by bone marrow transplant are important to survival.
Keywords: Alleles; Amino Acid Substitution; Animals; Binding Sites; cdc42 GTP-Binding Protein; Cell Line, Tumor; Child; Disease Susceptibility; Female; Genetic Association Studies; Genotype; Humans; Infant; Lymphohistiocytosis, Hemophagocytic; Male; Mice; Models, Molecular; Molecular Conformation; Mutation; Phenotype; Protein Binding

Paralog Studies Augment Gene Discovery: DDX and DHX Genes. - Paine, Ingrid; Posey, Jennifer E; Grochowski, Christopher M; Jhangiani, Shalini N; Rosenheck, Sarah; Kleyner, Robert; Marmorale, Taylor; Yoon, Margaret; Wang, Kai; Robison, Reid; Cappuccio, Gerarda; Pinelli, Michele; et al. (Am J Hum Genet, 2019)
Members of a paralogous gene family in which variation in one gene is known to cause disease are eight times more likely to also be associated with human disease. Recent studies have elucidated DHX30 and DDX3X as genes for which pathogenic variant alleles are involved in neurodevelopmental disorders. We hypothesized that variants in paralogous genes encoding members of the DExD/H-box RNA helicase superfamily might also underlie developmental delay and/or intellectual disability (DD and/or ID) disease phenotypes. Here we describe 15 unrelated individuals who have DD and/or ID, central nervous system (CNS) dysfunction, vertebral anomalies, and dysmorphic features and were found to have probably damaging variants in DExD/H-box RNA helicase genes. In addition, these individuals exhibit a variety of other tissue and organ system involvement including ocular, outer ear, hearing, cardiac, and kidney tissues. Five individuals with homozygous (one), compound-heterozygous (two), or de novo (two) missense variants in DHX37 were identified by exome sequencing. We identified ten total individuals with missense variants in three other DDX/DHX paralogs: DHX16 (four individuals), DDX54 (three individuals), and DHX34 (three individuals). Most identified variants are rare, predicted to be damaging, and occur at conserved amino acid residues. Taken together, these 15 individuals implicate the DExD/H-box helicases in both dominantly and recessively inherited neurodevelopmental phenotypes and highlight the potential for more than one disease mechanism underlying these disorders.
Keywords: DEAD-box RNA Helicases; Exome Sequencing; Female; Genetic Association Studies; Humans; Infant; Infant, Newborn; Male; Mutation, Missense; Neoplasm Proteins; Neurodevelopmental Disorders; Pedigree; RNA Helicases

Rare variants in SLC5A10 are associated with serum 1,5-anhydroglucitol (1,5-AG) in the Atherosclerosis Risk in Communities (ARIC) Study. - Loomis, Stephanie J; Köttgen, Anna; Li, Man; Tin, Adrienne; Coresh, Josef; Eric Boerwinkle; Richard A Gibbs; Donna M Muzny; Pankow, James; Selvin, Elizabeth; Duggal, Priya (Sci Rep, 2019)
Serum 1,5-anhydroglucitol (1,5-AG) is an emerging biomarker used to monitor glycemic control in persons with diabetes. We performed whole-exome sequencing, examining the association between rare, coding genetic variants and 1,5-AG among European ancestry (N = 6,589) and African ancestry (N = 2,309) participants without diagnosed diabetes in the Atherosclerosis Risk in Communities (ARIC) Study. Five variants representing 3 independent signals on chromosome 17 in SLC5A10, a glucose transporter not previously known to transport 1,5-AG, were associated with 1,5-AG levels up to 10.38 µg/mL lower per allele (1,5-AG range 3.4-32.8 µg/mL) in the European ancestry sample and validated in the African ancestry sample. Together these variants explained 6% of the variance in 1,5-AG. Two of these variants (rs61741107, p = 8.85E-56; rs148178887, p = 1.13E-36) were rare, nonsynonymous, and predicted to be damaging or deleterious by multiple algorithms. Gene-based SKAT-O analysis supported these results (SLC5A10 p = 5.13E-64 in European ancestry, validated in African ancestry, p = 0.006). Interestingly, these novel variants are not associated with other biomarkers of hyperglycemia or diabetes (p > 0.2). The large effect sizes and protein-altering, multiple independent signals suggest SLC5A10 may code for an important transporter of 1,5-AG in the kidney, with a potential nonglucose-related effect on 1,5-AG, impacting its clinical utility as a diabetes biomarker in this subpopulation.
Keywords: Atherosclerosis; Deoxyglucose; Exome Sequencing; Female; Humans; Longitudinal Studies; Male; Middle Aged; Polymorphism, Single Nucleotide; Risk Factors; Sodium-Glucose Transport Proteins

Reanalysis of Clinical Exome Sequencing Data. - Liu, Pengfei; Meng, Linyan; Normand, Elizabeth A; Xia, Fan; Song, Xiaofei; Ghazi, Andrew; Rosenfeld, Jill; Magoulas, Pilar L; Braxton, Alicia; Ward, Patricia; Dai, Hongzheng; Bo Yuan; et al. (N Engl J Med, 2019)
Keywords: Exome; Genetic Diseases, Inborn; Genetic Testing; Humans; Mutation; Phenotype; Sequence Analysis, DNA; Whole Exome Sequencing

A biallelic ANTXR1 variant expands the anthrax toxin receptor associated phenotype to tooth agenesis. - Dinckan, Nuriye; Du, Renqian; Akdemir, Zeynep C; Bayram, Yavuz; Jhangiani, Shalini N; Harshavardhan Doddapaneni; Jianhong Hu; Donna M Muzny; Guven, Yeliz; Aktoren, Oya; Kayserili, Hulya; Eric Boerwinkle; et al. (Am J Med Genet A, 2018)
Tooth development is regulated by multiple genetic pathways, which ultimately drive the complex interactions between the oral epithelium and mesenchyme. Disruptions at any time point during this process may lead to failure of tooth development, also known as tooth agenesis (TA). TA is a common craniofacial abnormality in humans and represents the failure to develop one or more permanent teeth. Many genes and potentially subtle variants in these genes contribute to the TA phenotype. We report the clinical and genetic impact of a rare homozygous ANTXR1 variant (c.1312C>T), identified by whole exome sequencing (WES), in a consanguineous Turkish family with TA. Mutations in ANTXR1 have been associated with GAPO (growth retardation, alopecia, pseudoanodontia, and optic atrophy) syndrome and infantile hemangioma, however no clinical characteristics associated with these conditions were observed in our study family. We detected the expression of Antxr1 in oral and dental tissues of developing mouse embryos, further supporting a role for this gene in tooth development. Our findings implicate ANTXR1 as a candidate gene for isolated TA, suggest the involvement of specific hypomorphic alleles, and expand the previously known ANTXR1-associated phenotypes.
Keywords: Alleles; Amino Acid Substitution; Animals; Anodontia; Child; Consanguinity; Exome Sequencing; Facies; Genetic Association Studies; Genotype; Humans; Male; Mice; Microfilament Proteins; Mutation; Neoplasm Proteins; Pedigree; Phenotype; Radiography; Receptors, Cell Surface

Challenges of Francisella classification exemplified by an atypical clinical isolate. - Matz, L M; Kamdar, K Y; Holder, M E; Ginger A Metcalf; Weissenberger, G M; Meng, Q; Vee, V; Han, Y; Donna M Muzny; Richard A Gibbs; Johnson, C L; Revell, P A; et al. (Diagn Microbiol Infect Dis, 2018)
The accumulation of sequenced Francisella strains has made it increasingly apparent that the 16S rRNA gene alone is not enough to stratify the Francisella genus into precise and clinically useful classifications. Continued whole-genome sequencing of isolates will provide a larger base of knowledge for targeted approaches with broad applicability. Additionally, examination of genomic information on a case-by-case basis will help resolve outstanding questions regarding strain stratification. We report the complete genome sequence of a clinical isolate, designated here as F. novicida-like strain TCH2015, acquired from the lymph node of a 6-year-old male. Two features were atypical for F. novicida: exhibition of functional oxidase activity and additional gene content, including proposed virulence determinants. These differences, which could potentially impact virulence and clinical diagnosis, emphasize the need for more comprehensive methods to profile Francisella isolates. This study highlights the value of whole-genome sequencing, which will lead to a more robust database of environmental and clinical genomes and inform strategies to improve detection and classification of Francisella strains.
Keywords: Child; DNA, Bacterial; Francisella; Genes, Bacterial; Genetic Variation; Genome, Bacterial; Genotype; Humans; Lymph Nodes; Male; Oxidoreductases; Sequence Analysis, DNA; Tularemia; Virulence Factors; Whole Genome Sequencing

Characterizing reduced coverage regions through comparison of exome and genome sequencing data across 10 centers. - Sanghvi, Rashesh V; Buhay, Christian J; Powell, Bradford C; Tsai, Ellen A; Dorschner, Michael O; Hong, Celine S; Lebo, Matthew S; Sasson, Ariella; Hanna, David S; McGee, Sean; Bowling, Kevin M; Cooper, Gregory M; et al. (Genet Med, 2018)
PURPOSE: As massively parallel sequencing is increasingly being used for clinical decision making, it has become critical to understand parameters that affect sequencing quality and to establish methods for measuring and reporting clinical sequencing standards. In this report, we propose a definition for reduced coverage regions and describe a set of standards for variant calling in clinical sequencing applications. METHODS: To enable sequencing centers to assess the regions of poor sequencing quality in their own data, we optimized and used a tool (ExCID) to identify reduced coverage loci within genes or regions of particular interest. We used this framework to examine sequencing data from 500 patients generated in 10 projects at sequencing centers in the National Human Genome Research Institute/National Cancer Institute Clinical Sequencing Exploratory Research Consortium. RESULTS: This approach identified reduced coverage regions in clinically relevant genes, including known clinically relevant loci that were uniquely missed at individual centers, in multiple centers, and in all centers. CONCLUSION: This report provides a process road map for clinical sequencing centers looking to perform similar analyses on their data.
Keywords: Base Sequence; Chromosome Mapping; Exome; Exome Sequencing; Genome, Human; High-Throughput Nucleotide Sequencing; Humans; Sequence Analysis, DNA; Software; Whole Genome Sequencing

Clinical exome sequencing for fetuses with ultrasound abnormalities and a suspected Mendelian disorder. - Normand, Elizabeth A; Braxton, Alicia; Nassef, Salma; Ward, Patricia A; Vetrini, Francesco; He, Weimin; Patel, Vipulkumar; Qu, Chunjing; Westerfield, Lauren E; Stover, Samantha; Dharmadhikari, Avinash V; Donna M Muzny; et al. (Genome Med, 2018)
BACKGROUND: Exome sequencing is now being incorporated into clinical care for pediatric and adult populations, but its integration into prenatal diagnosis has been more limited. One reason for this is the paucity of information about the clinical utility of exome sequencing in the prenatal setting. METHODS: We retrospectively reviewed indications, results, time to results (turnaround time, TAT), and impact of exome results for 146 consecutive "fetal exomes" performed in a clinical diagnostic laboratory between March 2012 and November 2017. We define a fetal exome as one performed on a sample obtained from a fetus or a product of conception with at least one structural anomaly detected by prenatal imaging or autopsy. Statistical comparisons were performed using Fisher's exact test. RESULTS: Prenatal exome yielded an overall molecular diagnostic rate of 32% (n = 46/146). Of the 46 molecular diagnoses, 50% were autosomal dominant disorders (n = 23/46), 41% were autosomal recessive disorders (n = 19/46), and 9% were X-linked disorders (n = 4/46). The molecular diagnostic rate was highest for fetuses with anomalies affecting multiple organ systems and for fetuses with craniofacial anomalies. Out of 146 cases, a prenatal trio exome option designed for ongoing pregnancies was performed on 62 fetal specimens, resulting in a diagnostic yield of 35% with an average TAT of 14 days for initial reporting (excluding tissue culture time). The molecular diagnoses led to refined recurrence risk estimates, altered medical management, and informed reproductive planning for families. CONCLUSION: Exome sequencing is a useful diagnostic tool when fetal structural anomalies suggest a genetic etiology, but other standard prenatal genetic tests did not provide a diagnosis.
Keywords: Exome Sequencing; Family; Fetus; Genetic Diseases, Inborn; Humans; Inheritance Patterns; Phenotype; Ultrasonography, Prenatal

Common Coding Variants in Are Associated With the Nav1.8 Late Current and Cardiac Conduction. - Macri, Vincenzo; Brody, Jennifer A; Arking, Dan E; Hucker, William J; Yin, Xiaoyan; Lin, Honghuang; Mills, Robert W; Sinner, Moritz F; Lubitz, Steven A; Liu, Ching-Ti; Morrison, Alanna C; Alonso, Alvaro; et al. (Circ Genom Precis Med, 2018)
BACKGROUND: Genetic variants at the / locus are strongly associated with electrocardiographic PR and QRS intervals. While is the canonical cardiac sodium channel gene, the role of in cardiac conduction is less well characterized. METHODS: We sequenced the locus in 3699 European-ancestry individuals to identify variants associated with cardiac conduction, and replicated our findings in 21,000 individuals of European ancestry. We examined association with expression in human atrial tissue. We explored the biophysical effect of variation on channel function using cellular electrophysiology. RESULTS: We identified 2 intronic single nucleotide polymorphisms in high linkage disequilibrium (  =0.86) with each other to be the strongest signals for PR (rs10428132, β=-4.74, =1.52×10) and QRS intervals (rs6599251, QRS β=-0.73; =1.2×10), respectively. Although these variants were not associated with or expression in human atrial tissue (n=490), they were in high linkage disequilibrium (  ≥0.72) with a common missense variant, rs6795970 (V1073A). In total, we identified 7 missense variants, 4 of which (I962V, P1045T, V1073A, and L1092P) were associated with cardiac conduction. These 4 missense variants cluster in the cytoplasmic linker of the second and third domains of the SCN10A protein and together form 6 common haplotypes. Using cellular electrophysiology, we found that haplotypes associated with shorter PR intervals had a significantly larger percentage of late current compared with wild-type (I962V+V1073A+L1092P, 20.2±3.3%, =0.03, and I962V+V1073A, 22.4±0.8%, =0.0004 versus wild-type 11.7±1.6%), and the haplotype associated with the longest PR interval had a significantly smaller late current percentage (P1045T, 6.4±1.2%, =0.03). CONCLUSIONS: Our findings suggest an association between genetic variation in , the late sodium current, and alterations in cardiac conduction.
Keywords: Biophysical Phenomena; Electrocardiography; Genetic Association Studies; Haplotypes; Heart Conduction System; Humans; Ion Channel Gating; Mutation, Missense; NAV1.8 Voltage-Gated Sodium Channel; Polymorphism, Single Nucleotide; Quantitative Trait Loci

Comparative genomics of the miniature wasp and pest control agent Trichogramma pretiosum. - Lindsey, Amelia R I; Kelkar, Yogeshwar D; Wu, Xin; Sun, Dan; Martinson, Ellen O; Yan, Zhichao; Rugman-Jones, Paul F; Hughes, Daniel S T; Murali, Shwetha C; Qu, Jiaxin; Dugan, Shannon; Lee, Sandra L; et al. (BMC Biol, 2018)
BACKGROUND: Trichogrammatids are minute parasitoid wasps that develop within other insect eggs. They are less than half a millimeter long, smaller than some protozoans. The Trichogrammatidae are one of the earliest branching families of Chalcidoidea: a diverse superfamily of approximately half a million species of parasitoid wasps, proposed to have evolved from a miniaturized ancestor. Trichogramma are frequently used in agriculture, released as biological control agents against major moth and butterfly pests. Additionally, Trichogramma are well known for their symbiotic bacteria that induce asexual reproduction in infected females. Knowledge of the genome sequence of Trichogramma is a major step towards further understanding its biology and potential applications in pest control. RESULTS: We report the 195-Mb genome sequence of Trichogramma pretiosum and uncover signatures of miniaturization and adaptation in Trichogramma and related parasitoids. Comparative analyses reveal relatively rapid evolution of proteins involved in ribosome biogenesis and function, transcriptional regulation, and ploidy regulation. Chalcids also show loss or especially rapid evolution of 285 gene clusters conserved in other Hymenoptera, including many that are involved in signal transduction and embryonic development. Comparisons between sexual and asexual lineages of Trichogramma pretiosum reveal that there is no strong evidence for genome degradation (e.g., gene loss) in the asexual lineage, although it does contain a lower repeat content than the sexual lineage. Trichogramma shows particularly rapid genome evolution compared to other hymenopterans. We speculate these changes reflect adaptations to miniaturization, and to life as a specialized egg parasitoid. CONCLUSIONS: The genomes of Trichogramma and related parasitoids are a valuable resource for future studies of these diverse and economically important insects, including explorations of parasitoid biology, symbiosis, asexuality, biological control, and the evolution of miniaturization. Understanding the molecular determinants of parasitism can also inform mass rearing of Trichogramma and other parasitoids for biological control.
Keywords: Animals; Evolution, Molecular; Genomics; Moths; Pest Control, Biological; Phylogeny; Wasps; Whole Genome Sequencing

Elucidating the molecular pathogenesis of glioma: integrated germline and somatic profiling of a familial glioma case series. - Jacobs, Daniel I; Fukumura, Kazutaka; Bainbridge, Matthew N; Armstrong, Georgina N; Tsavachidis, Spiridon; Gu, Xiangjun; Harshavardhan Doddapaneni; Jianhong Hu; Jayaseelan, Joy C; Donna M Muzny; Huse, Jason T; Bondy, Melissa L (Neuro Oncol, 2018)
BACKGROUND: The genomic characterization of sporadically arising gliomas has delineated molecularly and clinically distinct subclasses of disease. However, less is known about the molecular nature of gliomas that are familial in origin. We performed molecular subtyping of 163 tumor specimens from individuals with a family history of glioma and integrated germline and somatic genomic data to characterize the pathogenesis of 20 tumors in additional detail. METHODS: Immunohistochemical analyses were performed on formalin-fixed, paraffin-embedded tumor sections to determine molecular subtypes of glioma. For 20 cases, tumor DNA was exome sequenced on an Illumina HiSeq 2000 platform and copy number profiling was performed on the Illumina HumanOmniExpress BeadChip. Genotypes at glioma risk polymorphisms were determined from germline DNA profiled on the Illumina Infinium OncoArray and deleterious germline mutations were identified from germline sequencing data. RESULTS: All 3 molecular subtypes of sporadic glioma were represented in the overall case series, including molecular glioblastoma (n = 102), oligodendroglioma (n = 21), and astrocytoma (n = 20). Detailed profiling of 20 of these cases showed characteristic subtype-specific alterations at frequencies comparable to sporadic glioma cases. All 20 cases had alterations in genes regulating telomere length. Frequencies of common glioma risk alleles were similar to those among sporadic cases, and correlations between risk alleles and same-gene somatic mutations were not observed. CONCLUSIONS: This study illustrates that the molecular characteristics of familial tumors profiled largely recapitulate what is known about sporadic glioma and that both germline and somatic molecular features target common core pathways involved in gliomagenesis. KEY POINTS: 1. Familial and sporadic gliomas display highly comparable molecular landscapes. 2. Germline and somatic molecular events target common core pathways involved in gliomagenesis. 3. Carriage of germline glioma risk variants is not associated with somatic events in the same gene.
Keywords: Adult; Biomarkers, Tumor; Brain Neoplasms; DNA Copy Number Variations; DNA, Neoplasm; Exome; Genetic Predisposition to Disease; Genomics; Germ-Line Mutation; Glioma; Humans; Middle Aged; Prognosis

Genetic and mechanistic diversity in pediatric hemophagocytic lymphohistiocytosis. - Chinn, Ivan K; Eckstein, Olive S; Peckham-Gregory, Erin C; Goldberg, Baruch R; Forbes, Lisa R; Nicholas, Sarah K; Mace, Emily M; Vogel, Tiphanie P; Abhyankar, Harshal A; Diaz, Maria I; Heslop, Helen E; Krance, Robert A; et al. (Blood, 2018)
The HLH-2004 criteria are used to diagnose hemophagocytic lymphohistiocytosis (HLH), yet concern exists for their misapplication, resulting in suboptimal treatment of some patients. We sought to define the genomic spectrum and associated outcomes of a diverse cohort of children who met the HLH-2004 criteria. Genetic testing was performed clinically or through research-based whole-exome sequencing. Clinical metrics were analyzed with respect to genomic results. Of 122 subjects enrolled over the course of 17 years, 101 subjects received genetic testing. Biallelic familial HLH (fHLH) gene defects were identified in only 19 (19%) and correlated with presentation at younger than 1 year of age ( < .0001). Digenic fHLH variants were observed but lacked statistical support for disease association. In 28 (58%) of 48 subjects, research whole-exome sequencing analyses successfully identified likely molecular explanations, including underlying primary immunodeficiency diseases, dysregulated immune activation and proliferation disorders, and potentially novel genetic conditions. Two-thirds of patients identified by the HLH-2004 criteria had underlying etiologies for HLH, including genetic defects, autoimmunity, and malignancy. Overall survival was 45%, and increased mortality correlated with HLH triggered by infection or malignancy ( < .05). Differences in survival did not correlate with genetic profile or extent of therapy. HLH should be conceptualized as a phenotype of critical illness characterized by toxic activation of immune cells from different underlying mechanisms. In most patients with HLH, targeted sequencing of fHLH genes remains insufficient for identifying pathogenic mechanisms. Whole-exome sequencing, however, may identify specific therapeutic opportunities and affect hematopoietic stem cell transplantation options for these patients.
Keywords: Adolescent; Child; Child, Preschool; Cohort Studies; Female; Genetic Testing; Genome, Human; Genome-Wide Association Study; High-Throughput Nucleotide Sequencing; Humans; Infant; Infant, Newborn; Lymphohistiocytosis, Hemophagocytic; Male; Multifactorial Inheritance

The genome of the water strider Gerris buenoi reveals expansions of gene repertoires associated with adaptations to life on the water. - Armisén, David; Rajakumar, Rajendhran; Friedrich, Markus; Benoit, Joshua B; Robertson, Hugh M; Panfilio, Kristen A; Ahn, Seung-Joon; Poelchau, Monica F; Chao, Hsu; Dinh, Huyen; Harshavardhan Doddapaneni; Dugan, Shannon; et al. (BMC Genomics, 2018)
BACKGROUND: Having conquered water surfaces worldwide, the semi-aquatic bugs occupy ponds, streams, lakes, mangroves, and even open oceans. The diversity of this group has inspired a range of scientific studies from ecology and evolution to developmental genetics and hydrodynamics of fluid locomotion. However, the lack of a representative water strider genome hinders our ability to more thoroughly investigate the molecular mechanisms underlying the processes of adaptation and diversification within this group. RESULTS: Here we report the sequencing and manual annotation of the Gerris buenoi (G. buenoi) genome; the first water strider genome to be sequenced thus far. The size of the G. buenoi genome is approximately 1,000 Mb, and this sequencing effort has recovered 20,949 predicted protein-coding genes. Manual annotation uncovered a number of local (tandem and proximal) gene duplications and expansions of gene families known for their importance in a variety of processes associated with morphological and physiological adaptations to a water surface lifestyle. These expansions may affect key processes associated with growth, vision, desiccation resistance, detoxification, olfaction and epigenetic regulation. Strikingly, the G. buenoi genome contains three insulin receptors, suggesting key changes in the rewiring and function of the insulin pathway. Other genomic changes affecting with opsin genes may be associated with wavelength sensitivity shifts in opsins, which is likely to be key in facilitating specific adaptations in vision for diverse water habitats. CONCLUSIONS: Our findings suggest that local gene duplications might have played an important role during the evolution of water striders. Along with these findings, the sequencing of the G. buenoi genome now provides us the opportunity to pursue exciting research opportunities to further understand the genomic underpinnings of traits associated with the extreme body plan and life history of water striders.
Keywords: Adaptation, Physiological; Animals; Evolution, Molecular; Genome; Genomics; Heteroptera; Insect Proteins; Phenotype; Phylogeny

Hemimetabolous genomes reveal molecular basis of termite eusociality. - Harrison, Mark C; Jongepier, Evelien; Robertson, Hugh M; Arning, Nicolas; Bitard-Feildel, Tristan; Chao, Hsu; Childers, Christopher P; Dinh, Huyen; Harshavardhan Doddapaneni; Dugan, Shannon; Gowin, Johannes; Greiner, Carolin; et al. (Nat Ecol Evol, 2018)
Around 150 million years ago, eusocial termites evolved from within the cockroaches, 50 million years before eusocial Hymenoptera, such as bees and ants, appeared. Here, we report the 2-Gb genome of the German cockroach, Blattella germanica, and the 1.3-Gb genome of the drywood termite Cryptotermes secundus. We show evolutionary signatures of termite eusociality by comparing the genomes and transcriptomes of three termites and the cockroach against the background of 16 other eusocial and non-eusocial insects. Dramatic adaptive changes in genes underlying the production and perception of pheromones confirm the importance of chemical communication in the termites. These are accompanied by major changes in gene regulation and the molecular evolution of caste determination. Many of these results parallel molecular mechanisms of eusocial evolution in Hymenoptera. However, the specific solutions are remarkably different, thus revealing a striking case of convergence in one of the major evolutionary transitions in biological complexity.
Keywords: Animals; Biological Evolution; Blattellidae; Evolution, Molecular; Genome; Isoptera; Phylogeny; Social Behavior

Heterozygous Truncating Variants in POMP Escape Nonsense-Mediated Decay and Cause a Unique Immune Dysregulatory Syndrome. - Poli, M Cecilia; Ebstein, Frédéric; Nicholas, Sarah K; de Guzman, Marietta M; Forbes, Lisa R; Chinn, Ivan K; Mace, Emily M; Vogel, Tiphanie P; Carisey, Alexandre F; Benavides, Felipe; Coban-Akdemir, Zeynep H; Richard A Gibbs; et al. (Am J Hum Genet, 2018)
The proteasome processes proteins to facilitate immune recognition and host defense. When inherently defective, it can lead to aberrant immunity resulting in a dysregulated response that can cause autoimmunity and/or autoinflammation. Biallelic or digenic loss-of-function variants in some of the proteasome subunits have been described as causing a primary immunodeficiency disease that manifests as a severe dysregulatory syndrome: chronic atypical neutrophilic dermatosis with lipodystrophy and elevated temperature (CANDLE). Proteasome maturation protein (POMP) is a chaperone for proteasome assembly and is critical for the incorporation of catalytic subunits into the proteasome. Here, we characterize and describe POMP-related autoinflammation and immune dysregulation disease (PRAID) discovered in two unrelated individuals with a unique constellation of early-onset combined immunodeficiency, inflammatory neutrophilic dermatosis, and autoimmunity. We also begin to delineate a complex genetic mechanism whereby de novo heterozygous frameshift variants in the penultimate exon of POMP escape nonsense-mediated mRNA decay (NMD) and result in a truncated protein that perturbs proteasome assembly by a dominant-negative mechanism. To our knowledge, this mechanism has not been reported in any primary immunodeficiencies, autoinflammatory syndromes, or autoimmune diseases. Here, we define a unique hypo- and hyper-immune phenotype and report an immune dysregulation syndrome caused by frameshift mutations that escape NMD.
Keywords: Base Sequence; Cell Line; Endoplasmic Reticulum Stress; Exons; Family; Frameshift Mutation; Genetic Predisposition to Disease; Heterozygote; Humans; Immunologic Deficiency Syndromes; Immunophenotyping; Infant, Newborn; Inflammation; Interferon Type I; Male; Molecular Chaperones; Mutant Proteins; Mutation; Nonsense Mediated mRNA Decay; Phenotype; Proteasome Endopeptidase Complex; RNA, Messenger; Syndrome; Unfolded Protein Response

Identification of likely pathogenic and known variants in TSPEAR, LAMB3, BCOR, and WNT10A in four Turkish families with tooth agenesis. - Du, Renqian; Dinckan, Nuriye; Song, Xiaofei; Coban-Akdemir, Zeynep; Jhangiani, Shalini N; Guven, Yeliz; Aktoren, Oya; Kayserili, Hulya; Petty, Lauren E; Donna M Muzny; Below, Jennifer E; Eric Boerwinkle; et al. (Hum Genet, 2018)
Tooth agenesis (TA), the failure of development of one or more permanent teeth, is a common craniofacial abnormality observed in different world populations. The genetic etiology of TA is heterogeneous; more than a dozen genes have been associated with isolated or nonsyndromic TA, and more than 80 genes with syndromic forms. In this study, we applied whole exome sequencing (WES) to identify candidate genes contributing to TA in four Turkish families. Likely pathogenic variants with a low allele frequency in the general population were identified in four disease-associated genes, including two distinct variants in TSPEAR, associated with syndromic and isolated TA in one family each; a variant in LAMB3 associated with syndromic TA in one family; and a variant in BCOR plus a disease-associated WNT10A variant in one family with syndromic TA. With the notable exception of WNT10A (Tooth agenesis, selective, 4, MIM #150400), the genotype-phenotype relationships described in the present cohort represent an expansion of the clinical spectrum associated with these genes: TSPEAR (Deafness, autosomal recessive 98, MIM #614861), LAMB3 (Amelogenesis imperfecta, type IA, MIM #104530; Epidermolysis bullosa, junctional, MIMs #226700 and #226650), and BCOR (Microphthalmia, syndromic 2, MIM #300166). We provide evidence supporting the candidacy of these genes with TA, and propose TSPEAR as a novel nonsyndromic TA gene. Our data also suggest potential multilocus genomic variation, or mutational burden, in a single family, involving the BCOR and WNT10A loci, underscoring the complexity of the genotype-phenotype relationship in the common complex trait of TA.
Keywords: Anodontia; Cell Adhesion Molecules; Child; Child, Preschool; Female; Genetic Markers; Humans; Kalinin; Male; Mutation; Pedigree; Phenotype; Proteins; Proto-Oncogene Proteins; Repressor Proteins; Turkey; Wnt Proteins

Mismatch repair gene mutations lead to lynch syndrome colorectal cancer in rhesus macaques. - Dray, Beth K; Raveendran, Muthuswamy; R. Alan Harris; Benavides, Fernando; Gray, Stanton B; Perez, Carlos J; McArthur, Mark J; Williams, Lawrence E; Baze, Wallace B; Harshavardhan Doddapaneni; Donna M Muzny; Abee, Christian R; et al. (Genes Cancer, 2018)
Colorectal cancer accounts for a substantial number of deaths each year worldwide. Lynch Syndrome is a genetic form of colorectal cancer (CRC) caused by inherited mutations in DNA mismatch repair (MMR) genes. Although researchers have developed mouse models of Lynch Syndrome through targeted mutagenesis of MMR genes, the tumors that result differ in important ways from those in Lynch Syndrome patients. We identified 60 cases of CRC in rhesus macaques () at our facility since 2001. The tumors occur at the ileocecal junction, cecum and proximal colon and display clinicopathologic features similar to human Lynch Syndrome. We conducted immunohistochemical analysis of CRC tumors from several rhesus macaques, finding they frequently lack expression of MLH1 and PMS2 proteins, both critical MMR proteins involved in Lynch Syndrome. We also found that most macaque cases we tested exhibit microsatellite instability, a defining feature of Lynch Syndrome. Whole genome sequencing of rhesus macaque CRC cases identified mutations in and/or that are predicted to disrupt protein function. We conclude that this population of rhesus macaques constitutes a spontaneous model of Lynch Syndrome, matching the human disease in several significant characteristics, including genetic risk factors that parallel human Lynch Syndrome.

Mutations in PI3K110δ cause impaired natural killer cell function partially rescued by rapamycin treatment. - Ruiz-García, Raquel; Vargas-Hernandez, Alexander; Chinn, Ivan K; Angelo, Laura S; Cao, Tram N; Coban-Akdemir, Zeynep; Jhangiani, Shalini N; Meng, Qingchang; Forbes, Lisa R; Donna M Muzny; Allende, Luis M; Ehlayel, Mohammed S; et al. (J Allergy Clin Immunol, 2018)
BACKGROUND: Heterozygous gain-of-function mutations in PI3K110δ lead to lymphadenopathy, lymphoid hyperplasia, EBV and cytomegalovirus viremia, and sinopulmonary infections. OBJECTIVE: The known role of natural killer (NK) cell function in the control of EBV and cytomegalovirus prompted us to investigate the functional and phenotypic effects of PI3K110δ mutations on NK cell subsets and cytotoxic function. METHODS: Mutations in patients were identified by using whole-exome or targeted sequencing. We performed NK cell phenotyping and functional analysis of patients' cells using flow cytometry, standard Cr cytotoxicity assays, and quantitative confocal microscopy. RESULTS: PI3K110δ mutations led to an altered NK cell developmental phenotype and cytotoxic dysfunction. Impaired NK cell cytotoxicity was due to decreased conjugate formation with susceptible target cells and abrogated activation of cell machinery required for target cell killing. These defects were restored partially after initiation of treatment with rapamycin in 3 patients. CONCLUSION: We describe novel NK cell functional deficiency caused by PI3K110δ mutation, which is a likely contributor to the severe viremia observed in these patients. Rapamycin treatment partially restores NK cell function, providing a further rationale for its use in patients with this disease.
Keywords: Cell Differentiation; Cells, Cultured; Class I Phosphatidylinositol 3-Kinases; Cytomegalovirus; Cytomegalovirus Infections; Cytotoxicity, Immunologic; Epstein-Barr Virus Infections; Exome Sequencing; Herpesvirus 4, Human; Heterozygote; Humans; Immunologic Deficiency Syndromes; Immunological Synapses; Immunophenotyping; Killer Cells, Natural; Lymphocyte Activation; Microscopy, Confocal; Mutation; Phosphatidylinositol 3-Kinases; Sirolimus; Viremia

Novel CYP2A6 diplotypes identified through next-generation sequencing are associated with in-vitro and in-vivo nicotine metabolism. - Tanner, Julie-Anne; Zhu, Andy Z; Claw, Katrina G; Prasad, Bhagwat; Korchina, Viktoriya; Jianhong Hu; Harshavardhan Doddapaneni; Donna M Muzny; Schuetz, Erin G; Lerman, Caryn; Thummel, Kenneth E; Scherer, Steven E; et al. (Pharmacogenet Genomics, 2018)
OBJECTIVES: Smoking patterns and cessation rates vary widely across smokers and can be influenced by variation in rates of nicotine metabolism [i.e. cytochrome P450 2A6 (CYP2A6), enzyme activity]. There is high heritability of CYP2A6-mediated nicotine metabolism (60-80%) owing to known and unidentified genetic variation in the CYP2A6 gene. We aimed to identify and characterize additional genetic variants at the CYP2A6 gene locus. METHODS: A new CYP2A6-specific sequencing method was used to investigate genetic variation in CYP2A6. Novel variants were characterized in a White human liver bank that has been extensively phenotyped for CYP2A6. Linkage and haplotype structure for the novel single nucleotide polymorphisms (SNPs) were assessed. The association between novel five-SNP diplotypes and nicotine metabolism rate was investigated. RESULTS: Seven high-frequency (minor allele frequencies ≥6%) noncoding SNPs were identified as important contributors to CYP2A6 phenotypes in a White human liver bank (rs57837628, rs7260629, rs7259706, rs150298687 (also denoted rs4803381), rs56113850, rs28399453, and rs8192733), accounting for two times more variation in in-vitro CYP2A6 activity relative to the four established functional CYP2A6 variants that are frequently tested in Whites (CYP2A6*2, *4, *9, and *12). Two pairs of novel SNPs were in high linkage disequilibrium, allowing us to establish five-SNP diplotypes that were associated with CYP2A6 enzyme activity (rate of nicotine metabolism) in-vitro in the liver bank and in-vivo among smokers. CONCLUSION: The novel five-SNP diplotype may be useful to incorporate into CYP2A6 genotype models for personalized prediction of nicotine metabolism rate, cessation success, and response to pharmacotherapies.
Keywords: Cytochrome P-450 CYP2A6; Gene Frequency; Genome-Wide Association Study; High-Throughput Nucleotide Sequencing; Humans; In Vitro Techniques; Linkage Disequilibrium; Liver; Nicotine; Polymorphism, Single Nucleotide; Sequence Analysis, DNA; Tissue Banks; White People

Phenotype expansion and development in Kosaki overgrowth syndrome. - Gawliński, P; Pelc, M; Ciara, E; Jhangiani, S; Jurkiewicz, E; Gambin, T; Różdżyńska-Świątkowska, A; Dawidziuk, M; Coban-Akdemir, Z H; Guilbride, D L; Donna M Muzny; Lupski, J R; et al. (Clin Genet, 2018)
We expand the Kosaki overgrowth syndrome (KOGS) phenotype by over 70% to include 24 unreported KOGS symptoms, in a first male patient, the third overall associated with the PDGFRB c.1751C>G p.(Pro584Arg) mutation. Eighteen of these symptoms are unique to our patient, the remaining six are shared with other patients. Of the 24 unreported features overall, 6 show marked phenotype evolution and varying time of onset. The triangular face detected at 14 months and long palpebral fissures with lateral ectropion at 4 years are present in other members of the cohort. The remaining 4 are unique to Patient 5: pronounced macrocephaly from birth, increasingly triangular anterior skull from 14 months, camptodactyly, emerging at 4 years and worsening joint contractures from 6 years. Compilation of all new symptoms reported here with published clinical data further identifies at least 18 clinical parameters common to all cases to date, encompassing both known KOGS-associated PDGFRB mutations. We therefore propose a set of 18 core KOGS symptoms, with 16 present in early childhood. These results should also impact diagnostic/prognostic scope, intervention and outcome potential for KOGS patients, particularly for developmentally progressive conditions such as scoliosis and myofibroma.
Keywords: Adolescent; Child; Child, Preschool; Exome; Female; Genetic Association Studies; Genetic Predisposition to Disease; High-Throughput Nucleotide Sequencing; Humans; Male; Megalencephaly; Musculoskeletal Abnormalities; Mutation; Phenotype; Receptor, Platelet-Derived Growth Factor beta

Phenotypic expansion illuminates multilocus pathogenic variation. - Karaca, Ender; Posey, Jennifer E; Coban Akdemir, Zeynep; Pehlivan, Davut; Harel, Tamar; Jhangiani, Shalini N; Bayram, Yavuz; Song, Xiaofei; Bahrambeigi, Vahid; Yuregir, Ozge Ozalp; Bozdogan, Sevcan; Yesil, Gozde; et al. (Genet Med, 2018)
PURPOSE: Multilocus variation-pathogenic variants in two or more disease genes-can potentially explain the underlying genetic basis for apparent phenotypic expansion in cases for which the observed clinical features extend beyond those reported in association with a "known" disease gene. METHODS: Analyses focused on 106 patients, 19 for whom apparent phenotypic expansion was previously attributed to variation at known disease genes. We performed a retrospective computational reanalysis of whole-exome sequencing data using stringent Variant Call File filtering criteria to determine whether molecular diagnoses involving additional disease loci might explain the observed expanded phenotypes. RESULTS: Multilocus variation was identified in 31.6% (6/19) of families with phenotypic expansion and 2.3% (2/87) without phenotypic expansion. Intrafamilial clinical variability within two families was explained by multilocus variation identified in the more severely affected sibling. CONCLUSION: Our findings underscore the role of multiple rare variants at different loci in the etiology of genetically and clinically heterogeneous cohorts. Intrafamilial phenotypic and genotypic variability allowed a dissection of genotype-phenotype relationships in two families. Our data emphasize the critical role of the clinician in diagnostic genomic analyses and demonstrate that apparent phenotypic expansion may represent blended phenotypes resulting from pathogenic variation at more than one locus.
Keywords: Child, Preschool; Exome; Exome Sequencing; Female; Genetic Association Studies; Genetic Diseases, Inborn; Genetic Variation; Genotype; Heterozygote; High-Throughput Nucleotide Sequencing; Humans; Infant; Infant, Newborn; Male; Mutation; Pathology, Molecular; Pedigree; Phenotype

Phenotypic expansion in - a common cause of intellectual disability in females. - Wang, Xia; Posey, Jennifer E; Rosenfeld, Jill A; Bacino, Carlos A; Scaglia, Fernando; Immken, Ladonna; Harris, Jill M; Hickey, Scott E; Mosher, Theresa M; Slavotinek, Anne; Zhang, Jing; Beuten, Joke; et al. (Ann Clin Transl Neurol, 2018)
De variants in account for 1-3% of unexplained intellectual disability (ID) cases and are amongst the most common causes of ID especially in females. Forty-seven patients (44 females, 3 males) have been described. We identified 31 additional individuals carrying 29 unique variants, including 30 postnatal individuals with complex clinical presentations of developmental delay or ID, and one fetus with abnormal ultrasound findings. Rare or novel phenotypes observed include respiratory problems, congenital heart disease, skeletal muscle mitochondrial DNA depletion, and late-onset neurologic decline. Our findings expand the spectrum of DNA variants and phenotypes associated with disorders.

Prioritization of Candidate Genes for Congenital Diaphragmatic Hernia in a Critical Region on Chromosome 4p16 using a Machine-Learning Algorithm. - Callaway, Danielle A; Campbell, Ian M; Stover, Samantha R; Hernandez-Garcia, Andres; Jhangiani, Shalini N; Punetha, Jaya; Paine, Ingrid S; Posey, Jennifer E; Donna M Muzny; Lally, Kevin P; James R Lupski; Shaw, Chad A; et al. (J Pediatr Genet, 2018)
Wolf-Hirschhorn syndrome (WHS) is caused by partial deletion of the short arm of chromosome 4 and is characterized by dysmorphic facies, congenital heart defects, intellectual/developmental disability, and increased risk for congenital diaphragmatic hernia (CDH). In this report, we describe a stillborn girl with WHS and a large CDH. A literature review revealed 15 cases of WHS with CDH, which overlap a 2.3-Mb CDH critical region. We applied a machine-learning algorithm that integrates large-scale genomic knowledge to genes within the 4p16.3 CDH critical region and identified , , , , , , , and as genes whose haploinsufficiency may contribute to the development of CDH.

Reproductive Longevity Predicts Mutation Rates in Primates. - Thomas, Gregg W C; Wang, Richard J; Puri, Arthi; R. Alan Harris; Raveendran, Muthuswamy; Hughes, Daniel S T; Murali, Shwetha C; Williams, Lawrence E; Harshavardhan Doddapaneni; Donna M Muzny; Richard A Gibbs; Abee, Christian R; et al. (Curr Biol, 2018)
Mutation rates vary between species across several orders of magnitude, with larger organisms having the highest per-generation mutation rates. Hypotheses for this pattern typically invoke physiological or population-genetic constraints imposed on the molecular machinery preventing mutations [1]. However, continuing germline cell division in multicellular eukaryotes means that organisms with longer generation times and of larger size will leave more mutations to their offspring simply as a byproduct of their increased lifespan [2, 3]. Here, we deeply sequence the genomes of 30 owl monkeys (Aotus nancymaae) from six multi-generation pedigrees to demonstrate that paternal age is the major factor determining the number of de novo mutations in this species. We find that owl monkeys have an average mutation rate of 0.81 × 10 per site per generation, roughly 32% lower than the estimate in humans. Based on a simple model of reproductive longevity that does not require any changes to the mutational machinery, we show that this is the expected mutation rate in owl monkeys. We further demonstrate that our model predicts species-specific mutation rates in other primates, including study-specific mutation rates in humans based on the average paternal age. Our results suggest that variation in life history traits alone can explain variation in the per-generation mutation rate among primates, and perhaps among a wide range of multicellular organisms.
Keywords: Animals; Aotidae; Genetic Fitness; Genetics, Population; Genome; Humans; Longevity; Mutation; Mutation Rate; Pedigree; Population Density; Primates; Reproduction

The role of FREM2 and FRAS1 in the development of congenital diaphragmatic hernia. - Jordan, Valerie K; Beck, Tyler F; Hernandez-Garcia, Andres; Kundert, Peter N; Kim, Bum-Jun; Jhangiani, Shalini N; Gambin, Tomasz; Starkovich, Molly; Punetha, Jaya; Paine, Ingrid S; Posey, Jennifer E; Li, Alexander H; et al. (Hum Mol Genet, 2018)
Congenital diaphragmatic hernia (CDH) has been reported twice in individuals with a clinical diagnosis of Fraser syndrome, a genetic disorder that can be caused by recessive mutations affecting FREM2 and FRAS1. In the extracellular matrix, FREM2 and FRAS1 form a self-stabilizing complex with FREM1, a protein whose deficiency causes sac CDH in humans and mice. By sequencing FREM2 and FRAS1 in a CDH cohort, and searching online databases, we identified five individuals who carried recessive or double heterozygous, putatively deleterious variants in these genes which may represent susceptibility alleles. Three of these alleles were significantly enriched in our CDH cohort compared with ethnically matched controls. We subsequently demonstrated that 8% of Frem2ne/ne and 1% of Fras1Q1263*/Q1263* mice develop the same type of anterior sac CDH seen in FREM1-deficient mice. We went on to show that development of sac hernias in FREM1-deficient mice is preceded by failure of anterior mesothelial fold progression resulting in the persistence of an amuscular, poorly vascularized anterior diaphragm that is abnormally adherent to the underlying liver. Herniation occurs in the perinatal period when the expanding liver protrudes through this amuscular region of the anterior diaphragm that is juxtaposed to areas of muscular diaphragm. Based on these data, we conclude that deficiency of FREM2, and possibly FRAS1, are associated with an increased risk of developing CDH and that loss of the FREM1/FREM2/FRAS1 complex, or its function, leads to anterior sac CDH development through its effects on mesothelial fold progression.
Keywords: Animals; Child; Child, Preschool; Epithelium; Extracellular Matrix Proteins; Female; Hernias, Diaphragmatic, Congenital; Humans; Infant; Infant, Newborn; Male; Mice; Mice, Knockout; Mutation; Pregnancy; Receptors, Interleukin

Sequence-Based Analysis of Lipid-Related Metabolites in a Multiethnic Study. - Feofanova, Elena V; Yu, Bing; Ginger A Metcalf; Liu, Xiaoming; Donna M Muzny; Below, Jennifer E; Wagenknecht, Lynne E; Richard A Gibbs; Morrison, Alanna C; Eric Boerwinkle (Genetics, 2018)
Small molecule lipid-related metabolites are important components of fatty acid and steroid metabolism-two important contributors to human health. This study investigated the extent to which rare and common genetic variants spanning the human genome influence the lipid-related metabolome. Sequence data from 1552 European-Americans (EA) and 1872 African-Americans (AA) were analyzed to examine the impact of common and rare variants on the levels of 102 circulating lipid-related metabolites measured by a combination of chromatography and mass spectroscopy. We conducted single variant tests [minor allele frequency (MAF) > 5%, statistical significance -value ≤ 2.45 × 10] and tests aggregating rare variants (MAF ≤ 5%) across multiple genomic motifs, such as coding regions and regulatory domains, and sliding windows. Multiethnic meta-analyses detected 53 lipid-related metabolites-locus pairs, which were inspected for evidence of consistent signal between the two ethnic groups. Thirty-eight lipid-related metabolite-genomic region associations were consistent across ethnicities, among which seven were novel. The regions contain genes that are related to metabolite transport () and metabolism (, , , and ). Six of the seven novel findings lie in expression quantitative trait loci affecting the expression levels of 14 surrounding genes in multiple tissues. Imputed expression levels of 10 of the affected genes were associated with four corresponding lipid-related traits in at least one tissue. Our findings offer valuable insight into circulating lipid-related metabolite regulation in a multiethnic population.
Keywords: Black or African American; Female; Humans; Lipid Metabolism; Male; Metabolome; Middle Aged; Polymorphism, Single Nucleotide; Quantitative Trait Loci; White People

Sheep genome functional annotation reveals proximal regulatory elements contributed to the evolution of modern breeds. - Naval-Sanchez, Marina; Nguyen, Quan; McWilliam, Sean; Porto-Neto, Laercio R; Tellam, Ross; Vuocolo, Tony; Reverter, Antonio; Perez-Enciso, Miguel; Brauning, Rudiger; Clarke, Shannon; McCulloch, Alan; Zamani, Wahid; et al. (Nat Commun, 2018)
Domestication fundamentally reshaped animal morphology, physiology and behaviour, offering the opportunity to investigate the molecular processes driving evolutionary change. Here we assess sheep domestication and artificial selection by comparing genome sequence from 43 modern breeds (Ovis aries) and their Asian mouflon ancestor (O. orientalis) to identify selection sweeps. Next, we provide a comparative functional annotation of the sheep genome, validated using experimental ChIP-Seq of sheep tissue. Using these annotations, we evaluate the impact of selection and domestication on regulatory sequences and find that sweeps are significantly enriched for protein coding genes, proximal regulatory elements of genes and genome features associated with active transcription. Finally, we find individual sites displaying strong allele frequency divergence are enriched for the same regulatory features. Our data demonstrate that remodelling of gene expression is likely to have been one of the evolutionary forces that drove phenotypic diversification of this common livestock species.
Keywords: Animals; Breeding; Evolution, Molecular; Female; Gene Frequency; Genome; Male; Molecular Sequence Annotation; Phylogeny; Regulatory Elements, Transcriptional; Sheep

Sooty mangabey genome sequence provides insight into AIDS resistance in a natural SIV host. - Palesch, David; Bosinger, Steven E; Tharp, Gregory K; Vanderford, Thomas H; Paiardini, Mirko; Chahroudi, Ann; Johnson, Zachary P; Kirchhoff, Frank; Hahn, Beatrice H; Norgren, Robert B; Patel, Nirav B; Sodora, Donald L; et al. (Nature, 2018)
In contrast to infections with human immunodeficiency virus (HIV) in humans and simian immunodeficiency virus (SIV) in macaques, SIV infection of a natural host, sooty mangabeys (Cercocebus atys), is non-pathogenic despite high viraemia. Here we sequenced and assembled the genome of a captive sooty mangabey. We conducted genome-wide comparative analyses of transcript assemblies from C. atys and AIDS-susceptible species, such as humans and macaques, to identify candidates for host genetic factors that influence susceptibility. We identified several immune-related genes in the genome of C. atys that show substantial sequence divergence from macaques or humans. One of these sequence divergences, a C-terminal frameshift in the toll-like receptor-4 (TLR4) gene of C. atys, is associated with a blunted in vitro response to TLR-4 ligands. In addition, we found a major structural change in exons 3-4 of the immune-regulatory protein intercellular adhesion molecule 2 (ICAM-2); expression of this variant leads to reduced cell surface expression of ICAM-2. These data provide a resource for comparative genomic studies of HIV and/or SIV pathogenesis and may help to elucidate the mechanisms by which SIV-infected sooty mangabeys avoid AIDS.
Keywords: Acquired Immunodeficiency Syndrome; Amino Acid Sequence; Animals; Cell Adhesion Molecules; Cercocebus atys; Exons; Female; Frameshift Mutation; Genetic Predisposition to Disease; Genetic Variation; Genome; Genomics; HIV; Host Specificity; Humans; Macaca; Sequence Deletion; Simian Acquired Immunodeficiency Syndrome; Simian Immunodeficiency Virus; Species Specificity; Toll-Like Receptor 4; Transcriptome; Whole Genome Sequencing

Spontaneous Spongiform Brainstem Degeneration in a Young Mouse Lemur () with Conspicuous Behavioral, Motor, Growth, and Ocular Pathologies. - Schmidtke, Daniel; Lempp, Charlotte; Dubicanac, Marko; Radespiel, Ute; Zimmermann, Elke; Baumgärtner, Wolfgang; Kästner, Sabine; Meier, Martin; Balkema-Buschmann, Anne; R. Alan Harris; Raveendran, Muthuswamy; Donna M Muzny; et al. (Comp Med, 2018)
Here we report a case of severe growth retardation and neurologic abnormalities in a female gray mouse lemur (), a small NHP species for which the genomic sequence recently became available. The female lemur we present here died on postnatal day 125. This lemur had impaired development of motor skills and showed severe ataxia and tremors. In addition, hearing seemed normal whereas ophthalmic examination revealed incipient bilateral cataracts, abnormal pigmentation in the lens of the left eye, and a missing optokinetic nystagmus, which indicated impaired vision. Most prominently, the lemur showed severe growth retardation. Necropsy revealed maldevelopment of the left reproductive organs and unilateral dilation of the right lateral ventricle, which was confirmed on brain MRI. Brain histology further revealed large, bilateral areas of vacuolation within the brainstem, but immunohistochemistry indicated no sign of pathologic prion protein deposition. Full genomic sequencing of the lemur revealed a probably pathologic mutation in of the LARGE gene family, which has been associated with congenital muscular dystrophies. However, potentially functional mutations in other genes were also present. The observed behavioral and motor signs in the presented animal might have been linked to spongiform degeneration and resulting brainstem dysfunction and progressive muscle weakness. The macroscopic developmental abnormalities and ophthalmic findings might be genetic in origin and linked to the mutation in .
Keywords: Animals; Behavior, Animal; Brain Stem; Cheirogaleidae; Eye; Female; Growth Disorders; Neurodegenerative Diseases; Primate Diseases; Walker-Warburg Syndrome

Syndromic congenital myelofibrosis associated with a loss-of-function variant in . - Magoulas, Pilar L; Shchelochkov, Oleg A; Bainbridge, Matthew N; Ben-Shachar, Shay; Yatsenko, Svetlana; Potocki, Lorraine; Lewis, Richard A; Searby, Charles; Marcogliese, Andrea N; Elghetany, M Tarek; Zapata, Gladys; Hernández, Paula P; et al. (Blood, 2018)
There is a Commentary on this article in this issue.
Keywords: Abnormalities, Multiple; Bone Marrow Transplantation; Child; Consanguinity; Fatal Outcome; Female; Gonadal Dysgenesis, 46,XY; Hematopoietic Stem Cell Transplantation; Humans; Infant; Intellectual Disability; Male; Pedigree; Phenotype; Primary Myelofibrosis; Syndrome; Vesicular Transport Proteins

Temporal development of the gut microbiome in early childhood from the TEDDY study. - Stewart, Christopher J; Ajami, Nadim J; O'Brien, Jacqueline L; Hutchinson, Diane S; Smith, Daniel P; Wong, Matthew C; Ross, Matthew C; Lloyd, Richard E; Harshavardhan Doddapaneni; Ginger A Metcalf; Donna M Muzny; Richard A Gibbs; et al. (Nature, 2018)
The development of the microbiome from infancy to childhood is dependent on a range of factors, with microbial-immune crosstalk during this time thought to be involved in the pathobiology of later life diseases such as persistent islet autoimmunity and type 1 diabetes. However, to our knowledge, no studies have performed extensive characterization of the microbiome in early life in a large, multi-centre population. Here we analyse longitudinal stool samples from 903 children between 3 and 46 months of age by 16S rRNA gene sequencing (n = 12,005) and metagenomic sequencing (n = 10,867), as part of the The Environmental Determinants of Diabetes in the Young (TEDDY) study. We show that the developing gut microbiome undergoes three distinct phases of microbiome progression: a developmental phase (months 3-14), a transitional phase (months 15-30), and a stable phase (months 31-46). Receipt of breast milk, either exclusive or partial, was the most significant factor associated with the microbiome structure. Breastfeeding was associated with higher levels of Bifidobacterium species (B. breve and B. bifidum), and the cessation of breast milk resulted in faster maturation of the gut microbiome, as marked by the phylum Firmicutes. Birth mode was also significantly associated with the microbiome during the developmental phase, driven by higher levels of Bacteroides species (particularly B. fragilis) in infants delivered vaginally. Bacteroides was also associated with increased gut diversity and faster maturation, regardless of the birth mode. Environmental factors including geographical location and household exposures (such as siblings and furry pets) also represented important covariates. A nested case-control analysis revealed subtle associations between microbial taxonomy and the development of islet autoimmunity or type 1 diabetes. These data determine the structural and functional assembly of the microbiome in early life and provide a foundation for targeted mechanistic investigation into the consequences of microbial-immune crosstalk for long-term health.
Keywords: Adolescent; Animals; Bifidobacterium; Breast Feeding; Case-Control Studies; Child; Child, Preschool; Cluster Analysis; Datasets as Topic; Diabetes Mellitus, Type 1; Female; Firmicutes; Gastrointestinal Microbiome; Humans; Infant; Male; Milk, Human; Pets; RNA, Ribosomal, 16S; Siblings; Surveys and Questionnaires; Time Factors

The Toxicogenome of Hyalella azteca: A Model for Sediment Ecotoxicology and Evolutionary Toxicology. - Poynton, Helen C; Hasenbein, Simone; Benoit, Joshua B; Sepulveda, Maria S; Poelchau, Monica F; Hughes, Daniel S T; Murali, Shwetha C; Chen, Shuai; Glastad, Karl M; Goodisman, Michael A D; Werren, John H; Vineis, Joseph H; et al. (Environ Sci Technol, 2018)
Hyalella azteca is a cryptic species complex of epibenthic amphipods of interest to ecotoxicology and evolutionary biology. It is the primary crustacean used in North America for sediment toxicity testing and an emerging model for molecular ecotoxicology. To provide molecular resources for sediment quality assessments and evolutionary studies, we sequenced, assembled, and annotated the genome of the H. azteca U.S. Lab Strain. The genome quality and completeness is comparable with other ecotoxicological model species. Through targeted investigation and use of gene expression data sets of H. azteca exposed to pesticides, metals, and other emerging contaminants, we annotated and characterized the major gene families involved in sequestration, detoxification, oxidative stress, and toxicant response. Our results revealed gene loss related to light sensing, but a large expansion in chemoreceptors, likely underlying sensory shifts necessary in their low light habitats. Gene family expansions were also noted for cytochrome P450 genes, cuticle proteins, ion transporters, and include recent gene duplications in the metal sequestration protein, metallothionein. Mapping of differentially expressed transcripts to the genome significantly increased the ability to functionally annotate toxicant responsive genes. The H. azteca genome will greatly facilitate development of genomic tools for environmental assessments and promote an understanding of how evolution shapes toxicological pathways with implications for environmental and human health.
Keywords: Amphipoda; Animals; Ecotoxicology; Geologic Sediments; North America; Toxicity Tests; Water Pollutants, Chemical

Whole-Exome Sequencing Identifies Novel Variants for Tooth Agenesis. - Dinckan, N; Du, R; Petty, L E; Coban-Akdemir, Z; Jhangiani, S N; Paine, I; Baugh, E H; Erdem, A P; Kayserili, H; Harshavardhan Doddapaneni; Jianhong Hu; Donna M Muzny; et al. (J Dent Res, 2018)
Tooth agenesis is a common craniofacial abnormality in humans and represents failure to develop 1 or more permanent teeth. Tooth agenesis is complex, and variations in about a dozen genes have been reported as contributing to the etiology. Here, we combined whole-exome sequencing, array-based genotyping, and linkage analysis to identify putative pathogenic variants in candidate disease genes for tooth agenesis in 10 multiplex Turkish families. Novel homozygous and heterozygous variants in LRP6, DKK1, LAMA3, and COL17A1 genes, as well as known variants in WNT10A, were identified as likely pathogenic in isolated tooth agenesis. Novel variants in KREMEN1 were identified as likely pathogenic in 2 families with suspected syndromic tooth agenesis. Variants in more than 1 gene were identified segregating with tooth agenesis in 2 families, suggesting oligogenic inheritance. Structural modeling of missense variants suggests deleterious effects to the encoded proteins. Functional analysis of an indel variant (c.3607+3_6del) in LRP6 suggested that the predicted resulting mRNA is subject to nonsense-mediated decay. Our results support a major role for WNT pathways genes in the etiology of tooth agenesis while revealing new candidate genes. Moreover, oligogenic cosegregation was suggestive for complex inheritance and potentially complex gene product interactions during development, contributing to improved understanding of the genetic etiology of familial tooth agenesis.
Keywords: Anodontia; Exome Sequencing; Female; Genetic Linkage; Genetic Variation; Humans; Intercellular Signaling Peptides and Proteins; Laminin; Low Density Lipoprotein Receptor-Related Protein-6; Male; Membrane Proteins; Mutation, Missense; Pedigree; Real-Time Polymerase Chain Reaction; Turkey; Wnt Proteins

Enrichment of mutations in chromatin regulators in people with Rett syndrome lacking mutations in MECP2. - Sajan, Samin A; Jhangiani, Shalini N; Donna M Muzny; Richard A Gibbs; Lupski, James R; Glaze, Daniel G; Kaufmann, Walter E; Skinner, Steven A; Annese, Fran; Friez, Michael J; Lane, Jane; Percy, Alan K; et al. (Genet Med, 2017)
PURPOSE: Rett syndrome (RTT) is a neurodevelopmental disorder caused primarily by de novo mutations in MECP2 and sometimes in CDKL5 and FOXG1. However, some RTT patients lack mutations in these genes. METHODS: Twenty-two RTT patients without apparent MECP2, CDKL5, and FOXG1 mutations were subjected to both whole-exome sequencing and single-nucleotide polymorphism array-based copy-number variant (CNV) analyses. RESULTS: Three patients had MECP2 mutations initially missed by clinical testing. Of the remaining 19, 17 (89.5%) had 29 other likely pathogenic intragenic mutations and/or CNVs (10 patients had 2 or more). Interestingly, 13 patients had mutations in a gene/region previously reported in other neurodevelopmental disorders (NDDs), thereby providing a potential diagnostic yield of 68.4%. These mutations were significantly enriched in chromatin regulators (corrected P = 0.0068) and moderately enriched in postsynaptic cell membrane molecules (corrected P = 0.076), implicating glutamate receptor signaling. CONCLUSION: The genetic etiology of RTT without MECP2, CDKL5, and FOXG1 mutations is heterogeneous, overlaps with other NDDs, and complicated by a high mutation burden. Dysregulation of chromatin structure and abnormal excitatory synaptic signaling may form two common pathological bases of RTT.Genet Med 19 1, 13-19.
Keywords: Adolescent; Adult; Child; Child, Preschool; Chromatin; DNA Copy Number Variations; Exome Sequencing; Female; Forkhead Transcription Factors; Humans; Infant; Male; Methyl-CpG-Binding Protein 2; Mutation; Nerve Tissue Proteins; Polymorphism, Single Nucleotide; Protein Serine-Threonine Kinases; Rett Syndrome

Erratum to: The whole genome sequence of the Mediterranean fruit fly, Ceratitis capitata (Wiedemann), reveals insights into the biology and adaptive evolution of a highly invasive pest species. - Papanicolaou, Alexie; Schetelig, Marc F; Arensburger, Peter; Atkinson, Peter W; Benoit, Joshua B; Bourtzis, Kostas; Castañera, Pedro; Cavanaugh, John P; Chao, Hsu; Childers, Christopher; Curril, Ingrid; Dinh, Huyen; et al. (Genome Biol, 2017)

Evolutionary History of Chemosensory-Related Gene Families across the Arthropoda. - Eyun, Seong-Il; Soh, Ho Young; Posavi, Marijan; Munro, James B; Hughes, Daniel S T; Murali, Shwetha C; Qu, Jiaxin; Dugan, Shannon; Lee, Sandra L; Chao, Hsu; Dinh, Huyen; Yi Han; et al. (Mol Biol Evol, 2017)
Chemosensory-related gene (CRG) families have been studied extensively in insects, but their evolutionary history across the Arthropoda had remained relatively unexplored. Here, we address current hypotheses and prior conclusions on CRG family evolution using a more comprehensive data set. In particular, odorant receptors were hypothesized to have proliferated during terrestrial colonization by insects (hexapods), but their association with other pancrustacean clades and with independent terrestrial colonizations in other arthropod subphyla have been unclear. We also examine hypotheses on which arthropod CRG family is most ancient. Thus, we reconstructed phylogenies of CRGs, including those from new arthropod genomes and transcriptomes, and mapped CRG gains and losses across arthropod lineages. Our analysis was strengthened by including crustaceans, especially copepods, which reside outside the hexapod/branchiopod clade within the subphylum Pancrustacea. We generated the first high-resolution genome sequence of the copepod Eurytemora affinis and annotated its CRGs. We found odorant receptors and odorant binding proteins present only in hexapods (insects) and absent from all other arthropod lineages, indicating that they are not universal adaptations to land. Gustatory receptors likely represent the oldest chemosensory receptors among CRGs, dating back to the Placozoa. We also clarified and confirmed the evolutionary history of antennal ionotropic receptors across the Arthropoda. All antennal ionotropic receptors in E. affinis were expressed more highly in males than in females, suggestive of an association with male mate-recognition behavior. This study is the most comprehensive comparative analysis to date of CRG family evolution across the largest and most speciose metazoan phylum Arthropoda.
Keywords: Animals; Arthropods; Chemoreceptor Cells; Copepoda; Crustacea; Databases, Nucleic Acid; Evolution, Molecular; Genome; Insecta; Multigene Family; Phylogeny; Receptors, Odorant

Exome sequencing reveals novel genetic loci influencing obesity-related traits in Hispanic children. - Aniko Sabo; Mishra, Pamela; Dugan-Perez, Shannon; Voruganti, V Saroja; Kent, Jack W; Kalra, Divya; Cole, Shelley A; Comuzzie, Anthony G; Donna M Muzny; Richard A Gibbs; Butte, Nancy F (Obesity (Silver Spring), 2017)
OBJECTIVE: To perform whole exome sequencing in 928 Hispanic children and identify variants and genes associated with childhood obesity. METHODS: Single-nucleotide variants (SNVs) were identified from Illumina whole exome sequencing data using integrated read mapping, variant calling, and an annotation pipeline (Mercury). Association analyses of 74 obesity-related traits and exonic variants were performed using SeqMeta software. Rare autosomal variants were analyzed using gene-based association analyses, and common autosomal variants were analyzed at the SNV level. RESULTS: (1) Rare exonic variants in 10 genes and 16 common SNVs in 11 genes that were associated with obesity traits in a cohort of Hispanic children were identified, (2) novel rare variants in peroxisome biogenesis factor 1 (PEX1) associated with several obesity traits (weight, weight z score, BMI, BMI z score, waist circumference, fat mass, trunk fat mass) were discovered, and (3) previously reported SNVs associated with childhood obesity were replicated. CONCLUSIONS: Convergence of whole exome sequencing, a family-based design, and extensive phenotyping discovered novel rare and common variants associated with childhood obesity. Linking PEX1 to obesity phenotypes poses a novel mechanism of peroxisomal biogenesis and metabolism underlying the development of childhood obesity.
Keywords: Adolescent; ATPases Associated with Diverse Cellular Activities; Body Mass Index; Body Weight; Child; Child, Preschool; Cohort Studies; Exome; Genetic Loci; Genome-Wide Association Study; Hispanic or Latino; Humans; Membrane Proteins; Pediatric Obesity; Polymorphism, Single Nucleotide; Risk Factors; Sequence Analysis, DNA; Software; Waist Circumference; Young Adult

An exome sequencing study of Moebius syndrome including atypical cases reveals an individual with CFEOM3A and a mutation. - Patel, Ronak M; Liu, David; Gonzaga-Jauregui, Claudia; Jhangiani, Shalini; Lu, James T; Sutton, V Reid; Fernbach, Susan D; Azamian, Mahshid; White, Lisa; Edmond, Jane C; Paysse, Evelyn A; Belmont, John W; et al. (Cold Spring Harb Mol Case Stud, 2017)
Moebius syndrome is characterized by congenital unilateral or bilateral facial and abducens nerve palsies (sixth and seventh cranial nerves) causing facial weakness, feeding difficulties, and restricted ocular movements. Abnormalities of the chest wall such as Poland anomaly and variable limb defects are frequently associated with this syndrome. Most cases are isolated; however, rare families with autosomal dominant transmission with incomplete penetrance and variable expressivity have been described. The genetic basis of this condition remains unknown. In a cohort study of nine individuals suspected to have Moebius syndrome (six typical, three atypical), we performed whole-exome sequencing to try to identify a commonly mutated gene. Although no such gene was identified and we did not find mutations in and , we found a de novo heterozygous mutation, p.E410K, in the gene encoding tubulin beta 3 class III (), in an individual with atypical Moebius syndrome. This individual was diagnosed with near-complete ophthalmoplegia, agenesis of the corpus callosum, and absence of the septum pellucidum. No substantial limb abnormalities were noted. Mutations in have been associated with complex cortical dysplasia and other brain malformations and congenital fibrosis of extraocular muscles type 3A (CFEOM3A). Our report highlights the overlap of genetic etiology and clinical differences between CFEOM and Moebius syndrome and describes our approach to identifying candidate genes for typical and atypical Moebius syndrome.
Keywords: Child; Child, Preschool; Cohort Studies; Exome; Exome Sequencing; Eye Diseases, Hereditary; Facial Paralysis; Female; Humans; Infant; Male; Malformations of Cortical Development; Mobius Syndrome; Muscular Diseases; Mutation; Ocular Motility Disorders; Ophthalmoplegia; Orbital Diseases; Pedigree; Tubulin

Extremely low-coverage whole genome sequencing in South Asians captures population genomics information. - Rustagi, Navin; Zhou, Anbo; Watkins, W Scott; Gedvilaite, Erika; Wang, Shuoguo; Ramesh, Naveen; Donna M Muzny; Richard A Gibbs; Jorde, Lynn B; Fuli Yu; Xing, Jinchuan (BMC Genomics, 2017)
BACKGROUND: The cost of Whole Genome Sequencing (WGS) has decreased tremendously in recent years due to advances in next-generation sequencing technologies. Nevertheless, the cost of carrying out large-scale cohort studies using WGS is still daunting. Past simulation studies with coverage at ~2x have shown promise for using low coverage WGS in studies focused on variant discovery, association study replications, and population genomics characterization. However, the performance of low coverage WGS in populations with a complex history and no reference panel remains to be determined. RESULTS: South Indian populations are known to have a complex population structure and are an example of a major population group that lacks adequate reference panels. To test the performance of extremely low-coverage WGS (EXL-WGS) in populations with a complex history and to provide a reference resource for South Indian populations, we performed EXL-WGS on 185 South Indian individuals from eight populations to ~1.6x coverage. Using two variant discovery pipelines, SNPTools and GATK, we generated a consensus call set that has ~90% sensitivity for identifying common variants (minor allele frequency ≥ 10%). Imputation further improves the sensitivity of our call set. In addition, we obtained high-coverage for the whole mitochondrial genome to infer the maternal lineage evolutionary history of the Indian samples. CONCLUSIONS: Overall, we demonstrate that EXL-WGS with imputation can be a valuable study design for variant discovery with a dramatically lower cost than standard WGS, even in populations with a complex history and without available reference data. In addition, the South Indian EXL-WGS data generated in this study will provide a valuable resource for future Indian genomic studies.
Keywords: Asian People; Genetic Variation; Genome, Mitochondrial; Humans; Metagenomics; Whole Genome Sequencing

Generating Clinical Reports from Genomic Data on the Cloud-based Neptune Platform - Eric Venner; Leduc, Magalie S; Matthew N Bainbridge; Wu, Tsung-Jung; Kovar, Christie; Chiang, Theodore; Mullai Murugan; William J Salerno; Donna M Muzny; Richard A Gibbs (ACMG Annual Clinical Genetics Meeting 2017, 2017)
High throughput clinical analysis of DNA capture panels demand automated processing to provide timely and cost-efficient reporting. We developed Neptune, an automated analytical platform to sign-out and deliver clinical reports, to address this need. Initial data intake occurs in a HIPAA compliant environment on DNAnexus, and samples are de-identified before moving into the CLIA lab. After analysis with the Human Genome Sequencing Center’s Mercury Pipeline, Neptune’s custom annotation software identifies variants of putative clinical relevance for manual review and possible addition to a “VIP” database of clinically relevant variation. This resource draws on both public resources (ClinVar, literature review) and internal data sets accessed via Anton, the HGSC’s Hadoop-based data store. The VIP database currently houses 20,872 SNPs and 3,946 indels, and contains a curated set of copy number variants (CNVs) annotated with internal frequency data. Using Neptune’s manual review interface, a clinical geneticist updates the VIP database accordingly. Once all variants have been categorized, Neptune extracts reportable, pathogenic variants using the VIP set, and Neptune outputs an automated clinical pre-report populated with prioritized variants (or a negative report if no relevant variants are found), descriptive text, and coverage statistics produced by the HGSC’s ExCiD software. The modular nature of Neptune allows it to be deployed locally, on the cloud or as a hybrid. Clinical reports integrate SNVs, Indels and CNVs. Early applications include reporting for the National Institutes of Health eMERGE network where more than 12,500 samples and a panel of 109 genes will be processed in less than three years, as well as the Right10k pharmacogenomics project in collaboration with the Mayo Clinic.

Germline mutations in ABL1 cause an autosomal dominant syndrome characterized by congenital heart defects and skeletal malformations. - Wang, Xia; Charng, Wu-Lin; Chen, Chun-An; Rosenfeld, Jill A; Al Shamsi, Aisha; Al-Gazali, Lihadh; McGuire, Marianne; Mew, Nicholas Ah; Arnold, Georgianne L; Qu, Chunjing; Ding, Yan; Donna M Muzny; et al. (Nat Genet, 2017)
ABL1 is a proto-oncogene well known as part of the fusion gene BCR-ABL1 in the Philadelphia chromosome of leukemia cancer cells. Inherited germline ABL1 changes have not been associated with genetic disorders. Here we report ABL1 germline variants cosegregating with an autosomal dominant disorder characterized by congenital heart disease, skeletal abnormalities, and failure to thrive. The variant c.734A>G (p.Tyr245Cys) was found to occur de novo or cosegregate with disease in five individuals (families 1-3). Additionally, a de novo c.1066G>A (p.Ala356Thr) variant was identified in a sixth individual (family 4). We overexpressed the mutant constructs in HEK 293T cells and observed increased tyrosine phosphorylation, suggesting increased ABL1 kinase activities associated with both the p.Tyr245Cys and p.Ala356Thr substitutions. Our clinical and experimental findings, together with previously reported teratogenic effects of selective BCR-ABL inhibitors in humans and developmental defects in Abl1 knockout mice, suggest that ABL1 has an important role during organismal development.
Keywords: Abnormalities, Multiple; Animals; Bone Diseases, Developmental; Cell Line; Chromosome Disorders; Craniofacial Abnormalities; Feeding and Eating Disorders; Female; Fusion Proteins, bcr-abl; Germ-Line Mutation; Heart Defects, Congenital; HEK293 Cells; Humans; Leukemia, Myelogenous, Chronic, BCR-ABL Positive; Limb Deformities, Congenital; Male; Mice; Mice, Knockout; Philadelphia Chromosome; Phosphorylation; Proto-Oncogene Mas; Signal Transduction

The gut mycobiome of the Human Microbiome Project healthy cohort. - Nash, Andrea K; Auchtung, Thomas A; Wong, Matthew C; Smith, Daniel P; Gesell, Jonathan R; Ross, Matthew C; Stewart, Christopher J; Ginger A Metcalf; Donna M Muzny; Richard A Gibbs; Ajami, Nadim J; Petrosino, Joseph F (Microbiome, 2017)
BACKGROUND: Most studies describing the human gut microbiome in healthy and diseased states have emphasized the bacterial component, but the fungal microbiome (i.e., the mycobiome) is beginning to gain recognition as a fundamental part of our microbiome. To date, human gut mycobiome studies have primarily been disease centric or in small cohorts of healthy individuals. To contribute to existing knowledge of the human mycobiome, we investigated the gut mycobiome of the Human Microbiome Project (HMP) cohort by sequencing the Internal Transcribed Spacer 2 (ITS2) region as well as the 18S rRNA gene. RESULTS: Three hundred seventeen HMP stool samples were analyzed by ITS2 sequencing. Fecal fungal diversity was significantly lower in comparison to bacterial diversity. Yeast dominated the samples, comprising eight of the top 15 most abundant genera. Specifically, fungal communities were characterized by a high prevalence of Saccharomyces, Malassezia, and Candida, with S. cerevisiae, M. restricta, and C. albicans operational taxonomic units (OTUs) present in 96.8, 88.3, and 80.8% of samples, respectively. There was a high degree of inter- and intra-volunteer variability in fungal communities. However, S. cerevisiae, M. restricta, and C. albicans OTUs were found in 92.2, 78.3, and 63.6% of volunteers, respectively, in all samples donated over an approximately 1-year period. Metagenomic and 18S rRNA gene sequencing data agreed with ITS2 results; however, ITS2 sequencing provided greater resolution of the relatively low abundance mycobiome constituents. CONCLUSIONS: Compared to bacterial communities, the human gut mycobiome is low in diversity and dominated by yeast including Saccharomyces, Malassezia, and Candida. Both inter- and intra-volunteer variability in the HMP cohort were high, revealing that unlike bacterial communities, an individual's mycobiome is no more similar to itself over time than to another person's. Nonetheless, several fungal species persisted across a majority of samples, evidence that a core gut mycobiome may exist. ITS2 sequencing data provided greater resolution of the mycobiome membership compared to metagenomic and 18S rRNA gene sequencing data, suggesting that it is a more sensitive method for studying the mycobiome of stool samples.
Keywords: Candida; Cohort Studies; DNA, Ribosomal Spacer; Feces; Fungi; Gastrointestinal Microbiome; Genetic Variation; Healthy Volunteers; High-Throughput Nucleotide Sequencing; Humans; Malassezia; Metagenomics; Microbiota; Mycobiome; RNA, Ribosomal, 18S; Saccharomyces; Sequence Analysis, DNA

Homozygous and hemizygous CNV detection from exome sequencing data in a Mendelian disease cohort. - Gambin, Tomasz; Akdemir, Zeynep C; Bo Yuan; Gu, Shen; Chiang, Theodore; Carvalho, Claudia M B; Shaw, Chad; Jhangiani, Shalini; Boone, Philip M; Eldomery, Mohammad K; Karaca, Ender; Bayram, Yavuz; et al. (Nucleic Acids Res, 2017)
We developed an algorithm, HMZDelFinder, that uses whole exome sequencing (WES) data to identify rare and intragenic homozygous and hemizygous (HMZ) deletions that may represent complete loss-of-function of the indicated gene. HMZDelFinder was applied to 4866 samples in the Baylor-Hopkins Center for Mendelian Genomics (BHCMG) cohort and detected 773 HMZ deletion calls (567 homozygous or 206 hemizygous) with an estimated sensitivity of 86.5% (82% for single-exonic and 88% for multi-exonic calls) and precision of 78% (53% single-exonic and 96% for multi-exonic calls). Out of 773 HMZDelFinder-detected deletion calls, 82 were subjected to array comparative genomic hybridization (aCGH) and/or breakpoint PCR and 64 were confirmed. These include 18 single-exon deletions out of which 8 were exclusively detected by HMZDelFinder and not by any of seven other CNV detection tools examined. Further investigation of the 64 validated deletion calls revealed at least 15 pathogenic HMZ deletions. Of those, 7 accounted for 17-50% of pathogenic CNVs in different disease cohorts where 7.1-11% of the molecular diagnosis solved rate was attributed to CNVs. In summary, we present an algorithm to detect rare, intragenic, single-exon deletion CNVs using WES data; this tool can be useful for disease gene discovery efforts and clinical WES analyses.
Keywords: Algorithms; Alternative Splicing; Cohort Studies; Computational Biology; Consanguinity; Datasets as Topic; DNA Copy Number Variations; Exome; Genetic Diseases, Inborn; Hemizygote; High-Throughput Nucleotide Sequencing; Homozygote; Humans; Inheritance Patterns; Models, Genetic; Pedigree; Reproducibility of Results; Sequence Deletion; Workflow

The house spider genome reveals an ancient whole-genome duplication during arachnid evolution. - Schwager, Evelyn E; Sharma, Prashant P; Clarke, Thomas; Leite, Daniel J; Wierschin, Torsten; Pechmann, Matthias; Akiyama-Oda, Yasuko; Esposito, Lauren; Bechsgaard, Jesper; Bilde, Trine; Buffry, Alexandra D; Chao, Hsu; et al. (BMC Biol, 2017)
BACKGROUND: The duplication of genes can occur through various mechanisms and is thought to make a major contribution to the evolutionary diversification of organisms. There is increasing evidence for a large-scale duplication of genes in some chelicerate lineages including two rounds of whole genome duplication (WGD) in horseshoe crabs. To investigate this further, we sequenced and analyzed the genome of the common house spider Parasteatoda tepidariorum. RESULTS: We found pervasive duplication of both coding and non-coding genes in this spider, including two clusters of Hox genes. Analysis of synteny conservation across the P. tepidariorum genome suggests that there has been an ancient WGD in spiders. Comparison with the genomes of other chelicerates, including that of the newly sequenced bark scorpion Centruroides sculpturatus, suggests that this event occurred in the common ancestor of spiders and scorpions, and is probably independent of the WGDs in horseshoe crabs. Furthermore, characterization of the sequence and expression of the Hox paralogs in P. tepidariorum suggests that many have been subject to neo-functionalization and/or sub-functionalization since their duplication. CONCLUSIONS: Our results reveal that spiders and scorpions are likely the descendants of a polyploid ancestor that lived more than 450 MYA. Given the extensive morphological diversity and ecological adaptations found among these animals, rivaling those of vertebrates, our study of the ancient WGD event in Arachnopulmonata provides a new comparative platform to explore common and divergent evolutionary outcomes of polyploidization events across eukaryotes.
Keywords: Animals; Evolution, Molecular; Female; Gene Duplication; Genome; Male; Spiders; Synteny

Hybrid de novo genome assembly and centromere characterization of the gray mouse lemur (Microcebus murinus). - Larsen, Peter A; R. Alan Harris; Liu, Yue; Murali, Shwetha C; Campbell, C Ryan; Brown, Adam D; Sullivan, Beth A; Shelton, Jennifer; Brown, Susan J; Raveendran, Muthuswamy; Dudchenko, Olga; Machol, Ido; et al. (BMC Biol, 2017)
BACKGROUND: The de novo assembly of repeat-rich mammalian genomes using only high-throughput short read sequencing data typically results in highly fragmented genome assemblies that limit downstream applications. Here, we present an iterative approach to hybrid de novo genome assembly that incorporates datasets stemming from multiple genomic technologies and methods. We used this approach to improve the gray mouse lemur (Microcebus murinus) genome from early draft status to a near chromosome-scale assembly. METHODS: We used a combination of advanced genomic technologies to iteratively resolve conflicts and super-scaffold the M. murinus genome. RESULTS: We improved the M. murinus genome assembly to a scaffold N50 of 93.32 Mb. Whole genome alignments between our primary super-scaffolds and 23 human chromosomes revealed patterns that are congruent with historical comparative cytogenetic data, thus demonstrating the accuracy of our de novo scaffolding approach and allowing assignment of scaffolds to M. murinus chromosomes. Moreover, we utilized our independent datasets to discover and characterize sequences associated with centromeres across the mouse lemur genome. Quality assessment of the final assembly found 96% of mouse lemur canonical transcripts nearly complete, comparable to other published high-quality reference genome assemblies. CONCLUSIONS: We describe a new assembly of the gray mouse lemur (Microcebus murinus) genome with chromosome-scale scaffolds produced using a hybrid bioinformatic and sequencing approach. The approach is cost effective and produces superior results based on metrics of contiguity and completeness. Our results show that emerging genomic technologies can be used in combination to characterize centromeres of non-model species and to produce accurate de novo chromosome-scale genome assemblies of complex mammalian genomes.
Keywords: Animals; Centromere; Cheirogaleidae; Computational Biology; Female; Genome; High-Throughput Nucleotide Sequencing; Sequence Analysis, DNA

Improved full-length killer cell immunoglobulin-like receptor transcript discovery in Mauritian cynomolgus macaques. - Prall, Trent M; Graham, Michael E; Karl, Julie A; Wiseman, Roger W; Ericsen, Adam J; Raveendran, Muthuswamy; R. Alan Harris; Donna M Muzny; Richard A Gibbs; Jeffrey Rogers; O'Connor, David H (Immunogenetics, 2017)
Killer cell immunoglobulin-like receptors (KIRs) modulate disease progression of pathogens including HIV, malaria, and hepatitis C. Cynomolgus and rhesus macaques are widely used as nonhuman primate models to study human pathogens, and so, considerable effort has been put into characterizing their KIR genetics. However, previous studies have relied on cDNA cloning and Sanger sequencing that lack the throughput of current sequencing platforms. In this study, we present a high throughput, full-length allele discovery method utilizing Pacific Biosciences circular consensus sequencing (CCS). We also describe a new approach to Macaque Exome Sequencing (MES) and the development of the Rhexome1.0, an adapted target capture reagent that includes macaque-specific capture probe sets. By using sequence reads generated by whole genome sequencing (WGS) and MES to inform primer design, we were able to increase the sensitivity of KIR allele discovery. We demonstrate this increased sensitivity by defining nine novel alleles within a cohort of Mauritian cynomolgus macaques (MCM), a geographically isolated population with restricted KIR genetics that was thought to be completely characterized. Finally, we describe an approach to genotyping KIRs directly from sequence reads generated using WGS/MES reads. The findings presented here expand our understanding of KIR genetics in MCM by associating new genes with all eight KIR haplotypes and demonstrating the existence of at least one KIR3DS gene associated with every haplotype.
Keywords: Animals; Exome; Gene Frequency; High-Throughput Nucleotide Sequencing; Macaca fascicularis; Receptors, KIR; Sequence Analysis, DNA

Lessons learned from additional research analyses of unsolved clinical exome cases. - Eldomery, Mohammad K; Coban-Akdemir, Zeynep; Harel, Tamar; Rosenfeld, Jill A; Gambin, Tomasz; Stray-Pedersen, Asbjørg; Küry, Sébastien; Mercier, Sandra; Lessel, Davor; Denecke, Jonas; Wiszniewski, Wojciech; Penney, Samantha; et al. (Genome Med, 2017)
BACKGROUND: Given the rarity of most single-gene Mendelian disorders, concerted efforts of data exchange between clinical and scientific communities are critical to optimize molecular diagnosis and novel disease gene discovery. METHODS: We designed and implemented protocols for the study of cases for which a plausible molecular diagnosis was not achieved in a clinical genomics diagnostic laboratory (i.e. unsolved clinical exomes). Such cases were recruited to a research laboratory for further analyses, in order to potentially: (1) accelerate novel disease gene discovery; (2) increase the molecular diagnostic yield of whole exome sequencing (WES); and (3) gain insight into the genetic mechanisms of disease. Pilot project data included 74 families, consisting mostly of parent-offspring trios. Analyses performed on a research basis employed both WES from additional family members and complementary bioinformatics approaches and protocols. RESULTS: Analysis of all possible modes of Mendelian inheritance, focusing on both single nucleotide variants (SNV) and copy number variant (CNV) alleles, yielded a likely contributory variant in 36% (27/74) of cases. If one includes candidate genes with variants identified within a single family, a potential contributory variant was identified in a total of ~51% (38/74) of cases enrolled in this pilot study. The molecular diagnosis was achieved in 30/63 trios (47.6%). Besides this, the analysis workflow yielded evidence for pathogenic variants in disease-associated genes in 4/6 singleton cases (66.6%), 1/1 multiplex family involving three affected siblings, and 3/4 (75%) quartet families. Both the analytical pipeline and the collaborative efforts between the diagnostic and research laboratories provided insights that allowed recent disease gene discoveries (PURA, TANGO2, EMC1, GNB5, ATAD3A, and MIPEP) and increased the number of novel genes, defined in this study as genes identified in more than one family (DHX30 and EBF3). CONCLUSION: An efficient genomics pipeline in which clinical sequencing in a diagnostic laboratory is followed by the detailed reanalysis of unsolved cases in a research environment, supplemented with WES data from additional family members, and subject to adjuvant bioinformatics analyses including relaxed variant filtering parameters in informatics pipelines, can enhance the molecular diagnostic yield and provide mechanistic insights into Mendelian disorders. Implementing these approaches requires collaborative clinical molecular diagnostic and research efforts.
Keywords: Adenosine Triphosphatases; ATPases Associated with Diverse Cellular Activities; Computational Biology; DNA Copy Number Variations; DNA-Binding Proteins; Exome; Female; Genetic Diseases, Inborn; Genomics; GTP-Binding Protein beta Subunits; Humans; Male; Membrane Proteins; Metalloendopeptidases; Mitochondrial Proteins; Pilot Projects; Polymorphism, Single Nucleotide; Sequence Analysis, DNA; Transcription Factors

Loss of Nardilysin, a Mitochondrial Co-chaperone for α-Ketoglutarate Dehydrogenase, Promotes mTORC1 Activation and Neurodegeneration. - Yoon, Wan Hee; Sandoval, Hector; Nagarkar-Jaiswal, Sonal; Jaiswal, Manish; Yamamoto, Shinya; Haelterman, Nele A; Putluri, Nagireddy; Putluri, Vasanta; Sreekumar, Arun; Tos, Tulay; Aksoy, Ayse; Donti, Taraka; et al. (Neuron, 2017)
We previously identified mutations in Nardilysin (dNrd1) in a forward genetic screen designed to isolate genes whose loss causes neurodegeneration in Drosophila photoreceptor neurons. Here we show that NRD1 is localized to mitochondria, where it recruits mitochondrial chaperones and assists in the folding of α-ketoglutarate dehydrogenase (OGDH), a rate-limiting enzyme in the Krebs cycle. Loss of Nrd1 or Ogdh leads to an increase in α-ketoglutarate, a substrate for OGDH, which in turn leads to mTORC1 activation and a subsequent reduction in autophagy. Inhibition of mTOR activity by rapamycin or partially restoring autophagy delays neurodegeneration in dNrd1 mutant flies. In summary, this study reveals a novel role for NRD1 as a mitochondrial co-chaperone for OGDH and provides a mechanistic link between mitochondrial metabolic dysfunction, mTORC1 signaling, and impaired autophagy in neurodegeneration.
Keywords: Animals; Autophagy; Drosophila; Drosophila melanogaster; Drosophila Proteins; Ketoglutarate Dehydrogenase Complex; Ketoglutaric Acids; Lysine; Mechanistic Target of Rapamycin Complex 1; Metalloendopeptidases; Mitochondria; Molecular Chaperones; Multiprotein Complexes; Neurodegenerative Diseases; TOR Serine-Threonine Kinases

Neonatal fractures as a presenting feature of LMOD3-associated congenital myopathy. - Abbott, Megan; Jain, Mahim; Pferdehirt, Rachel; Chen, Yuqing; Tran, Alyssa; Duz, Mehmet B; Seven, Mehmet; Richard A Gibbs; Donna M Muzny; Lee, Brendan; Marom, Ronit; Burrage, Lindsay C (Am J Med Genet A, 2017)
Nemaline myopathy is a rare inherited disorder characterized by weakness, hypotonia, and depressed deep tendon reflexes. It is clinically and genetically heterogeneous, with the most severe phenotype presenting as perinatal akinesia, severe muscle weakness, feeding difficulties and respiratory failure, leading to early mortality. Pathogenic variants in 12 genes, encoding components of the sarcomere or factors related to myogenesis, have been reported in patients affected with the disorder. Here, we describe an early, lethal presentation of decreased fetal movements, hypotonia, muscle weakness, and neonatal respiratory failure requiring ventilator support in three siblings from a consanguineous family. All exhibited perinatal fractures, and thus, a skeletal dysplasia was considered as possibly contributing to the phenotype. However, whole exome sequencing revealed a homozygous, loss-of-function pathogenic variant in LMOD3, which has recently been associated with nemaline myopathy and, in a subset of patients, perinatal fractures. This case demonstrates the importance of considering congenital neuromuscular disorders in the differential diagnosis of perinatal fractures.
Keywords: Female; Fractures, Bone; Homozygote; Humans; Infant, Newborn; Male; Microfilament Proteins; Muscle Proteins; Mutation; Myopathies, Structural, Congenital; Pedigree

The next generation of population-based spinal muscular atrophy carrier screening: comprehensive pan-ethnic SMN1 copy-number and sequence variant analysis by massively parallel sequencing. - Feng, Yanming; Ge, Xiaoyan; Meng, Linyan; Scull, Jennifer; Li, Jianli; Tian, Xia; Zhang, Tao; Jin, Weihong; Cheng, Hanyin; Wang, Xia; Tokita, Mari; Liu, Pengfei; et al. (Genet Med, 2017)
PURPOSE: To investigate pan-ethnic SMN1 copy-number and sequence variation by hybridization-based target enrichment coupled with massively parallel sequencing or next-generation sequencing (NGS). METHODS: NGS reads aligned to SMN1 and SMN2 exon 7 were quantified to determine the total combined copy number of SMN1 and SMN2. The ratio of SMN1 to SMN2 was calculated based on a single-nucleotide difference that distinguishes the two genes. SMN1 copy-number results were compared between the NGS and quantitative polymerase chain reaction and/or multiplex ligation-dependent probe amplification. The NGS data set was also queried for the g.27134T>G single-nucleotide polymorphism (SNP) and other SMN1 sequence pathogenic variants. RESULTS: The sensitivity of the test to detect spinal muscular atrophy (SMA) carriers with one copy of SMN1 was 100% (95% confidence interval (CI): 95.9-100%; n = 90) and specificity was 99.6% (95% CI: 99.4-99.7%; n = 6,648). Detection of the g.27134T>G SNP by NGS was 100% concordant with an restriction fragment-length polymorphism method (n = 493). Ten single-nucleotide variants in SMN1 were detectable by NGS and confirmed by gene-specific amplicon-based sequencing. This comprehensive approach yielded SMA carrier detection rates of 90.3-95.0% in five ethnic groups studied. CONCLUSION: We have developed a novel, comprehensive SMN1 copy-number and sequence variant analysis method by NGS that demonstrated improved SMA carrier detection rates across the entire population examined.Genet Med advance online publication 19 January 2017.
Keywords: Gene Dosage; Genetic Carrier Screening; High-Throughput Nucleotide Sequencing; Humans; Muscular Atrophy, Spinal; Polymorphism, Single Nucleotide; Reproducibility of Results; Sensitivity and Specificity; Survival of Motor Neuron 1 Protein; Survival of Motor Neuron 2 Protein

An Organismal CNV Mutator Phenotype Restricted to Early Human Development. - Liu, Pengfei; Bo Yuan; Carvalho, Claudia M B; Wuster, Arthur; Walter, Klaudia; Zhang, Ling; Gambin, Tomasz; Chong, Zechen; Campbell, Ian M; Coban Akdemir, Zeynep; Gelowani, Violet; Writzl, Karin; et al. (Cell, 2017)
De novo copy number variants (dnCNVs) arising at multiple loci in a personal genome have usually been considered to reflect cancer somatic genomic instabilities. We describe a multiple dnCNV (MdnCNV) phenomenon in which individuals with genomic disorders carry five to ten constitutional dnCNVs. These CNVs originate from independent formation incidences, are predominantly tandem duplications or complex gains, exhibit breakpoint junction features reminiscent of replicative repair, and show increased de novo point mutations flanking the rearrangement junctions. The active CNV mutation shower appears to be restricted to a transient perizygotic period. We propose that a defect in the CNV formation process is responsible for the "CNV-mutator state," and this state is dampened after early embryogenesis. The constitutional MdnCNV phenomenon resembles chromosomal instability in various cancers. Investigations of this phenomenon may provide unique access to understanding genomic disorders, structural variant mutagenesis, human evolution, and cancer biology.
Keywords: Chromosome Aberrations; Chromosome Breakpoints; Chromosome Duplication; DNA Copy Number Variations; DNA Replication; Embryonic Development; Female; Gametogenesis; Genetic Diseases, Inborn; Genomic Instability; Humans; Male; Mutation

Practical Approaches for Whole-Genome Sequence Analysis of Heart- and Blood-Related Traits. - Morrison, Alanna C; Huang, Zhuoyi; Yu, Bing; Ginger A Metcalf; Liu, Xiaoming; Ballantyne, Christie; Coresh, Josef; Fuli Yu; Donna M Muzny; Feofanova, Elena; Rustagi, Navin; Richard A Gibbs; et al. (Am J Hum Genet, 2017)
Whole-genome sequencing (WGS) allows for a comprehensive view of the sequence of the human genome. We present and apply integrated methodologic steps for interrogating WGS data to characterize the genetic architecture of 10 heart- and blood-related traits in a sample of 1,860 African Americans. In order to evaluate the contribution of regulatory and non-protein coding regions of the genome, we conducted aggregate tests of rare variation across the entire genomic landscape using a sliding window, complemented by an annotation-based assessment of the genome using predefined regulatory elements and within the first intron of all genes. These tests were performed treating all variants equally as well as with individual variants weighted by a measure of predicted functional consequence. Significant findings were assessed in 1,705 individuals of European ancestry. After these steps, we identified and replicated components of the genomic landscape significantly associated with heart- and blood-related traits. For two traits, lipoprotein(a) levels and neutrophil count, aggregate tests of low-frequency and rare variation were significantly associated across multiple motifs. For a third trait, cardiac troponin T, investigation of regulatory domains identified a locus on chromosome 9. These practical approaches for WGS analysis led to the identification of informative genomic regions and also showed that defined non-coding regions, such as first introns of genes and regulatory domains, are associated with important risk factor phenotypes. This study illustrates the tractable nature of WGS data and outlines an approach for characterizing the genetic architecture of complex traits.
Keywords: Black or African American; C-Reactive Protein; Cholesterol, HDL; Cholesterol, LDL; Chromosomes, Human, Pair 9; Gene Frequency; Genome, Human; Genome-Wide Association Study; Genomics; Hemoglobins; Humans; Introns; Leukocyte Count; Lipoprotein(a); Magnesium; Natriuretic Peptide, Brain; Neutrophils; Peptide Fragments; Phosphorus; Platelet Count; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Troponin T; White People

Primary immunodeficiency diseases: Genomic approaches delineate heterogeneous Mendelian disorders. - Stray-Pedersen, Asbjørg; Sorte, Hanne Sørmo; Samarakoon, Pubudu; Gambin, Tomasz; Chinn, Ivan K; Coban Akdemir, Zeynep H; Erichsen, Hans Christian; Forbes, Lisa R; Gu, Shen; Bo Yuan; Jhangiani, Shalini N; Donna M Muzny; et al. (J Allergy Clin Immunol, 2017)
BACKGROUND: Primary immunodeficiency diseases (PIDDs) are clinically and genetically heterogeneous disorders thus far associated with mutations in more than 300 genes. The clinical phenotypes derived from distinct genotypes can overlap. Genetic etiology can be a prognostic indicator of disease severity and can influence treatment decisions. OBJECTIVE: We sought to investigate the ability of whole-exome screening methods to detect disease-causing variants in patients with PIDDs. METHODS: Patients with PIDDs from 278 families from 22 countries were investigated by using whole-exome sequencing. Computational copy number variant (CNV) prediction pipelines and an exome-tiling chromosomal microarray were also applied to identify intragenic CNVs. Analytic approaches initially focused on 475 known or candidate PIDD genes but were nonexclusive and further tailored based on clinical data, family history, and immunophenotyping. RESULTS: A likely molecular diagnosis was achieved in 110 (40%) unrelated probands. Clinical diagnosis was revised in about half (60/110) and management was directly altered in nearly a quarter (26/110) of families based on molecular findings. Twelve PIDD-causing CNVs were detected, including 7 smaller than 30 Kb that would not have been detected with conventional diagnostic CNV arrays. CONCLUSION: This high-throughput genomic approach enabled detection of disease-related variants in unexpected genes; permitted detection of low-grade constitutional, somatic, and revertant mosaicism; and provided evidence of a mutational burden in mixed PIDD immunophenotypes.
Keywords: Adolescent; Adult; Aged; Child; Child, Preschool; DNA Copy Number Variations; Female; Genomics; High-Throughput Nucleotide Sequencing; Humans; Immunologic Deficiency Syndromes; Infant; Male; Middle Aged; Young Adult

Resolution of Disease Phenotypes Resulting from Multilocus Genomic Variation. - Posey, Jennifer E; Harel, Tamar; Liu, Pengfei; Rosenfeld, Jill A; James, Regis A; Coban Akdemir, Zeynep H; Walkiewicz, Magdalena; Bi, Weimin; Xiao, Rui; Ding, Yan; Xia, Fan; Beaudet, Arthur L; et al. (N Engl J Med, 2017)
BACKGROUND: Whole-exome sequencing can provide insight into the relationship between observed clinical phenotypes and underlying genotypes. METHODS: We conducted a retrospective analysis of data from a series of 7374 consecutive unrelated patients who had been referred to a clinical diagnostic laboratory for whole-exome sequencing; our goal was to determine the frequency and clinical characteristics of patients for whom more than one molecular diagnosis was reported. The phenotypic similarity between molecularly diagnosed pairs of diseases was calculated with the use of terms from the Human Phenotype Ontology. RESULTS: A molecular diagnosis was rendered for 2076 of 7374 patients (28.2%); among these patients, 101 (4.9%) had diagnoses that involved two or more disease loci. We also analyzed parental samples, when available, and found that de novo variants accounted for 67.8% (61 of 90) of pathogenic variants in autosomal dominant disease genes and 51.7% (15 of 29) of pathogenic variants in X-linked disease genes; both variants were de novo in 44.7% (17 of 38) of patients with two monoallelic variants. Causal copy-number variants were found in 12 patients (11.9%) with multiple diagnoses. Phenotypic similarity scores were significantly lower among patients in whom the phenotype resulted from two distinct mendelian disorders that affected different organ systems (50 patients) than among patients with disorders that had overlapping phenotypic features (30 patients) (median score, 0.21 vs. 0.36; P=1.77×10). CONCLUSIONS: In our study, we found multiple molecular diagnoses in 4.9% of cases in which whole-exome sequencing was informative. Our results show that structured clinical ontologies can be used to determine the degree of overlap between two mendelian diseases in the same patient; the diseases can be distinct or overlapping. Distinct disease phenotypes affect different organ systems, whereas overlapping disease phenotypes are more likely to be caused by two genes encoding proteins that interact within the same pathway. (Funded by the National Institutes of Health and the Ting Tsung and Wei Fong Chao Foundation.).
Keywords: Exome; Genetic Diseases, Inborn; Genetic Variation; Genotyping Techniques; High-Throughput Nucleotide Sequencing; Humans; Phenotype; Retrospective Studies; Sequence Analysis, DNA

REST Final-Exon-Truncating Mutations Cause Hereditary Gingival Fibromatosis. - Bayram, Yavuz; White, Janson J; Elcioglu, Nursel; Cho, Megan T; Zadeh, Neda; Gedikbasi, Asuman; Palanduz, Sukru; Ozturk, Sukru; Cefle, Kivanc; Kasapcopur, Ozgur; Coban Akdemir, Zeynep; Pehlivan, Davut; et al. (Am J Hum Genet, 2017)
Hereditary gingival fibromatosis (HGF) is the most common genetic form of gingival fibromatosis that develops as a slowly progressive, benign, localized or generalized enlargement of keratinized gingiva. HGF is a genetically heterogeneous disorder and can be transmitted either as an autosomal-dominant or autosomal-recessive trait or appear sporadically. To date, four loci (2p22.1, 2p23.3-p22.3, 5q13-q22, and 11p15) have been mapped to autosomes and one gene (SOS1) has been associated with the HGF trait observed to segregate in a dominant inheritance pattern. Here we report 11 individuals with HGF from three unrelated families. Whole-exome sequencing (WES) revealed three different truncating mutations including two frameshifts and one nonsense variant in RE1-silencing transcription factor (REST) in the probands from all families and further genetic and genomic analyses confirmed the WES-identified findings. REST is a transcriptional repressor that is expressed throughout the body; it has different roles in different cellular contexts, such as oncogenic and tumor-suppressor functions and hematopoietic and cardiac differentiation. Here we show the consequences of germline final-exon-truncating mutations in REST for organismal development and the association with the HGF phenotype.
Keywords: Adolescent; Base Sequence; Chromosome Segregation; Exons; Family; Female; Fibromatosis, Gingival; Genetic Predisposition to Disease; Humans; Male; Middle Aged; Mutation; Pedigree; Repressor Proteins

SVachra: a tool to identify genomic structural variation in mate pair sequencing data containing inward and outward facing reads. - Hampton, Oliver A; English, Adam C; Wang, Mark; Salerno, William J; Liu, Yue; Donna M Muzny; Yi Han; Wheeler, David A; Worley, Kim C; Lupski, James R; Richard A Gibbs (BMC Genomics, 2017)
BACKGROUND: Characterization of genomic structural variation (SV) is essential to expanding the research and clinical applications of genome sequencing. Reliance upon short DNA fragment paired end sequencing has yielded a wealth of single nucleotide variants and internal sequencing read insertions-deletions, at the cost of limited SV detection. Multi-kilobase DNA fragment mate pair sequencing has supplemented the void in SV detection, but introduced new analytic challenges requiring SV detection tools specifically designed for mate pair sequencing data. Here, we introduce SVachra - Structural Variation Assessment of CHRomosomal Aberrations, a breakpoint calling program that identifies large insertions-deletions, inversions, inter- and intra-chromosomal translocations utilizing both inward and outward facing read types generated by mate pair sequencing. RESULTS: We demonstrate SVachra's utility by executing the program on large-insert (Illumina Nextera) mate pair sequencing data from the personal genome of a single subject (HS1011). An additional data set of long-read (Pacific BioSciences RSII) was also generated to validate SV calls from SVachra and other comparison SV calling programs. SVachra exhibited the highest validation rate and reported the widest distribution of SV types and size ranges when compared to other SV callers. CONCLUSIONS: SVachra is a highly specific breakpoint calling program that exhibits a more unbiased SV detection methodology than other callers.
Keywords: Genetic Variation; Genomics; Sequence Analysis, DNA

Unraveling genetic predisposition to familial or early onset gastric cancer using germline whole-exome sequencing. - Vogelaar, Ingrid P; van der Post, Rachel S; van Krieken, J Han Jm; Spruijt, Liesbeth; van Zelst-Stams, Wendy Ag; Kets, C Marleen; Lubinski, Jan; Jakubowska, Anna; Teodorczyk, Urszula; Aalfs, Cora M; van Hest, Liselotte P; Pinheiro, Hugo; et al. (Eur J Hum Genet, 2017)
Recognition of individuals with a genetic predisposition to gastric cancer (GC) enables preventive measures. However, the underlying cause of genetic susceptibility to gastric cancer remains largely unexplained. We performed germline whole-exome sequencing on leukocyte DNA of 54 patients from 53 families with genetically unexplained diffuse-type and intestinal-type GC to identify novel GC-predisposing candidate genes. As young age at diagnosis and familial clustering are hallmarks of genetic tumor susceptibility, we selected patients that were diagnosed below the age of 35, patients from families with two cases of GC at or below age 60 and patients from families with three GC cases at or below age 70. All included individuals were tested negative for germline CDH1 mutations before or during the study. Variants that were possibly deleterious according to in silico predictions were filtered using several independent approaches that were based on gene function and gene mutation burden in controls. Despite a rigorous search, no obvious candidate GC predisposition genes were identified. This negative result stresses the importance of future research studies in large, homogeneous cohorts.
Keywords: Adult; Aged; Antigens, CD; Cadherins; Early Detection of Cancer; Exome; Female; Genetic Predisposition to Disease; Genetic Testing; Germ-Line Mutation; Humans; Male; Middle Aged; Sequence Analysis, DNA; Stomach Neoplasms

Use of Exome Sequencing for Infants in Intensive Care Units: Ascertainment of Severe Single-Gene Disorders and Effect on Medical Management. - Meng, Linyan; Pammi, Mohan; Saronwala, Anirudh; Magoulas, Pilar; Ghazi, Andrew Ray; Vetrini, Francesco; Zhang, Jing; He, Weimin; Dharmadhikari, Avinash V; Qu, Chunjing; Ward, Patricia; Braxton, Alicia; et al. (JAMA Pediatr, 2017)
IMPORTANCE: While congenital malformations and genetic diseases are a leading cause of early infant death, to our knowledge, the contribution of single-gene disorders in this group is undetermined. OBJECTIVE: To determine the diagnostic yield and use of clinical exome sequencing in critically ill infants. DESIGN, SETTING, AND PARTICIPANTS: Clinical exome sequencing was performed for 278 unrelated infants within the first 100 days of life who were admitted to Texas Children's Hospital in Houston, Texas, during a 5-year period between December 2011 and January 2017. Exome sequencing types included proband exome, trio exome, and critical trio exome, a rapid genomic assay for seriously ill infants. MAIN OUTCOMES AND MEASURES: Indications for testing, diagnostic yield of clinical exome sequencing, turnaround time, molecular findings, patient age at diagnosis, and effect on medical management among a group of critically ill infants who were suspected to have genetic disorders. RESULTS: The mean (SEM) age for infants participating in the study was 28.5 (1.7) days; of these, the mean (SEM) age was 29.0 (2.2) days for infants undergoing proband exome sequencing, 31.5 (3.9) days for trio exome, and 22.7 (3.9) days for critical trio exome. Clinical indications for exome sequencing included a range of medical concerns. Overall, a molecular diagnosis was achieved in 102 infants (36.7%) by clinical exome sequencing, with relatively low yield for cardiovascular abnormalities. The diagnosis affected medical management for 53 infants (52.0%) and had a substantial effect on informed redirection of care, initiation of new subspecialist care, medication/dietary modifications, and furthering life-saving procedures in select patients. Critical trio exome sequencing revealed a molecular diagnosis in 32 of 63 infants (50.8%) at a mean (SEM) of 33.1 (5.6) days of life with a mean (SEM) turnaround time of 13.0 (0.4) days. Clinical care was altered by the diagnosis in 23 of 32 patients (71.9%). The diagnostic yield, patient age at diagnosis, and medical effect in the group that underwent critical trio exome sequencing were significantly different compared with the group who underwent regular exome testing. For deceased infants (n = 81), genetic disorders were molecularly diagnosed in 39 (48.1%) by exome sequencing, with implications for recurrence risk counseling. CONCLUSIONS AND RELEVANCE: Exome sequencing is a powerful tool for the diagnostic evaluation of critically ill infants with suspected monogenic disorders in the neonatal and pediatric intensive care units and its use has a notable effect on clinical decision making.
Keywords: Adult; Critical Care; Disease Management; Exome; Exome Sequencing; Genetic Counseling; Genetic Diseases, Inborn; Humans; Infant; Infant Care; Infant, Newborn; Intensive Care Units, Pediatric; Length of Stay; Retrospective Studies; Texas

Whole exome sequencing in 342 congenital cardiac left sided lesion cases reveals extensive genetic heterogeneity and complex inheritance patterns. - Li, Alexander H; Hanchard, Neil A; Furthner, Dieter; Fernbach, Susan; Azamian, Mahshid; Nicosia, Annarita; Rosenfeld, Jill; Donna M Muzny; D'Alessandro, Lisa C A; Morris, Shaine; Jhangiani, Shalini; Parekh, Dhaval R; et al. (Genome Med, 2017)
BACKGROUND: Left-sided lesions (LSLs) account for an important fraction of severe congenital cardiovascular malformations (CVMs). The genetic contributions to LSLs are complex, and the mutations that cause these malformations span several diverse biological signaling pathways: TGFB, NOTCH, SHH, and more. Here, we use whole exome sequence data generated in 342 LSL cases to identify likely damaging variants in putative candidate CVM genes. METHODS: Using a series of bioinformatics filters, we focused on genes harboring population-rare, putative loss-of-function (LOF), and predicted damaging variants in 1760 CVM candidate genes constructed a priori from the literature and model organism databases. Gene variants that were not observed in a comparably sequenced control dataset of 5492 samples without severe CVM were then subjected to targeted validation in cases and parents. Whole exome sequencing data from 4593 individuals referred for clinical sequencing were used to bolster evidence for the role of candidate genes in CVMs and LSLs. RESULTS: Our analyses revealed 28 candidate variants in 27 genes, including 17 genes not previously associated with a human CVM disorder, and revealed diverse patterns of inheritance among LOF carriers, including 9 confirmed de novo variants in both novel and newly described human CVM candidate genes (ACVR1, JARID2, NR2F2, PLRG1, SMURF1) as well as established syndromic CVM genes (KMT2D, NF1, TBX20, ZEB2). We also identified two genes (DNAH5, OFD1) with evidence of recessive and hemizygous inheritance patterns, respectively. Within our clinical cohort, we also observed heterozygous LOF variants in JARID2 and SMAD1 in individuals with cardiac phenotypes, and collectively, carriers of LOF variants in our candidate genes had a four times higher odds of having CVM (odds ratio = 4.0, 95% confidence interval 2.5-6.5). CONCLUSIONS: Our analytical strategy highlights the utility of bioinformatic resources, including human disease records and model organism phenotyping, in novel gene discovery for rare human disease. The results underscore the extensive genetic heterogeneity underlying non-syndromic LSLs, and posit potential novel candidate genes and complex modes of inheritance in this important group of birth defects.
Keywords: Exome Sequencing; Female; Genetic Heterogeneity; Heart Defects, Congenital; Humans; Inheritance Patterns; Male

Whole-exome sequencing in the molecular diagnosis of individuals with congenital anomalies of the kidney and urinary tract and identification of a new causative gene. - Bekheirnia, Mir Reza; Bekheirnia, Nasim; Bainbridge, Matthew N; Gu, Shen; Coban Akdemir, Zeynep Hande; Gambin, Tomek; Janzen, Nicolette K; Jhangiani, Shalini N; Donna M Muzny; Michael, Mini; Brewer, Eileen D; Elenberg, Ewa; et al. (Genet Med, 2017)
PURPOSE: To investigate the utility of whole-exome sequencing (WES) to define a molecular diagnosis for patients clinically diagnosed with congenital anomalies of kidney and urinary tract (CAKUT). METHODS: WES was performed in 62 families with CAKUT. WES data were analyzed for single-nucleotide variants (SNVs) in 35 known CAKUT genes, putatively deleterious sequence changes in new candidate genes, and potentially disease-associated copy-number variants (CNVs). RESULTS: In approximately 5% of families, pathogenic SNVs were identified in PAX2, HNF1B, and EYA1. Observed phenotypes in these families expand the current understanding about the role of these genes in CAKUT. Four pathogenic CNVs were also identified using two CNV detection tools. In addition, we found one deleterious de novo SNV in FOXP1 among the 62 families with CAKUT. The clinical database of the Baylor Miraca Genetics laboratory was queried and seven additional unrelated individuals with novel de novo SNVs in FOXP1 were identified. Six of these eight individuals with FOXP1 SNVs have syndromic urinary tract defects, implicating this gene in urinary tract development. CONCLUSION: We conclude that WES can be used to identify molecular etiology (SNVs, CNVs) in a subset of individuals with CAKUT. WES can also help identify novel CAKUT genes.Genet Med 19 4, 412-420.
Keywords: Adolescent; Child; Child, Preschool; DNA Copy Number Variations; Exome Sequencing; Female; Forkhead Transcription Factors; Genetic Predisposition to Disease; Hepatocyte Nuclear Factor 1-beta; Humans; Infant; Intracellular Signaling Peptides and Proteins; Male; Nuclear Proteins; PAX2 Transcription Factor; Pedigree; Polymorphism, Single Nucleotide; Protein Tyrosine Phosphatases; Repressor Proteins; Urogenital Abnormalities; Vesico-Ureteral Reflux; Young Adult

Whole-genome sequencing study of serum peptide levels: the Atherosclerosis Risk in Communities study. - de Vries, Paul S; Yu, Bing; Feofanova, Elena V; Ginger A Metcalf; Brown, Michael R; Zeighami, Atefeh L; Liu, Xiaoming; Donna M Muzny; Richard A Gibbs; Eric Boerwinkle; Morrison, Alanna C (Hum Mol Genet, 2017)
Oligopeptides are important markers of protein metabolism, as they are cleaved from larger polypeptides and proteins. Genetic association studies may help elucidate their origin and function. In 1,552 European Americans and 1,872 African Americans of the Atherosclerosis Risk in Communities study, we performed whole-genome and whole-exome sequencing and measured serum levels of 25 peptides. Common variants (minor allele frequency > 5%) were analysed individually. We grouped low-frequency variants (minor allele frequency ≤ 5%) by a genome-wide sliding window using region-based aggregate tests. Furthermore, low-frequency regulatory variants were grouped by gene, as were functional coding variants. All analyses were performed separately in each ancestry group and then meta-analysed. We identified 22 common variant associations with peptide levels (P-value < 4.2 × 10-10), including 16 novel gene-peptide pairs. Notably, variants in kinin-kallikrein genes KNG1, F12, KLKB1, and ACE were associated with several different peptides. Variants in KLKB1 and ACE were associated with a fragment of complement component 3f. Both common variants and low-frequency coding variants in CPN1 were associated with a fibrinogen cleavage peptide. Four sliding windows were significantly associated with peptide levels (P-value < 4.2 × 10-10). Our results highlight the importance of the kinin-kallikrein system in the regulation of serum peptide levels, strengthen the evidence for a broad link between the kinin-kallikrein and complement systems, and suggest a role of CPN1 in the conversion of fibrinogen to fibrin.
Keywords: Alleles; Atherosclerosis; Black or African American; Exome; Female; Gene Frequency; Genetic Association Studies; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Kallikreins; Male; Middle Aged; Peptides; Polymorphism, Single Nucleotide; Proteins; Risk Factors; White People; Whole Genome Sequencing

Ampullary Cancers Harbor ELF3 Tumor Suppressor Gene Mutations and Exhibit Frequent WNT Dysregulation. - Marie-Claude Gingras; Covington, Kyle R; Chang, David K; Donehower, Lawrence A; Gill, Anthony J; Ittmann, Michael M; Creighton, Chad J; Johns, Amber L; Shinbrot, Eve; Dewal, Ninad; Fisher, William E; Pilarsky, Christian; et al. (Cell Rep, 2016)
The ampulla of Vater is a complex cellular environment from which adenocarcinomas arise to form a group of histopathologically heterogenous tumors. To evaluate the molecular features of these tumors, 98 ampullary adenocarcinomas were evaluated and compared to 44 distal bile duct and 18 duodenal adenocarcinomas. Genomic analyses revealed mutations in the WNT signaling pathway among half of the patients and in all three adenocarcinomas irrespective of their origin and histological morphology. These tumors were characterized by a high frequency of inactivating mutations of ELF3, a high rate of microsatellite instability, and common focal deletions and amplifications, suggesting common attributes in the molecular pathogenesis are at play in these tumors. The high frequency of WNT pathway activating mutation, coupled with small-molecule inhibitors of β-catenin in clinical trials, suggests future treatment decisions for these patients may be guided by genomic analysis.
Keywords: Adenocarcinoma; Ampulla of Vater; Base Sequence; DNA-Binding Proteins; Duodenal Neoplasms; Genomic Instability; Humans; Microsatellite Repeats; Molecular Sequence Data; Mutation; Pancreatic Neoplasms; Proto-Oncogene Proteins c-ets; Transcription Factors; Wnt Signaling Pathway

Association of MTOR Mutations With Developmental Brain Disorders, Including Megalencephaly, Focal Cortical Dysplasia, and Pigmentary Mosaicism. - Mirzaa, Ghayda M; Campbell, Catarina D; Solovieff, Nadia; Goold, Carleton; Jansen, Laura A; Menon, Suchithra; Timms, Andrew E; Conti, Valerio; Biag, Jonathan D; Adams, Carissa; Boyle, Evan August; Collins, Sarah; et al. (JAMA Neurol, 2016)
IMPORTANCE: Focal cortical dysplasia (FCD), hemimegalencephaly, and megalencephaly constitute a spectrum of malformations of cortical development with shared neuropathologic features. These disorders are associated with significant childhood morbidity and mortality. OBJECTIVE: To identify the underlying molecular cause of FCD, hemimegalencephaly, and diffuse megalencephaly. DESIGN, SETTING, AND PARTICIPANTS: Patients with FCD, hemimegalencephaly, or megalencephaly (mean age, 11.7 years; range, 2-32 years) were recruited from Pediatric Hospital A. Meyer, the University of Hong Kong, and Seattle Children's Research Institute from June 2012 to June 2014. Whole-exome sequencing (WES) was performed on 8 children with FCD or hemimegalencephaly using standard-depth (50-60X) sequencing in peripheral samples (blood, saliva, or skin) from the affected child and their parents and deep (150-180X) sequencing in affected brain tissue. Targeted sequencing and WES were used to screen 93 children with molecularly unexplained diffuse or focal brain overgrowth. Histopathologic and functional assays of phosphatidylinositol 3-kinase-AKT (serine/threonine kinase)-mammalian target of rapamycin (mTOR) pathway activity in resected brain tissue and cultured neurons were performed to validate mutations. MAIN OUTCOMES AND MEASURES: Whole-exome sequencing and targeted sequencing identified variants associated with this spectrum of developmental brain disorders. RESULTS: Low-level mosaic mutations of MTOR were identified in brain tissue in 4 children with FCD type 2a with alternative allele fractions ranging from 0.012 to 0.086. Intermediate-level mosaic mutation of MTOR (p.Thr1977Ile) was also identified in 3 unrelated children with diffuse megalencephaly and pigmentary mosaicism in skin. Finally, a constitutional de novo mutation of MTOR (p.Glu1799Lys) was identified in 3 unrelated children with diffuse megalencephaly and intellectual disability. Molecular and functional analysis in 2 children with FCD2a from whom multiple affected brain tissue samples were available revealed a mutation gradient with an epicenter in the most epileptogenic area. When expressed in cultured neurons, all MTOR mutations identified here drive constitutive activation of mTOR complex 1 and enlarged neuronal size. CONCLUSIONS AND RELEVANCE: In this study, mutations of MTOR were associated with a spectrum of brain overgrowth phenotypes extending from FCD type 2a to diffuse megalencephaly, distinguished by different mutations and levels of mosaicism. These mutations may be sufficient to cause cellular hypertrophy in cultured neurons and may provide a demonstration of the pattern of mosaicism in brain and substantiate the link between mosaic mutations of MTOR and pigmentary mosaicism in skin.
Keywords: Adolescent; Adult; Amino Acids; Animals; Cells, Cultured; Cerebral Cortex; Child; Child, Preschool; Developmental Disabilities; Embryo, Mammalian; Female; Gene Expression Regulation; Genetic Association Studies; Humans; Intercellular Signaling Peptides and Proteins; Male; Malformations of Cortical Development; Mechanistic Target of Rapamycin Complex 1; Megalencephaly; Mosaicism; Multiprotein Complexes; Mutation; Nerve Tissue Proteins; Neurons; Rats; Retrospective Studies; TOR Serine-Threonine Kinases; Young Adult

Association of the IGF1 gene with fasting insulin levels. - Willems, Sara M; Cornes, Belinda K; Brody, Jennifer A; Morrison, Alanna C; Lipovich, Leonard; Dauriz, Marco; Chen, Yuning; Liu, Ching-Ti; Rybin, Denis V; Richard A Gibbs; Donna M Muzny; Pankow, James S; et al. (Eur J Hum Genet, 2016)
Insulin-like growth factor 1 (IGF-I) has been associated with insulin resistance. Genome-wide association studies (GWASs) of fasting insulin (FI) identified single-nucleotide variants (SNVs) near the IGF1 gene, raising two hypotheses: (1) these associations are mediated by IGF-I levels and (2) these noncoding variants either tag other functional variants in the region or are directly functional. In our study, analyses including 5141 individuals from population-based cohorts suggest that FI associations near IGF1 are not mediated by IGF-I. Analyses of targeted sequencing data in 3539 individuals reveal a large number of novel rare variants at the IGF1 locus and show a FI association with a subset of rare nonsynonymous variants (PSKAT=5.7 × 10(-4)). Conditional analyses suggest that this association is partly explained by the GWAS signal and the presence of a residual independent rare variant effect (Pconditional=0.019). Annotation using ENCODE data suggests that the GWAS variants may have a direct functional role in insulin biology. In conclusion, our study provides insight into variation present at the IGF1 locus and into the genetic architecture underlying FI levels, suggesting that FI associations of SNVs near IGF1 are not mediated by IGF-I and suggesting a role for both rare nonsynonymous and common functional variants in insulin biology.
Keywords: Adult; Aged; Fasting; Female; Humans; Insulin; Insulin-Like Growth Factor I; Male; Middle Aged; Polymorphism, Single Nucleotide

Bi-allelic Mutations in PKD1L1 Are Associated with Laterality Defects in Humans. - Vetrini, Francesco; D'Alessandro, Lisa C A; Akdemir, Zeynep C; Braxton, Alicia; Azamian, Mahshid S; Eldomery, Mohammad K; Miller, Kathryn; Kois, Chelsea; Sack, Virginia; Shur, Natasha; Rijhsinghani, Asha; Chandarana, Jignesh; et al. (Am J Hum Genet, 2016)
Disruption of the establishment of left-right (L-R) asymmetry leads to situs anomalies ranging from situs inversus totalis (SIT) to situs ambiguus (heterotaxy). The genetic causes of laterality defects in humans are highly heterogeneous. Via whole-exome sequencing (WES), we identified homozygous mutations in PKD1L1 from three affected individuals in two unrelated families. PKD1L1 encodes a polycystin-1-like protein and its loss of function is known to cause laterality defects in mouse and medaka fish models. Family 1 had one fetus and one deceased child with heterotaxy and complex congenital heart malformations. WES identified a homozygous splicing mutation, c.6473+2_6473+3delTG, which disrupts the invariant splice donor site in intron 42, in both affected individuals. In the second family, a homozygous c.5072G>C (p.Cys1691Ser) missense mutation was detected in an individual with SIT and congenital heart disease. The p.Cys1691Ser substitution affects a highly conserved cysteine residue and is predicted by molecular modeling to disrupt a disulfide bridge essential for the proper folding of the G protein-coupled receptor proteolytic site (GPS) motif. Damaging effects associated with substitutions of this conserved cysteine residue in the GPS motif have also been reported in other genes, namely GPR56, BAI3, and PKD1 in human and lat-1 in C. elegans, further supporting the likely pathogenicity of p.Cys1691Ser in PKD1L1. The identification of bi-allelic PKD1L1 mutations recapitulates previous findings regarding phenotypic consequences of loss of function of the orthologous genes in mice and medaka fish and further expands our understanding of genetic contributions to laterality defects in humans.
Keywords: Alleles; Amino Acid Motifs; Amino Acid Sequence; Animals; Caenorhabditis elegans; Cysteine; Exome; Female; Fetal Diseases; Functional Laterality; Heart Defects, Congenital; Heterotaxy Syndrome; Homozygote; Humans; Infant, Newborn; Introns; Male; Membrane Proteins; Mice; Middle Aged; Models, Molecular; Mutation; Mutation, Missense; Oryzias; Pedigree; RNA Splicing; Situs Inversus

Biallelic Mutations in UNC80 Cause Persistent Hypotonia, Encephalopathy, Growth Retardation, and Severe Intellectual Disability. - Stray-Pedersen, Asbjørg; Cobben, Jan-Maarten; Prescott, Trine E; Lee, Sora; Cang, Chunlei; Aranda, Kimberly; Ahmed, Sohnee; Alders, Marielle; Gerstner, Thorsten; Aslaksen, Kathinka; Tétreault, Martine; Qin, Wen; et al. (Am J Hum Genet, 2016)
Ion channel proteins are required for both the establishment of resting membrane potentials and the generation of action potentials. Hundreds of mutations in genes encoding voltage-gated ion channels responsible for action potential generation have been found to cause severe neurological diseases. In contrast, the roles of voltage-independent "leak" channels, important for the establishment and maintenance of resting membrane potentials upon which action potentials are generated, are not well established in human disease. UNC80 is a large component of the NALCN sodium-leak channel complex that regulates the basal excitability of the nervous system. Loss-of-function mutations of NALCN cause infantile hypotonia with psychomotor retardation and characteristic facies (IHPRF). We report four individuals from three unrelated families who have homozygous missense or compound heterozygous truncating mutations in UNC80 and persistent hypotonia, encephalopathy, growth failure, and severe intellectual disability. Compared to control cells, HEK293T cells transfected with an expression plasmid containing the c.5098C>T (p.Pro1700Ser) UNC80 mutation found in one individual showed markedly decreased NALCN channel currents. Our findings demonstrate the fundamental significance of UNC80 and basal ionic conductance to human health.
Keywords: Adolescent; Alleles; Brain Diseases; Carrier Proteins; Child; Child, Preschool; Female; Growth Disorders; Humans; Intellectual Disability; Membrane Proteins; Muscle Hypotonia; Mutation; Severity of Illness Index

Clinical Sequencing Exploratory Research Consortium: Accelerating Evidence-Based Practice of Genomic Medicine. - Green, Robert C; Goddard, Katrina A B; Jarvik, Gail P; Amendola, Laura M; Appelbaum, Paul S; Berg, Jonathan S; Bernhardt, Barbara A; Biesecker, Leslie G; Biswas, Sawona; Blout, Carrie L; Bowling, Kevin M; Brothers, Kyle B; et al. (Am J Hum Genet, 2016)
Despite rapid technical progress and demonstrable effectiveness for some types of diagnosis and therapy, much remains to be learned about clinical genome and exome sequencing (CGES) and its role within the practice of medicine. The Clinical Sequencing Exploratory Research (CSER) consortium includes 18 extramural research projects, one National Human Genome Research Institute (NHGRI) intramural project, and a coordinating center funded by the NHGRI and National Cancer Institute. The consortium is exploring analytic and clinical validity and utility, as well as the ethical, legal, and social implications of sequencing via multidisciplinary approaches; it has thus far recruited 5,577 participants across a spectrum of symptomatic and healthy children and adults by utilizing both germline and cancer sequencing. The CSER consortium is analyzing data and creating publically available procedures and tools related to participant preferences and consent, variant classification, disclosure and management of primary and secondary findings, health outcomes, and integration with electronic health records. Future research directions will refine measures of clinical utility of CGES in both germline and somatic testing, evaluate the use of CGES for screening in healthy individuals, explore the penetrance of pathogenic variants through extensive phenotyping, reduce discordances in public databases of genes and variants, examine social and ethnic disparities in the provision of genomics services, explore regulatory issues, and estimate the value and downstream costs of sequencing. The CSER consortium has established a shared community of research sites by using diverse approaches to pursue the evidence-based development of best practices in genomic medicine.
Keywords: Adult; Biomedical Research; Cardiovascular Diseases; Child; Clinical Trials as Topic; Evidence-Based Practice; Exome; Genome, Human; Genomics; High-Throughput Nucleotide Sequencing; Humans; National Human Genome Research Institute (U.S.); Polymorphism, Single Nucleotide; Population Groups; Software; United States

Diagnostic Yield of Clinical Tumor and Germline Whole-Exome Sequencing for Children With Solid Tumors. - Parsons, D Williams; Roy, Angshumoy; Yang, Yaping; Wang, Tao; Scollon, Sarah; Bergstrom, Katie; Kerstein, Robin A; Gutierrez, Stephanie; Petersen, Andrea K; Bavle, Abhishek; Lin, Frank Y; López-Terrada, Dolores H; et al. (JAMA Oncol, 2016)
IMPORTANCE: Whole-exome sequencing (WES) has the potential to reveal tumor and germline mutations of clinical relevance, but the diagnostic yield for pediatric patients with solid tumors is unknown. OBJECTIVE: To characterize the diagnostic yield of combined tumor and germline WES for children with solid tumors. DESIGN: Unselected children with newly diagnosed and previously untreated central nervous system (CNS) and non-CNS solid tumors were prospectively enrolled in the BASIC3 study at a large academic children's hospital during a 23-month period from August 2012 through June 2014. Blood and tumor samples underwent WES in a certified clinical laboratory with genetic results categorized on the basis of perceived clinical relevance and entered in the electronic health record. MAIN OUTCOMES AND MEASURES: Clinical categorization of somatic mutations; frequencies of deleterious germline mutations related to patient phenotype and incidental medically-actionable mutations. RESULTS: Of the first 150 participants (80 boys and 70 girls, mean age, 7.4 years), tumor samples adequate for WES were available from 121 patients (81%). Somatic mutations of established clinical utility (category I) were reported in 4 (3%) of 121 patients, with mutations of potential utility (category II) detected in an additional 29 (24%) of 121 patients. CTNNB1 was the gene most frequently mutated, with recurrent mutations in KIT, TSC2, and MAPK pathway genes (BRAF, KRAS, and NRAS) also identified. Mutations in consensus cancer genes (category III) were found in an additional 24 (20%) of 121 tumors. Fewer than half of somatic mutations identified were in genes known to be recurrently mutated in the tumor type tested. Diagnostic germline findings related to patient phenotype were discovered in 15 (10%) of 150 cases: 13 pathogenic or likely pathogenic dominant mutations in adult and pediatric cancer susceptibility genes (including 2 each in TP53, VHL, and BRCA1), 1 recessive liver disorder with hepatocellular carcinoma (TJP2), and 1 renal diagnosis (CLCN5). Incidental findings were reported in 8 (5%) of 150 patients. Most patients harbored germline uncertain variants in cancer genes (98%), pharmacogenetic variants (89%), and recessive carrier mutations (85%). CONCLUSIONS AND RELEVANCE: Tumor and germline WES revealed mutations in a broad spectrum of genes previously implicated in both adult and pediatric cancers. Combined reporting of tumor and germline WES identified diagnostic and/or potentially actionable findings in nearly 40% of newly diagnosed pediatric patients with solid tumors.

DVL3 Alleles Resulting in a -1 Frameshift of the Last Exon Mediate Autosomal-Dominant Robinow Syndrome. - White, Janson J; Mazzeu, Juliana F; Hoischen, Alexander; Bayram, Yavuz; Withers, Marjorie; Gezdirici, Alper; Kimonis, Virginia; Steehouwer, Marloes; Jhangiani, Shalini N; Donna M Muzny; Richard A Gibbs; van Bon, Bregje W M; et al. (Am J Hum Genet, 2016)
Robinow syndrome is a rare congenital disorder characterized by mesomelic limb shortening, genital hypoplasia, and distinctive facial features. Recent reports have identified, in individuals with dominant Robinow syndrome, a specific type of variant characterized by being uniformly located in the penultimate exon of DVL1 and resulting in a -1 frameshift allele with a premature termination codon that escapes nonsense-mediated decay. Here, we studied a cohort of individuals who had been clinically diagnosed with Robinow syndrome but who had not received a molecular diagnosis from variant studies of DVL1, WNT5A, and ROR2. Because of the uniform location of frameshift variants in DVL1-mediated Robinow syndrome and the functional redundancy of DVL1, DVL2, and DVL3, we elected to pursue direct Sanger sequencing of the penultimate exon of DVL1 and its paralogs DVL2 and DVL3 to search for potential disease-associated variants. Remarkably, targeted sequencing identified five unrelated individuals harboring heterozygous, de novo frameshift variants in DVL3, including two splice acceptor mutations and three 1 bp deletions. Similar to the variants observed in DVL1-mediated Robinow syndrome, all variants in DVL3 result in a -1 frameshift, indicating that these highly specific alterations might be a common cause of dominant Robinow syndrome. Here, we review the current knowledge of these peculiar variant alleles in DVL1- and DVL3-mediated Robinow syndrome and further elucidate the phenotypic features present in subjects with DVL1 and DVL3 frameshift mutations.
Keywords: Adaptor Proteins, Signal Transducing; Alleles; Base Sequence; Codon, Nonsense; Craniofacial Abnormalities; Dishevelled Proteins; Dwarfism; Exons; Female; Frameshift Mutation; Genetic Variation; Humans; Limb Deformities, Congenital; Male; Molecular Sequence Data; Phosphoproteins; Proto-Oncogene Proteins; Receptor Tyrosine Kinase-like Orphan Receptors; Sequence Analysis, DNA; Sequence Deletion; Urogenital Abnormalities; Wnt Proteins; Wnt-5a Protein

Exome sequencing in mostly consanguineous Arab families with neurologic disease provides a high potential molecular diagnosis rate. - Charng, Wu-Lin; Karaca, Ender; Coban Akdemir, Zeynep; Gambin, Tomasz; Atik, Mehmed M; Gu, Shen; Posey, Jennifer E; Jhangiani, Shalini N; Donna M Muzny; Harshavardhan Doddapaneni; Jianhong Hu; Eric Boerwinkle; et al. (BMC Med Genomics, 2016)
BACKGROUND: Neurodevelopment is orchestrated by a wide range of genes, and the genetic causes of neurodevelopmental disorders are thus heterogeneous. We applied whole exome sequencing (WES) for molecular diagnosis and in silico analysis to identify novel disease gene candidates in a cohort from Saudi Arabia with primarily Mendelian neurologic diseases. METHODS: We performed WES in 31 mostly consanguineous Arab families and analyzed both single nucleotide and copy number variants (CNVs) from WES data. Interaction/expression network and pathway analyses, as well as paralog studies were utilized to investigate potential pathogenicity and disease association of novel candidate genes. Additional cases for candidate genes were identified through the clinical WES database at Baylor Miraca Genetics Laboratories and GeneMatcher. RESULTS: We found known pathogenic or novel variants in known disease genes with phenotypic expansion in 6 families, disease-associated CNVs in 2 families, and 12 novel disease gene candidates in 11 families, including KIF5B, GRM7, FOXP4, MLLT1, and KDM2B. Overall, a potential molecular diagnosis was provided by variants in known disease genes in 17 families (54.8 %) and by novel candidate disease genes in an additional 11 families, making the potential molecular diagnostic rate ~90 %. CONCLUSIONS: Molecular diagnostic rate from WES is improved by exome-predicted CNVs. Novel candidate disease gene discovery is facilitated by paralog studies and through the use of informatics tools and available databases to identify additional evidence for pathogenicity. TRIAL REGISTRATION: Not applicable.
Keywords: Arabs; Cohort Studies; Consanguinity; Data Mining; Databases, Genetic; DNA Copy Number Variations; Exome; Female; High-Throughput Nucleotide Sequencing; Humans; Male; Molecular Diagnostic Techniques; Nervous System Diseases; Pedigree; Phenotype; Polymorphism, Single Nucleotide; Sequence Analysis, DNA

Genome of the Asian longhorned beetle (Anoplophora glabripennis), a globally significant invasive species, reveals key functional and evolutionary innovations at the beetle-plant interface. - McKenna, Duane D; Scully, Erin D; Pauchet, Yannick; Hoover, Kelli; Kirsch, Roy; Geib, Scott M; Mitchell, Robert F; Waterhouse, Robert M; Ahn, Seung-Joon; Arsala, Deanna; Benoit, Joshua B; Blackmon, Heath; et al. (Genome Biol, 2016)
BACKGROUND: Relatively little is known about the genomic basis and evolution of wood-feeding in beetles. We undertook genome sequencing and annotation, gene expression assays, studies of plant cell wall degrading enzymes, and other functional and comparative studies of the Asian longhorned beetle, Anoplophora glabripennis, a globally significant invasive species capable of inflicting severe feeding damage on many important tree species. Complementary studies of genes encoding enzymes involved in digestion of woody plant tissues or detoxification of plant allelochemicals were undertaken with the genomes of 14 additional insects, including the newly sequenced emerald ash borer and bull-headed dung beetle. RESULTS: The Asian longhorned beetle genome encodes a uniquely diverse arsenal of enzymes that can degrade the main polysaccharide networks in plant cell walls, detoxify plant allelochemicals, and otherwise facilitate feeding on woody plants. It has the metabolic plasticity needed to feed on diverse plant species, contributing to its highly invasive nature. Large expansions of chemosensory genes involved in the reception of pheromones and plant kairomones are consistent with the complexity of chemical cues it uses to find host plants and mates. CONCLUSIONS: Amplification and functional divergence of genes associated with specialized feeding on plants, including genes originally obtained via horizontal gene transfer from fungi and bacteria, contributed to the addition, expansion, and enhancement of the metabolic repertoire of the Asian longhorned beetle, certain other phytophagous beetles, and to a lesser degree, other phytophagous insects. Our results thus begin to establish a genomic basis for the evolutionary success of beetles on plants.
Keywords: Animals; Coleoptera; Evolution, Molecular; Gene Transfer, Horizontal; Genome, Insect; Host-Parasite Interactions; Introduced Species; Larva; Sequence Analysis, DNA; Trees

Genomic Profiling of Pediatric Acute Myeloid Leukemia Reveals a Changing Mutational Landscape from Disease Diagnosis to Relapse. - Farrar, Jason E; Schuback, Heather L; Ries, Rhonda E; Wai, Daniel; Hampton, Oliver A; Treviño, Lisa R; Alonzo, Todd A; Guidry Auvil, Jaime M; Davidsen, Tanja M; Gesuwan, Patee; Hermida, Leandro; Donna M Muzny; et al. (Cancer Res, 2016)
The genomic and clinical information used to develop and implement therapeutic approaches for acute myelogenous leukemia (AML) originated primarily from adult patients and has been generalized to patients with pediatric AML. However, age-specific molecular alterations are becoming more evident and may signify the need to age-stratify treatment regimens. The NCI/COG TARGET-AML initiative used whole exome capture sequencing (WXS) to interrogate the genomic landscape of matched trios representing specimens collected upon diagnosis, remission, and relapse from 20 cases of de novo childhood AML. One hundred forty-five somatic variants at diagnosis (median 6 mutations/patient) and 149 variants at relapse (median 6.5 mutations) were identified and verified by orthogonal methodologies. Recurrent somatic variants [in (greater than or equal to) 2 patients] were identified for 10 genes (FLT3, NRAS, PTPN11, WT1, TET2, DHX15, DHX30, KIT, ETV6, KRAS), with variable persistence at relapse. The variant allele fraction (VAF), used to measure the prevalence of somatic mutations, varied widely at diagnosis. Mutations that persisted from diagnosis to relapse had a significantly higher diagnostic VAF compared with those that resolved at relapse (median VAF 0.43 vs. 0.24, P < 0.001). Further analysis revealed that 90% of the diagnostic variants with VAF >0.4 persisted to relapse compared with 28% with VAF <0.2 (P < 0.001). This study demonstrates significant variability in the mutational profile and clonal evolution of pediatric AML from diagnosis to relapse. Furthermore, mutations with high VAF at diagnosis, representing variants shared across a leukemic clonal structure, may constrain the genomic landscape at relapse and help to define key pathways for therapeutic targeting. Cancer Res; 76(8); 2197-205. ©2016 AACR.
Keywords: Adolescent; Child; Child, Preschool; DNA Copy Number Variations; Female; Gene Expression Profiling; Humans; Infant; Leukemia, Myeloid, Acute; Male; Mutation; Recurrence

Hutterite-type cataract maps to chromosome 6p21.32-p21.31, cosegregates with a homozygous mutation in LEMD2, and is associated with sudden cardiac death. - Boone, Philip M; Bo Yuan; Gu, Shen; Ma, Zhiwei; Gambin, Tomasz; Gonzaga-Jauregui, Claudia; Jain, Mahim; Murdock, Todd J; White, Janson J; Jhangiani, Shalini N; Kimberly Walker; Wang, Qiaoyan; et al. (Mol Genet Genomic Med, 2016)
BACKGROUND: Juvenile-onset cataracts are known among the Hutterites of North America. Despite being identified over 30 years ago, this autosomal recessive condition has not been mapped, and the disease gene is unknown. METHODS: We performed whole exome sequencing of three Hutterite-type cataract trios and follow-up genotyping and mapping in four extended kindreds. RESULTS: Trio exomes enabled genome-wide autozygosity mapping, which localized the disease gene to a 9.5-Mb region on chromosome 6p. This region contained two candidate variants, LEMD2 c.T38G and MUC21 c.665delC. Extended pedigrees recruited for variant genotyping revealed multiple additional relatives with juvenile-onset cataract, as well as six deceased relatives with both cataracts and sudden cardiac death. The candidate variants were genotyped in 84 family members, including 17 with cataracts; only the variant in LEMD2 cosegregated with cataracts (LOD = 9.62). SNP-based fine mapping within the 9.5 Mb linked region supported this finding by refining the cataract locus to a 0.5- to 2.9-Mb subregion (6p21.32-p21.31) containing LEMD2 but not MUC21. LEMD2 is expressed in mouse and human lenses and encodes a LEM domain-containing protein; the c.T38G missense mutation is predicted to mutate a highly conserved residue within this domain (p.Leu13Arg). CONCLUSION: We performed a genetic and genomic study of Hutterite-type cataract and found evidence for an association of this phenotype with sudden cardiac death. Using combined genetic and genomic approaches, we mapped cataracts to a small portion of chromosome 6 and propose that they result from a homozygous missense mutation in LEMD2.

Identification of a RAI1-associated disease network through integration of exome sequencing, transcriptomics, and 3D genomics. - Loviglio, Maria Nicla; Beck, Christine R; White, Janson J; Leleu, Marion; Harel, Tamar; Guex, Nicolas; Niknejad, Anne; Bi, Weimin; Chen, Edward S; Crespo, Isaac; Yan, Jiong; Charng, Wu-Lin; et al. (Genome Med, 2016)
BACKGROUND: Smith-Magenis syndrome (SMS) is a developmental disability/multiple congenital anomaly disorder resulting from haploinsufficiency of RAI1. It is characterized by distinctive facial features, brachydactyly, sleep disturbances, and stereotypic behaviors. METHODS: We investigated a cohort of 15 individuals with a clinical suspicion of SMS who showed neither deletion in the SMS critical region nor damaging variants in RAI1 using whole exome sequencing. A combination of network analysis (co-expression and biomedical text mining), transcriptomics, and circularized chromatin conformation capture (4C-seq) was applied to verify whether modified genes are part of the same disease network as known SMS-causing genes. RESULTS: Potentially deleterious variants were identified in nine of these individuals using whole-exome sequencing. Eight of these changes affect KMT2D, ZEB2, MAP2K2, GLDC, CASK, MECP2, KDM5C, and POGZ, known to be associated with Kabuki syndrome 1, Mowat-Wilson syndrome, cardiofaciocutaneous syndrome, glycine encephalopathy, mental retardation and microcephaly with pontine and cerebellar hypoplasia, X-linked mental retardation 13, X-linked mental retardation Claes-Jensen type, and White-Sutton syndrome, respectively. The ninth individual carries a de novo variant in JAKMIP1, a regulator of neuronal translation that was recently found deleted in a patient with autism spectrum disorder. Analyses of co-expression and biomedical text mining suggest that these pathologies and SMS are part of the same disease network. Further support for this hypothesis was obtained from transcriptome profiling that showed that the expression levels of both Zeb2 and Map2k2 are perturbed in Rai1 mice. As an orthogonal approach to potentially contributory disease gene variants, we used chromatin conformation capture to reveal chromatin contacts between RAI1 and the loci flanking ZEB2 and GLDC, as well as between RAI1 and human orthologs of the genes that show perturbed expression in our Rai1 mouse model. CONCLUSIONS: These holistic studies of RAI1 and its interactions allow insights into SMS and other disorders associated with intellectual disability and behavioral abnormalities. Our findings support a pan-genomic approach to the molecular diagnosis of a distinctive disorder.
Keywords: Animals; Embryo, Mammalian; Exome; Female; Gene Regulatory Networks; Genomics; Humans; Male; Mice; Mice, Inbred C57BL; Mice, Knockout; Mutation; Phenotype; Real-Time Polymerase Chain Reaction; Reverse Transcriptase Polymerase Chain Reaction; RNA, Messenger; Smith-Magenis Syndrome; Trans-Activators; Transcription Factors; Transcriptome

Identification of Intellectual Disability Genes in Female Patients with a Skewed X-Inactivation Pattern. - Fieremans, Nathalie; Van Esch, Hilde; Holvoet, Maureen; Van Goethem, Gert; Devriendt, Koenraad; Rosello, Monica; Mayo, Sonia; Martinez, Francisco; Jhangiani, Shalini; Donna M Muzny; Richard A Gibbs; Lupski, James R; et al. (Hum Mutat, 2016)
Intellectual disability (ID) is a heterogeneous disorder with an unknown molecular etiology in many cases. Previously, X-linked ID (XLID) studies focused on males because of the hemizygous state of their X chromosome. Carrier females are generally unaffected because of the presence of a second normal allele, or inactivation of the mutant X chromosome in most of their cells (skewing). However, in female ID patients, we hypothesized that the presence of skewing of X-inactivation would be an indicator for an X chromosomal ID cause. We analyzed the X-inactivation patterns of 288 females with ID, and found that 22 (7.6%) had extreme skewing (>90%), which is significantly higher than observed in the general population (3.6%; P = 0.029). Whole-exome sequencing of 19 females with extreme skewing revealed causal variants in six females in the XLID genes DDX3X, NHS, WDR45, MECP2, and SMC1A. Interestingly, variants in genes escaping X-inactivation presumably cause both XLID and skewing of X-inactivation in three of these patients. Moreover, variants likely accounting for skewing only were detected in MED12, HDAC8, and TAF9B. All tested candidate causative variants were de novo events. Hence, extreme skewing is a good indicator for the presence of X-linked variants in female patients.
Keywords: Carrier Proteins; Cell Cycle Proteins; Chromosomal Proteins, Non-Histone; DEAD-box RNA Helicases; Exome; Female; Genetic Variation; Humans; Intellectual Disability; Membrane Proteins; Methyl-CpG-Binding Protein 2; Nuclear Proteins; Sequence Analysis, DNA; X Chromosome Inactivation

Loss-of-function variants influence the human serum metabolome. - Yu, Bing; Li, Alexander H; Ginger A Metcalf; Donna M Muzny; Morrison, Alanna C; White, Simon; Mosley, Thomas H; Richard A Gibbs; Eric Boerwinkle (Sci Adv, 2016)
The metabolome is a collection of small molecules resulting from multiple cellular and biological processes that can act as biomarkers of disease, and African-Americans exhibit high levels of genetic diversity. Exome sequencing of a sample of deeply phenotyped African-Americans allowed us to analyze the effects of annotated loss-of-function (LoF) mutations on 308 serum metabolites measured by untargeted liquid and gas chromatography coupled with mass spectrometry. In an independent sample, we identified and replicated four genes harboring six LoF mutations that significantly affected five metabolites. These sites were related to a 19 to 45% difference in geometric mean metabolite levels, with an average effect size of 25%. We show that some of the affected metabolites are risk predictors or diagnostic biomarkers of disease and, using the principle of Mendelian randomization, are in the causal pathway of disease. For example, LoF mutations in SLCO1B1 elevate the levels of hexadecanedioate, a fatty acid significantly associated with increased blood pressure levels and risk of incident heart failure in both African-Americans and an independent sample of European-Americans. We show that SLCO1B1 LoF mutations significantly increase the risk of incident heart failure, thus implicating the metabolite in the causal pathway of disease. These results reveal new avenues into gene function and the understanding of disease etiology by integrating -omic technologies into a deeply phenotyped population study.
Keywords: Aged; Biomarkers; Black or African American; Exome; Female; Genetic Variation; Heart Failure; High-Throughput Nucleotide Sequencing; Humans; Hypertension; Liver-Specific Organic Anion Transporter 1; Male; Metabolome; Middle Aged; Mutation; Risk Factors; White People

MIPEP recessive variants cause a syndrome of left ventricular non-compaction, hypotonia, and infantile death. - Eldomery, Mohammad K; Akdemir, Zeynep C; Vögtle, F-Nora; Charng, Wu-Lin; Mulica, Patrycja; Rosenfeld, Jill A; Gambin, Tomasz; Gu, Shen; Burrage, Lindsay C; Al Shamsi, Aisha; Penney, Samantha; Jhangiani, Shalini N; et al. (Genome Med, 2016)
BACKGROUND: Mitochondrial presequence proteases perform fundamental functions as they process about 70 % of all mitochondrial preproteins that are encoded in the nucleus and imported posttranslationally. The mitochondrial intermediate presequence protease MIP/Oct1, which carries out precursor processing, has not yet been established to have a role in human disease. METHODS: Whole exome sequencing was performed on four unrelated probands with left ventricular non-compaction (LVNC), developmental delay (DD), seizures, and severe hypotonia. Proposed pathogenic variants were confirmed by Sanger sequencing or array comparative genomic hybridization. Functional analysis of the identified MIP variants was performed using the model organism Saccharomyces cerevisiae as the protein and its functions are highly conserved from yeast to human. RESULTS: Biallelic single nucleotide variants (SNVs) or copy number variants (CNVs) in MIPEP, which encodes MIP, were present in all four probands, three of whom had infantile/childhood death. Two patients had compound heterozygous SNVs (p.L582R/p.L71Q and p.E602*/p.L306F) and one patient from a consanguineous family had a homozygous SNV (p.K343E). The fourth patient, identified through the GeneMatcher tool, a part of the Matchmaker Exchange Project, was found to have inherited a paternal SNV (p.H512D) and a maternal CNV (1.4-Mb deletion of 13q12.12) that includes MIPEP. All amino acids affected in the patients' missense variants are highly conserved from yeast to human and therefore S. cerevisiae was employed for functional analysis (for p.L71Q, p.L306F, and p.K343E). The mutations p.L339F (human p.L306F) and p.K376E (human p.K343E) resulted in a severe decrease of Oct1 protease activity and accumulation of non-processed Oct1 substrates and consequently impaired viability under respiratory growth conditions. The p.L83Q (human p.L71Q) failed to localize to the mitochondria. CONCLUSIONS: Our findings reveal for the first time the role of the mitochondrial intermediate peptidase in human disease. Loss of MIP function results in a syndrome which consists of LVNC, DD, seizures, hypotonia, and cataracts. Our approach highlights the power of data exchange and the importance of an interrelationship between clinical and research efforts for disease gene discovery.
Keywords: Adult; Amino Acid Sequence; Female; Genes, Recessive; Heart Defects, Congenital; Humans; Infant; Infant, Newborn; Male; Metalloendopeptidases; Muscle Hypotonia; Pedigree; Phenotype; Sequence Homology, Amino Acid; Sudden Infant Death; Syndrome

Molecular diagnostic experience of whole-exome sequencing in adult patients. - Posey, Jennifer E; Rosenfeld, Jill A; James, Regis A; Bainbridge, Matthew; Niu, Zhiyv; Wang, Xia; Dhar, Shweta; Wiszniewski, Wojciech; Akdemir, Zeynep H C; Gambin, Tomasz; Xia, Fan; Person, Richard E; et al. (Genet Med, 2016)
PURPOSE: Whole-exome sequencing (WES) is increasingly used as a diagnostic tool in medicine, but prior reports focus on predominantly pediatric cohorts with neurologic or developmental disorders. We describe the diagnostic yield and characteristics of WES in adults. METHODS: We performed a retrospective analysis of consecutive WES reports for adults from a diagnostic laboratory. Phenotype composition was determined using Human Phenotype Ontology terms. RESULTS: Molecular diagnoses were reported for 17.5% (85/486) of adults, which is lower than that for a primarily pediatric population (25.2%; P = 0.0003); the diagnostic rate was higher (23.9%) for those 18-30 years of age compared to patients older than 30 years (10.4%; P = 0.0001). Dual Mendelian diagnoses contributed to 7% of diagnoses, revealing blended phenotypes. Diagnoses were more frequent among individuals with abnormalities of the nervous system, skeletal system, head/neck, and growth. Diagnostic rate was independent of family history information, and de novo mutations contributed to 61.4% of autosomal dominant diagnoses. CONCLUSION: Early WES experience in adults demonstrates molecular diagnoses in a substantial proportion of patients, informing clinical management, recurrence risk, and recommendations for relatives. A positive family history was not predictive, consistent with molecular diagnoses often revealed by de novo events, informing the Mendelian basis of genetic disease in adults.Genet Med 18 7, 678-685.
Keywords: Adult; Exome; Female; Genetic Diseases, Inborn; Genetic Predisposition to Disease; Genetic Testing; Genome, Human; High-Throughput Nucleotide Sequencing; Humans; Male; Pathology, Molecular

Monoallelic and Biallelic Variants in EMC1 Identified in Individuals with Global Developmental Delay, Hypotonia, Scoliosis, and Cerebellar Atrophy. - Harel, Tamar; Yesil, Gozde; Bayram, Yavuz; Coban-Akdemir, Zeynep; Charng, Wu-Lin; Karaca, Ender; Al Asmari, Ali; Eldomery, Mohammad K; Hunter, Jill V; Jhangiani, Shalini N; Rosenfeld, Jill A; Pehlivan, Davut; et al. (Am J Hum Genet, 2016)
The paradigm of a single gene associated with one specific phenotype and mode of inheritance has been repeatedly challenged. Genotype-phenotype correlations can often be traced to different mutation types, localization of the variants in distinct protein domains, or the trigger of or escape from nonsense-mediated decay. Using whole-exome sequencing, we identified homozygous variants in EMC1 that segregated with a phenotype of developmental delay, hypotonia, scoliosis, and cerebellar atrophy in three families. In addition, a de novo heterozygous EMC1 variant was seen in an individual with a similar clinical and MRI imaging phenotype. EMC1 encodes a member of the endoplasmic reticulum (ER)-membrane protein complex (EMC), an evolutionarily conserved complex that has been proposed to have multiple roles in ER-associated degradation, ER-mitochondria tethering, and proper assembly of multi-pass transmembrane proteins. Perturbations of protein folding and organelle crosstalk have been implicated in neurodegenerative processes including cerebellar atrophy. We propose EMC1 as a gene in which either biallelic or monoallelic variants might lead to a syndrome including intellectual disability and preferential degeneration of the cerebellum.
Keywords: Adolescent; Alleles; Amino Acid Sequence; Atrophy; Cerebellum; Child; Child, Preschool; Developmental Disabilities; Endoplasmic Reticulum-Associated Degradation; Female; Genetic Association Studies; Genetic Variation; Heterozygote; Humans; Magnetic Resonance Imaging; Male; Membrane Proteins; Molecular Sequence Data; Muscle Hypotonia; Mutation; Pedigree; Protein Folding; Proteins; Scoliosis

Multiallelic Positions in the Human Genome: Challenges for Genetic Analyses. - Campbell, Ian M; Gambin, Tomasz; Jhangiani, Shalini; Grove, Megan L; Veeraraghavan, Narayanan; Donna M Muzny; Shaw, Chad A; Richard A Gibbs; Eric Boerwinkle; Fuli Yu; Lupski, James R (Hum Mutat, 2016)
As the amount of human genomic sequence available from personal genomes and exomes has increased, so too has the observation of genomic positions having two or more alternative alleles, so-called multiallelic sites. For portions of the haploid genome that are present in more than one copy, including segmental duplications, variation at such multisite variant positions becomes even more complex. Despite the frequency of multiallelic variants, a number of commonly used resources and tools in genomic research and diagnostics do not support these multiallelic variants all together or require special modifications. Here, we explore the frequency of multiallelic sites in large samples with whole exome sequencing and discuss potential outcomes of failing to account for multiple variant alleles. We also briefly discuss some commonly utilized resources that fully support multiallelic sites.
Keywords: Alleles; Exome; Genome, Human; Humans

Multifaceted biological insights from a draft genome sequence of the tobacco hornworm moth, Manduca sexta. - Kanost, Michael R; Arrese, Estela L; Cao, Xiaolong; Chen, Yun-Ru; Chellapilla, Sanjay; Goldsmith, Marian R; Grosse-Wilde, Ewald; Heckel, David G; Herndon, Nicolae; Jiang, Haobo; Papanicolaou, Alexie; Qu, Jiaxin; et al. (Insect Biochem Mol Biol, 2016)
Manduca sexta, known as the tobacco hornworm or Carolina sphinx moth, is a lepidopteran insect that is used extensively as a model system for research in insect biochemistry, physiology, neurobiology, development, and immunity. One important benefit of this species as an experimental model is its extremely large size, reaching more than 10 g in the larval stage. M. sexta larvae feed on solanaceous plants and thus must tolerate a substantial challenge from plant allelochemicals, including nicotine. We report the sequence and annotation of the M. sexta genome, and a survey of gene expression in various tissues and developmental stages. The Msex_1.0 genome assembly resulted in a total genome size of 419.4 Mbp. Repetitive sequences accounted for 25.8% of the assembled genome. The official gene set is comprised of 15,451 protein-coding genes, of which 2498 were manually curated. Extensive RNA-seq data from many tissues and developmental stages were used to improve gene models and for insights into gene expression patterns. Genome wide synteny analysis indicated a high level of macrosynteny in the Lepidoptera. Annotation and analyses were carried out for gene families involved in a wide spectrum of biological processes, including apoptosis, vacuole sorting, growth and development, structures of exoskeleton, egg shells, and muscle, vision, chemosensation, ion channels, signal transduction, neuropeptide signaling, neurotransmitter synthesis and transport, nicotine tolerance, lipid metabolism, and immunity. This genome sequence, annotation, and analysis provide an important new resource from a well-studied model insect species and will facilitate further biochemical and mechanistic experimental studies of many biological systems in insects.
Keywords: Animals; Gene Expression; Gene Expression Profiling; Genome, Insect; Larva; Manduca; Pupa; Sequence Analysis, DNA; Synteny

Multilevel Genomics-Based Taxonomy of Renal Cell Carcinoma. - Chen, Fengju; Zhang, Yiqun; Şenbabaoğlu, Yasin; Ciriello, Giovanni; Yang, Lixing; Reznik, Ed; Shuch, Brian; Micevic, Goran; De Velasco, Guillermo; Shinbrot, Eve; Noble, Michael S; Lu, Yiling; et al. (Cell Rep, 2016)
On the basis of multidimensional and comprehensive molecular characterization (including DNA methalylation and copy number, RNA, and protein expression), we classified 894 renal cell carcinomas (RCCs) of various histologic types into nine major genomic subtypes. Site of origin within the nephron was one major determinant in the classification, reflecting differences among clear cell, chromophobe, and papillary RCC. Widespread molecular changes associated with TFE3 gene fusion or chromatin modifier genes were present within a specific subtype and spanned multiple subtypes. Differences in patient survival and in alteration of specific pathways (including hypoxia, metabolism, MAP kinase, NRF2-ARE, Hippo, immune checkpoint, and PI3K/AKT/mTOR) could further distinguish the subtypes. Immune checkpoint markers and molecular signatures of T cell infiltrates were both highest in the subtype associated with aggressive clear cell RCC. Differences between the genomic subtypes suggest that therapeutic strategies could be tailored to each RCC disease subset.
Keywords: Basic Helix-Loop-Helix Leucine Zipper Transcription Factors; Carcinoma, Renal Cell; Chromatin; Gene Expression Profiling; Genomics; Humans; Kidney Neoplasms; MicroRNAs; Mutation; Phosphatidylinositol 3-Kinases; Proto-Oncogene Proteins c-akt; RNA, Messenger; Signal Transduction; Survival Rate; TOR Serine-Threonine Kinases

Mutations in the nuclear bile acid receptor FXR cause progressive familial intrahepatic cholestasis. - Gomez-Ospina, Natalia; Potter, Carol J; Xiao, Rui; Manickam, Kandamurugu; Kim, Mi-Sun; Kim, Kang Ho; Shneider, Benjamin L; Picarsic, Jennifer L; Jacobson, Theodora A; Zhang, Jing; He, Weimin; Liu, Pengfei; et al. (Nat Commun, 2016)
Neonatal cholestasis is a potentially life-threatening condition requiring prompt diagnosis. Mutations in several different genes can cause progressive familial intrahepatic cholestasis, but known genes cannot account for all familial cases. Here we report four individuals from two unrelated families with neonatal cholestasis and mutations in NR1H4, which encodes the farnesoid X receptor (FXR), a bile acid-activated nuclear hormone receptor that regulates bile acid metabolism. Clinical features of severe, persistent NR1H4-related cholestasis include neonatal onset with rapid progression to end-stage liver disease, vitamin K-independent coagulopathy, low-to-normal serum gamma-glutamyl transferase activity, elevated serum alpha-fetoprotein and undetectable liver bile salt export pump (ABCB11) expression. Our findings demonstrate a pivotal function for FXR in bile acid homeostasis and liver protection.
Keywords: ATP Binding Cassette Transporter, Subfamily B, Member 11; ATP-Binding Cassette Transporters; Bile Acids and Salts; Cholestasis, Intrahepatic; Female; Humans; Male; Mutation; Receptors, Cytoplasmic and Nuclear; Young Adult

Novel patient-derived xenograft and cell line models for therapeutic testing of pediatric liver cancer. - Bissig-Choisat, Beatrice; Kettlun-Leyton, Claudia; Legras, Xavier D; Zorman, Barry; Barzi, Mercedes; Chen, Leon L; Amin, Mansi D; Huang, Yung-Hsin; Pautler, Robia G; Hampton, Oliver A; Prakash, Masand M; Yang, Diane; et al. (J Hepatol, 2016)
BACKGROUND & AIMS: Pediatric liver cancer is a rare but serious disease whose incidence is rising, and for which the therapeutic options are limited. Development of more targeted, less toxic therapies is hindered by the lack of an experimental animal model that captures the heterogeneity and metastatic capability of these tumors. METHODS: Here we established an orthotopic engraftment technique to model a series of patient-derived tumor xenograft (PDTX) from pediatric liver cancers of all major histologic subtypes: hepatoblastoma, hepatocellular cancer and hepatocellular malignant neoplasm. We utilized standard (immuno) staining methods for histological characterization, RNA sequencing for gene expression profiling and genome sequencing for identification of druggable targets. We also adapted stem cell culturing techniques to derive two new pediatric cancer cell lines from the xenografted mice. RESULTS: The patient-derived tumor xenografts recapitulated the histologic, genetic, and biological characteristics-including the metastatic behavior-of the corresponding primary tumors. Furthermore, the gene expression profiles of the two new liver cancer cell lines closely resemble those of the primary tumors. Targeted therapy of PDTX from an aggressive hepatocellular malignant neoplasm with the MEK1 inhibitor trametinib and pan-class I PI3 kinase inhibitor NVP-BKM120 resulted in significant growth inhibition, thus confirming this PDTX model as a valuable tool to study tumor biology and patient-specific therapeutic responses. CONCLUSIONS: The novel metastatic xenograft model and the isogenic xenograft-derived cell lines described in this study provide reliable tools for developing mutation- and patient-specific therapies for pediatric liver cancer. LAY SUMMARY: Pediatric liver cancer is a rare but serious disease and no experimental animal model currently captures the complexity and metastatic capability of these tumors. We have established a novel animal model using human tumor tissue that recapitulates the genetic and biological characteristics of this cancer. We demonstrate that our patient-derived animal model, as well as two new cell lines, are useful tools for experimental therapies.
Keywords: Animals; Carcinoma, Hepatocellular; Cell Line, Tumor; Child; Disease Models, Animal; Heterografts; Humans; Liver Neoplasms; Mice; Neoplasm Transplantation; Xenograft Model Antitumor Assays

An open access pilot freely sharing cancer genomic data from participants in Texas. - Becnel, Lauren B; Pereira, Stacey; Drummond, Jennifer A; Marie-Claude Gingras; Covington, Kyle R; Kovar, Christie L; Harshavardhan Doddapaneni; Jianhong Hu; Donna M Muzny; McGuire, Amy L; Wheeler, David A; Richard A Gibbs (Sci Data, 2016)
Genomic data sharing in cancer has been restricted to aggregate or controlled-access initiatives to protect the privacy of research participants. By limiting access to these data, it has been argued that the autonomy of individuals who decide to participate in data sharing efforts has been superseded and the utility of the data as research and educational tools reduced. In a pilot Open Access (OA) project from the CPRIT-funded Texas Cancer Research Biobank, many Texas cancer patients were willing to openly share genomic data from tumor and normal matched pair specimens. For the first time, genetic data from 7 human cancer cases with matched normal are freely available without requirement for data use agreements nor any major restriction except that end users cannot attempt to re-identify the participants (http://txcrb.org/open.html).
Keywords: Access to Information; Biological Specimen Banks; Databases, Genetic; DNA, Neoplasm; Genome, Human; Humans; Information Dissemination; Pancreatic Neoplasms; Texas

PEHO Syndrome May Represent Phenotypic Expansion at the Severe End of the Early-Onset Encephalopathies. - Gawlinski, Pawel; Posmyk, Renata; Gambin, Tomasz; Sielicka, Danuta; Chorazy, Monika; Nowakowska, Beata; Jhangiani, Shalini N; Donna M Muzny; Bekiesinska-Figatowska, Monika; Bal, Jerzy; Eric Boerwinkle; Richard A Gibbs; et al. (Pediatr Neurol, 2016)
BACKGROUND: Progressive encephalopathy with edema, hypsarrhythmia and optic atrophy (PEHO) syndrome is a distinct neurodevelopmental disorder. Patients without optic nerve atrophy and brain imaging abnormalities but fulfilling other PEHO criteria are often described as a PEHO-like syndrome. The molecular bases of both clinically defined conditions remain unknown in spite of the widespread application of genome analyses in both clinic and research. METHODS: We enrolled two patients with a prior diagnosis of PEHO and two individuals with PEHO-like syndrome. All four individuals subsequently underwent whole-exome sequencing and comprehensive genomic analysis. RESULTS: We identified disease-causing mutations in known genes associated with neurodevelopmental disorders including GNAO1 and CDKL5 in two of four individuals. One patient with PEHO syndrome and a de novoGNAO1 mutation was found to have an additional de novo mutation in HESX1 that is associated with optic atrophy. CONCLUSIONS: We hypothesize that PEHO and PEHO-like syndrome may represent a severe end of the spectrum of the early-onset encephalopathies and, in some instances, its complex phenotype may result from an aggregated effect of mutations at two loci.
Keywords: Brain Edema; Child; Child, Preschool; Female; GTP-Binding Protein alpha Subunits, Gi-Go; Humans; Infant; Male; Mutation; Neurodegenerative Diseases; Optic Atrophy; Phenotype; Protein Serine-Threonine Kinases; Spasms, Infantile

Phenotypic Expansion of Congenital Disorder of Glycosylation Due to SRD5A3 Null Mutation. - Tuysuz, Beyhan; Pehlivan, Davut; Özkök, Ahmet; Jhangiani, Shalini; Yalcinkaya, Cengiz; Zeybek, Çiğdem Aktuğlu; Donna M Muzny; Lupski, James R; Richard A Gibbs; Jaeken, Jaak (JIMD Rep, 2016)
We present a boy, admitted at 4 months, with facial dysmorphism, hypertrichosis, loose skin, bilateral inguinal hernia, severe hypotonia, psychomotor disability, seizures with hypsarrhythmia (West syndrome), hepatosplenomegaly, increased serum transaminases, iris coloboma, glaucoma, corneal clouding and bilateral dilated lateral ventricles, and extra-axial post-cerebellar space. Serum transferrin isoelectrofocusing (IEF) showed a type 1 pattern. Whole-exome genotyping showed a previously reported homozygous nonsense mutation c.320G>A; p.Trp107X in SRD5A3. Epilepsy and glaucoma have been reported only once in the 19 described SRD5A3-congenital glycosylation defect patients, and corneal clouding not at all.

POGZ truncating alleles cause syndromic intellectual disability. - White, Janson; Beck, Christine R; Harel, Tamar; Posey, Jennifer E; Jhangiani, Shalini N; Tang, Sha; Farwell, Kelly D; Powis, Zöe; Mendelsohn, Nancy J; Baker, Janice A; Pollack, Lynda; Mason, Kati J; et al. (Genome Med, 2016)
BACKGROUND: Large-scale cohort-based whole exome sequencing of individuals with neurodevelopmental disorders (NDDs) has identified numerous novel candidate disease genes; however, detailed phenotypic information is often lacking in such studies. De novo mutations in pogo transposable element with zinc finger domain (POGZ) have been identified in six independent and diverse cohorts of individuals with NDDs ranging from autism spectrum disorder to developmental delay. METHODS: Whole exome sequencing was performed on five unrelated individuals. Sanger sequencing was used to validate variants and segregate mutations with the phenotype in available family members. RESULTS: We identified heterozygous truncating mutations in POGZ in five unrelated individuals, which were confirmed to be de novo or not present in available parental samples. Careful review of the phenotypes revealed shared features that included developmental delay, intellectual disability, hypotonia, behavioral abnormalities, and similar facial characteristics. Variable features included short stature, microcephaly, strabismus and hearing loss. CONCLUSIONS: While POGZ has been associated with neurodevelopmental disorders in large cohort studies, our data suggest that loss of function variants in POGZ lead to an identifiable syndrome of NDD with specific phenotypic traits. This study exemplifies the era of human reverse clinical genomics ushered in by large disease-directed cohort studies; first defining a new syndrome molecularly and, only subsequently, phenotypically.
Keywords: Adolescent; Adult; Alleles; Child, Preschool; Exome; Female; Heterozygote; Humans; Infant; Intellectual Disability; Male; Mutation; Sequence Analysis, DNA; Transposases

The population genomics of rhesus macaques (Macaca mulatta) based on whole-genome sequences. - Xue, Cheng; Raveendran, Muthuswamy; R. Alan Harris; Fawcett, Gloria L; Liu, Xiaoming; White, Simon; Dahdouli, Mahmoud; Rio Deiros, David; Below, Jennifer E; Salerno, William; Cox, Laura; Fan, Guoping; et al. (Genome Res, 2016)
Rhesus macaques (Macaca mulatta) are the most widely used nonhuman primate in biomedical research, have the largest natural geographic distribution of any nonhuman primate, and have been the focus of much evolutionary and behavioral investigation. Consequently, rhesus macaques are one of the most thoroughly studied nonhuman primate species. However, little is known about genome-wide genetic variation in this species. A detailed understanding of extant genomic variation among rhesus macaques has implications for the use of this species as a model for studies of human health and disease, as well as for evolutionary population genomics. Whole-genome sequencing analysis of 133 rhesus macaques revealed more than 43.7 million single-nucleotide variants, including thousands predicted to alter protein sequences, transcript splicing, and transcription factor binding sites. Rhesus macaques exhibit 2.5-fold higher overall nucleotide diversity and slightly elevated putative functional variation compared with humans. This functional variation in macaques provides opportunities for analyses of coding and noncoding variation, and its cellular consequences. Despite modestly higher levels of nonsynonymous variation in the macaques, the estimated distribution of fitness effects and the ratio of nonsynonymous to synonymous variants suggest that purifying selection has had stronger effects in rhesus macaques than in humans. Demographic reconstructions indicate this species has experienced a consistently large but fluctuating population size. Overall, the results presented here provide new insights into the population genomics of nonhuman primates and expand genomic information directly relevant to primate models of human disease.
Keywords: Animals; Evolution, Molecular; Female; Genetic Fitness; High-Throughput Nucleotide Sequencing; Macaca mulatta; Models, Animal; Polymorphism, Single Nucleotide; Population Density; Whole Genome Sequencing

Postmortem genetic screening for the identification, verification, and reporting of genetic variants contributing to the sudden death of the young. - Methner, D Nicole R; Steven E Scherer; Welch, Katherine; Walkiewicz, Magdalena; Eng, Christine M; Belmont, John W; Powell, Mark C; Korchina, Viktoriya; Harshavardhan Doddapaneni; Donna M Muzny; Richard A Gibbs; Wolf, Dwayne A; et al. (Genome Res, 2016)
Each year in the United States, thousands of cases of sudden and unexpected deaths of infants, children, and young adults are assigned an undetermined cause of death after postmortem investigation and autopsy. Heritable genetic variants have been suggested as the cause of up to a third of sudden death (SD) cases. Elucidation of the genetic variants involved in SD cases is important to not only help establish cause and manner of death of these individuals, but to also aid in determining whether familial genetic testing should be considered. Previously, these types of postmortem screenings have not been a feasible option for most county medical examiners' and coroners' offices. We sequenced full exons of 64 genes associated with SD in the largest known cohort (351) of infant and young SD decedents using massively parallel sequencing at <$600 per sample. Genetic variants were assessed through literature review and clinical evaluation by a multidisciplinary consortium of experts. Thirteen individuals (3.7%), eight infants (2.8% of those <1 yr of age) and five children/young adults (7.0% of those >1 yr of age), were found to have a reportable genetic variant contributing to SD. These percentages represent an estimate lower than those previously reported. Overall yields and results likely vary between studies due to differences in evaluation techniques and reporting. Additionally, we recommend ongoing assessment of data, including nonreported novel variants, as technology and literature continually advance. This study demonstrates a strategy to implement molecular autopsies in medicolegal investigations of young SD decedents.
Keywords: Adolescent; Adult; Autopsy; Cardiomyopathies; Child; Child, Preschool; Death, Sudden; Diagnosis; Female; Genetic Testing; Genetic Variation; Humans; Infant; Infant, Newborn; Male; United States; Young Adult

A potential founder variant in in three Norwegian families with warts, molluscum contagiosum, and T-cell dysfunction. - Sorte, Hanne S; Osnes, Liv T; Fevang, Børre; Aukrust, Pål; Erichsen, Hans C; Backe, Paul H; Abrahamsen, Tore G; Kittang, Ole B; Øverland, Torstein; Jhangiani, Shalini N; Donna M Muzny; Vigeland, Magnus D; et al. (Mol Genet Genomic Med, 2016)
BACKGROUND: Four patients from three Norwegian families presented with a common skin phenotype of warts, molluscum contagiosum, and dermatitis since early childhood, and various other immunological features. Warts are a common manifestation of (HPV), but when they are overwhelming, disseminated and/or persistent, and presenting together with other immunological features, a primary immunodeficiency disease (PIDD) may be suspected. METHODS AND RESULTS: The four patients were exome sequenced as part of a larger study for detecting genetic causes of primary immunodeficiencies. No disease-causing variants were identified in known primary immunodeficiency genes or in other disease-related OMIM genes. However, the same homozygous missense variant in (also known as ) was identified in all four patients. In each family, the variant was located within a narrow region of homozygosity, representing a potential region of autozygosity. is a protein of undetermined function. A role in T-cell activation has been suggested and the mouse protein homolog (Rltpr) is essential for costimulation of T-cell activation via CD28, and for the development of regulatory T cells. Immunophenotyping demonstrated reduced regulatory, CD4+ memory, and CD4+ follicular T cells in all four patients. In addition, they all seem to have a deficiency in IFN -synthesis in CD4+ T cells and NK cells. CONCLUSIONS: We report a novel primary immunodeficiency, and a differential molecular diagnosis to ,,,,,,, and related diseases. The specific variant may represent a Norwegian founder variant segregating on a population-specific haplotype.

Rare Exome Sequence Variants in CLCN6 Reduce Blood Pressure Levels and Hypertension Risk. - Yu, Bing; Pulit, Sara L; Hwang, Shih-Jen; Brody, Jennifer A; Amin, Najaf; Auer, Paul L; Bis, Joshua C; Eric Boerwinkle; Burke, Gregory L; Chakravarti, Aravinda; Correa, Adolfo; Dreisbach, Albert W; et al. (Circ Cardiovasc Genet, 2016)
BACKGROUND: Rare genetic variants influence blood pressure (BP). METHODS AND RESULTS: Whole-exome sequencing was performed on DNA samples from 17 956 individuals of European ancestry and African ancestry (14 497, first-stage discovery and 3459, second-stage discovery) to examine the effect of rare variants on hypertension and 4 BP traits: systolic BP, diastolic BP, pulse pressure, and mean arterial pressure. Tests of ≈170 000 common variants (minor allele frequency, ≥1%; statistical significance, P≤2.9×10(-7)) and gene-based tests of rare variants (minor allele frequency, <1%; ≈17 000 genes; statistical significance, P≤1.5×10(-6)) were evaluated for each trait and ancestry, followed by multiethnic meta-analyses. In the first-stage discovery, rare coding variants (splicing, stop-gain, stop-loss, nonsynonymous variants, or indels) in CLCN6 were associated with lower diastolic BP (cumulative minor allele frequency, 1.3%; β=-3.20; P=4.1×10(-6)) and were independent of a nearby common variant (rs17367504) previously associated with BP. CLCN6 rare variants were also associated with lower systolic BP (β=-4.11; P=2.8×10(-4)), mean arterial pressure (β=-3.50; P=8.9×10(-6)), and reduced hypertension risk (odds ratio, 0.72; P=0.017). Meta-analysis of the 2-stage discovery samples showed that CLCN6 was associated with lower diastolic BP at exome-wide significance (cumulative minor allele frequency, 1.1%; β=-3.30; P=5.0×10(-7)). CONCLUSIONS: These findings implicate the effect of rare coding variants in CLCN6 in BP variation and offer new insights into BP regulation.
Keywords: Alleles; Black People; Blood Pressure; Chloride Channels; Exome; Female; Gene Frequency; Humans; Hypertension; Male; Risk Factors; White People

Recurrent De Novo and Biallelic Variation of ATAD3A, Encoding a Mitochondrial Membrane Protein, Results in Distinct Neurological Syndromes. - Harel, Tamar; Yoon, Wan Hee; Garone, Caterina; Gu, Shen; Coban-Akdemir, Zeynep; Eldomery, Mohammad K; Posey, Jennifer E; Jhangiani, Shalini N; Rosenfeld, Jill A; Cho, Megan T; Fox, Stephanie; Withers, Marjorie; et al. (Am J Hum Genet, 2016)
ATPase family AAA-domain containing protein 3A (ATAD3A) is a nuclear-encoded mitochondrial membrane protein implicated in mitochondrial dynamics, nucleoid organization, protein translation, cell growth, and cholesterol metabolism. We identified a recurrent de novo ATAD3A c.1582C>T (p.Arg528Trp) variant by whole-exome sequencing (WES) in five unrelated individuals with a core phenotype of global developmental delay, hypotonia, optic atrophy, axonal neuropathy, and hypertrophic cardiomyopathy. We also describe two families with biallelic variants in ATAD3A, including a homozygous variant in two siblings, and biallelic ATAD3A deletions mediated by nonallelic homologous recombination (NAHR) between ATAD3A and gene family members ATAD3B and ATAD3C. Tissue-specific overexpression of bor, the Drosophila mutation homologous to the human c.1582C>T (p.Arg528Trp) variant, resulted in a dramatic decrease in mitochondrial content, aberrant mitochondrial morphology, and increased autophagy. Homozygous null bor larvae showed a significant decrease of mitochondria, while overexpression of bor resulted in larger, elongated mitochondria. Finally, fibroblasts of an affected individual exhibited increased mitophagy. We conclude that the p.Arg528Trp variant functions through a dominant-negative mechanism that results in small mitochondria that trigger mitophagy, resulting in a reduction in mitochondrial content. ATAD3A variation represents an additional link between mitochondrial dynamics and recognizable neurological syndromes, as seen with MFN2, OPA1, DNM1L, and STAT2 mutations.
Keywords: Adenosine Triphosphatases; Adult; Alleles; Animals; ATPases Associated with Diverse Cellular Activities; Axons; Cardiomyopathies; Child; Child, Preschool; Developmental Disabilities; DNA Copy Number Variations; Drosophila melanogaster; Female; Fibroblasts; Homozygote; Humans; Infant; Infant, Newborn; Male; Membrane Proteins; Mitochondria; Mitochondrial Proteins; Muscle Hypotonia; Muscles; Mutation; Nervous System Diseases; Neurons; Optic Atrophy; Phenotype; Polymorphism, Single Nucleotide; Syndrome; Young Adult

Recurrent Muscle Weakness with Rhabdomyolysis, Metabolic Crises, and Cardiac Arrhythmia Due to Bi-allelic TANGO2 Mutations. - Lalani, Seema R; Liu, Pengfei; Rosenfeld, Jill A; Watkin, Levi B; Chiang, Theodore; Leduc, Magalie S; Zhu, Wenmiao; Ding, Yan; Pan, Shujuan; Vetrini, Francesco; Miyake, Christina Y; Shinawi, Marwan; et al. (Am J Hum Genet, 2016)
The underlying genetic etiology of rhabdomyolysis remains elusive in a significant fraction of individuals presenting with recurrent metabolic crises and muscle weakness. Using exome sequencing, we identified bi-allelic mutations in TANGO2 encoding transport and Golgi organization 2 homolog (Drosophila) in 12 subjects with episodic rhabdomyolysis, hypoglycemia, hyperammonemia, and susceptibility to life-threatening cardiac tachyarrhythmias. A recurrent homozygous c.460G>A (p.Gly154Arg) mutation was found in four unrelated individuals of Hispanic/Latino origin, and a homozygous ∼34 kb deletion affecting exons 3-9 was observed in two families of European ancestry. One individual of mixed Hispanic/European descent was found to be compound heterozygous for c.460G>A (p.Gly154Arg) and the deletion of exons 3-9. Additionally, a homozygous exons 4-6 deletion was identified in a consanguineous Middle Eastern Arab family. No homozygotes have been reported for these changes in control databases. Fibroblasts derived from a subject with the recurrent c.460G>A (p.Gly154Arg) mutation showed evidence of increased endoplasmic reticulum stress and a reduction in Golgi volume density in comparison to control. Our results show that the c.460G>A (p.Gly154Arg) mutation and the exons 3-9 heterozygous deletion in TANGO2 are recurrent pathogenic alleles present in the Latino/Hispanic and European populations, respectively, causing considerable morbidity in the homozygotes in these populations.
Keywords: Alleles; Arabs; Arrhythmias, Cardiac; Base Sequence; Child; Child, Preschool; Endoplasmic Reticulum Stress; Exome; Exons; Female; Gene Deletion; Golgi Apparatus; Hispanic or Latino; Homozygote; Humans; Infant; Male; Molecular Sequence Data; Muscle Weakness; Pedigree; Rhabdomyolysis; White People

The role of combined SNV and CNV burden in patients with distal symmetric polyneuropathy. - Pehlivan, Davut; Beck, Christine R; Okamoto, Yuji; Harel, Tamar; Akdemir, Zeynep H C; Jhangiani, Shalini N; Withers, Marjorie A; Goksungur, Meryem Tuba; Carvalho, Claudia M B; Czesnik, Dirk; Gonzaga-Jauregui, Claudia; Wiszniewski, Wojciech; et al. (Genet Med, 2016)
PURPOSE: Charcot-Marie-Tooth (CMT) disease is a heterogeneous group of genetic disorders of the peripheral nervous system. Copy-number variants (CNVs) contribute significantly to CMT, as duplication of PMP22 underlies the majority of CMT1 cases. We hypothesized that CNVs and/or single-nucleotide variants (SNVs) might exist in patients with CMT with an unknown molecular genetic etiology. METHODS: Two hundred patients with CMT, negative for both SNV mutations in several CMT genes and for CNVs involving PMP22, were screened for CNVs by high-resolution oligonucleotide array comparative genomic hybridization. Whole-exome sequencing was conducted on individuals with rare, potentially pathogenic CNVs. RESULTS: Putatively causative CNVs were identified in five subjects (~2.5%); four of the five map to known neuropathy genes. Breakpoint sequencing revealed Alu-Alu-mediated junctions as a predominant contributor. Exome sequencing identified MFN2 SNVs in two of the individuals. CONCLUSION: Neuropathy-associated CNV outside of the PMP22 locus is rare in CMT. Nevertheless, there is potential clinical utility in testing for CNVs and exome sequencing in CMT cases negative for the CMT1A duplication. These findings suggest that complex phenotypes including neuropathy can potentially be caused by a combination of SNVs and CNVs affecting more than one disease-associated locus and contributing to a mutational burden.Genet Med 18 5, 443-451.
Keywords: Adult; Age of Onset; Charcot-Marie-Tooth Disease; Child, Preschool; Comparative Genomic Hybridization; DNA Copy Number Variations; Exome; Female; Genetic Predisposition to Disease; GTP Phosphohydrolases; High-Throughput Nucleotide Sequencing; Humans; Male; Mitochondrial Proteins; Motor Neurons; Myelin P0 Protein; Myelin Proteins; Neural Conduction; Polymorphism, Single Nucleotide; Polyneuropathies

SV-STAT accurately detects structural variation via alignment to reference-based assemblies. - Davis, Caleb F; Ritter, Deborah I; Wheeler, David A; Wang, Hongmei; Ding, Yan; Dugan, Shannon P; Bainbridge, Matthew N; Donna M Muzny; Rao, Pulivarthi H; Man, Tsz-Kwong; Plon, Sharon E; Richard A Gibbs; et al. (Source Code Biol Med, 2016)
BACKGROUND: Genomic deletions, inversions, and other rearrangements known collectively as structural variations (SVs) are implicated in many human disorders. Technologies for sequencing DNA provide a potentially rich source of information in which to detect breakpoints of structural variations at base-pair resolution. However, accurate prediction of SVs remains challenging, and existing informatics tools predict rearrangements with significant rates of false positives or negatives. RESULTS: To address this challenge, we developed 'Structural Variation detection by STAck and Tail' (SV-STAT) which implements a novel scoring metric. The software uses this statistic to quantify evidence for structural variation in genomic regions suspected of harboring rearrangements. To demonstrate SV-STAT, we used targeted and genome-wide approaches. First, we applied a custom capture array followed by Roche/454 and SV-STAT to three pediatric B-lineage acute lymphoblastic leukemias, identifying five structural variations joining known and novel breakpoint regions. Next, we detected SVs genome-wide in paired-end Illumina data collected from additional tumor samples. SV-STAT showed predictive accuracy as high as or higher than leading alternatives. The software is freely available under the terms of the GNU General Public License version 3 at https://gitorious.org/svstat/svstat. CONCLUSIONS: SV-STAT works across multiple sequencing chemistries, paired and single-end technologies, targeted or whole-genome strategies, and it complements existing SV-detection software. The method is a significant advance towards accurate detection and genotyping of genomic rearrangements from DNA sequencing data.

A t(5;16) translocation is the likely driver of a syndrome with ambiguous genitalia, facial dysmorphism, intellectual disability, and speech delay. - Ozantürk, Ayşegül; Davis, Erica E; Aniko Sabo; Weiss, Marjan M; Donna M Muzny; Dugan-Perez, Shannon; Sistermans, Erik A; Richard A Gibbs; Özgül, Köksal R; Yalnızoglu, Dilek; Serdaroglu, Esra; Dursun, Ali; et al. (Cold Spring Harb Mol Case Stud, 2016)
Genetic studies grounded on monogenic paradigms have accelerated both gene discovery and molecular diagnosis. At the same time, complex genomic rearrangements are also appreciated as potent drivers of disease pathology. Here, we report two male siblings with a dysmorphic face, ambiguous genitalia, intellectual disability, and speech delay. Through quad-based whole-exome sequencing and concomitant molecular cytogenetic testing, we identified two copy-number variants (CNVs) in both affected individuals likely arising from a balanced translocation: a 13.5-Mb duplication on Chromosome 16 (16q23.1 → 16qter) and a 7.7-Mb deletion on Chromosome 5 (5p15.31 → 5pter), as well as a hemizygous missense variant in CXorf36 (also known as DIA1R). The 5p terminal deletion has been associated previously with speech delay, whereas craniofacial dysmorphia and genital/urinary anomalies have been reported in patients with a terminal duplication of 16q. However, dosage changes in either genomic region alone could not account for the overall clinical presentation in our family; functional testing of CXorf36 in zebrafish did not induce defects in neurogenesis or the craniofacial skeleton. Notably, literature and database analysis revealed a similar dosage disruption in two siblings with extensive phenotypic overlap with our patients. Taken together, our data suggest that dosage perturbation of genes within the two chromosomal regions likely drives the syndromic manifestations of our patients and highlight how multiple genetic lesions can contribute to complex clinical pathologies.

Targeted sequencing of genome wide significant loci associated with bone mineral density (BMD) reveals significant novel and rare variants: the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) targeted sequencing study. - Hsu, Yi-Hsiang; Li, Guo; Liu, Ching-Ti; Brody, Jennifer A; Karasik, David; Chou, Wen-Chi; Demissie, Serkalem; Nandakumar, Kannabiran; Zhou, Yanhua; Cheng, Chia-Ho; Gill, Richard; Richard A Gibbs; et al. (Hum Mol Genet, 2016)
Bone mineral density (BMD) is a heritable phenotype that predicts fracture risk. We performed fine-mapping by targeted sequencing at WLS, MEF2C, ARHGAP1/F2 and JAG1 loci prioritized by eQTL and bioinformatic approaches among 56 BMD loci from our previous GWAS meta-analysis. Targeted sequencing was conducted in 1,291 Caucasians from the Framingham Heart Study ( n =  925) and Cardiovascular Health Study ( n =  366), including 206 women and men with extreme low femoral neck (FN) BMD. A total of 4,964 sequence variants (SNVs) were observed and 80% were rare with MAF <1%. The associations between previously identified SNPs in these loci and BMD, while nominally significant in sequenced participants, were no longer significant after multiple testing corrections. Conditional analyses did not find protein-coding variants that may be responsible for GWAS signals. On the other hand, in the sequenced subjects, we identified novel associations in WLS , ARHGAP1 , and 5' of MEF2C ( P- values < 8x10  -   5 ; false discovery rate (FDR) q-values < 0.01) that were much more strongly associated with BMD compared to the GWAS SNPs. These associated SNVs are less-common; independent from previous GWAS signals in the same loci; and located in gene regulatory elements. Our findings suggest that protein-coding variants in selected GWAS loci did not contribute to GWAS signals. By performing targeted sequencing in GWAS loci, we identified less-common and rare non-coding SNVs associated with BMD independently from GWAS common SNPs, suggesting both common and less-common variants may associate with disease risks and phenotypes in the same loci.
Keywords: Aging; Bone Density; Cardiovascular Diseases; Cohort Studies; Epidemiologic Studies; Female; Femur Neck; Genetic Predisposition to Disease; Genome-Wide Association Study; GTPase-Activating Proteins; Humans; Male; MEF2 Transcription Factors; Middle Aged; Polymorphism, Single Nucleotide

Two male sibs with severe micrognathia and a missense variant in MED12. - Prescott, Trine E; Kulseth, Mari Ann; Heimdal, Ketil R; Stadheim, Barbro; Hopp, Einar; Gambin, Tomasz; Coban Akdemir, Zeynep H; Jhangiani, Shalini N; Donna M Muzny; Richard A Gibbs; Lupski, James R; Stray-Pedersen, Asbjørg (Eur J Med Genet, 2016)
Missense variants in MED12 cause three partially overlapping dysmorphic X-linked intellectual disability (XLID) syndromes: Lujan-Fryns syndrome (also known as Lujan syndrome), FG syndrome (also known as Opitz-Kaveggia syndrome) and X-linked Ohdo syndrome. We report a family with two severely micrognathic male sibs, a 10½ year old boy and a fetus, in which hemizygosity for a previously unreported missense variant in exon 13 of MED12 (NM_005120.2), c.1862G > A, p.(Arg621Gln) was detected by whole exome sequencing. The affected sibs shared no other rare variant with relevance to the phenotype. X-chromosome inactivation in blood was completely skewed (100:0) in the unaffected heterozygous mother, most likely as a result of preferential inactivation of the X-chromosome harbouring the missense variant in MED12. Neither the unaffected brother nor the unaffected maternal grandfather carried the missense variant in MED12. In the 10½ year old boy, upper airway obstruction secondary to Pierre Robin sequence necessitated a tracheostomy for the first 10 months of life. He has mild to moderate intellectual disability and some dysmorphic features seen in MED12-related syndromes. In addition, he has a horizontal gaze paresis, anomalies of the inner ear, and a cervical block vertebra. This report contributes to the expanding phenotypic range associated with MED12-mutations.
Keywords: Exons; Genes, X-Linked; Genetic Association Studies; Genotype; Humans; Infant; Male; Mediator Complex; Micrognathism; Mutation, Missense; Pedigree; Phenotype; Polymorphism, Single Nucleotide; Severity of Illness Index; Siblings; Tomography, X-Ray Computed; X Chromosome Inactivation

Unique features of a global human ectoparasite identified through sequencing of the bed bug genome. - Benoit, Joshua B; Adelman, Zach N; Reinhardt, Klaus; Dolan, Amanda; Poelchau, Monica; Jennings, Emily C; Szuter, Elise M; Hagan, Richard W; Gujar, Hemant; Shukla, Jayendra Nath; Zhu, Fang; Mohan, M; et al. (Nat Commun, 2016)
The bed bug, Cimex lectularius, has re-established itself as a ubiquitous human ectoparasite throughout much of the world during the past two decades. This global resurgence is likely linked to increased international travel and commerce in addition to widespread insecticide resistance. Analyses of the C. lectularius sequenced genome (650 Mb) and 14,220 predicted protein-coding genes provide a comprehensive representation of genes that are linked to traumatic insemination, a reduced chemosensory repertoire of genes related to obligate hematophagy, host-symbiont interactions, and several mechanisms of insecticide resistance. In addition, we document the presence of multiple putative lateral gene transfer events. Genome sequencing and annotation establish a solid foundation for future research on mechanisms of insecticide resistance, human-bed bug and symbiont-bed bug associations, and unique features of bed bug biology that contribute to the unprecedented success of C. lectularius as a human ectoparasite.
Keywords: Animals; Bedbugs; Ectoparasitic Infestations; Feeding Behavior; Gene Transfer, Horizontal; Genome; Host-Parasite Interactions; Humans; Insecticide Resistance; Insecticides; Sequence Analysis, DNA

Whole exome sequencing identifies the first STRADA point mutation in a patient with polyhydramnios, megalencephaly, and symptomatic epilepsy syndrome (PMSE). - Bi, Weimin; Glass, Ian A; Donna M Muzny; Richard A Gibbs; Eng, Christine M; Yang, Yaping; Sun, Angela (Am J Med Genet A, 2016)
Polyhydramnios, megalencephaly, and symptomatic epilepsy syndrome (PMSE) is an ultra rare neurodevelopmental disorder characterized by severe, infantile-onset intractable epilepsy, neurocognitive delay, macrocephaly, and craniofacial dysmorphism. The molecular diagnosis of this condition has thus far only been made in 16 Old Order Mennonite patients carrying a homozygous 7 kb founder deletion of exons 9-13 of STRADA. We performed clinical whole exome sequencing (WES) on a 4-year-old Indian male with global developmental delay, history of failure to thrive, infantile spasms, repetitive behaviors, hypotonia, low muscle mass, marked joint laxity, and dysmorphic facial features including tall forehead, long face, arched eyebrows, small chin, wide mouth, and tented upper lip. A homozygous single nucleotide duplication, c.842dupA (p.D281fs), in exon 10 of STRADA was identified. Sanger sequencing confirmed the mutation in the individual and identified both parents as carriers. In light of the molecular discoveries, the patient's clinical phenotype was considered to be a good fit for PMSE. We identified for the first time a homozygous point mutation in STRADA causing PMSE. Additional bi-allelic mutations related to PMSE thus far have not been observed in Baylor ∼6,000 consecutive clinical WES cases, supporting the rarity of this disorder. Our findings may have treatment implications for the patient since previous studies have shown rapamycin as a potential therapeutic agent for the seizures and cognitive problems in PMSE patients. © 2016 Wiley Periodicals, Inc.
Keywords: Adaptor Proteins, Vesicular Transport; Child, Preschool; DNA Mutational Analysis; Epilepsy; Exome; Facies; Genetic Association Studies; Genotype; High-Throughput Nucleotide Sequencing; Humans; Male; Megalencephaly; Pedigree; Phenotype; Physical Examination; Point Mutation; Polyhydramnios; Psychomotor Disorders; Syndrome

Whole Exome Sequencing in Atrial Fibrillation. - Lubitz, Steven A; Brody, Jennifer A; Bihlmeyer, Nathan A; Roselli, Carolina; Weng, Lu-Chen; Christophersen, Ingrid E; Alonso, Alvaro; Eric Boerwinkle; Richard A Gibbs; Bis, Joshua C; Cupples, L Adrienne; Mohler, Peter J; et al. (PLoS Genet, 2016)
Atrial fibrillation (AF) is a morbid and heritable arrhythmia. Over 35 genes have been reported to underlie AF, most of which were described in small candidate gene association studies. Replication remains lacking for most, and therefore the contribution of coding variation to AF susceptibility remains poorly understood. We examined whole exome sequencing data in a large community-based sample of 1,734 individuals with and 9,423 without AF from the Framingham Heart Study, Cardiovascular Health Study, Atherosclerosis Risk in Communities Study, and NHLBI-GO Exome Sequencing Project and meta-analyzed the results. We also examined whether genetic variation was enriched in suspected AF genes (N = 37) in AF cases versus controls. The mean age ranged from 59 to 73 years; 8,656 (78%) were of European ancestry. None of the 99,404 common variants evaluated was significantly associated after adjusting for multiple testing. Among the most significantly associated variants was a common (allele frequency = 86%) missense variant in SYNPO2L (rs3812629, p.Pro707Leu, [odds ratio 1.27, 95% confidence interval 1.13-1.43, P = 6.6x10-5]) which lies at a known AF susceptibility locus and is in linkage disequilibrium with a top marker from prior analyses at the locus. We did not observe significant associations between rare variants and AF in gene-based tests. Individuals with AF did not display any statistically significant enrichment for common or rare coding variation in previously implicated AF genes. In conclusion, we did not observe associations between coding genetic variants and AF, suggesting that large-effect coding variation is not the predominant mechanism underlying AF. A coding variant in SYNPO2L requires further evaluation to determine whether it is causally related to AF. Efforts to identify biologically meaningful coding variation underlying AF may require large sample sizes or populations enriched for large genetic effects.
Keywords: Aged; Atrial Fibrillation; Exome; Female; Gene Frequency; Genetic Association Studies; Genetic Predisposition to Disease; High-Throughput Nucleotide Sequencing; Humans; Male; Microfilament Proteins; Middle Aged; Polymorphism, Single Nucleotide

Whole genome sequence analysis of serum amino acid levels. - Yu, Bing; de Vries, Paul S; Ginger A Metcalf; Wang, Zhe; Feofanova, Elena V; Liu, Xiaoming; Donna M Muzny; Wagenknecht, Lynne E; Richard A Gibbs; Morrison, Alanna C; Eric Boerwinkle (Genome Biol, 2016)
BACKGROUND: Blood levels of amino acids are important biomarkers of disease and are influenced by synthesis, protein degradation, and gene-environment interactions. Whole genome sequence analysis of amino acid levels may establish a paradigm for analyzing quantitative risk factors. RESULTS: In a discovery cohort of 1872 African Americans and a replication cohort of 1552 European Americans we sequenced exons and whole genomes and measured serum levels of 70 amino acids. Rare and low-frequency variants (minor allele frequency ≤5%) were analyzed by three types of aggregating motifs defined by gene exons, regulatory regions, or genome-wide sliding windows. Common variants (minor allele frequency >5%) were analyzed individually. Over all four analysis strategies, 14 gene-amino acid associations were identified and replicated. The 14 loci accounted for an average of 1.8% of the variance in amino acid levels, which ranged from 0.4 to 9.7%. Among the identified locus-amino acid pairs, four are novel and six have been reported to underlie known Mendelian conditions. These results suggest that there may be substantial genetic effects on amino acid levels in the general population that may underlie inborn errors of metabolism. We also identify a predicted promoter variant in AGA (the gene that encodes aspartylglucosaminidase) that is significantly associated with asparagine levels, with an effect that is independent of any observed coding variants. CONCLUSIONS: These data provide insights into genetic influences on circulating amino acid levels by integrating -omic technologies in a multi-ethnic population. The results also help establish a paradigm for whole genome sequence analysis of quantitative traits.
Keywords: Adult; Aged; Amino Acids; Biomarkers; Exons; Female; Genome, Human; Genome-Wide Association Study; High-Throughput Nucleotide Sequencing; Humans; Male; Middle Aged; Nucleotide Motifs; Polymorphism, Single Nucleotide; Population Surveillance; Regulatory Sequences, Nucleic Acid

The whole genome sequence of the Mediterranean fruit fly, Ceratitis capitata (Wiedemann), reveals insights into the biology and adaptive evolution of a highly invasive pest species. - Papanicolaou, Alexie; Schetelig, Marc F; Arensburger, Peter; Atkinson, Peter W; Benoit, Joshua B; Bourtzis, Kostas; Castañera, Pedro; Cavanaugh, John P; Chao, Hsu; Childers, Christopher; Curril, Ingrid; Dinh, Huyen; et al. (Genome Biol, 2016)
BACKGROUND: The Mediterranean fruit fly (medfly), Ceratitis capitata, is a major destructive insect pest due to its broad host range, which includes hundreds of fruits and vegetables. It exhibits a unique ability to invade and adapt to ecological niches throughout tropical and subtropical regions of the world, though medfly infestations have been prevented and controlled by the sterile insect technique (SIT) as part of integrated pest management programs (IPMs). The genetic analysis and manipulation of medfly has been subject to intensive study in an effort to improve SIT efficacy and other aspects of IPM control. RESULTS: The 479 Mb medfly genome is sequenced from adult flies from lines inbred for 20 generations. A high-quality assembly is achieved having a contig N50 of 45.7 kb and scaffold N50 of 4.06 Mb. In-depth curation of more than 1800 messenger RNAs shows specific gene expansions that can be related to invasiveness and host adaptation, including gene families for chemoreception, toxin and insecticide metabolism, cuticle proteins, opsins, and aquaporins. We identify genes relevant to IPM control, including those required to improve SIT. CONCLUSIONS: The medfly genome sequence provides critical insights into the biology of one of the most serious and widespread agricultural pests. This knowledge should significantly advance the means of controlling the size and invasive potential of medfly populations. Its close relationship to Drosophila, and other insect species important to agriculture and human health, will further comparative functional and structural studies of insect genomes that should broaden our understanding of gene family evolution.
Keywords: Animals; Animals, Genetically Modified; Biological Evolution; Ceratitis capitata; Genome, Insect; High-Throughput Nucleotide Sequencing; Humans; Introduced Species; Molecular Sequence Annotation; Pest Control, Biological

Whole-Exome Sequencing Identifies Loci Associated with Blood Cell Traits and Reveals a Role for Alternative GFI1B Splice Variants in Human Hematopoiesis. - Polfus, Linda M; Khajuria, Rajiv K; Schick, Ursula M; Pankratz, Nathan; Pazoki, Raha; Brody, Jennifer A; Chen, Ming-Huei; Auer, Paul L; Floyd, James S; Huang, Jie; Lange, Leslie; van Rooij, Frank J A; et al. (Am J Hum Genet, 2016)
Circulating blood cell counts and indices are important indicators of hematopoietic function and a number of clinical parameters, such as blood oxygen-carrying capacity, inflammation, and hemostasis. By performing whole-exome sequence association analyses of hematologic quantitative traits in 15,459 community-dwelling individuals, followed by in silico replication in up to 52,024 independent samples, we identified two previously undescribed coding variants associated with lower platelet count: a common missense variant in CPS1 (rs1047891, MAF = 0.33, discovery + replication p = 6.38 × 10(-10)) and a rare synonymous variant in GFI1B (rs150813342, MAF = 0.009, discovery + replication p = 1.79 × 10(-27)). By performing CRISPR/Cas9 genome editing in hematopoietic cell lines and follow-up targeted knockdown experiments in primary human hematopoietic stem and progenitor cells, we demonstrate an alternative splicing mechanism by which the GFI1B rs150813342 variant suppresses formation of a GFI1B isoform that preferentially promotes megakaryocyte differentiation and platelet production. These results demonstrate how unbiased studies of natural variation in blood cell traits can provide insight into the regulation of human hematopoiesis.
Keywords: Alternative Splicing; Blood Platelets; CRISPR-Cas Systems; DNA Mutational Analysis; Exome; Gene Editing; Genetic Loci; Hematopoiesis; Hematopoietic Stem Cells; Humans; Megakaryocytes; Platelet Count; Proto-Oncogene Proteins; Repressor Proteins

Whole-Exome Sequencing in Familial Parkinson Disease. - Farlow, Janice L; Robak, Laurie A; Hetrick, Kurt; Bowling, Kevin; Eric Boerwinkle; Coban-Akdemir, Zeynep H; Gambin, Tomasz; Richard A Gibbs; Gu, Shen; Jain, Preti; Jankovic, Joseph; Jhangiani, Shalini; et al. (JAMA Neurol, 2016)
IMPORTANCE: Parkinson disease (PD) is a progressive neurodegenerative disease for which susceptibility is linked to genetic and environmental risk factors. OBJECTIVE: To identify genetic variants contributing to disease risk in familial PD. DESIGN, SETTING, AND PARTICIPANTS: A 2-stage study design that included a discovery cohort of families with PD and a replication cohort of familial probands was used. In the discovery cohort, rare exonic variants that segregated in multiple affected individuals in a family and were predicted to be conserved or damaging were retained. Genes with retained variants were prioritized if expressed in the brain and located within PD-relevant pathways. Genes in which prioritized variants were observed in at least 4 families were selected as candidate genes for replication in the replication cohort. The setting was among individuals with familial PD enrolled from academic movement disorder specialty clinics across the United States. All participants had a family history of PD. MAIN OUTCOMES AND MEASURES: Identification of genes containing rare, likely deleterious, genetic variants in individuals with familial PD using a 2-stage exome sequencing study design. RESULTS: The 93 individuals from 32 families in the discovery cohort (49.5% [46 of 93] female) had a mean (SD) age at onset of 61.8 (10.0) years. The 49 individuals with familial PD in the replication cohort (32.6% [16 of 49] female) had a mean (SD) age at onset of 50.1 (15.7) years. Discovery cohort recruitment dates were 1999 to 2009, and replication cohort recruitment dates were 2003 to 2014. Data analysis dates were 2011 to 2015. Three genes containing a total of 13 rare and potentially damaging variants were prioritized in the discovery cohort. Two of these genes (TNK2 and TNR) also had rare variants that were predicted to be damaging in the replication cohort. All 9 variants identified in the 2 replicated genes in 12 families across the discovery and replication cohorts were confirmed via Sanger sequencing. CONCLUSIONS AND RELEVANCE: TNK2 and TNR harbored rare, likely deleterious, variants in individuals having familial PD, with similar findings in an independent cohort. To our knowledge, these genes have not been previously associated with PD, although they have been linked to critical neuronal functions. Further studies are required to confirm a potential role for these genes in the pathogenesis of PD.
Keywords: Adult; Aged; Cohort Studies; Exome; Female; Genetic Predisposition to Disease; Genetic Variation; Humans; Male; Middle Aged; Parkinsonian Disorders; Protein-Tyrosine Kinases; Sequence Analysis, DNA; Tenascin

Whole-exome sequencing reveals an inherited R566X mutation of the epithelial sodium channel β-subunit in a case of early-onset phenotype of Liddle syndrome. - Polfus, Linda M; Eric Boerwinkle; Richard A Gibbs; Ginger A Metcalf; Donna M Muzny; Veeraraghavan, Narayanan; Grove, Megan; Shete, Sanjay; Wallace, Stephanie; Milewicz, Dianna; Hanchard, Neil; Lupski, James R; et al. (Cold Spring Harb Mol Case Stud, 2016)
To comprehensively evaluate a European-American child with severe hypertension, whole-exome sequencing (WES) was performed on the child and parents, which identified causal variation of the proband's early-onset disease. The proband's hypertension was resistant to treatment, requiring a multiple drug regimen including amiloride, spironolactone, and hydrochlorothiazide. We suspected a monogenic form of hypertension because of the persistent hypokalemia with low plasma levels of renin and aldosterone. To address this, we focused on rare functional variants and indels, and performed gene-based tests incorporating linkage scores and allele frequency and filtered on deleterious functional mutations. Drawing upon clinical presentation, 27 genes were selected evidenced to cause monogenic hypertension and matched to the gene-based results. This resulted in the identification of a stop-gain mutation in an epithelial sodium channel (ENaC), , an established Liddle syndrome gene, shared by the child and her father. Interestingly, the father also harbored a missense mutation (p.Trp552Arg) in the α-subunit of the ENaC trimer, , possibly pointing to pseudohypoaldosteronism type I. This case is unique in that we present the early-onset disease and treatment response caused by a canonical stop-gain mutation (p.Arg566*) as well as ENaC digenic hits in the father, emphasizing the utility of WES informing precision medicine.
Keywords: Adult; Aldosterone; Alleles; Amiloride; Child, Preschool; Epithelial Sodium Channels; Exome; Exome Sequencing; Female; Gene Frequency; Germ-Line Mutation; Humans; Hydrochlorothiazide; Hypertension; Hypokalemia; Liddle Syndrome; Male; Mutation; Mutation, Missense; Renin

16S gut community of the Cameron County Hispanic Cohort. - Ross, Matthew C; Donna M Muzny; McCormick, Joseph B; Richard A Gibbs; Fisher-Hoch, Susan P; Petrosino, Joseph F (Microbiome, 2015)
BACKGROUND: Obesity and type 2 diabetes (T2D) are major public health concerns worldwide, and their prevalence has only increased in recent years. Mexican Americans are disproportionately afflicted by obesity and T2D, and rates are even higher in the United States-Mexico border region. To determine the factors associated with the increased risk of T2D, obesity, and other diseases in this population, the Cameron County Hispanic Cohort was established in 2004. RESULTS: In this study, we characterized the 16S gut community of a subset of 63 subjects from this unique cohort. We found that these communities, when compared to Human Microbiome Project subjects, exhibit community shifts often observed in obese and T2D individuals in published studies. We also examined microbial network relationships between operational taxonomic units (OTUs) in the Cameron County Hispanic Cohort (CCHC) and three additional datasets. We identified a group of seven genera that form a tightly interconnected network present in all four tested datasets, dominated by butyrate producers, which are often increased in obese individuals while being depleted in T2D patients. CONCLUSIONS: Through a combination of increased disease prevalence and relatively high gut microbial homogeneity in the subset of CCHC members we examined, we believe that the CCHC may represent an ideal community to dissect mechanisms underlying the role of the gut microbiome in human health and disease. The lack of CCHC subject gut community segregation based on all tested metadata suggests that the community structure we observe in the CCHC likely occurs early in life, and endures. This persistent 'disease'-related gut microbial community in CCHC subjects may enhance existing genetic or lifestyle predispositions to the prevalent diseases of the CCHC, leading to increased attack rates of obesity, T2D, non-alcoholic fatty liver disease, and others.

Allelic Mutations of KITLG, Encoding KIT Ligand, Cause Asymmetric and Unilateral Hearing Loss and Waardenburg Syndrome Type 2. - Zazo Seco, Celia; Serrão de Castro, Luciana; van Nierop, Josephine W; Morín, Matías; Jhangiani, Shalini; Verver, Eva J J; Schraders, Margit; Maiwald, Nadine; Wesdorp, Mieke; Venselaar, Hanka; Spruijt, Liesbeth; Oostrik, Jaap; et al. (Am J Hum Genet, 2015)
Linkage analysis combined with whole-exome sequencing in a large family with congenital and stable non-syndromic unilateral and asymmetric hearing loss (NS-UHL/AHL) revealed a heterozygous truncating mutation, c.286_303delinsT (p.Ser96Ter), in KITLG. This mutation co-segregated with NS-UHL/AHL as a dominant trait with reduced penetrance. By screening a panel of probands with NS-UHL/AHL, we found an additional mutation, c.200_202del (p.His67_Cys68delinsArg). In vitro studies revealed that the p.His67_Cys68delinsArg transmembrane isoform of KITLG is not detectable at the cell membrane, supporting pathogenicity. KITLG encodes a ligand for the KIT receptor. Also, KITLG-KIT signaling and MITF are suggested to mutually interact in melanocyte development. Because mutations in MITF are causative of Waardenburg syndrome type 2 (WS2), we screened KITLG in suspected WS2-affected probands. A heterozygous missense mutation, c.310C>G (p.Leu104Val), that segregated with WS2 was identified in a small family. In vitro studies revealed that the p.Leu104Val transmembrane isoform of KITLG is located at the cell membrane, as is wild-type KITLG. However, in culture media of transfected cells, the p.Leu104Val soluble isoform of KITLG was reduced, and no soluble p.His67_Cys68delinsArg and p.Ser96Ter KITLG could be detected. These data suggest that mutations in KITLG associated with NS-UHL/AHL have a loss-of-function effect. We speculate that the mechanism of the mutation underlying WS2 and leading to membrane incorporation and reduced secretion of KITLG occurs via a dominant-negative or gain-of-function effect. Our study unveils different phenotypes associated with KITLG, previously associated with pigmentation abnormalities, and will thereby improve the genetic counseling given to individuals with KITLG variants.
Keywords: Alleles; Animals; Female; Fluorescent Antibody Technique; Genetic Linkage; Hearing Loss, Unilateral; Humans; Male; Mice; Mutation; NIH 3T3 Cells; Pedigree; Phenotype; Prognosis; Real-Time Polymerase Chain Reaction; Reverse Transcriptase Polymerase Chain Reaction; RNA, Messenger; Stem Cell Factor; Waardenburg Syndrome

Analysis of loss-of-function variants and 20 risk factor phenotypes in 8,554 individuals identifies loci influencing chronic disease. - Li, Alexander H; Morrison, Alanna C; Kovar, Christie; Cupples, L Adrienne; Brody, Jennifer A; Polfus, Linda M; Yu, Bing; Ginger A Metcalf; Donna M Muzny; Veeraraghavan, Narayanan; Liu, Xiaoming; Lumley, Thomas; et al. (Nat Genet, 2015)
A typical human exome harbors dozens of loss-of-function (LOF) variants, which can lower disease risk factor levels and affect drug efficacy. We hypothesized that LOF variants are enriched in genes influencing risk factor levels and the onset of common chronic diseases, such as cardiovascular disease and diabetes. To test this hypothesis, we sequenced the exomes of 8,554 individuals and analyzed the effects of predicted LOF variants on 20 chronic disease risk factor phenotypes. Analysis of this sample as discovery and replication strata of equal size verified two relationships in well-studied genes (PCSK9 and APOC3) and identified eight new loci. Previously unknown relationships included elevated fasting glucose in carriers of heterozygous LOF variation in TXNDC5, which encodes a biomarker for type 1 diabetes progression, and apparent recessive effects of C1QTNF8 on serum magnesium levels. These data demonstrate the utility of functional-variant annotation within a large sample of deeply phenotyped individuals for gene discovery.
Keywords: Atherosclerosis; Chronic Disease; Exome; Gene Frequency; Genetic Association Studies; Genetic Loci; Genetic Predisposition to Disease; Genome, Human; Humans; Molecular Sequence Annotation; Phenotype; Polymorphism, Single Nucleotide; Risk Factors

Assessing structural variation in a personal genome-towards a human reference diploid genome. - English, Adam C; Salerno, William J; Hampton, Oliver A; Gonzaga-Jauregui, Claudia; Ambreth, Shruthi; Ritter, Deborah I; Beck, Christine R; Davis, Caleb F; Dahdouli, Mahmoud; Ma, Singer; Carroll, Andrew; Veeraraghavan, Narayanan; et al. (BMC Genomics, 2015)
BACKGROUND: Characterizing large genomic variants is essential to expanding the research and clinical applications of genome sequencing. While multiple data types and methods are available to detect these structural variants (SVs), they remain less characterized than smaller variants because of SV diversity, complexity, and size. These challenges are exacerbated by the experimental and computational demands of SV analysis. Here, we characterize the SV content of a personal genome with Parliament, a publicly available consensus SV-calling infrastructure that merges multiple data types and SV detection methods. RESULTS: We demonstrate Parliament's efficacy via integrated analyses of data from whole-genome array comparative genomic hybridization, short-read next-generation sequencing, long-read (Pacific BioSciences RSII), long-insert (Illumina Nextera), and whole-genome architecture (BioNano Irys) data from the personal genome of a single subject (HS1011). From this genome, Parliament identified 31,007 genomic loci between 100 bp and 1 Mbp that are inconsistent with the hg19 reference assembly. Of these loci, 9,777 are supported as putative SVs by hybrid local assembly, long-read PacBio data, or multi-source heuristics. These SVs span 59 Mbp of the reference genome (1.8%) and include 3,801 events identified only with long-read data. The HS1011 data and complete Parliament infrastructure, including a BAM-to-SV workflow, are available on the cloud-based service DNAnexus. CONCLUSIONS: HS1011 SV analysis reveals the limits and advantages of multiple sequencing technologies, specifically the impact of long-read SV discovery. With the full Parliament infrastructure, the HS1011 data constitute a public resource for novel SV discovery, software calibration, and personal genome structural variation analysis.
Keywords: Computational Biology; Databases, Genetic; Diploidy; Genome, Human; Genomic Structural Variation; Humans; Sequence Analysis, DNA; Software

Association of Rare Loss-Of-Function Alleles in HAL, Serum Histidine: Levels and Incident Coronary Heart Disease. - Yu, Bing; Li, Alexander H; Donna M Muzny; Veeraraghavan, Narayanan; de Vries, Paul S; Bis, Joshua C; Musani, Solomon K; Alexander, Danny; Morrison, Alanna C; Franco, Oscar H; Uitterlinden, Andre; Hofman, Albert; et al. (Circ Cardiovasc Genet, 2015)
BACKGROUND: Histidine is a semiessential amino acid with antioxidant and anti-inflammatory properties. Few data are available on the associations between genetic variants, histidine levels, and incident coronary heart disease (CHD) in a population-based sample. METHODS AND RESULTS: By conducting whole exome sequencing on 1152 African Americans in the Atherosclerosis Risk in Communities (ARIC) study and focusing on loss-of-function (LoF) variants, we identified 3 novel rare LoF variants in HAL, a gene that encodes histidine ammonia-lyase in the first step of histidine catabolism. These LoF variants had large effects on blood histidine levels (β=0.26; P=1.2×10(-13)). The positive association with histidine levels was replicated by genotyping an independent sample of 718 ARIC African Americans (minor allele frequency=1%; P=1.2×10(-4)). In addition, high blood histidine levels were associated with reduced risk of developing incident CHD with an average of 21.5 years of follow-up among African Americans (hazard ratio=0.18; P=1.9×10(-4)). This finding was validated in an independent sample of European Americans from the Framingham Heart Study (FHS) Offspring Cohort. However, LoF variants in HAL were not directly significantly associated with incident CHD after meta-analyzing results from the CHARGE Consortium. CONCLUSIONS: Three LoF mutations in HAL were associated with increased histidine levels, which in turn were shown to be inversely related to the risk of CHD among both African Americans and European Americans. Future investigations on the association between HAL gene variation and CHD are warranted.
Keywords: Adult; Alleles; Black or African American; Coronary Disease; Female; Histidine; Histidine Ammonia-Lyase; Humans; Male; Mutation; White People

BCOR-CCNB3 fusions are frequent in undifferentiated sarcomas of male children. - Peters, Tricia L; Kumar, Vijetha; Polikepahad, Sumanth; Lin, Frank Y; Sarabia, Stephen F; Liang, Yu; Wang, Wei-Lien; Lazar, Alexander J; Harshavardhan Doddapaneni; Chao, Hsu; Donna M Muzny; Wheeler, David A; et al. (Mod Pathol, 2015)
The BCOR-CCNB3 fusion gene, resulting from a chromosome X paracentric inversion, was recently described in translocation-negative 'Ewing-like' sarcomas arising in bone and soft tissue. Genetic subclassification of undifferentiated unclassified sarcomas may potentially offer markers for reproducible diagnosis and substrates for therapy. Using whole transcriptome paired-end RNA sequencing (RNA-seq) we unexpectedly identified BCOR-CCNB3 fusion transcripts in an undifferentiated spindle-cell sarcoma. RNA-seq results were confirmed through direct RT-PCR of tumor RNA and cloning of the genomic breakpoints from tumor DNA. Five additional undifferentiated sarcomas with BCOR-CCNB3 fusions were identified in a series of 42 pediatric and adult unclassified sarcomas. Genomic breakpoint analysis demonstrated unique breakpoint locations in each case at the DNA level even though the resulting fusion mRNA was identical in all cases. All patients with BCOR-CCNB3 sarcoma were males diagnosed in mid childhood (7-13 years of age). Tumors were equally distributed between axial and extra-axial locations. Five of the six tumors were soft-tissue lesions with either predominant spindle-cell morphology or spindle-cell areas interspersed with ovoid to round cells. CCNB3 immunohistochemistry showed strong nuclear positivity in five tumors before oncologic therapy, but was patchy to negative in post-treatment tumor samples. An RT-PCR assay developed to detect the fusion transcript in archival formalin-fixed tissue was positive in all six cases, with high sensitivity and specificity in both pre- and post-treated samples. This study adds to recent reports on the clinicopathologic spectrum of BCOR-CCNB3 fusion-positive sarcomas, a newly emerging entity within the undifferentiated unclassified sarcoma category and describes a simple RT-PCR assay that in conjunction with CCNB3 immunohistochemistry can be useful in diagnosing these tumors.
Keywords: Adolescent; Adult; Aged; Child; Cyclin B; Female; Humans; Male; Middle Aged; Oncogene Fusion; Proto-Oncogene Proteins; Repressor Proteins; Sarcoma; Soft Tissue Neoplasms; Young Adult

Convergent evolution of the genomes of marine mammals. - Foote, Andrew D; Liu, Yue; Thomas, Gregg W C; Vinar, Tomas; Alföldi, Jessica; Deng, Jixin; Dugan, Shannon; van Elk, Cornelis E; Hunter, Margaret E; Joshi, Vandita; Ziad Khan; Kovar, Christie; et al. (Nat Genet, 2015)
Marine mammals from different mammalian orders share several phenotypic traits adapted to the aquatic environment and therefore represent a classic example of convergent evolution. To investigate convergent evolution at the genomic level, we sequenced and performed de novo assembly of the genomes of three species of marine mammals (the killer whale, walrus and manatee) from three mammalian orders that share independently evolved phenotypic adaptations to a marine existence. Our comparative genomic analyses found that convergent amino acid substitutions were widespread throughout the genome and that a subset of these substitutions were in genes evolving under positive selection and putatively associated with a marine phenotype. However, we found higher levels of convergent amino acid substitutions in a control set of terrestrial sister taxa to the marine mammals. Our results suggest that, whereas convergent molecular evolution is relatively common, adaptive molecular convergence linked to phenotypic convergence is comparatively rare.
Keywords: Adaptation, Physiological; Amino Acid Substitution; Animals; Evolution, Molecular; Genome; Humans; Mammals; Phenotype; Phylogeny; Selection, Genetic

COPA mutations impair ER-Golgi transport and cause hereditary autoimmune-mediated lung disease and arthritis. - Watkin, Levi B; Jessen, Birthe; Wiszniewski, Wojciech; Vece, Timothy J; Jan, Max; Sha, Youbao; Thamsen, Maike; Santos-Cortez, Regie L P; Lee, Kwanghyuk; Gambin, Tomasz; Forbes, Lisa R; Law, Christopher S; et al. (Nat Genet, 2015)
Unbiased genetic studies have uncovered surprising molecular mechanisms in human cellular immunity and autoimmunity. We performed whole-exome sequencing and targeted sequencing in five families with an apparent mendelian syndrome of autoimmunity characterized by high-titer autoantibodies, inflammatory arthritis and interstitial lung disease. We identified four unique deleterious variants in the COPA gene (encoding coatomer subunit α) affecting the same functional domain. Hypothesizing that mutant COPA leads to defective intracellular transport via coat protein complex I (COPI), we show that COPA variants impair binding to proteins targeted for retrograde Golgi-to-ER transport. Additionally, expression of mutant COPA results in ER stress and the upregulation of cytokines priming for a T helper type 17 (TH17) response. Patient-derived CD4(+) T cells also demonstrate significant skewing toward a TH17 phenotype that is implicated in autoimmunity. Our findings uncover an unexpected molecular link between a vesicular transport protein and a syndrome of autoimmunity manifested by lung and joint disease.
Keywords: Amino Acid Sequence; Arthritis; Autoimmune Diseases; Child, Preschool; Coatomer Protein; Endoplasmic Reticulum; Endoplasmic Reticulum Stress; Female; Genetic Association Studies; Genetic Predisposition to Disease; Golgi Apparatus; HEK293 Cells; Humans; Infant; Lod Score; Lung Diseases, Interstitial; Male; Molecular Sequence Data; Pedigree; Protein Transport

De Novo GMNN Mutations Cause Autosomal-Dominant Primordial Dwarfism Associated with Meier-Gorlin Syndrome. - Burrage, Lindsay C; Charng, Wu-Lin; Eldomery, Mohammad K; Willer, Jason R; Davis, Erica E; Lugtenberg, Dorien; Zhu, Wenmiao; Leduc, Magalie S; Akdemir, Zeynep C; Azamian, Mahshid; Zapata, Gladys; Hernandez, Patricia P; et al. (Am J Hum Genet, 2015)
Meier-Gorlin syndrome (MGS) is a genetically heterogeneous primordial dwarfism syndrome known to be caused by biallelic loss-of-function mutations in one of five genes encoding pre-replication complex proteins: ORC1, ORC4, ORC6, CDT1, and CDC6. Mutations in these genes cause disruption of the origin of DNA replication initiation. To date, only an autosomal-recessive inheritance pattern has been described in individuals with this disorder, with a molecular etiology established in about three-fourths of cases. Here, we report three subjects with MGS and de novo heterozygous mutations in the 5' end of GMNN, encoding the DNA replication inhibitor geminin. We identified two truncating mutations in exon 2 (the 1(st) coding exon), c.16A>T (p.Lys6(∗)) and c.35_38delTCAA (p.Ile12Lysfs(∗)4), and one missense mutation, c.50A>G (p.Lys17Arg), affecting the second-to-last nucleotide of exon 2 and possibly RNA splicing. Geminin is present during the S, G2, and M phases of the cell cycle and is degraded during the metaphase-anaphase transition by the anaphase-promoting complex (APC), which recognizes the destruction box sequence near the 5' end of the geminin protein. All three GMNN mutations identified alter sites 5' to residue Met28 of the protein, which is located within the destruction box. We present data supporting a gain-of-function mechanism, in which the GMNN mutations result in proteins lacking the destruction box and hence increased protein stability and prolonged inhibition of replication leading to autosomal-dominant MGS.
Keywords: Adolescent; Amino Acid Sequence; Base Sequence; Cell Cycle; Child, Preschool; Congenital Microtia; Dwarfism; Exons; Female; Geminin; Gene Expression; Genes, Dominant; Growth Disorders; Heterozygote; High-Throughput Nucleotide Sequencing; Humans; Inheritance Patterns; Male; Micrognathism; Molecular Sequence Data; Mutation; Patella; Pedigree; Protein Stability; Proteolysis; RNA Splicing; Sequence Alignment

The distribution and mutagenesis of short coding INDELs from 1,128 whole exomes. - Challis, Danny; Antunes, Lilian; Garrison, Erik; Banks, Eric; Evani, Uday S; Donna M Muzny; Poplin, Ryan; Richard A Gibbs; Marth, Gábor; Fuli Yu (BMC Genomics, 2015)
BACKGROUND: Identifying insertion/deletion polymorphisms (INDELs) with high confidence has been intrinsically challenging in short-read sequencing data. Here we report our approach for improving INDEL calling accuracy by using a machine learning algorithm to combine call sets generated with three independent methods, and by leveraging the strengths of each individual pipeline. Utilizing this approach, we generated a consensus exome INDEL call set from a large dataset generated by the 1000 Genomes Project (1000G), maximizing both the sensitivity and the specificity of the calls. RESULTS: This consensus exome INDEL call set features 7,210 INDELs, from 1,128 individuals across 13 populations included in the 1000 Genomes Phase 1 dataset, with a false discovery rate (FDR) of about 7.0%. CONCLUSIONS: In our study we further characterize the patterns and distributions of these exonic INDELs with respect to density, allele length, and site frequency spectrum, as well as the potential mutagenic mechanisms of coding INDELs in humans.
Keywords: Computational Biology; Exome; Genome, Human; High-Throughput Nucleotide Sequencing; Human Genome Project; Humans; INDEL Mutation; Machine Learning; Mutagenesis

DVL1 frameshift mutations clustering in the penultimate exon cause autosomal-dominant Robinow syndrome. - White, Janson; Mazzeu, Juliana F; Hoischen, Alexander; Jhangiani, Shalini N; Gambin, Tomasz; Alcino, Michele Calijorne; Penney, Samantha; Saraiva, Jorge M; Hove, Hanne; Skovby, Flemming; Kayserili, Hulya; Estrella, Elicia; et al. (Am J Hum Genet, 2015)
Robinow syndrome is a genetically heterogeneous disorder characterized by mesomelic limb shortening, genital hypoplasia, and distinctive facial features and for which both autosomal-recessive and autosomal-dominant inheritance patterns have been described. Causative variants in the non-canonical signaling gene WNT5A underlie a subset of autosomal-dominant Robinow syndrome (DRS) cases, but most individuals with DRS remain without a molecular diagnosis. We performed whole-exome sequencing in four unrelated DRS-affected individuals without coding mutations in WNT5A and found heterozygous DVL1 exon 14 mutations in three of them. Targeted Sanger sequencing in additional subjects with DRS uncovered DVL1 exon 14 mutations in five individuals, including a pair of monozygotic twins. In total, six distinct frameshift mutations were found in eight subjects, and all were heterozygous truncating variants within the penultimate exon of DVL1. In five families in which samples from unaffected parents were available, the variants were demonstrated to represent de novo mutations. All variant alleles are predicted to result in a premature termination codon within the last exon, escape nonsense-mediated decay (NMD), and most likely generate a C-terminally truncated protein with a distinct -1 reading-frame terminus. Study of the transcripts extracted from affected subjects' leukocytes confirmed expression of both wild-type and variant alleles, supporting the hypothesis that mutant mRNA escapes NMD. Genomic variants identified in our study suggest that truncation of the C-terminal domain of DVL1, a protein hypothesized to have a downstream role in the Wnt-5a non-canonical pathway, is a common cause of DRS.
Keywords: Adaptor Proteins, Signal Transducing; Amino Acid Sequence; Base Sequence; Craniofacial Abnormalities; Dishevelled Proteins; DNA Primers; Dwarfism; Exome; Exons; Frameshift Mutation; Gene Components; Humans; Limb Deformities, Congenital; Molecular Sequence Data; Phosphoproteins; Sequence Analysis, DNA; Urogenital Abnormalities

Exome Sequence Analysis Suggests that Genetic Burden Contributes to Phenotypic Variability and Complex Neuropathy. - Gonzaga-Jauregui, Claudia; Harel, Tamar; Gambin, Tomasz; Kousi, Maria; Griffin, Laurie B; Francescatto, Ludmila; Ozes, Burcak; Karaca, Ender; Jhangiani, Shalini N; Bainbridge, Matthew N; Lawson, Kim S; Pehlivan, Davut; et al. (Cell Rep, 2015)
Charcot-Marie-Tooth (CMT) disease is a clinically and genetically heterogeneous distal symmetric polyneuropathy. Whole-exome sequencing (WES) of 40 individuals from 37 unrelated families with CMT-like peripheral neuropathy refractory to molecular diagnosis identified apparent causal mutations in ∼ 45% (17/37) of families. Three candidate disease genes are proposed, supported by a combination of genetic and in vivo studies. Aggregate analysis of mutation data revealed a significantly increased number of rare variants across 58 neuropathy-associated genes in subjects versus controls, confirmed in a second ethnically discrete neuropathy cohort, suggesting that mutation burden potentially contributes to phenotypic variability. Neuropathy genes shown to have highly penetrant Mendelizing variants (HPMVs) and implicated by burden in families were shown to interact genetically in a zebrafish assay exacerbating the phenotype established by the suppression of single genes. Our findings suggest that the combinatorial effect of rare variants contributes to disease burden and variable expressivity.
Keywords: Animals; Charcot-Marie-Tooth Disease; Exome; Female; Genetic Load; Genetic Variation; HSP40 Heat-Shock Proteins; Humans; Male; Mutation; Myelin P2 Protein; Pedigree; Penetrance; Peripheral Nervous System Diseases; Phenotype; Serine C-Palmitoyltransferase; Suppression, Genetic; Zebrafish

Exome sequencing reveals homozygous TRIM2 mutation in a patient with early onset CMT and bilateral vocal cord paralysis. - Pehlivan, Davut; Coban Akdemir, Zeynep; Karaca, Ender; Bayram, Yavuz; Jhangiani, Shalini; Yildiz, Edibe Pembegul; Donna M Muzny; Uluc, Kayihan; Richard A Gibbs; Elcioglu, Nursel; Lupski, James R; Harel, Tamar (Hum Genet, 2015)
Charcot-Marie-Tooth disease is a heterogeneous group of inherited distal symmetric polyneuropathies associated with mutations in genes encoding components essential for normal functioning of the Schwann cell and axon. TRIM2, encoding a ligase that ubiquitinates the neurofilament light chain, was recently associated with early-onset neuropathy in a single patient. We report a TRIM2 homozygous missense mutation (c.2000A>C; p.D667A) in a patient with peripheral neuropathy and bilateral vocal cord paralysis, allowing for further delineation of the associated phenotypic spectrum.
Keywords: Adult; Charcot-Marie-Tooth Disease; Exome; Female; High-Throughput Nucleotide Sequencing; Homozygote; Humans; Infant, Newborn; Male; Mutation, Missense; Nuclear Proteins; Vocal Cord Paralysis

Extreme Sensory Complexity Encoded in the 10-Megabase Draft Genome Sequence of the Chromatically Acclimating Cyanobacterium Tolypothrix sp. PCC 7601. - Yerrapragada, Shaila; Shukla, Animesh; Hallsworth-Pepin, Kymberlie; Choi, Kwangmin; Wollam, Aye; Clifton, Sandra; Qin, Xiang; Donna M Muzny; Raghuraman, Sriram; Ashki, Haleh; Uzman, Akif; Highlander, Sarah K; et al. (Genome Announc, 2015)
Tolypothrix sp. PCC 7601 is a freshwater filamentous cyanobacterium with complex responses to environmental conditions. Here, we present its 9.96-Mbp draft genome sequence, containing 10,065 putative protein-coding sequences, including 305 predicted two-component system proteins and 27 putative phytochrome-class photoreceptors, the most such proteins in any sequenced genome.

FBN1 contributing to familial congenital diaphragmatic hernia. - Beck, Tyler F; Campeau, Philippe M; Jhangiani, Shalini N; Gambin, Tomasz; Li, Alexander H; Abo-Zahrah, Reem; Jordan, Valerie K; Hernandez-Garcia, Andres; Wiszniewski, Wojciech K; Donna M Muzny; Richard A Gibbs; Eric Boerwinkle; et al. (Am J Med Genet A, 2015)
Congenital diaphragmatic hernia (CDH) is a relatively common, life--threatening birth defect. We present a family with recurrent CDH--paraesophageal and central--for whom exome sequencing (ES) revealed a frameshift mutation (c.4969_4970insA, p.Ile1657Asnfs*30) in the fibrillin 1 gene (FBN1) that causes Marfan syndrome. A diagnosis of Marfan syndrome had not been considered previously in this family. However, a review of the literature demonstrated that FBN1 mutations have an unusual pattern of CDH in which paraesophageal hernias are particularly common. Subsequent clinical evaluations revealed evidence for ectopia lentis in affected family members supporting a clinical diagnosis of Marfan syndrome. Since only two other cases of familial CDH have been described in association with FBN1 mutations, we investigated an oligogenic hypothesis by examining ES data for deleterious sequence changes in other CDH-related genes. This search revealed putatively deleterious sequence changes in four other genes that have been shown to cause diaphragm defects in humans and/or mice--FREM1, DES, PAX3 and MET. It is unclear whether these changes, alone or in aggregate, are contributing to the development of CDH in this family. However, their individual contribution is likely to be small compared to that of the frameshift mutation in FBN1. We conclude that ES can be used to identify both major and minor genetic factors that may contribute to CDH. These results also suggest that ES should be considered in the diagnostic evaluation of individuals and families with CDH, particularly when other diagnostic modalities have failed to reveal a molecular etiology.
Keywords: Adult; Child, Preschool; DNA Mutational Analysis; Exome; Female; Fibrillin-1; Fibrillins; Frameshift Mutation; Genetic Association Studies; Hernias, Diaphragmatic, Congenital; Humans; Male; Marfan Syndrome; Microfilament Proteins; Pedigree

Genes that Affect Brain Structure and Function Identified by Rare Variant Analyses of Mendelian Neurologic Disease. - Karaca, Ender; Harel, Tamar; Pehlivan, Davut; Jhangiani, Shalini N; Gambin, Tomasz; Coban Akdemir, Zeynep; Gonzaga-Jauregui, Claudia; Erdin, Serkan; Bayram, Yavuz; Campbell, Ian M; Hunter, Jill V; Atik, Mehmed M; et al. (Neuron, 2015)
Development of the human nervous system involves complex interactions among fundamental cellular processes and requires a multitude of genes, many of which remain to be associated with human disease. We applied whole exome sequencing to 128 mostly consanguineous families with neurogenetic disorders that often included brain malformations. Rare variant analyses for both single nucleotide variant (SNV) and copy number variant (CNV) alleles allowed for identification of 45 novel variants in 43 known disease genes, 41 candidate genes, and CNVs in 10 families, with an overall potential molecular cause identified in >85% of families studied. Among the candidate genes identified, we found PRUNE, VARS, and DHX37 in multiple families and homozygous loss-of-function variants in AGBL2, SLC18A2, SMARCA1, UBQLN1, and CPLX1. Neuroimaging and in silico analysis of functional and expression proximity between candidate and known disease genes allowed for further understanding of genetic networks underlying specific types of brain malformations.
Keywords: Brain; Cohort Studies; Databases, Genetic; Female; Gene Regulatory Networks; Genetic Association Studies; Genetic Variation; Humans; Male; Mendelian Randomization Analysis; Nervous System Diseases; Pedigree

The Genetic Basis of Mendelian Phenotypes: Discoveries, Challenges, and Opportunities. - Chong, Jessica X; Buckingham, Kati J; Jhangiani, Shalini N; Boehm, Corinne; Sobreira, Nara; Smith, Joshua D; Harrell, Tanya M; McMillin, Margaret J; Wiszniewski, Wojciech; Gambin, Tomasz; Coban Akdemir, Zeynep H; Doheny, Kimberly; et al. (Am J Hum Genet, 2015)
Discovering the genetic basis of a Mendelian phenotype establishes a causal link between genotype and phenotype, making possible carrier and population screening and direct diagnosis. Such discoveries also contribute to our knowledge of gene function, gene regulation, development, and biological mechanisms that can be used for developing new therapeutics. As of February 2015, 2,937 genes underlying 4,163 Mendelian phenotypes have been discovered, but the genes underlying ∼50% (i.e., 3,152) of all known Mendelian phenotypes are still unknown, and many more Mendelian conditions have yet to be recognized. This is a formidable gap in biomedical knowledge. Accordingly, in December 2011, the NIH established the Centers for Mendelian Genomics (CMGs) to provide the collaborative framework and infrastructure necessary for undertaking large-scale whole-exome sequencing and discovery of the genetic variants responsible for Mendelian phenotypes. In partnership with 529 investigators from 261 institutions in 36 countries, the CMGs assessed 18,863 samples from 8,838 families representing 579 known and 470 novel Mendelian phenotypes as of January 2015. This collaborative effort has identified 956 genes, including 375 not previously associated with human health, that underlie a Mendelian phenotype. These results provide insight into study design and analytical strategies, identify novel mechanisms of disease, and reveal the extensive clinical variability of Mendelian phenotypes. Discovering the gene underlying every Mendelian phenotype will require tackling challenges such as worldwide ascertainment and phenotypic characterization of families affected by Mendelian conditions, improvement in sequencing and analytical techniques, and pervasive sharing of phenotypic and genomic data among researchers, clinicians, and families.
Keywords: Genetic Diseases, Inborn; Genetics, Medical; Humans; Phenotype; Proteins

The genomes of two key bumblebee species with primitive eusocial organization. - Sadd, Ben M; Barribeau, Seth M; Bloch, Guy; de Graaf, Dirk C; Dearden, Peter; Elsik, Christine G; Gadau, Jürgen; Grimmelikhuijzen, Cornelis J P; Hasselmann, Martin; Lozier, Jeffrey D; Robertson, Hugh M; Smagghe, Guy; et al. (Genome Biol, 2015)
BACKGROUND: The shift from solitary to social behavior is one of the major evolutionary transitions. Primitively eusocial bumblebees are uniquely placed to illuminate the evolution of highly eusocial insect societies. Bumblebees are also invaluable natural and agricultural pollinators, and there is widespread concern over recent population declines in some species. High-quality genomic data will inform key aspects of bumblebee biology, including susceptibility to implicated population viability threats. RESULTS: We report the high quality draft genome sequences of Bombus terrestris and Bombus impatiens, two ecologically dominant bumblebees and widely utilized study species. Comparing these new genomes to those of the highly eusocial honeybee Apis mellifera and other Hymenoptera, we identify deeply conserved similarities, as well as novelties key to the biology of these organisms. Some honeybee genome features thought to underpin advanced eusociality are also present in bumblebees, indicating an earlier evolution in the bee lineage. Xenobiotic detoxification and immune genes are similarly depauperate in bumblebees and honeybees, and multiple categories of genes linked to social organization, including development and behavior, show high conservation. Key differences identified include a bias in bumblebee chemoreception towards gustation from olfaction, and striking differences in microRNAs, potentially responsible for gene regulation underlying social and other traits. CONCLUSIONS: These two bumblebee genomes provide a foundation for post-genomic research on these key pollinators and insect societies. Overall, gene repertoires suggest that the route to advanced eusociality in bees was mediated by many small changes in many genes and processes, and not by notable expansion or depauperation.
Keywords: Animals; Bee Venoms; Bees; Behavior, Animal; Chemoreceptor Cells; Chromosome Mapping; Databases, Genetic; Evolution, Molecular; Female; Gene Expression Regulation; Gene Rearrangement; Genes, Insect; Genomics; Interspersed Repetitive Sequences; Male; Open Reading Frames; Polymorphism, Single Nucleotide; Selenoproteins; Sequence Analysis, DNA; Social Behavior; Species Specificity; Synteny

Genomic profiling of Sézary syndrome identifies alterations of key T cell signaling and differentiation genes. - Wang, Linghua; Ni, Xiao; Covington, Kyle R; Yang, Betty Y; Shiu, Jessica; Zhang, Xiang; Xi, Liu; Meng, Qingchang; Langridge, Timothy; Drummond, Jennifer; Donehower, Lawrence A; Harshavardhan Doddapaneni; et al. (Nat Genet, 2015)
Sézary syndrome is a rare leukemic form of cutaneous T cell lymphoma characterized by generalized redness, scaling, itching and increased numbers of circulating atypical T lymphocytes. It is rarely curable, with poor prognosis. Here we present a multiplatform genomic analysis of 37 patients with Sézary syndrome that implicates dysregulation of cell cycle checkpoint and T cell signaling. Frequent somatic alterations were identified in TP53, CARD11, CCR4, PLCG1, CDKN2A, ARID1A, RPS6KA1 and ZEB1. Activating CCR4 and CARD11 mutations were detected in nearly one-third of patients. ZEB1, encoding a transcription repressor essential for T cell differentiation, was deleted in over one-half of patients. IL32 and IL2RG were overexpressed in nearly all cases. Our results demonstrate profound disruption of key signaling pathways in Sézary syndrome and suggest potential targets for new therapies.
Keywords: Case-Control Studies; Cell Differentiation; Exome; Gene Expression Regulation, Neoplastic; Gene Regulatory Networks; Genetic Drift; Genomics; High-Throughput Nucleotide Sequencing; Humans; Lymphocyte Activation; Mutation; Prognosis; Sezary Syndrome; Signal Transduction; Skin Neoplasms; Survival Rate; T-Lymphocytes

Genomic signatures of cooperation and conflict in the social amoeba. - Ostrowski, Elizabeth A; Shen, Yufeng; Tian, Xiangjun; Sucgang, Richard; Jiang, Huaiyang; Qu, Jiaxin; Katoh-Kurasawa, Mariko; Brock, Debra A; Dinh, Christopher; Lara-Garduno, Fremiet; Lee, Sandra L; Kovar, Christie L; et al. (Curr Biol, 2015)
Cooperative systems are susceptible to invasion by selfish individuals that profit from receiving the social benefits but fail to contribute. These so-called "cheaters" can have a fitness advantage in the laboratory, but it is unclear whether cheating provides an important selective advantage in nature. We used a population genomic approach to examine the history of genes involved in cheating behaviors in the social amoeba Dictyostelium discoideum, testing whether these genes experience rapid evolutionary change as a result of conflict over spore-stalk fate. Candidate genes and surrounding regions showed elevated polymorphism, unusual patterns of linkage disequilibrium, and lower levels of population differentiation, but they did not show greater between-species divergence. The signatures were most consistent with frequency-dependent selection acting to maintain multiple alleles, suggesting that conflict may lead to stalemate rather than an escalating arms race. Our results reveal the evolutionary dynamics of cooperation and cheating and underscore how sequence-based approaches can be used to elucidate the history of conflicts that are difficult to observe directly.
Keywords: Dictyostelium; Evolution, Molecular; Genome, Protozoan; Genomics; Polymorphism, Genetic; Selection, Genetic

Germline mutations in shelterin complex genes are associated with familial glioma. - Bainbridge, Matthew N; Armstrong, Georgina N; Gramatges, M Monica; Bertuch, Alison A; Jhangiani, Shalini N; Harshavardhan Doddapaneni; Lewis, Lora; Tombrello, Joseph; Tsavachidis, Spyros; Liu, Yanhong; Jalali, Ali; Plon, Sharon E; et al. (J Natl Cancer Inst, 2015)
Gliomas are the most common brain tumor, with several histological subtypes of various malignancy grade. The genetic contribution to familial glioma is not well understood. Using whole exome sequencing of 90 individuals from 55 families, we identified two families with mutations in POT1 (p.G95C, p.E450X), a member of the telomere shelterin complex, shared by both affected individuals in each family and predicted to impact DNA binding and TPP1 binding, respectively. Validation in a separate cohort of 264 individuals from 246 families identified an additional mutation in POT1 (p.D617Efs), also predicted to disrupt TPP1 binding. All families with POT1 mutations had affected members with oligodendroglioma, a specific subtype of glioma more sensitive to irradiation. These findings are important for understanding the origin of glioma and could have importance for the future diagnostics and treatment of glioma.
Keywords: Adult; Aged; Brain Neoplasms; Exome; Female; Genetic Predisposition to Disease; Germ-Line Mutation; Glioma; Humans; Male; Middle Aged; Oligodendroglioma; Pedigree; Shelterin Complex; Telomere-Binding Proteins

Global transcriptional disturbances underlie Cornelia de Lange syndrome and related phenotypes. - Bo Yuan; Pehlivan, Davut; Karaca, Ender; Patel, Nisha; Charng, Wu-Lin; Gambin, Tomasz; Gonzaga-Jauregui, Claudia; Sutton, V Reid; Yesil, Gozde; Bozdogan, Sevcan Tug; Tos, Tulay; Koparir, Asuman; et al. (J Clin Invest, 2015)
Cornelia de Lange syndrome (CdLS) is a genetically heterogeneous disorder that presents with extensive phenotypic variability, including facial dysmorphism, developmental delay/intellectual disability (DD/ID), abnormal extremities, and hirsutism. About 65% of patients harbor mutations in genes that encode subunits or regulators of the cohesin complex, including NIPBL, SMC1A, SMC3, RAD21, and HDAC8. Wiedemann-Steiner syndrome (WDSTS), which shares CdLS phenotypic features, is caused by mutations in lysine-specific methyltransferase 2A (KMT2A). Here, we performed whole-exome sequencing (WES) of 2 male siblings clinically diagnosed with WDSTS; this revealed a hemizygous, missense mutation in SMC1A that was predicted to be deleterious. Extensive clinical evaluation and WES of 32 Turkish patients clinically diagnosed with CdLS revealed the presence of a de novo heterozygous nonsense KMT2A mutation in 1 patient without characteristic WDSTS features. We also identified de novo heterozygous mutations in SMC3 or SMC1A that affected RNA splicing in 2 independent patients with combined CdLS and WDSTS features. Furthermore, in families from 2 separate world populations segregating an autosomal-recessive disorder with CdLS-like features, we identified homozygous mutations in TAF6, which encodes a core transcriptional regulatory pathway component. Together, our data, along with recent transcriptome studies, suggest that CdLS and related phenotypes may be "transcriptomopathies" rather than cohesinopathies.
Keywords: Adolescent; Adult; Cell Cycle Proteins; Child; Child, Preschool; Chondroitin Sulfate Proteoglycans; Chromosomal Proteins, Non-Histone; Codon, Nonsense; De Lange Syndrome; Exome; Exonucleases; Gene Expression Profiling; Gene Expression Regulation; Genome-Wide Association Study; Heterozygote; Histone Deacetylases; Histone-Lysine N-Methyltransferase; Humans; Infant; Male; Myeloid-Lymphoid Leukemia Protein; Phenotype; Proteins; Repressor Proteins; Transcriptome

Hemichordate genomes and deuterostome origins. - Simakov, Oleg; Kawashima, Takeshi; Marlétaz, Ferdinand; Jenkins, Jerry; Koyanagi, Ryo; Mitros, Therese; Hisata, Kanako; Bredeson, Jessen; Shoguchi, Eiichi; Gyoja, Fuki; Yue, Jia-Xing; Chen, Yi-Chih; et al. (Nature, 2015)
Acorn worms, also known as enteropneust (literally, 'gut-breathing') hemichordates, are marine invertebrates that share features with echinoderms and chordates. Together, these three phyla comprise the deuterostomes. Here we report the draft genome sequences of two acorn worms, Saccoglossus kowalevskii and Ptychodera flava. By comparing them with diverse bilaterian genomes, we identify shared traits that were probably inherited from the last common deuterostome ancestor, and then explore evolutionary trajectories leading from this ancestor to hemichordates, echinoderms and chordates. The hemichordate genomes exhibit extensive conserved synteny with amphioxus and other bilaterians, and deeply conserved non-coding sequences that are candidates for conserved gene-regulatory elements. Notably, hemichordates possess a deuterostome-specific genomic cluster of four ordered transcription factor genes, the expression of which is associated with the development of pharyngeal 'gill' slits, the foremost morphological innovation of early deuterostomes, and is probably central to their filter-feeding lifestyle. Comparative analysis reveals numerous deuterostome-specific gene novelties, including genes found in deuterostomes and marine microbes, but not other animals. The putative functions of these genes can be linked to physiological, metabolic and developmental specializations of the filter-feeding ancestor.
Keywords: Animals; Chordata, Nonvertebrate; Conserved Sequence; Echinodermata; Evolution, Molecular; Genome; Multigene Family; Phylogeny; Signal Transduction; Synteny; Transforming Growth Factor beta

High-Quality Draft Genome Sequence of Francisella tularensis subsp. holarctica Strain OR96-0246. - Atkins, L M; Holder, M E; Ajami, N J; Ginger A Metcalf; Weissenberger, G M; Wang, M; Vee, V; Han, Y; Donna M Muzny; Richard A Gibbs; Petrosino, J F (Genome Announc, 2015)
The bacterial pathogen Francisella tularensis was recently renewed as a tier-one select agent. F. tularensis subsp. tularensis (type A) and holarctica (type B) are of clinical relevance. Here, we report the complete genome of a virulent F. tularensis type B strain and describe its usefulness in comparative genomics.

Homozygous loss-of-function mutations in SOHLH1 in patients with nonsyndromic hypergonadotropic hypogonadism. - Bayram, Yavuz; Gulsuner, Suleyman; Guran, Tulay; Abaci, Ayhan; Yesil, Gozde; Gulsuner, Hilal Unal; Atay, Zeynep; Pierce, Sarah B; Gambin, Tomasz; Lee, Ming; Turan, Serap; Bober, Ece; et al. (J Clin Endocrinol Metab, 2015)
CONTEXT: Hypergonadotropic hypogonadism presents in females with delayed or arrested puberty, primary or secondary amenorrhea due to gonadal dysfunction, and is further characterized by elevated gonadotropins and low sex steroids. Chromosomal aberrations and various specific gene defects can lead to hypergonadotropic hypogonadism. Responsible genes include those with roles in gonadal development or maintenance, sex steroid synthesis, or end-organ resistance to gonadotropins. Identification of novel causative genes in this disorder will contribute to our understanding of the regulation of human reproductive function. OBJECTIVES: The aim of this study was to identify and report the gene responsible for autosomal-recessive hypergonadotropic hypogonadism in two unrelated families. DESIGN AND PARTICIPANTS: Clinical evaluation and whole-exome sequencing were performed in two pairs of sisters with nonsyndromic hypergonadotropic hypogonadism from two unrelated families. RESULTS: Exome sequencing analysis revealed two different truncating mutations in the same gene: SOHLH1 c.705delT (p.Pro235fs*4) and SOHLH1 c.27C>G (p.Tyr9stop). Both mutations were unique to the families and segregation was consistent with Mendelian expectations for an autosomal-recessive mode of inheritance. CONCLUSIONS: Sohlh1 was known from previous mouse studies to be a transcriptional regulator that functions in the maintenance and survival of primordial ovarian follicles, but loss-of-function mutations in human females have not been reported. Our results provide evidence that homozygous-truncating mutations in SOHLH1 cause female nonsyndromic hypergonadotropic hypogonadism.
Keywords: Adolescent; Basic Helix-Loop-Helix Transcription Factors; Child; Exome; Female; Homozygote; Humans; Hypogonadism; Mutation

Loss of Function Mutations in NNT Are Associated With Left Ventricular Noncompaction. - Bainbridge, Matthew N; Davis, Erica E; Choi, Wen-Yee; Dickson, Amy; Martinez, Hugo R; Wang, Min; Dinh, Huyen; Donna M Muzny; Pignatelli, Ricardo; Katsanis, Nicholas; Eric Boerwinkle; Richard A Gibbs; et al. (Circ Cardiovasc Genet, 2015)
BACKGROUND: Left ventricular noncompaction (LVNC) is an autosomal-dominant, genetically heterogeneous cardiomyopathy with variable severity, which may co-occur with cardiac hypertrophy. METHODS AND RESULTS: Here, we generated whole exome sequence data from multiple members from 5 families with LVNC. In 4 of 5 families, the candidate causative mutation segregates with disease in known LVNC genes MYH7 and TPM1. Subsequent sequencing of MYH7 in a larger LVNC cohort identified 7 novel likely disease causing variants. In the fifth family, we identified a frameshift mutation in NNT, a nuclear-encoded mitochondrial protein, not implicated previously in human cardiomyopathies. Resequencing of NNT in additional LVNC families identified a second likely pathogenic missense allele. Suppression of nnt in zebrafish caused early ventricular malformation and contractility defects, probably driven by altered cardiomyocyte proliferation. In vivo complementation studies showed that mutant human NNT failed to rescue nnt morpholino-induced heart dysfunction, indicating a probable haploinsufficiency mechanism. CONCLUSIONS: Together, our data expand the genetic spectrum of LVNC and demonstrate how the intersection of whole exome sequence with in vivo functional studies can accelerate the identification of genes that drive human genetic disorders.
Keywords: Animals; Animals, Genetically Modified; Embryo, Nonmammalian; Exome; Family Health; Female; Frameshift Mutation; Genetic Complementation Test; Genetic Predisposition to Disease; Humans; Isolated Noncompaction of the Ventricular Myocardium; Luminescent Proteins; Male; Microscopy, Confocal; Mitochondrial Proteins; NADP Transhydrogenase, AB-Specific; Pedigree; Sequence Analysis, DNA; Zebrafish

Low-frequency and rare exome chip variants associate with fasting glucose and type 2 diabetes susceptibility. - Wessel, Jennifer; Chu, Audrey Y; Willems, Sara M; Wang, Shuai; Yaghootkar, Hanieh; Brody, Jennifer A; Dauriz, Marco; Hivert, Marie-France; Raghavan, Sridharan; Lipovich, Leonard; Hidalgo, Bertha; Fox, Keolu; et al. (Nat Commun, 2015)
Fasting glucose and insulin are intermediate traits for type 2 diabetes. Here we explore the role of coding variation on these traits by analysis of variants on the HumanExome BeadChip in 60,564 non-diabetic individuals and in 16,491 T2D cases and 81,877 controls. We identify a novel association of a low-frequency nonsynonymous SNV in GLP1R (A316T; rs10305492; MAF=1.4%) with lower FG (β=-0.09±0.01 mmol l(-1), P=3.4 × 10(-12)), T2D risk (OR[95%CI]=0.86[0.76-0.96], P=0.010), early insulin secretion (β=-0.07±0.035 pmolinsulin mmolglucose(-1), P=0.048), but higher 2-h glucose (β=0.16±0.05 mmol l(-1), P=4.3 × 10(-4)). We identify a gene-based association with FG at G6PC2 (pSKAT=6.8 × 10(-6)) driven by four rare protein-coding SNVs (H177Y, Y207S, R283X and S324P). We identify rs651007 (MAF=20%) in the first intron of ABO at the putative promoter of an antisense lncRNA, associating with higher FG (β=0.02±0.004 mmol l(-1), P=1.3 × 10(-8)). Our approach identifies novel coding variant associations and extends the allelic spectrum of variation underlying diabetes-related quantitative traits and T2D susceptibility.
Keywords: Black People; Blood Glucose; Diabetes Mellitus, Type 2; Exome; Fasting; Genetic Association Studies; Genetic Loci; Genetic Predisposition to Disease; Genetic Variation; Glucagon-Like Peptide-1 Receptor; Glucose-6-Phosphatase; Humans; Insulin; Mutation Rate; Oligonucleotide Array Sequence Analysis; Polymorphism, Single Nucleotide; White People

Lucilia cuprina genome unlocks parasitic fly biology to underpin future interventions. - Anstead, Clare A; Korhonen, Pasi K; Young, Neil D; Hall, Ross S; Jex, Aaron R; Murali, Shwetha C; Hughes, Daniel S T; Lee, Siu F; Perry, Trent; Stroehlein, Andreas J; Ansell, Brendan R E; Breugelmans, Bert; et al. (Nat Commun, 2015)
Lucilia cuprina is a parasitic fly of major economic importance worldwide. Larvae of this fly invade their animal host, feed on tissues and excretions and progressively cause severe skin disease (myiasis). Here we report the sequence and annotation of the 458-megabase draft genome of Lucilia cuprina. Analyses of this genome and the 14,544 predicted protein-encoding genes provide unique insights into the fly's molecular biology, interactions with the host animal and insecticide resistance. These insights have broad implications for designing new methods for the prevention and control of myiasis.
Keywords: Animals; Diptera; Female; Gene Expression Regulation; Genome, Insect; Insect Proteins; Insecticide Resistance; Insecticides; Larva; Male; Transcriptome

A massive expansion of effector genes underlies gall-formation in the wheat pest Mayetiola destructor. - Zhao, Chaoyang; Escalante, Lucio Navarro; Chen, Hang; Benatti, Thiago R; Qu, Jiaxin; Chellapilla, Sanjay; Waterhouse, Robert M; Wheeler, David; Andersson, Martin N; Bao, Riyue; Batterton, Matthew; Behura, Susanta K; et al. (Curr Biol, 2015)
Gall-forming arthropods are highly specialized herbivores that, in combination with their hosts, produce extended phenotypes with unique morphologies [1]. Many are economically important, and others have improved our understanding of ecology and adaptive radiation [2]. However, the mechanisms that these arthropods use to induce plant galls are poorly understood. We sequenced the genome of the Hessian fly (Mayetiola destructor; Diptera: Cecidomyiidae), a plant parasitic gall midge and a pest of wheat (Triticum spp.), with the aim of identifying genic modifications that contribute to its plant-parasitic lifestyle. Among several adaptive modifications, we discovered an expansive reservoir of potential effector proteins. Nearly 5% of the 20,163 predicted gene models matched putative effector gene transcripts present in the M. destructor larval salivary gland. Another 466 putative effectors were discovered among the genes that have no sequence similarities in other organisms. The largest known arthropod gene family (family SSGP-71) was also discovered within the effector reservoir. SSGP-71 proteins lack sequence homologies to other proteins, but their structures resemble both ubiquitin E3 ligases in plants and E3-ligase-mimicking effectors in plant pathogenic bacteria. SSGP-71 proteins and wheat Skp proteins interact in vivo. Mutations in different SSGP-71 genes avoid the effector-triggered immunity that is directed by the wheat resistance genes H6 and H9. Results point to effectors as the agents responsible for arthropod-induced plant gall formation.
Keywords: Adaptation, Biological; Amino Acid Sequence; Animals; Base Sequence; Chromosomes; Diptera; Larva; Models, Genetic; Molecular Sequence Data; Multigene Family; Phylogeny; Plant Tumors; Sequence Analysis, DNA; Sequence Homology; Sexual Behavior, Animal; Triticum; Two-Hybrid System Techniques; Ubiquitin-Protein Ligases

Mutations in COL27A1 cause Steel syndrome and suggest a founder mutation effect in the Puerto Rican population. - Gonzaga-Jauregui, Claudia; Gamble, Candace N; Bo Yuan; Penney, Samantha; Jhangiani, Shalini; Donna M Muzny; Richard A Gibbs; Lupski, James R; Hecht, Jacqueline T (Eur J Hum Genet, 2015)
Osteochondrodysplasias represent a large group of developmental structural disorders that can be caused by mutations in a variety of genes responsible for chondrocyte development, differentiation, mineralization and early ossification. The application of whole-exome sequencing to disorders apparently segregating as Mendelian traits has proven to be an effective approach to disease gene identification for conditions with unknown molecular etiology. We identified a homozygous missense variant p.(Gly697Arg) in COL27A1, in a family with Steel syndrome and no consanguinity. Interestingly, the identified variant seems to have arisen as a founder mutation in the Puerto Rican population.
Keywords: Amino Acid Sequence; Child, Preschool; Comparative Genomic Hybridization; Exome; Female; Fibrillar Collagens; Follow-Up Studies; Founder Effect; Genotype; Hispanic or Latino; Humans; Infant; Male; Molecular Sequence Data; Mutation; Osteochondrodysplasias; Pedigree; Polymorphism, Single Nucleotide; Prostaglandins F; Puerto Rico; Sequence Alignment

New mutations in the RAB28 gene in 2 Spanish families with cone-rod dystrophy. - Riveiro-Álvarez, Rosa; Xie, Yajing Angela; López-Martínez, Miguel-Ángel; Gambin, Tomasz; Pérez-Carro, Raquel; Ávila-Fernández, Almudena; López-Molina, María-Isabel; Zernant, Jana; Jhangiani, Shalini; Donna M Muzny; Bo Yuan; Eric Boerwinkle; et al. (JAMA Ophthalmol, 2015)
IMPORTANCE: The families evaluated in this study represent the second report of cone-rod dystrophy (CRD) cases caused by mutations in RAB28, a recently discovered gene associated with CRD. OBJECTIVE: To determine the disease-causing gene in 2 families of Spanish descent presenting with CRD who do not have ABCA4 mutations. DESIGN, SETTING, AND PARTICIPANTS: Molecular genetics and observational case studies of 2 families, each with 1 affected proband with CRD and 3 or 5 unaffected family members. The affected individual from each family received a complete ophthalmic examination including assessment of refractive errors and best-corrected visual acuity, biomicroscopy, color fundus photography, electroretinography analysis, and visual-evoked potential analysis. After complete sequencing of the ABCA4 gene with negative results, the screening for disease-causing mutations was performed by whole-exome sequencing. Possible disease-associated variants were determined by filtering based on minor allele frequency, predicted pathogenicity, and segregation analysis in all family members. MAIN OUTCOMES AND MEASURES: The appearance of the macula was evaluated by clinical examination, fundus photography, and fundus autofluorescence imaging, and visual function was assessed by electroretinography. Disease-causing mutations were assessed by sequence analyses. RESULTS: Ophthalmologic findings included markedly reduced visual acuity, bull's eye maculopathy, foveal hyperpigmentation, peripapillary atrophy, dyschromatopsia, extinguished photopic responses, and reduced scotopic responses observed on electroretinography consistent with the CRD phenotype often associated with ABCA4 mutations. Although no ABCA4 mutations were detected in either patient, whole-exome sequencing analysis identified 2 new homozygous mutations in the recently described RAB28 gene, the c.172 + 1G>C splice site variant in IVS2 and the missense c.T651G:p.C217W substitution. Both variants were determined as deleterious by predictive programs and were segregated with the disease in both families. Sequencing of 107 additional patients of Spanish descent with CRD did not reveal other cases with RAB28 mutations. CONCLUSIONS AND RELEVANCE: Deleterious mutations in RAB28 result in a classic CRD phenotype and are an infrequent cause of CRD in the Spanish population.
Keywords: Adolescent; Adult; Child; Diagnosis, Differential; DNA Mutational Analysis; Female; Follow-Up Studies; Genetic Predisposition to Disease; Hispanic or Latino; Humans; Male; Microscopy, Acoustic; Mutation; Pedigree; Phenotype; rab GTP-Binding Proteins; Retinitis Pigmentosa; Retrospective Studies; Young Adult

PacBio-LITS: a large-insert targeted sequencing method for characterization of human disease-associated chromosomal structural variations. - Wang, Min; Beck, Christine R; English, Adam C; Meng, Qingchang; Buhay, Christian; Yi Han; Harshavardhan Doddapaneni; Fuli Yu; Eric Boerwinkle; Lupski, James R; Donna M Muzny; Richard A Gibbs (BMC Genomics, 2015)
BACKGROUND: Generation of long (>5 Kb) DNA sequencing reads provides an approach for interrogation of complex regions in the human genome. Currently, large-insert whole genome sequencing (WGS) technologies from Pacific Biosciences (PacBio) enable analysis of chromosomal structural variations (SVs), but the cost to achieve the required sequence coverage across the entire human genome is high. RESULTS: We developed a method (termed PacBio-LITS) that combines oligonucleotide-based DNA target-capture enrichment technologies with PacBio large-insert library preparation to facilitate SV studies at specific chromosomal regions. PacBio-LITS provides deep sequence coverage at the specified sites at substantially reduced cost compared with PacBio WGS. The efficacy of PacBio-LITS is illustrated by delineating the breakpoint junctions of low copy repeat (LCR)-associated complex structural rearrangements on chr17p11.2 in patients diagnosed with Potocki-Lupski syndrome (PTLS; MIM#610883). We successfully identified previously determined breakpoint junctions in three PTLS cases, and also were able to discover novel junctions in repetitive sequences, including LCR-mediated breakpoints. The new information has enabled us to propose mechanisms for formation of these structural variants. CONCLUSIONS: The new method leverages the cost efficiency of targeted capture-sequencing as well as the mappability and scaffolding capabilities of long sequencing reads generated by the PacBio platform. It is therefore suitable for studying complex SVs, especially those involving LCRs, inversions, and the generation of chimeric Alu elements at the breakpoints. Other genomic research applications, such as haplotype phasing and small insertion and deletion validation could also benefit from this technology.
Keywords: Chromosome Aberrations; Gene Library; Gene Rearrangement; Genetic Association Studies; Genomics; High-Throughput Nucleotide Sequencing; Humans; Workflow

Population genomic analysis of 962 whole genome sequences of humans reveals natural selection in non-coding regions. - Fuli Yu; Lu, Jian; Liu, Xiaoming; Gazave, Elodie; Chang, Diana; Raj, Srilakshmi; Hunter-Zinck, Haley; Blekhman, Ran; Arbiza, Leonardo; Van Hout, Cris; Morrison, Alanna; Johnson, Andrew D; et al. (PLoS One, 2015)
Whole genome analysis in large samples from a single population is needed to provide adequate power to assess relative strengths of natural selection across different functional components of the genome. In this study, we analyzed next-generation sequencing data from 962 European Americans, and found that as expected approximately 60% of the top 1% of positive selection signals lie in intergenic regions, 33% in intronic regions, and slightly over 1% in coding regions. Several detailed functional annotation categories in intergenic regions showed statistically significant enrichment in positively selected loci when compared to the null distribution of the genomic span of ENCODE categories. There was a significant enrichment of purifying selection signals detected in enhancers, transcription factor binding sites, microRNAs and target sites, but not on lincRNA or piRNAs, suggesting different evolutionary constraints for these domains. Loci in "repressed or low activity regions" and loci near or overlapping the transcription start site were the most significantly over-represented annotations among the top 1% of signals for positive selection.
Keywords: DNA, Intergenic; Genetic Loci; Humans; Metagenomics; Open Reading Frames; Polymorphism, Single Nucleotide

Rare variants in the notch signaling pathway describe a novel type of autosomal recessive Klippel-Feil syndrome. - Karaca, Ender; Yuregir, Ozge O; Bozdogan, Sevcan T; Aslan, Huseyin; Pehlivan, Davut; Jhangiani, Shalini N; Akdemir, Zeynep C; Gambin, Tomasz; Bayram, Yavuz; Atik, Mehmed M; Erdin, Serkan; Donna M Muzny; et al. (Am J Med Genet A, 2015)
Klippel-Feil syndrome is a rare disorder represented by a subgroup of segmentation defects of the vertebrae and characterized by fusion of the cervical vertebrae, low posterior hairline, and short neck with limited motion. Both autosomal dominant and recessive inheritance patterns were reported in families with Klippel-Feil. Mutated genes for both dominant (GDF6 and GDF3) and recessive (MEOX1) forms of Klippel-Feil syndrome have been shown to be involved in somite development via transcription regulation and signaling pathways. Heterotaxy arises from defects in proteins that function in the development of left-right asymmetry of the developing embryo. We describe a consanguineous family with a male proband who presents with classical Klippel-Feil syndrome together with heterotaxy (situs inversus totalis). The present patient also had Sprengel's deformity, deformity of the sternum, and a solitary kidney. Using exome sequencing, we identified a homozygous frameshift mutation (c.299delT; p.L100fs) in RIPPLY2, a gene shown to play a crucial role in somitogenesis and participate in the Notch signaling pathway via negatively regulating Tbx6. Our data confirm RIPPLY2 as a novel gene for autosomal recessive Klippel-Feil syndrome, and in addition-from a mechanistic standpoint-suggest the possibility that mutations in RIPPLY2 could also lead to heterotaxy. © 2015 Wiley Periodicals, Inc.
Keywords: Adolescent; Base Sequence; Female; Humans; Klippel-Feil Syndrome; Male; Molecular Sequence Data; Mutation; Pedigree; Radiography; Receptors, Notch; Signal Transduction; Spine

Rise and fall of subclones from diagnosis to relapse in pediatric B-acute lymphoblastic leukaemia. - Ma, Xiaotu; Edmonson, Michael; Yergeau, Donald; Donna M Muzny; Hampton, Oliver A; Rusch, Michael; Song, Guangchun; Easton, John; Harvey, Richard C; Wheeler, David A; Ma, Jing; Harshavardhan Doddapaneni; et al. (Nat Commun, 2015)
There is incomplete understanding of genetic heterogeneity and clonal evolution during cancer progression. Here we use deep whole-exome sequencing to describe the clonal architecture and evolution of 20 pediatric B-acute lymphoblastic leukaemias from diagnosis to relapse. We show that clonal diversity is comparable at diagnosis and relapse and clonal survival from diagnosis to relapse is not associated with mutation burden. Six pathways were frequently mutated, with NT5C2, CREBBP, WHSC1, TP53, USH2A, NRAS and IKZF1 mutations enriched at relapse. Half of the leukaemias had multiple subclonal mutations in a pathway or gene at diagnosis, but mostly with only one, usually minor clone, surviving therapy to acquire additional mutations and become the relapse founder clone. Relapse-specific mutations in NT5C2 were found in nine cases, with mutations in four cases being in descendants of the relapse founder clone. These results provide important insights into the genetic basis of treatment failure in ALL and have implications for the early detection of mutations driving relapse.
Keywords: 5'-Nucleotidase; Child; Clonal Evolution; Clone Cells; CREB-Binding Protein; Disease Progression; DNA Copy Number Variations; Exome; Extracellular Matrix Proteins; Female; GTP Phosphohydrolases; Histone-Lysine N-Methyltransferase; Humans; Ikaros Transcription Factor; Male; Membrane Proteins; Mutation; Neoplasm Recurrence, Local; Precursor B-Cell Lymphoblastic Leukemia-Lymphoma; Repressor Proteins; Tumor Suppressor Protein p53

Secondary findings and carrier test frequencies in a large multiethnic sample. - Gambin, Tomasz; Jhangiani, Shalini N; Below, Jennifer E; Campbell, Ian M; Wiszniewski, Wojciech; Donna M Muzny; Staples, Jeffrey; Morrison, Alanna C; Bainbridge, Matthew N; Penney, Samantha; McGuire, Amy L; Richard A Gibbs; et al. (Genome Med, 2015)
BACKGROUND: Besides its growing importance in clinical diagnostics and understanding the genetic basis of Mendelian and complex diseases, whole exome sequencing (WES) is a rich source of additional information of potential clinical utility for physicians, patients and their families. We analyzed the frequency and nature of single nucleotide variants (SNVs) considered secondary findings and recessive disease allele carrier status in the exomes of 8554 individuals from a large, randomly sampled cohort study and 2514 patients from a study of presumed Mendelian disease having undergone WES. METHODS: We used the same sequencing platform and data processing pipeline to analyze all samples and characterized the distributions of reported pathogenic (ClinVar, Human Gene Mutation Database (HGMD)) and predicted deleterious variants in the pre-specified American College of Medical Genetics and Genomics (ACMG) secondary findings and recessive disease genes in different ethnic groups. RESULTS: In the 56 ACMG secondary findings genes, the average number of predicted deleterious variants per individual was 0.74, and the mean number of ClinVar reported pathogenic variants was 0.06. We observed an average of 10 deleterious and 0.78 ClinVar reported pathogenic variants per individual in 1423 autosomal recessive disease genes. By repeatedly sampling pairs of exomes, 0.5 % of the randomly generated couples were at 25 % risk of having an affected offspring for an autosomal recessive disorder based on the ClinVar variants. CONCLUSIONS: By investigating reported pathogenic and novel, predicted deleterious variants we estimated the lower and upper limits of the population fraction for which exome sequencing may reveal additional medically relevant information. We suggest that the observed wide range for the lower and upper limits of these frequency numbers will be gradually reduced due to improvement in classification databases and prediction algorithms.

Structure and function of the healthy pre-adolescent pediatric gut microbiome. - Hollister, Emily B; Riehle, Kevin; Luna, Ruth Ann; Weidler, Erica M; Rubio-Gonzales, Michelle; Mistretta, Toni-Ann; Raza, Sabeen; Harshavardhan Doddapaneni; Ginger A Metcalf; Donna M Muzny; Richard A Gibbs; Petrosino, Joseph F; et al. (Microbiome, 2015)
BACKGROUND: The gut microbiome influences myriad host functions, including nutrient acquisition, immune modulation, brain development, and behavior. Although human gut microbiota are recognized to change as we age, information regarding the structure and function of the gut microbiome during childhood is limited. Using 16S rRNA gene and shotgun metagenomic sequencing, we characterized the structure, function, and variation of the healthy pediatric gut microbiome in a cohort of school-aged, pre-adolescent children (ages 7-12 years). We compared the healthy pediatric gut microbiome with that of healthy adults previously recruited from the same region (Houston, TX, USA). RESULTS: Although healthy children and adults harbored similar numbers of taxa and functional genes, their composition and functional potential differed significantly. Children were enriched in Bifidobacterium spp., Faecalibacterium spp., and members of the Lachnospiraceae, while adults harbored greater abundances of Bacteroides spp. From a functional perspective, significant differences were detected with respect to the relative abundances of genes involved in vitamin synthesis, amino acid degradation, oxidative phosphorylation, and triggering mucosal inflammation. Children's gut communities were enriched in functions which may support ongoing development, while adult communities were enriched in functions associated with inflammation, obesity, and increased risk of adiposity. CONCLUSIONS: Previous studies suggest that the human gut microbiome is relatively stable and adult-like after the first 1 to 3 years of life. Our results suggest that the healthy pediatric gut microbiome harbors compositional and functional qualities that differ from those of healthy adults and that the gut microbiome may undergo a more prolonged development than previously suspected.
Keywords: Adult; Age Factors; Biodiversity; Child; Cluster Analysis; DNA Barcoding, Taxonomic; Female; Gastrointestinal Microbiome; Healthy Volunteers; Humans; Male; Metagenome; RNA, Ribosomal, 16S

Targeted sequencing in chromosome 17q linkage region identifies familial glioma candidates in the Gliogene Consortium. - Jalali, Ali; Amirian, E Susan; Bainbridge, Matthew N; Armstrong, Georgina N; Liu, Yanhong; Tsavachidis, Spyros; Jhangiani, Shalini N; Plon, Sharon E; Lau, Ching C; Claus, Elizabeth B; Barnholtz-Sloan, Jill S; Il'yasova, Dora; et al. (Sci Rep, 2015)
Glioma is a rare, but highly fatal, cancer that accounts for the majority of malignant primary brain tumors. Inherited predisposition to glioma has been consistently observed within non-syndromic families. Our previous studies, which involved non-parametric and parametric linkage analyses, both yielded significant linkage peaks on chromosome 17q. Here, we use data from next generation and Sanger sequencing to identify familial glioma candidate genes and variants on chromosome 17q for further investigation. We applied a filtering schema to narrow the original list of 4830 annotated variants down to 21 very rare (<0.1% frequency), non-synonymous variants. Our findings implicate the MYO19 and KIF18B genes and rare variants in SPAG9 and RUNDC1 as candidates worthy of further investigation. Burden testing and functional studies are planned.
Keywords: Adult; Brain Neoplasms; Chromosomes, Human, Pair 17; Family; Female; Genetic Linkage; Genetic Variation; Glioma; Humans; Male; Middle Aged; Mutation; Pedigree; Sequence Analysis, DNA; Young Adult

Tissue-specific transcriptome sequencing analysis expands the non-human primate reference transcriptome resource (NHPRTR). - Peng, Xinxia; Thierry-Mieg, Jean; Thierry-Mieg, Danielle; Nishida, Andrew; Pipes, Lenore; Bozinoski, Marjan; Thomas, Matthew J; Kelly, Sara; Weiss, Jeffrey M; Raveendran, Muthuswamy; Donna M Muzny; Richard A Gibbs; et al. (Nucleic Acids Res, 2015)
The non-human primate reference transcriptome resource (NHPRTR, available online at http://nhprtr.org/) aims to generate comprehensive RNA-seq data from a wide variety of non-human primates (NHPs), from lemurs to hominids. In the 2012 Phase I of the NHPRTR project, 19 billion fragments or 3.8 terabases of transcriptome sequences were collected from pools of ∼ 20 tissues in 15 species and subspecies. Here we describe a major expansion of NHPRTR by adding 10.1 billion fragments of tissue-specific RNA-seq data. For this effort, we selected 11 of the original 15 NHP species and subspecies and constructed total RNA libraries for the same ∼ 15 tissues in each. The sequence quality is such that 88% of the reads align to human reference sequences, allowing us to compute the full list of expression abundance across all tissues for each species, using the reads mapped to human genes. This update also includes improved transcript annotations derived from RNA-seq data for rhesus and cynomolgus macaques, two of the most commonly used NHP models and additional RNA-seq data compiled from related projects. Together, these comprehensive reference transcriptomes from multiple primates serve as a valuable community resource for genome annotation, gene dynamics and comparative functional analysis.
Keywords: Animals; Databases, Genetic; Gene Expression Profiling; Internet; Macaca; Molecular Sequence Annotation; Organ Specificity; Primates; Reference Standards; Sequence Alignment; Sequence Analysis, RNA

Whole Exome Sequencing Identifies an Adult-Onset Case of Methylmalonic Aciduria and Homocystinuria Type C (cblC) with Non-Syndromic Bull's Eye Maculopathy. - Collison, Frederick T; Xie, Yajing Angela; Gambin, Tomasz; Jhangiani, Shalini; Donna M Muzny; Richard A Gibbs; Lupski, James R; Fishman, Gerald A; Allikmets, Rando (Ophthalmic Genet, 2015)
BACKGROUND: Methylmalonic aciduria and homocystinuria type C (cblC), a disorder of vitamin B12 (cobalamin) metabolism caused by mutations in the MMACHC gene, presents with many systemic symptoms, including neurological, cognitive, psychiatric, and thromboembolic events. Retinal phenotypes, including maculopathy, pigmentary retinopathy, and optic atrophy are common in early onset form of the disease but are rare in adult onset forms. MATERIALS AND METHODS: An adult Hispanic female presented with decreased central vision, bilateral pericentral ring scotomas and bull's eye-appearing macular lesions at 28 years of age. Her medical history was otherwise unremarkable except for iron deficiency anemia and both urinary tract and kidney infections. Screening of the ABCA4 gene, mutations in which frequently cause bull's eye maculopathy, was negative. Subsequently, analysis with whole exome sequencing was performed. RESULTS: Whole exome sequencing discovered compound heterozygous mutations in MMACHC, c.G482A:p.Arg161Gln and c.270_271insA:p.Arg91Lysfs*14, which segregated with the disease in the family. The genetic diagnosis was confirmed by biochemical laboratory testing, showing highly elevated urine methylmalonic acid/creatinine and homocysteine levels, and suggesting disease management with hydroxycobalamin injections and carnitine supplementation. CONCLUSIONS: In summary, a unique case of an adult patient with bull's eye macular lesions and no clinically relevant systemic symptoms was diagnosed with cblC by genetic screening and follow-up biochemical laboratory tests.
Keywords: Adult; Carrier Proteins; Electroretinography; Exome; Female; Genetic Testing; Heterozygote; Homocystinuria; Humans; Macular Degeneration; Mutation; Oxidoreductases; Pedigree; Scotoma; Sequence Analysis, DNA; Tomography, Optical Coherence; Visual Acuity; Visual Fields; Vitamin B 12; Vitamin B 12 Deficiency; Vitamin B Complex

Whole-exome sequencing identifies homozygous GPR161 mutation in a family with pituitary stalk interruption syndrome. - Karaca, Ender; Buyukkaya, Ramazan; Pehlivan, Davut; Charng, Wu-Lin; Yaykasli, Kursat O; Bayram, Yavuz; Gambin, Tomasz; Withers, Marjorie; Atik, Mehmed M; Arslanoglu, Ilknur; Bolu, Semih; Erdin, Serkan; et al. (J Clin Endocrinol Metab, 2015)
CONTEXT: Pituitary stalk interruption syndrome (PSIS) is a rare, congenital anomaly of the pituitary gland characterized by pituitary gland insufficiency, thin or discontinuous pituitary stalk, anterior pituitary hypoplasia, and ectopic positioning of the posterior pituitary gland (neurohypophysis). The clinical presentation of patients with PSIS varies from isolated growth hormone (GH) deficiency to combined pituitary insufficiency and accompanying extrapituitary findings. Mutations in HESX1, LHX4, OTX2, SOX3, and PROKR2 have been associated with PSIS in less than 5% of cases; thus, the underlying genetic etiology for the vast majority of cases remains to be determined. OBJECTIVE: We applied whole-exome sequencing (WES) to a consanguineous family with two affected siblings who have pituitary gland insufficiency and radiographic findings of hypoplastic (thin) pituitary gland, empty sella, ectopic neurohypophysis, and interrupted pitiutary stalk-characteristic clinical diagnostic findings of PSIS. DESIGN AND PARTICIPANTS: WES was applied to two affected and one unaffected siblings. RESULTS: WES of two affected and one unaffected sibling revealed a unique homozygous missense mutation in GPR161, which encodes the orphan G protein-coupled receptor 161, a protein responsible for transducing extracellular signals across the plasma membrane into the cell. CONCLUSION: Mutations of GPR161 may be implicated as a potential novel cause of PSIS.
Keywords: Adolescent; Child, Preschool; Exome; Female; Genome-Wide Association Study; Humans; Hypopituitarism; Mutation; Pituitary Gland; Receptors, G-Protein-Coupled

Whole-exome sequencing points to considerable genetic heterogeneity of cerebral palsy. - McMichael, G; Bainbridge, M N; Haan, E; Corbett, M; Gardner, A; Thompson, S; van Bon, B W M; van Eyk, C L; Broadbent, J; Reynolds, C; O'Callaghan, M E; Nguyen, L S; et al. (Mol Psychiatry, 2015)
Cerebral palsy (CP) is a common, clinically heterogeneous group of disorders affecting movement and posture. Its prevalence has changed little in 50 years and the causes remain largely unknown. The genetic contribution to CP causation has been predicted to be ~2%. We performed whole-exome sequencing of 183 cases with CP including both parents (98 cases) or one parent (67 cases) and 18 singleton cases (no parental DNA). We identified and validated 61 de novo protein-altering variants in 43 out of 98 (44%) case-parent trios. Initial prioritization of variants for causality was by mutation type, whether they were known or predicted to be deleterious and whether they occurred in known disease genes whose clinical spectrum overlaps CP. Further, prioritization used two multidimensional frameworks-the Residual Variation Intolerance Score and the Combined Annotation-dependent Depletion score. Ten de novo mutations in three previously identified disease genes (TUBA1A (n=2), SCN8A (n=1) and KDM5C (n=1)) and in six novel candidate CP genes (AGAP1, JHDM1D, MAST1, NAA35, RFX2 and WIPI2) were predicted to be potentially pathogenic for CP. In addition, we identified four predicted pathogenic, hemizygous variants on chromosome X in two known disease genes, L1CAM and PAK3, and in two novel candidate CP genes, CD99L2 and TENM1. In total, 14% of CP cases, by strict criteria, had a potentially disease-causing gene variant. Half were in novel genes. The genetic heterogeneity highlights the complexity of the genetic contribution to CP. Function and pathway studies are required to establish the causative role of these putative pathogenic CP genes.
Keywords: Adult; Animals; Cerebral Palsy; Cohort Studies; Exome; Female; Gene Library; Genetic Heterogeneity; Genetic Predisposition to Disease; Gestational Age; Humans; Male; Mutation; Parents; Sequence Analysis, DNA

Association of levels of fasting glucose and insulin with rare variants at the chromosome 11p11.2-MADD locus: Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium Targeted Sequencing Study. - Cornes, Belinda K; Brody, Jennifer A; Nikpoor, Naghmeh; Morrison, Alanna C; Chu, Huan; Ahn, Byung Soo; Wang, Shuai; Dauriz, Marco; Barzilay, Joshua I; Dupuis, Josée; Florez, Jose C; Coresh, Josef; et al. (Circ Cardiovasc Genet, 2014)
BACKGROUND: Common variation at the 11p11.2 locus, encompassing MADD, ACP2, NR1H3, MYBPC3, and SPI1, has been associated in genome-wide association studies with fasting glucose and insulin (FI). In the Cohorts for Heart and Aging Research in Genomic Epidemiology Targeted Sequencing Study, we sequenced 5 gene regions at 11p11.2 to identify rare, potentially functional variants influencing fasting glucose or FI levels. METHODS AND RESULTS: Sequencing (mean depth, 38×) across 16.1 kb in 3566 individuals without diabetes mellitus identified 653 variants, 79.9% of which were rare (minor allele frequency <1%) and novel. We analyzed rare variants in 5 gene regions with FI or fasting glucose using the sequence kernel association test. At NR1H3, 53 rare variants were jointly associated with FI (P=2.73×10(-3)); of these, 7 were predicted to have regulatory function and showed association with FI (P=1.28×10(-3)). Conditioning on 2 previously associated variants at MADD (rs7944584, rs10838687) did not attenuate this association, suggesting that there are >2 independent signals at 11p11.2. One predicted regulatory variant, chr11:47227430 (hg18; minor allele frequency=0.00068), contributed 20.6% to the overall sequence kernel association test score at NR1H3, lies in intron 2 of NR1H3, and is a predicted binding site for forkhead box A1 (FOXA1), a transcription factor associated with insulin regulation. In human HepG2 hepatoma cells, the rare chr11:47227430 A allele disrupted FOXA1 binding and reduced FOXA1-dependent transcriptional activity. CONCLUSIONS: Sequencing at 11p11.2-NR1H3 identified rare variation associated with FI. One variant, chr11:47227430, seems to be functional, with the rare A allele reducing transcription factor FOXA1 binding and FOXA1-dependent transcriptional activity.
Keywords: Aged; Aged, 80 and over; Aging; Blood Glucose; Chromosomes, Human, Pair 11; Cohort Studies; Death Domain Receptor Signaling Adaptor Proteins; Diabetes Mellitus, Type 2; Fasting; Female; Gene Frequency; Genetic Variation; Genome-Wide Association Study; Genomics; Guanine Nucleotide Exchange Factors; Heart Diseases; Humans; Insulin; Male; Middle Aged; Polymorphism, Single Nucleotide; Sequence Analysis, DNA

Associations of NINJ2 sequence variants with incident ischemic stroke in the Cohorts for Heart and Aging in Genomic Epidemiology (CHARGE) consortium. - Bis, Joshua C; DeStefano, Anita; Liu, Xiaoming; Brody, Jennifer A; Choi, Seung Hoan; Verhaaren, Benjamin F J; Debette, Stephanie; Ikram, M Arfan; Shahar, Eyal; Butler, Kenneth R; Gottesman, Rebecca F; Donna M Muzny; et al. (PLoS One, 2014)
BACKGROUND: Stroke, the leading neurologic cause of death and disability, has a substantial genetic component. We previously conducted a genome-wide association study (GWAS) in four prospective studies from the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium and demonstrated that sequence variants near the NINJ2 gene are associated with incident ischemic stroke. Here, we sought to fine-map functional variants in the region and evaluate the contribution of rare variants to ischemic stroke risk. METHODS AND RESULTS: We sequenced 196 kb around NINJ2 on chromosome 12p13 among 3,986 European ancestry participants, including 475 ischemic stroke cases, from the Atherosclerosis Risk in Communities Study, Cardiovascular Health Study, and Framingham Heart Study. Meta-analyses of single-variant tests for 425 common variants (minor allele frequency [MAF] ≥ 1%) confirmed the original GWAS results and identified an independent intronic variant, rs34166160 (MAF = 0.012), most significantly associated with incident ischemic stroke (HR = 1.80, p = 0.0003). Aggregating 278 putatively-functional variants with MAF≤ 1% using count statistics, we observed a nominally statistically significant association, with the burden of rare NINJ2 variants contributing to decreased ischemic stroke incidence (HR = 0.81; p = 0.026). CONCLUSION: Common and rare variants in the NINJ2 region were nominally associated with incident ischemic stroke among a subset of CHARGE participants. Allelic heterogeneity at this locus, caused by multiple rare, low frequency, and common variants with disparate effects on risk, may explain the difficulties in replicating the original GWAS results. Additional studies that take into account the complex allelic architecture at this locus are needed to confirm these findings.
Keywords: Cell Adhesion Molecules, Neuronal; Female; Genetic Association Studies; Genetic Heterogeneity; Humans; Introns; Ischemia; Male; Myocardial Infarction; Polymorphism, Single Nucleotide; Prospective Studies; Sequence Analysis, DNA; White People

Comparative validation of the D. melanogaster modENCODE transcriptome annotation. - Chen, Zhen-Xia; Sturgill, David; Qu, Jiaxin; Jiang, Huaiyang; Park, Soo; Boley, Nathan; Suzuki, Ana Maria; Fletcher, Anthony R; Plachetzki, David C; FitzGerald, Peter C; Artieri, Carlo G; Atallah, Joel; et al. (Genome Res, 2014)
Accurate gene model annotation of reference genomes is critical for making them useful. The modENCODE project has improved the D. melanogaster genome annotation by using deep and diverse high-throughput data. Since transcriptional activity that has been evolutionarily conserved is likely to have an advantageous function, we have performed large-scale interspecific comparisons to increase confidence in predicted annotations. To support comparative genomics, we filled in divergence gaps in the Drosophila phylogeny by generating draft genomes for eight new species. For comparative transcriptome analysis, we generated mRNA expression profiles on 81 samples from multiple tissues and developmental stages of 15 Drosophila species, and we performed cap analysis of gene expression in D. melanogaster and D. pseudoobscura. We also describe conservation of four distinct core promoter structures composed of combinations of elements at three positions. Overall, each type of genomic feature shows a characteristic divergence rate relative to neutral models, highlighting the value of multispecies alignment in annotating a target genome that should prove useful in the annotation of other high priority genomes, especially human and other mammalian genomes that are rich in noncoding sequences. We report that the vast majority of elements in the annotation are evolutionarily conserved, indicating that the annotation will be an important springboard for functional genetic testing by the Drosophila community.
Keywords: Animals; Cluster Analysis; Computational Biology; Drosophila melanogaster; Evolution, Molecular; Exons; Female; Gene Expression Profiling; Genome, Insect; Humans; Male; Molecular Sequence Annotation; Nucleotide Motifs; Phylogeny; Position-Specific Scoring Matrices; Promoter Regions, Genetic; Reproducibility of Results; RNA Editing; RNA Splice Sites; RNA Splicing; Transcription Initiation Site; Transcriptome

De novo truncating mutations in AHDC1 in individuals with syndromic expressive language delay, hypotonia, and sleep apnea. - Xia, Fan; Bainbridge, Matthew N; Tan, Tiong Yang; Wangler, Michael F; Scheuerle, Angela E; Zackai, Elaine H; Harr, Margaret H; Sutton, V Reid; Nalam, Roopa L; Zhu, Wenmiao; Nash, Margot; Ryan, Monique M; et al. (Am J Hum Genet, 2014)
Clinical whole-exome sequencing (WES) for identification of mutations leading to Mendelian disease has been offered to the medical community since 2011. Clinically undiagnosed neurological disorders are the most frequent basis for test referral, and currently, approximately 25% of such cases are diagnosed at the molecular level. To date, there are approximately 4,000 "known" disease-associated loci, and many are associated with striking dysmorphic features, making genotype-phenotype correlations relatively straightforward. A significant fraction of cases, however, lack characteristic dysmorphism or clinical pathognomonic traits and are dependent upon molecular tests for definitive diagnoses. Further, many molecular diagnoses are guided by recent gene-disease association discoveries. Hence, there is a critical interplay between clinical testing and research leading to gene-disease association discovery. Here, we describe four probands, all of whom presented with hypotonia, intellectual disability, global developmental delay, and mildly dysmorphic facial features. Three of the four also had sleep apnea. Each was a simplex case without a remarkable family history. Using WES, we identified AHDC1 de novo truncating mutations that most likely cause this genetic syndrome.
Keywords: Child; Child, Preschool; DNA-Binding Proteins; Exome; Female; Humans; Infant; Intellectual Disability; Language Development Disorders; Male; Muscle Hypotonia; Mutation; Sleep Apnea Syndromes; Syndrome

Draft genome sequences and description of Lactobacillus rhamnosus strains L31, L34, and L35. - Boonma, Prapaporn; Spinler, Jennifer K; Qin, Xiang; Jittaprasatsin, Chutima; Donna M Muzny; Harshavardhan Doddapaneni; Richard A Gibbs; Petrosino, Joe; Tumwasorn, Somying; Versalovic, James (Stand Genomic Sci, 2014)
Lactobacillus rhamnosus is a facultative, lactic acid bacterium in the phylum Firmicutes. Lactobacillus spp. are generally considered beneficial, and specific strains of L. rhamnosus are validated probiotics. We describe the draft genomes of three L. rhamnosus strains (L31, L34, and L35) isolated from the feces of Thai breastfed infants, which exhibit anti-inflammatory properties in vitro. The three genomes range between 2.8 - 2.9 Mb, and contain approximately 2,700 protein coding genes.

A drosophila genetic resource of mutants to study mechanisms underlying human genetic diseases. - Yamamoto, Shinya; Jaiswal, Manish; Charng, Wu-Lin; Gambin, Tomasz; Karaca, Ender; Mirzaa, Ghayda; Wiszniewski, Wojciech; Sandoval, Hector; Haelterman, Nele A; Xiong, Bo; Zhang, Ke; Bayat, Vafa; et al. (Cell, 2014)
Invertebrate model systems are powerful tools for studying human disease owing to their genetic tractability and ease of screening. We conducted a mosaic genetic screen of lethal mutations on the Drosophila X chromosome to identify genes required for the development, function, and maintenance of the nervous system. We identified 165 genes, most of whose function has not been studied in vivo. In parallel, we investigated rare variant alleles in 1,929 human exomes from families with unsolved Mendelian disease. Genes that are essential in flies and have multiple human homologs were found to be likely to be associated with human diseases. Merging the human data sets with the fly genes allowed us to identify disease-associated mutations in six families and to provide insights into microcephaly associated with brain dysgenesis. This bidirectional synergism between fly genetics and human genomics facilitates the functional annotation of evolutionarily conserved genes involved in human health.
Keywords: Animals; Disease; Disease Models, Animal; Drosophila melanogaster; Genetic Testing; Humans; Inheritance Patterns; RNA Interference; X Chromosome

Exonic duplication CNV of NDRG1 associated with autosomal-recessive HMSN-Lom/CMT4D. - Okamoto, Yuji; Goksungur, Meryem Tuba; Pehlivan, Davut; Beck, Christine R; Gonzaga-Jauregui, Claudia; Donna M Muzny; Atik, Mehmed M; Carvalho, Claudia M B; Matur, Zeliha; Bayraktar, Serife; Boone, Philip M; Akyuz, Kaya; et al. (Genet Med, 2014)
PURPOSE: Copy-number variations as a mutational mechanism contribute significantly to human disease. Approximately one-half of the patients with Charcot-Marie-Tooth (CMT) disease have a 1.4 Mb duplication copy-number variation as the cause of their neuropathy. However, non-CMT1A neuropathy patients rarely have causative copy-number variations, and to date, autosomal-recessive disease has not been associated with copy-number variation as a mutational mechanism. METHODS: We performed Agilent 8 × 60 K array comparative genomic hybridization on DNA from 12 recessive Turkish families with CMT disease. Additional molecular studies were conducted to detect breakpoint junctions and to evaluate gene expression levels in a family in which we detected an intragenic duplication copy-number variation. RESULTS: We detected an ~6.25 kb homozygous intragenic duplication in NDRG1, a gene known to be causative for recessive HMSNL/CMT4D, in three individuals from a Turkish family with CMT neuropathy. Further studies showed that this intragenic copy-number variation resulted in a homozygous duplication of exons 6-8 that caused decreased mRNA expression of NDRG1. CONCLUSION: Exon-focused high-resolution array comparative genomic hybridization enables the detection of copy-number variation carrier states in recessive genes, particularly small copy-number variations encompassing or disrupting single genes. In families for whom a molecular diagnosis has not been elucidated by conventional clinical assays, an assessment for copy-number variations in known CMT genes might be considered.
Keywords: Adult; Base Sequence; Cell Cycle Proteins; Charcot-Marie-Tooth Disease; Comparative Genomic Hybridization; DNA Copy Number Variations; Female; Gene Duplication; Gene Expression; Genes, Recessive; Humans; Intracellular Signaling Peptides and Proteins; Male; Mutation; Refsum Disease; Sequence Analysis, DNA; Turkey; Young Adult

Exonuclease mutations in DNA polymerase epsilon reveal replication strand specific mutation patterns and human origins of replication. - Shinbrot, Eve; Henninger, Erin E; Weinhold, Nils; Covington, Kyle R; Göksenin, A Yasemin; Schultz, Nikolaus; Chao, Hsu; Harshavardhan Doddapaneni; Donna M Muzny; Richard A Gibbs; Sander, Chris; Pursell, Zachary F; et al. (Genome Res, 2014)
Tumors with somatic mutations in the proofreading exonuclease domain of DNA polymerase epsilon (POLE-exo*) exhibit a novel mutator phenotype, with markedly elevated TCT→TAT and TCG→TTG mutations and overall mutation frequencies often exceeding 100 mutations/Mb. Here, we identify POLE-exo* tumors in numerous cancers and classify them into two groups, A and B, according to their mutational properties. Group A mutants are found only in POLE, whereas Group B mutants are found in POLE and POLD1 and appear to be nonfunctional. In Group A, cell-free polymerase assays confirm that mutations in the exonuclease domain result in high mutation frequencies with a preference for C→A mutation. We describe the patterns of amino acid substitutions caused by POLE-exo* and compare them to other tumor types. The nucleotide preference of POLE-exo* leads to increased frequencies of recurrent nonsense mutations in key tumor suppressors such as TP53, ATM, and PIK3R1. We further demonstrate that strand-specific mutation patterns arise from some of these POLE-exo* mutants during genome duplication. This is the first direct proof of leading strand-specific replication by human POLE, which has only been demonstrated in yeast so far. Taken together, the extremely high mutation frequency and strand specificity of mutations provide a unique identifier of eukaryotic origins of replication.
Keywords: Ataxia Telangiectasia Mutated Proteins; Class Ia Phosphatidylinositol 3-Kinase; Codon, Nonsense; Databases, Genetic; DNA Mutational Analysis; DNA Polymerase II; DNA Polymerase III; DNA Replication; Exonucleases; Genome-Wide Association Study; Humans; Microsatellite Instability; Models, Molecular; Mutation, Missense; Neoplasms; Phosphatidylinositol 3-Kinases; Protein Structure, Tertiary; Replication Origin; Tumor Suppressor Protein p53

The first myriapod genome sequence reveals conservative arthropod gene content and genome organisation in the centipede Strigamia maritima. - Chipman, Ariel D; Ferrier, David E K; Brena, Carlo; Qu, Jiaxin; Hughes, Daniel S T; Schröder, Reinhard; Torres-Oliva, Montserrat; Znassi, Nadia; Jiang, Huaiyang; Almeida, Francisca C; Alonso, Claudio R; Apostolou, Zivkos; et al. (PLoS Biol, 2014)
Myriapods (e.g., centipedes and millipedes) display a simple homonomous body plan relative to other arthropods. All members of the class are terrestrial, but they attained terrestriality independently of insects. Myriapoda is the only arthropod class not represented by a sequenced genome. We present an analysis of the genome of the centipede Strigamia maritima. It retains a compact genome that has undergone less gene loss and shuffling than previously sequenced arthropods, and many orthologues of genes conserved from the bilaterian ancestor that have been lost in insects. Our analysis locates many genes in conserved macro-synteny contexts, and many small-scale examples of gene clustering. We describe several examples where S. maritima shows different solutions from insects to similar problems. The insect olfactory receptor gene family is absent from S. maritima, and olfaction in air is likely effected by expansion of other receptor gene families. For some genes S. maritima has evolved paralogues to generate coding sequence diversity, where insects use alternate splicing. This is most striking for the Dscam gene, which in Drosophila generates more than 100,000 alternate splice forms, but in S. maritima is encoded by over 100 paralogues. We see an intriguing linkage between the absence of any known photosensory proteins in a blind organism and the additional absence of canonical circadian clock genes. The phylogenetic position of myriapods allows us to identify where in arthropod phylogeny several particular molecular mechanisms and traits emerged. For example, we conclude that juvenile hormone signalling evolved with the emergence of the exoskeleton in the arthropods and that RR-1 containing cuticle proteins evolved in the lineage leading to Mandibulata. We also identify when various gene expansions and losses occurred. The genome of S. maritima offers us a unique glimpse into the ancestral arthropod genome, while also displaying many adaptations to its specific life history.
Keywords: Animals; Arthropods; Circadian Rhythm Signaling Peptides and Proteins; DNA Methylation; Evolution, Molecular; Female; Genome; Genome, Mitochondrial; Hormones; Male; Multigene Family; Phylogeny; Polymorphism, Genetic; Protein Kinases; Receptors, Odorant; RNA, Untranslated; Selenoproteins; Sex Chromosomes; Synteny; Transcription Factors

Gibbon genome and the fast karyotype evolution of small apes. - Carbone, Lucia; R. Alan Harris; Gnerre, Sante; Veeramah, Krishna R; Lorente-Galdos, Belen; Huddleston, John; Meyer, Thomas J; Herrero, Javier; Roos, Christian; Aken, Bronwen; Anaclerio, Fabio; Archidiacono, Nicoletta; et al. (Nature, 2014)
Gibbons are small arboreal apes that display an accelerated rate of evolutionary chromosomal rearrangement and occupy a key node in the primate phylogeny between Old World monkeys and great apes. Here we present the assembly and analysis of a northern white-cheeked gibbon (Nomascus leucogenys) genome. We describe the propensity for a gibbon-specific retrotransposon (LAVA) to insert into chromosome segregation genes and alter transcription by providing a premature termination site, suggesting a possible molecular mechanism for the genome plasticity of the gibbon lineage. We further show that the gibbon genera (Nomascus, Hylobates, Hoolock and Symphalangus) experienced a near-instantaneous radiation ∼5 million years ago, coincident with major geographical changes in southeast Asia that caused cycles of habitat compression and expansion. Finally, we identify signatures of positive selection in genes important for forelimb development (TBX5) and connective tissues (COL1A1) that may have been involved in the adaptation of gibbons to their arboreal habitat.
Keywords: Animals; Evolution, Molecular; Genome; Hominidae; Humans; Hylobates; Karyotype; Molecular Sequence Data; Phylogeny; Retroelements; Selection, Genetic; Transcription Termination, Genetic

Heterozygous de novo and inherited mutations in the smooth muscle actin (ACTG2) gene underlie megacystis-microcolon-intestinal hypoperistalsis syndrome. - Wangler, Michael F; Gonzaga-Jauregui, Claudia; Gambin, Tomasz; Penney, Samantha; Moss, Timothy; Chopra, Atul; Probst, Frank J; Xia, Fan; Yang, Yaping; Werlin, Steven; Eglite, Ieva; Kornejeva, Liene; et al. (PLoS Genet, 2014)
Megacystis-microcolon-intestinal hypoperistalsis syndrome (MMIHS) is a rare disorder of enteric smooth muscle function affecting the intestine and bladder. Patients with this severe phenotype are dependent on total parenteral nutrition and urinary catheterization. The cause of this syndrome has remained a mystery since Berdon's initial description in 1976. No genes have been clearly linked to MMIHS. We used whole-exome sequencing for gene discovery followed by targeted Sanger sequencing in a cohort of patients with MMIHS and intestinal pseudo-obstruction. We identified heterozygous ACTG2 missense variants in 15 unrelated subjects, ten being apparent de novo mutations. Ten unique variants were detected, of which six affected CpG dinucleotides and resulted in missense mutations at arginine residues, perhaps related to biased usage of CpG containing codons within actin genes. We also found some of the same heterozygous mutations that we observed as apparent de novo mutations in MMIHS segregating in families with intestinal pseudo-obstruction, suggesting that ACTG2 is responsible for a spectrum of smooth muscle disease. ACTG2 encodes γ2 enteric actin and is the first gene to be clearly associated with MMIHS, suggesting an important role for contractile proteins in enteric smooth muscle disease.
Keywords: Abnormalities, Multiple; Actins; Adolescent; Adult; Child; Child, Preschool; Colon; Exome; Female; Heterozygote; Humans; Intestinal Pseudo-Obstruction; Male; Muscle, Smooth; Mutation; Urinary Bladder

Human CLP1 mutations alter tRNA biogenesis, affecting both peripheral and central nervous system function. - Karaca, Ender; Weitzer, Stefan; Pehlivan, Davut; Shiraishi, Hiroshi; Gogakos, Tasos; Hanada, Toshikatsu; Jhangiani, Shalini N; Wiszniewski, Wojciech; Withers, Marjorie; Campbell, Ian M; Erdin, Serkan; Isikay, Sedat; et al. (Cell, 2014)
CLP1 is a RNA kinase involved in tRNA splicing. Recently, CLP1 kinase-dead mice were shown to display a neuromuscular disorder with loss of motor neurons and muscle paralysis. Human genome analyses now identified a CLP1 homozygous missense mutation (p.R140H) in five unrelated families, leading to a loss of CLP1 interaction with the tRNA splicing endonuclease (TSEN) complex, largely reduced pre-tRNA cleavage activity, and accumulation of linear tRNA introns. The affected individuals develop severe motor-sensory defects, cortical dysgenesis, and microcephaly. Mice carrying kinase-dead CLP1 also displayed microcephaly and reduced cortical brain volume due to the enhanced cell death of neuronal progenitors that is associated with reduced numbers of cortical neurons. Our data elucidate a neurological syndrome defined by CLP1 mutations that impair tRNA splicing. Reduction of a founder mutation to homozygosity illustrates the importance of rare variations in disease and supports the clan genomics hypothesis.
Keywords: Abnormalities, Multiple; Animals; Central Nervous System Diseases; Cerebrum; Child, Preschool; Endoribonucleases; Female; Fibroblasts; Humans; Infant; Male; Mice; Mice, Inbred CBA; Microcephaly; Mutation, Missense; Nuclear Proteins; Peripheral Nervous System Diseases; Phosphotransferases; RNA, Transfer; RNA-Binding Proteins; Transcription Factors

Launching genomics into the cloud: deployment of Mercury, a next generation sequence analysis pipeline. - Reid, Jeffrey G; Carroll, Andrew; Veeraraghavan, Narayanan; Dahdouli, Mahmoud; Sundquist, Andreas; English, Adam; Bainbridge, Matthew; White, Simon; Salerno, William; Buhay, Christian; Fuli Yu; Donna M Muzny; et al. (BMC Bioinformatics, 2014)
BACKGROUND: Massively parallel DNA sequencing generates staggering amounts of data. Decreasing cost, increasing throughput, and improved annotation have expanded the diversity of genomics applications in research and clinical practice. This expanding scale creates analytical challenges: accommodating peak compute demand, coordinating secure access for multiple analysts, and sharing validated tools and results. RESULTS: To address these challenges, we have developed the Mercury analysis pipeline and deployed it in local hardware and the Amazon Web Services cloud via the DNAnexus platform. Mercury is an automated, flexible, and extensible analysis workflow that provides accurate and reproducible genomic results at scales ranging from individuals to large cohorts. CONCLUSIONS: By taking advantage of cloud computing and with Mercury implemented on the DNAnexus platform, we have demonstrated a powerful combination of a robust and fully validated software pipeline and a scalable computational resource that, to date, we have applied to more than 10,000 whole genome and whole exome samples.
Keywords: Genome; Genomics; High-Throughput Nucleotide Sequencing; Humans; Internet; Software

Mammalian Y chromosomes retain widely expressed dosage-sensitive regulators. - Bellott, Daniel W; Hughes, Jennifer F; Skaletsky, Helen; Brown, Laura G; Pyntikova, Tatyana; Cho, Ting-Jan; Koutseva, Natalia; Zaghlul, Sara; Graves, Tina; Rock, Susie; Kremitzki, Colin; Fulton, Robert S; et al. (Nature, 2014)
The human X and Y chromosomes evolved from an ordinary pair of autosomes, but millions of years ago genetic decay ravaged the Y chromosome, and only three per cent of its ancestral genes survived. We reconstructed the evolution of the Y chromosome across eight mammals to identify biases in gene content and the selective pressures that preserved the surviving ancestral genes. Our findings indicate that survival was nonrandom, and in two cases, convergent across placental and marsupial mammals. We conclude that the gene content of the Y chromosome became specialized through selection to maintain the ancestral dosage of homologous X-Y gene pairs that function as broadly expressed regulators of transcription, translation and protein stability. We propose that beyond its roles in testis determination and spermatogenesis, the Y chromosome is essential for male viability, and has unappreciated roles in Turner's syndrome and in phenotypic differences between the sexes in health and disease.
Keywords: Animals; Chromosomes, Human, X; Chromosomes, Human, Y; Disease; Evolution, Molecular; Female; Gene Dosage; Gene Expression Regulation; Health; Humans; Male; Mammals; Marsupialia; Molecular Sequence Annotation; Molecular Sequence Data; Protein Biosynthesis; Protein Stability; Selection, Genetic; Sequence Homology; Sex Characteristics; Spermatogenesis; Testis; Transcription, Genetic; Turner Syndrome; X Chromosome; Y Chromosome

Molecular findings among patients referred for clinical whole-exome sequencing. - Yang, Yaping; Donna M Muzny; Xia, Fan; Niu, Zhiyv; Person, Richard; Ding, Yan; Ward, Patricia; Braxton, Alicia; Wang, Min; Buhay, Christian; Veeraraghavan, Narayanan; Hawes, Alicia; et al. (JAMA, 2014)
IMPORTANCE: Clinical whole-exome sequencing is increasingly used for diagnostic evaluation of patients with suspected genetic disorders. OBJECTIVE: To perform clinical whole-exome sequencing and report (1) the rate of molecular diagnosis among phenotypic groups, (2) the spectrum of genetic alterations contributing to disease, and (3) the prevalence of medically actionable incidental findings such as FBN1 mutations causing Marfan syndrome. DESIGN, SETTING, AND PATIENTS: Observational study of 2000 consecutive patients with clinical whole-exome sequencing analyzed between June 2012 and August 2014. Whole-exome sequencing tests were performed at a clinical genetics laboratory in the United States. Results were reported by clinical molecular geneticists certified by the American Board of Medical Genetics and Genomics. Tests were ordered by the patient's physician. The patients were primarily pediatric (1756 [88%]; mean age, 6 years; 888 females [44%], 1101 males [55%], and 11 fetuses [1% gender unknown]), demonstrating diverse clinical manifestations most often including nervous system dysfunction such as developmental delay. MAIN OUTCOMES AND MEASURES: Whole-exome sequencing diagnosis rate overall and by phenotypic category, mode of inheritance, spectrum of genetic events, and reporting of incidental findings. RESULTS: A molecular diagnosis was reported for 504 patients (25.2%) with 58% of the diagnostic mutations not previously reported. Molecular diagnosis rates for each phenotypic category were 143/526 (27.2%; 95% CI, 23.5%-31.2%) for the neurological group, 282/1147 (24.6%; 95% CI, 22.1%-27.2%) for the neurological plus other organ systems group, 30/83 (36.1%; 95% CI, 26.1%-47.5%) for the specific neurological group, and 49/244 (20.1%; 95% CI, 15.6%-25.8%) for the nonneurological group. The Mendelian disease patterns of the 527 molecular diagnoses included 280 (53.1%) autosomal dominant, 181 (34.3%) autosomal recessive (including 5 with uniparental disomy), 65 (12.3%) X-linked, and 1 (0.2%) mitochondrial. Of 504 patients with a molecular diagnosis, 23 (4.6%) had blended phenotypes resulting from 2 single gene defects. About 30% of the positive cases harbored mutations in disease genes reported since 2011. There were 95 medically actionable incidental findings in genes unrelated to the phenotype but with immediate implications for management in 92 patients (4.6%), including 59 patients (3%) with mutations in genes recommended for reporting by the American College of Medical Genetics and Genomics. CONCLUSIONS AND RELEVANCE: Whole-exome sequencing provided a potential molecular diagnosis for 25% of a large cohort of patients referred for evaluation of suspected genetic conditions, including detection of rare genetic events and new mutations contributing to disease. The yield of whole-exome sequencing may offer advantages over traditional molecular diagnostic approaches in certain patients.
Keywords: Adolescent; Adult; Child; Child, Preschool; Exome; Female; Fetus; Genetic Diseases, Inborn; Genetic Testing; Genomics; Humans; Incidental Findings; Infant; Infant, Newborn; Male; Molecular Diagnostic Techniques; Mutation; Phenotype; Referral and Consultation; Sequence Analysis, DNA

Monoallelic and biallelic mutations in MAB21L2 cause a spectrum of major eye malformations. - Rainger, Joe; Pehlivan, Davut; Johansson, Stefan; Bengani, Hemant; Sanchez-Pulido, Luis; Williamson, Kathleen A; Ture, Mehmet; Barker, Heather; Rosendahl, Karen; Spranger, Jürgen; Horn, Denise; Meynert, Alison; et al. (Am J Hum Genet, 2014)
We identified four different missense mutations in the single-exon gene MAB21L2 in eight individuals with bilateral eye malformations from five unrelated families via three independent exome sequencing projects. Three mutational events altered the same amino acid (Arg51), and two were identical de novo mutations (c.151C>T [p.Arg51Cys]) in unrelated children with bilateral anophthalmia, intellectual disability, and rhizomelic skeletal dysplasia. c.152G>A (p.Arg51His) segregated with autosomal-dominant bilateral colobomatous microphthalmia in a large multiplex family. The fourth heterozygous mutation (c.145G>A [p.Glu49Lys]) affected an amino acid within two residues of Arg51 in an adult male with bilateral colobomata. In a fifth family, a homozygous mutation (c.740G>A [p.Arg247Gln]) altering a different region of the protein was identified in two male siblings with bilateral retinal colobomata. In mouse embryos, Mab21l2 showed strong expression in the developing eye, pharyngeal arches, and limb bud. As predicted by structural homology, wild-type MAB21L2 bound single-stranded RNA, whereas this activity was lost in all altered forms of the protein. MAB21L2 had no detectable nucleotidyltransferase activity in vitro, and its function remains unknown. Induced expression of wild-type MAB21L2 in human embryonic kidney 293 cells increased phospho-ERK (pERK1/2) signaling. Compared to the wild-type and p.Arg247Gln proteins, the proteins with the Glu49 and Arg51 variants had increased stability. Abnormal persistence of pERK1/2 signaling in MAB21L2-expressing cells during development is a plausible pathogenic mechanism for the heterozygous mutations. The phenotype associated with the homozygous mutation might be a consequence of complete loss of MAB21L2 RNA binding, although the cellular function of this interaction remains unknown.
Keywords: Adult; Alleles; Animals; Anophthalmos; Brain Diseases, Metabolic, Inborn; Coloboma; Corneal Opacity; Exome; Eye Proteins; Female; Gene Expression; HEK293 Cells; Heterozygote; Homozygote; Humans; Intellectual Disability; Intracellular Signaling Peptides and Proteins; Male; Mice; Microcephaly; Microphthalmos; Mutation, Missense; Pedigree; Phenotype; Protein Conformation; Signal Transduction

Mutational landscape of aggressive cutaneous squamous cell carcinoma. - Pickering, Curtis R; Zhou, Jane H; Lee, J Jack; Drummond, Jennifer A; Peng, S Andrew; Saade, Rami E; Tsai, Kenneth Y; Curry, Jonathan L; Tetzlaff, Michael T; Lai, Stephen Y; Yu, Jun; Donna M Muzny; et al. (Clin Cancer Res, 2014)
PURPOSE: Aggressive cutaneous squamous cell carcinoma (cSCC) is often a disfiguring and lethal disease. Very little is currently known about the mutations that drive aggressive cSCC. EXPERIMENTAL DESIGN: Whole-exome sequencing was performed on 39 cases of aggressive cSCC to identify driver genes and novel therapeutic targets. Significantly, mutated genes were identified with MutSig or complementary methods developed to specifically identify candidate tumor suppressors based upon their inactivating mutation bias. RESULTS: Despite the very high-mutational background caused by UV exposure, 23 candidate drivers were identified, including the well-known cancer-associated genes TP53, CDKN2A, NOTCH1, AJUBA, HRAS, CASP8, FAT1, and KMT2C (MLL3). Three novel candidate tumor suppressors with putative links to cancer or differentiation, NOTCH2, PARD3, and RASA1, were also identified as possible drivers in cSCC. KMT2C mutations were associated with poor outcome and increased bone invasion. CONCLUSIONS: The mutational spectrum of cSCC is similar to that of head and neck squamous cell carcinoma and dominated by tumor-suppressor genes. These results improve the foundation for understanding this disease and should aid in identifying and treating aggressive cSCC.
Keywords: Carcinoma, Squamous Cell; Cluster Analysis; Computational Biology; Disease Progression; DNA Copy Number Variations; Exome; Genomics; High-Throughput Nucleotide Sequencing; Humans; Mutation; Prognosis; Skin Neoplasms

Mutations in PURA cause profound neonatal hypotonia, seizures, and encephalopathy in 5q31.3 microdeletion syndrome. - Lalani, Seema R; Zhang, Jing; Schaaf, Christian P; Brown, Chester W; Magoulas, Pilar; Tsai, Anne Chun-Hui; El-Gharbawy, Areeg; Wierenga, Klaas J; Bartholomew, Dennis; Fong, Chin-To; Barbaro-Dieber, Tina; Kukolich, Mary K; et al. (Am J Hum Genet, 2014)
5q31.3 microdeletion syndrome is characterized by neonatal hypotonia, encephalopathy with or without epilepsy, and severe developmental delay, and the minimal critical deletion interval harbors three genes. We describe 11 individuals with clinical features of 5q31.3 microdeletion syndrome and de novo mutations in PURA, encoding transcriptional activator protein Pur-α, within the critical region. These data implicate causative PURA mutations responsible for the severe neurological phenotypes observed in this syndrome.
Keywords: Abnormalities, Multiple; Amino Acid Sequence; Animals; Base Sequence; Caenorhabditis elegans; Chromosome Deletion; Chromosome Mapping; Chromosomes, Human, Pair 5; DNA-Binding Proteins; Humans; Molecular Sequence Data; Muscle Hypotonia; Mutation; Seizures; Sequence Analysis, DNA; Syndrome; Transcription Factors

Mutually exclusive recurrent somatic mutations in MAP2K1 and BRAF support a central role for ERK activation in LCH pathogenesis. - Chakraborty, Rikhia; Hampton, Oliver A; Shen, Xiaoyun; Simko, Stephen J; Shih, Albert; Abhyankar, Harshal; Lim, Karen Phaik Har; Covington, Kyle R; Treviño, Lisa; Dewal, Ninad; Donna M Muzny; Harshavardhan Doddapaneni; et al. (Blood, 2014)
Langerhans cell histiocytosis (LCH) is a myeloproliferative disorder characterized by lesions composed of pathological CD207(+) dendritic cells with an inflammatory infiltrate. BRAFV600E remains the only recurrent mutation reported in LCH. In order to evaluate the spectrum of somatic mutations in LCH, whole exome sequencing was performed on matched LCH and normal tissue samples obtained from 41 patients. Lesions from other histiocytic disorders, juvenile xanthogranuloma, Erdheim-Chester disease, and Rosai-Dorfman disease were also evaluated. All of the lesions from histiocytic disorders were characterized by an extremely low overall rate of somatic mutations. Notably, 33% (7/21) of LCH cases with wild-type BRAF and none (0/20) with BRAFV600E harbored somatic mutations in MAP2K1 (6 in-frame deletions and 1 missense mutation) that induced extracellular signal-regulated kinase (ERK) phosphorylation in vitro. Single cases of somatic mutations of the mitogen-activated protein kinase (MAPK) pathway genes ARAF and ERBB3 were also detected. The ability of MAPK pathway inhibitors to suppress MAPK kinase and ERK phosphorylation in cell culture and primary tumor models was dependent on the specific LCH mutation. The findings of this study support a model in which ERK activation is a universal end point in LCH arising from pathological activation of upstream signaling proteins.
Keywords: Dendritic Cells; Disease Progression; Erdheim-Chester Disease; HEK293 Cells; Histiocytosis, Langerhans-Cell; Histiocytosis, Sinus; Humans; MAP Kinase Kinase 1; MAP Kinase Signaling System; Mutation, Missense; Proto-Oncogene Proteins B-raf; Xanthogranuloma, Juvenile

Natural variation in genome architecture among 205 Drosophila melanogaster Genetic Reference Panel lines. - Huang, Wen; Massouras, Andreas; Inoue, Yutaka; Peiffer, Jason; Ràmia, Miquel; Tarone, Aaron M; Turlapati, Lavanya; Zichner, Thomas; Zhu, Dianhui; Lyman, Richard F; Magwire, Michael M; Blankenburg, Kerstin; et al. (Genome Res, 2014)
The Drosophila melanogaster Genetic Reference Panel (DGRP) is a community resource of 205 sequenced inbred lines, derived to improve our understanding of the effects of naturally occurring genetic variation on molecular and organismal phenotypes. We used an integrated genotyping strategy to identify 4,853,802 single nucleotide polymorphisms (SNPs) and 1,296,080 non-SNP variants. Our molecular population genomic analyses show higher deletion than insertion mutation rates and stronger purifying selection on deletions. Weaker selection on insertions than deletions is consistent with our observed distribution of genome size determined by flow cytometry, which is skewed toward larger genomes. Insertion/deletion and single nucleotide polymorphisms are positively correlated with each other and with local recombination, suggesting that their nonrandom distributions are due to hitchhiking and background selection. Our cytogenetic analysis identified 16 polymorphic inversions in the DGRP. Common inverted and standard karyotypes are genetically divergent and account for most of the variation in relatedness among the DGRP lines. Intriguingly, variation in genome size and many quantitative traits are significantly associated with inversions. Approximately 50% of the DGRP lines are infected with Wolbachia, and four lines have germline insertions of Wolbachia sequences, but effects of Wolbachia infection on quantitative traits are rarely significant. The DGRP complements ongoing efforts to functionally annotate the Drosophila genome. Indeed, 15% of all D. melanogaster genes segregate for potentially damaged proteins in the DGRP, and genome-wide analyses of quantitative traits identify novel candidate genes. The DGRP lines, sequence data, genotypes, quality scores, phenotypes, and analysis and visualization tools are publicly available.
Keywords: Animals; Chromatin; Drosophila melanogaster; Female; Genetic Linkage; Genetic Variation; Genome Size; Genome, Insect; Genome-Wide Association Study; Genotype; Genotyping Techniques; High-Throughput Nucleotide Sequencing; INDEL Mutation; Linkage Disequilibrium; Male; Molecular Sequence Annotation; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait, Heritable; Reproducibility of Results

New syndrome with retinitis pigmentosa is caused by nonsense mutations in retinol dehydrogenase RDH11. - Xie, Yajing Angela; Lee, Winston; Cai, Carolyn; Gambin, Tomasz; Nõupuu, Kalev; Sujirakul, Tharikarn; Ayuso, Carmen; Jhangiani, Shalini; Donna M Muzny; Eric Boerwinkle; Richard A Gibbs; Greenstein, Vivienne C; et al. (Hum Mol Genet, 2014)
Retinitis pigmentosa (RP), a genetically heterogeneous group of retinopathies that occur in both non-syndromic and syndromic forms, is caused by mutations in ∼100 genes. Although recent advances in next-generation sequencing have aided in the discovery of novel RP genes, a number of the underlying contributing genes and loci remain to be identified. We investigated three siblings, born to asymptomatic parents of Italian-American descent, who each presented with atypical RP with systemic features, including facial dysmorphologies, psychomotor developmental delays recognized since early childhood, learning disabilities and short stature. RP-associated ophthalmological findings included salt-and-pepper retinopathy, attenuation of the arterioles and generalized rod-cone dysfunction as determined by almost extinguished electroretinogram in 2 of 3 siblings. Atypical for RP features included mottled macula at an early age and peripapillary sparing of the retinal pigment epithelium. Whole-exome sequencing data, queried under a recessive model of inheritance, identified compound heterozygous stop mutations, c.C199T:p.R67* and c.C322T:p.R108*, in the retinol dehydrogenase 11 (RDH11) gene, resulting in a non-functional protein, in all affected children. In summary, deleterious mutations in RDH11, an important enzyme for vision-related and systemic retinoic acid metabolism, cause a new syndrome with RP.
Keywords: Adolescent; Child; Codon, Nonsense; Female; Humans; Male; Oxidoreductases; Pedigree; Phenotype; Retinitis Pigmentosa; Syndrome; Vision Tests; Visual Acuity; Young Adult

Next-generation sequencing identifies rare variants associated with Noonan syndrome. - Chen, Peng-Chieh; Yin, Jiani; Yu, Hui-Wen; Yuan, Tao; Fernandez, Minerva; Yung, Christina K; Trinh, Quang M; Peltekova, Vanya D; Reid, Jeffrey G; Tworog-Dube, Erica; Morgan, Margaret B; Donna M Muzny; et al. (Proc Natl Acad Sci U S A, 2014)
Noonan syndrome (NS) is a relatively common genetic disorder, characterized by typical facies, short stature, developmental delay, and cardiac abnormalities. Known causative genes account for 70-80% of clinically diagnosed NS patients, but the genetic basis for the remaining 20-30% of cases is unknown. We performed next-generation sequencing on germ-line DNA from 27 NS patients lacking a mutation in the known NS genes. We identified gain-of-function alleles in Ras-like without CAAX 1 (RIT1) and mitogen-activated protein kinase kinase 1 (MAP2K1) and previously unseen loss-of-function variants in RAS p21 protein activator 2 (RASA2) that are likely to cause NS in these patients. Expression of the mutant RASA2, MAP2K1, or RIT1 alleles in heterologous cells increased RAS-ERK pathway activation, supporting a causative role in NS pathogenesis. Two patients had more than one disease-associated variant. Moreover, the diagnosis of an individual initially thought to have NS was revised to neurofibromatosis type 1 based on an NF1 nonsense mutation detected in this patient. Another patient harbored a missense mutation in NF1 that resulted in decreased protein stability and impaired ability to suppress RAS-ERK activation; however, this patient continues to exhibit a NS-like phenotype. In addition, a nonsense mutation in RPS6KA3 was found in one patient initially diagnosed with NS whose diagnosis was later revised to Coffin-Lowry syndrome. Finally, we identified other potential candidates for new NS genes, as well as potential carrier alleles for unrelated syndromes. Taken together, our data suggest that next-generation sequencing can provide a useful adjunct to RASopathy diagnosis and emphasize that the standard clinical categories for RASopathies might not be adequate to describe all patients.
Keywords: Alleles; Genetic Association Studies; High-Throughput Nucleotide Sequencing; Humans; MAP Kinase Kinase 1; MAP Kinase Signaling System; Mutation; Neurofibromin 1; Noonan Syndrome; ras Proteins

Novel somatic and germline mutations in intracranial germ cell tumours. - Wang, Linghua; Yamaguchi, Shigeru; Burstein, Matthew D; Terashima, Keita; Chang, Kyle; Ng, Ho-Keung; Nakamura, Hideo; He, Zongxiao; Harshavardhan Doddapaneni; Lewis, Lora; Wang, Mark; Suzuki, Tomonari; et al. (Nature, 2014)
Intracranial germ cell tumours (IGCTs) are a group of rare heterogeneous brain tumours that are clinically and histologically similar to the more common gonadal GCTs. IGCTs show great variation in their geographical and gender distribution, histological composition and treatment outcomes. The incidence of IGCTs is historically five- to eightfold greater in Japan and other East Asian countries than in Western countries, with peak incidence near the time of puberty. About half of the tumours are located in the pineal region. The male-to-female incidence ratio is approximately 3-4:1 overall, but is even higher for tumours located in the pineal region. Owing to the scarcity of tumour specimens available for research, little is currently known about this rare disease. Here we report the analysis of 62 cases by next-generation sequencing, single nucleotide polymorphism array and expression array. We find the KIT/RAS signalling pathway frequently mutated in more than 50% of IGCTs, including novel recurrent somatic mutations in KIT, its downstream mediators KRAS and NRAS, and its negative regulator CBL. Novel somatic alterations in the AKT/mTOR pathway included copy number gains of the AKT1 locus at 14q32.33 in 19% of patients, with corresponding upregulation of AKT1 expression. We identified loss-of-function mutations in BCORL1, a transcriptional co-repressor and tumour suppressor. We report significant enrichment of novel and rare germline variants in JMJD1C, which codes for a histone demethylase and is a coactivator of the androgen receptor, among Japanese IGCT patients. This study establishes a molecular foundation for understanding the biology of IGCTs and suggests potentially promising therapeutic strategies focusing on the inhibition of KIT/RAS activation and the AKT1/mTOR pathway.
Keywords: Adult; Brain Neoplasms; Child; Female; Germ-Line Mutation; Humans; Japan; Male; Mutation; Neoplasms, Germ Cell and Embryonal; Oncogene Protein v-akt; Proto-Oncogene Proteins c-kit; ras Proteins; Reproducibility of Results; Signal Transduction; TOR Serine-Threonine Kinases; Young Adult

NR2F1 mutations cause optic atrophy with intellectual disability. - Bosch, Daniëlle G M; Boonstra, F Nienke; Gonzaga-Jauregui, Claudia; Xu, Mafei; de Ligt, Joep; Jhangiani, Shalini; Wiszniewski, Wojciech; Donna M Muzny; Yntema, Helger G; Pfundt, Rolph; Vissers, Lisenka E L M; Spruijt, Liesbeth; et al. (Am J Hum Genet, 2014)
Optic nerve atrophy and hypoplasia can be primary disorders or can result from trans-synaptic degeneration arising from cerebral visual impairment (CVI). Here we report six individuals with CVI and/or optic nerve abnormalities, born after an uneventful pregnancy and delivery, who have either de novo heterozygous missense mutations in NR2F1, also known as COUP-TFI, or deletions encompassing NR2F1. All affected individuals show mild to moderate intellectual impairment. NR2F1 encodes a nuclear receptor protein that regulates transcription. A reporter assay showed that missense mutations in the zinc-finger DNA-binding domain and the putative ligand-binding domain decrease NR2F1 transcriptional activity. These findings indicate that NR2F1 plays an important role in the neurodevelopment of the visual system and that its disruption can lead to optic atrophy with intellectual disability.
Keywords: Adolescent; Adult; Amino Acid Sequence; Child; Child, Preschool; COUP Transcription Factor I; DNA-Binding Proteins; Female; Genotype; Humans; Intellectual Disability; Male; Molecular Sequence Data; Mutation, Missense; Optic Atrophy; Phenotype; Young Adult; Zinc Fingers

PGM3 mutations cause a congenital disorder of glycosylation with severe immunodeficiency and skeletal dysplasia. - Stray-Pedersen, Asbjørg; Backe, Paul H; Sorte, Hanne S; Mørkrid, Lars; Chokshi, Niti Y; Erichsen, Hans Christian; Gambin, Tomasz; Elgstøen, Katja B P; Bjørås, Magnar; Wlodarski, Marcin W; Krüger, Marcus; Jhangiani, Shalini N; et al. (Am J Hum Genet, 2014)
Human phosphoglucomutase 3 (PGM3) catalyzes the conversion of N-acetyl-glucosamine (GlcNAc)-6-phosphate into GlcNAc-1-phosphate during the synthesis of uridine diphosphate (UDP)-GlcNAc, a sugar nucleotide critical to multiple glycosylation pathways. We identified three unrelated children with recurrent infections, congenital leukopenia including neutropenia, B and T cell lymphopenia, and progression to bone marrow failure. Whole-exome sequencing demonstrated deleterious mutations in PGM3 in all three subjects, delineating their disease to be due to an unsuspected congenital disorder of glycosylation (CDG). Functional studies of the disease-associated PGM3 variants in E. coli cells demonstrated reduced PGM3 activity for all mutants tested. Two of the three children had skeletal anomalies resembling Desbuquois dysplasia: short stature, brachydactyly, dysmorphic facial features, and intellectual disability. However, these additional features were absent in the third child, showing the clinical variability of the disease. Two children received hematopoietic stem cell transplantation of cord blood and bone marrow from matched related donors; both had successful engraftment and correction of neutropenia and lymphopenia. We define PGM3-CDG as a treatable immunodeficiency, document the power of whole-exome sequencing in gene discoveries for rare disorders, and illustrate the utility of genomic analyses in studying combined and variable phenotypes.
Keywords: Bone Diseases, Developmental; Congenital Disorders of Glycosylation; Female; Humans; Immunologic Deficiency Syndromes; Male; Mutation; Pedigree; Phosphoglucomutase

Recurrent CNVs and SNVs at the NPHP1 locus contribute pathogenic alleles to Bardet-Biedl syndrome. - Lindstrand, Anna; Davis, Erica E; Carvalho, Claudia M B; Pehlivan, Davut; Willer, Jason R; Tsai, I-Chun; Ramanathan, Subhadra; Zuppan, Craig; Aniko Sabo; Donna M Muzny; Richard A Gibbs; Liu, Pengfei; et al. (Am J Hum Genet, 2014)
Homozygosity for a recurrent 290 kb deletion of NPHP1 is the most frequent cause of isolated nephronophthisis (NPHP) in humans. A deletion of the same genomic interval has also been detected in individuals with Joubert syndrome (JBTS), and in the mouse, Nphp1 interacts genetically with Ahi1, a known JBTS locus. Given these observations, we investigated the contribution of NPHP1 in Bardet-Biedl syndrome (BBS), a ciliopathy of intermediate severity. By using a combination of array-comparative genomic hybridization, TaqMan copy number assays, and sequencing, we studied 200 families affected by BBS. We report a homozygous NPHP1 deletion CNV in a family with classical BBS that is transmitted with autosomal-recessive inheritance. Further, we identified heterozygous NPHP1 deletions in two more unrelated persons with BBS who bear primary mutations at another BBS locus. In parallel, we identified five families harboring an SNV in NPHP1 resulting in a conserved missense change, c.14G>T (p.Arg5Leu), that is enriched in our Hispanic pedigrees; in each case, affected individuals carried additional bona fide pathogenic alleles in another BBS gene. In vivo functional modeling in zebrafish embryos demonstrated that c.14G>T is a loss-of-function variant, and suppression of nphp1 in concert with each of the primary BBS loci found in our NPHP1-positive pedigrees exacerbated the severity of the phenotype. These results suggest that NPHP1 mutations are probably rare primary causes of BBS that contribute to the mutational burden of the disorder.
Keywords: Adaptor Proteins, Signal Transducing; Alleles; Animals; Bardet-Biedl Syndrome; Cytoskeletal Proteins; DNA Copy Number Variations; Gastrulation; Genetic Loci; Heterozygote; Homozygote; Humans; Kidney; Membrane Proteins; Mice; Pedigree; Sequence Deletion; Zebrafish

The relationship of JAK2(V617F) and acquired UPD at chromosome 9p in polycythemia vera. - Wang, L; Swierczek, S I; Lanikova, L; Kim, S J; Hickman, K; Kimberly Walker; Wang, K; Drummond, J; Harshavardhan Doddapaneni; Reid, J G; Donna M Muzny; Richard A Gibbs; et al. (Leukemia, 2014)
Keywords: Chromosomes, Human, Pair 9; Genotype; Humans; Janus Kinase 2; Polycythemia Vera; Uniparental Disomy

Sequence analysis of six blood pressure candidate regions in 4,178 individuals: the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) targeted sequencing study. - Morrison, Alanna C; Bis, Joshua C; Hwang, Shih-Jen; Ehret, Georg B; Lumley, Thomas; Rice, Kenneth; Donna M Muzny; Richard A Gibbs; Eric Boerwinkle; Psaty, Bruce M; Chakravarti, Aravinda; Levy, Daniel (PLoS One, 2014)
BACKGROUND: Genome-wide association studies (GWAS) identified multiple loci for blood pressure (BP) and hypertension. Six genes--ATP2B1, CACNB2, CYP17A1, JAG1, PLEKHA7, and SH2B3--were evaluated for sequence variation with large effects on systolic blood pressure (SBP), diastolic blood pressure (DBP), pulse pressure (PP), and mean arterial pressure (MAP). METHODS AND RESULTS: Targeted genomic sequence was determined in 4,178 European ancestry participants from the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium. Common variants (≥50 minor allele copies) were evaluated individually and rare variants (minor allele frequency, MAF≤1%) were aggregated by locus. 464 common variants were identified across the 6 genes. An upstream CYP17A1 variant, rs11191416 (MAF = 0.09), was the most significant association for SBP (P = 0.0005); however the association was attenuated (P = 0.0469) after conditioning on the GWAS index single nucleotide polymorphism (SNP). A PLEKHA7 intronic variant was the strongest DBP association (rs12806040, MAF = 0.007, P = 0.0006) and was not in LD (r² = 0.01) with the GWAS SNP. A CACNB2 intronic SNP, rs1571787, was the most significant association with PP (MAF = 0.27, P = 0.0003), but was not independent from the GWAS SNP (r² = 0.34). Three variants (rs6163 and rs743572 in the CYP17A1 region and rs112467382 in PLEKHA7) were associated with BP traits (P<0.001). Rare variation, aggregately assessed in the 6 regions, was not significantly associated with BP measures. CONCLUSION: Six targeted gene regions, previously identified by GWAS, did not harbor novel variation with large effects on BP in this sample.
Keywords: Aging; Blood Pressure; Cohort Studies; Heart; Humans; Sequence Analysis

The sheep genome illuminates biology of the rumen and lipid metabolism. - Jiang, Yu; Xie, Min; Chen, Wenbin; Talbot, Richard; Maddox, Jillian F; Faraut, Thomas; Wu, Chunhua; Donna M Muzny; Li, Yuxiang; Zhang, Wenguang; Stanton, Jo-Ann; Brauning, Rudiger; et al. (Science, 2014)
Sheep (Ovis aries) are a major source of meat, milk, and fiber in the form of wool and represent a distinct class of animals that have a specialized digestive organ, the rumen, that carries out the initial digestion of plant material. We have developed and analyzed a high-quality reference sheep genome and transcriptomes from 40 different tissues. We identified highly expressed genes encoding keratin cross-linking proteins associated with rumen evolution. We also identified genes involved in lipid metabolism that had been amplified and/or had altered tissue expression patterns. This may be in response to changes in the barrier lipids of the skin, an interaction between lipid metabolism and wool synthesis, and an increased role of volatile fatty acids in ruminants compared with nonruminant animals.
Keywords: Amino Acid Sequence; Animals; Fatty Acids, Volatile; Gene Expression Regulation; Genome; Keratins, Hair-Specific; Lipid Metabolism; Molecular Sequence Data; Phylogeny; Rumen; Sheep, Domestic; Transcriptome; Wool

The somatic genomic landscape of chromophobe renal cell carcinoma. - Davis, Caleb F; Ricketts, Christopher J; Wang, Min; Yang, Lixing; Cherniack, Andrew D; Shen, Hui; Buhay, Christian; Kang, Hyojin; Kim, Sang Cheol; Fahey, Catherine C; Hacker, Kathryn E; Bhanot, Gyan; et al. (Cancer Cell, 2014)
We describe the landscape of somatic genomic alterations of 66 chromophobe renal cell carcinomas (ChRCCs) on the basis of multidimensional and comprehensive characterization, including mtDNA and whole-genome sequencing. The result is consistent that ChRCC originates from the distal nephron compared with other kidney cancers with more proximal origins. Combined mtDNA and gene expression analysis implicates changes in mitochondrial function as a component of the disease biology, while suggesting alternative roles for mtDNA mutations in cancers relying on oxidative phosphorylation. Genomic rearrangements lead to recurrent structural breakpoints within TERT promoter region, which correlates with highly elevated TERT expression and manifestation of kataegis, representing a mechanism of TERT upregulation in cancer distinct from previously observed amplifications and point mutations.
Keywords: Base Sequence; Carcinoma, Renal Cell; Chromosome Breakpoints; Chromosome Deletion; Chromosomes, Human; DNA Copy Number Variations; DNA Methylation; DNA Mutational Analysis; DNA, Mitochondrial; Exome; Genome, Human; Humans; Kidney Neoplasms; Molecular Sequence Data; Promoter Regions, Genetic; Telomerase; Transcriptome

Targeted sequencing in candidate genes for atrial fibrillation: the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Targeted Sequencing Study. - Lin, Honghuang; Sinner, Moritz F; Brody, Jennifer A; Arking, Dan E; Lunetta, Kathryn L; Rienstra, Michiel; Lubitz, Steven A; Magnani, Jared W; Sotoodehnia, Nona; McKnight, Barbara; McManus, David D; Eric Boerwinkle; et al. (Heart Rhythm, 2014)
BACKGROUND: Genome-wide association studies (GWAS) have identified common genetic variants that predispose to atrial fibrillation (AF). It is unclear whether rare and low-frequency variants in genes implicated by such GWAS confer additional risk of AF. OBJECTIVE: To study the association of genetic variants with AF at GWAS top loci. METHODS: In the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Targeted Sequencing Study, we selected and sequenced 77 target gene regions from GWAS loci of complex diseases or traits, including 4 genes hypothesized to be related to AF (PRRX1, CAV1, CAV2, and ZFHX3). Sequencing was performed in participants with (n = 948) and without (n = 3330) AF from the Atherosclerosis Risk in Communities Study, the Cardiovascular Health Study, the Framingham Heart Study, and the Massachusetts General Hospital. RESULTS: One common variant (rs11265611; P = 1.70 × 10(-6)) intronic to IL6R (interleukin-6 receptor gene) was significantly associated with AF after Bonferroni correction (odds ratio 0.70; 95% confidence interval 0.58-0.85). The variant was not genotyped or imputed by prior GWAS, but it is in linkage disequilibrium (r(2) = .69) with the single-nucleotide polymorphism, with the strongest association with AF so far at this locus (rs4845625). In the rare variant joint analysis, damaging variants within the PRRX1 region showed significant association with AF after Bonferroni correction (P = .01). CONCLUSIONS: We identified 1 common single-nucleotide polymorphism and 1 gene region that were significantly associated with AF. Future sequencing efforts with larger sample sizes and more comprehensive genome coverage are anticipated to identify additional AF-related variants.
Keywords: Aged; Atrial Fibrillation; Female; Genetic Predisposition to Disease; Genetic Variation; Genome-Wide Association Study; Homeodomain Proteins; Humans; Linkage Disequilibrium; Male; Middle Aged; Polymorphism, Single Nucleotide; Receptors, Interleukin-6

Trans-ancestry mutational landscape of hepatocellular carcinoma genomes. - Totoki, Yasushi; Tatsuno, Kenji; Covington, Kyle R; Ueda, Hiroki; Creighton, Chad J; Kato, Mamoru; Tsuji, Shingo; Donehower, Lawrence A; Slagle, Betty L; Nakamura, Hiromi; Yamamoto, Shogo; Shinbrot, Eve; et al. (Nat Genet, 2014)
Diverse epidemiological factors are associated with hepatocellular carcinoma (HCC) prevalence in different populations. However, the global landscape of the genetic changes in HCC genomes underpinning different epidemiological and ancestral backgrounds still remains uncharted. Here a collection of data from 503 liver cancer genomes from different populations uncovered 30 candidate driver genes and 11 core pathway modules. Furthermore, a collaboration of two large-scale cancer genome projects comparatively analyzed the trans-ancestry substitution signatures in 608 liver cancer cases and identified unique mutational signatures that predominantly contribute to Asian cases. This work elucidates previously unexplored ancestry-associated mutational processes in HCC development. A combination of hotspot TERT promoter mutation, TERT focal amplification and viral genome integration occurs in more than 68% of cases, implicating TERT as a central and ancestry-independent node of hepatocarcinogenesis. Newly identified alterations in genes encoding metabolic enzymes, chromatin remodelers and a high proportion of mTOR pathway activations offer potential therapeutic and diagnostic opportunities.
Keywords: Algorithms; Asian People; Carcinoma, Hepatocellular; CpG Islands; DNA Mutational Analysis; Exome; Gene Expression Regulation, Neoplastic; Genome, Human; Genome, Viral; Hepacivirus; Hepatitis B virus; Humans; Japan; Liver Neoplasms; Models, Statistical; Mutation; Principal Component Analysis; Telomerase; TOR Serine-Threonine Kinases; United States; White People

Whole exome sequencing identifies novel genes for fetal hemoglobin response to hydroxyurea in children with sickle cell anemia. - Sheehan, Vivien A; Crosby, Jacy R; Aniko Sabo; Mortier, Nicole A; Howard, Thad A; Donna M Muzny; Dugan-Perez, Shannon; Aygun, Banu; Nottage, Kerri A; Eric Boerwinkle; Richard A Gibbs; Ware, Russell E; et al. (PLoS One, 2014)
Hydroxyurea has proven efficacy in children and adults with sickle cell anemia (SCA), but with considerable inter-individual variability in the amount of fetal hemoglobin (HbF) produced. Sibling and twin studies indicate that some of that drug response variation is heritable. To test the hypothesis that genetic modifiers influence pharmacological induction of HbF, we investigated phenotype-genotype associations using whole exome sequencing of children with SCA treated prospectively with hydroxyurea to maximum tolerated dose (MTD). We analyzed 171 unrelated patients enrolled in two prospective clinical trials, all treated with dose escalation to MTD. We examined two MTD drug response phenotypes: HbF (final %HbF minus baseline %HbF), and final %HbF. Analyzing individual genetic variants, we identified multiple low frequency and common variants associated with HbF induction by hydroxyurea. A validation cohort of 130 pediatric sickle cell patients treated to MTD with hydroxyurea was genotyped for 13 non-synonymous variants with the strongest association with HbF response to hydroxyurea in the discovery cohort. A coding variant in Spalt-like transcription factor, or SALL2, was associated with higher final HbF in this second independent replication sample and SALL2 represents an outstanding novel candidate gene for further investigation. These findings may help focus future functional studies and provide new insights into the pharmacological HbF upregulation by hydroxyurea in patients with SCA.
Keywords: Anemia, Sickle Cell; Child; Cohort Studies; DNA-Binding Proteins; Dose-Response Relationship, Drug; Exome; Fetal Hemoglobin; Genomics; Humans; Hydroxyurea; Maximum Tolerated Dose; Open Reading Frames; Phenotype; Prospective Studies; Sequence Analysis, DNA; Transcription Factors; Treatment Outcome

Whole exome sequencing identifies three novel mutations in ANTXR1 in families with GAPO syndrome. - Bayram, Yavuz; Pehlivan, Davut; Karaca, Ender; Gambin, Tomasz; Jhangiani, Shalini N; Erdin, Serkan; Gonzaga-Jauregui, Claudia; Wiszniewski, Wojciech; Donna M Muzny; Elcioglu, Nursel H; Yildirim, M Selman; Bozkurt, Banu; et al. (Am J Med Genet A, 2014)
GAPO syndrome (OMIM#230740) is the acronym for growth retardation, alopecia, pseudoanodontia, and optic atrophy. About 35 cases have been reported, making it among one of the rarest recessive conditions. Distinctive craniofacial features including alopecia, rarefaction of eyebrows and eyelashes, frontal bossing, high forehead, mid-facial hypoplasia, hypertelorism, and thickened eyelids and lips make GAPO syndrome a clinically recognizable phenotype. While this genomic study was in progress mutations in ANTXR1 were reported to cause GAPO syndrome. In our study we performed whole exome sequencing (WES) for five affected individuals from three Turkish kindreds segregating the GAPO trait. Exome sequencing analysis identified three novel homozygous mutations including; one frame-shift (c.1220_1221insT; p.Ala408Cysfs*2), one splice site (c.411A>G; p.Gln137Gln), and one non-synonymous (c.1150G>A; p.Gly384Ser) mutation in the ANTXR1 gene. Our studies expand the allelic spectrum in this rare condition and potentially provide insight into the role of ANTXR1 in the regulation of the extracellular matrix.
Keywords: Adolescent; Adult; Alopecia; Anodontia; Base Sequence; Child; Chromosome Segregation; DNA Mutational Analysis; Exome; Facies; Family; Female; Growth Disorders; Humans; Male; Microfilament Proteins; Molecular Sequence Data; Mutation; Neoplasm Proteins; Optic Atrophies, Hereditary; Pedigree; Protein Structure, Tertiary; Receptors, Cell Surface

Whole-exome sequencing links TMCO1 defect syndrome with cerebro-facio-thoracic dysplasia. - Pehlivan, Davut; Karaca, Ender; Aydin, Hatip; Beck, Christine R; Gambin, Tomasz; Donna M Muzny; Bilge Geckinli, B; Karaman, Ali; Jhangiani, Shalini N; Richard A Gibbs; Lupski, James R (Eur J Hum Genet, 2014)
Whole-exome sequencing (WES) is a type of disruptive technology that has tremendous influence on human and clinical genetics research. An efficient and cost-effective method, WES is now widely used as a diagnostic tool for identifying the molecular basis of genetic syndromes that are often challenging to diagnose. Here we report a patient with a clinical diagnosis of cerebro-facio-thoracic dysplasia (CFTD; MIM#213980) in whom we identified a homozygous splice-site mutation in the transmembrane and coiled-coil domains 1 (TMCO1) gene using WES. TMCO1 mutations cause craniofacial dysmorphism, skeletal anomalies characterized by multiple malformations of the vertebrae and ribs, and intellectual disability (MIM#614132). A retrospective review revealed that clinical manifestations of both syndromes are very similar and overlap remarkably. We propose that mutations of TMCO1 are not only responsible for craniofacial dysmorphism, skeletal anomalies and mental retardation syndrome but also for CFTD.
Keywords: Abnormalities, Multiple; Calcium Channels; Exome; Humans; Infant; Intellectual Disability; Male; Membrane Proteins; Mutation; Protein Isoforms

Whole-exome sequencing of polycythemia vera revealed novel driver genes and somatic mutation shared by T cells and granulocytes. - Wang, L; Swierczek, S I; Drummond, J; Hickman, K; Kim, S J; Kimberly Walker; Harshavardhan Doddapaneni; Donna M Muzny; Richard A Gibbs; Wheeler, D A; Prchal, J T (Leukemia, 2014)
To better understand the underlying molecular basis of polycythemia vera (PV), we performed whole-exome sequencing and DNA copy-number analysis of 31 -positive patients and further investigated the evolution of somatic mutations using longitudinal samples. In addition to and 9pUPD, we identified frequent recurrent somatic mutation in , and . Forty two percent of patients had a somatic mutation in at least one epigenetic modifier gene. In 4 of 31 patients, variant allele abundance suggested mutation of was preceded by other somatic mutations including , and . Strikingly, in 7 patients, apparent germline variants were detected at COSMIC codons in one or more PV-related genes in which we had also discovered somatic mutations across the cohort, suggesting that some pre- mutations contribute to substantial T-lymphocyte progeny. This study contributes to novel understanding of the complexity of PV pathogenesis.
Keywords: DNA (Cytosine-5-)-Methyltransferases; DNA Methyltransferase 3A; Exome; Granulocytes; Humans; Janus Kinase 2; Mutation; Polycythemia Vera; Repressor Proteins; Sequence Analysis, DNA; T-Lymphocytes

Analysis of rare, exonic variation amongst subjects with autism spectrum disorders and population controls. - Liu, Li; Aniko Sabo; Neale, Benjamin M; Nagaswamy, Uma; Stevens, Christine; Lim, Elaine; Bodea, Corneliu A; Donna M Muzny; Reid, Jeffrey G; Banks, Eric; Coon, Hillary; DePristo, Mark; et al. (PLoS Genet, 2013)
We report on results from whole-exome sequencing (WES) of 1,039 subjects diagnosed with autism spectrum disorders (ASD) and 870 controls selected from the NIMH repository to be of similar ancestry to cases. The WES data came from two centers using different methods to produce sequence and to call variants from it. Therefore, an initial goal was to ensure the distribution of rare variation was similar for data from different centers. This proved straightforward by filtering called variants by fraction of missing data, read depth, and balance of alternative to reference reads. Results were evaluated using seven samples sequenced at both centers and by results from the association study. Next we addressed how the data and/or results from the centers should be combined. Gene-based analyses of association was an obvious choice, but should statistics for association be combined across centers (meta-analysis) or should data be combined and then analyzed (mega-analysis)? Because of the nature of many gene-based tests, we showed by theory and simulations that mega-analysis has better power than meta-analysis. Finally, before analyzing the data for association, we explored the impact of population structure on rare variant analysis in these data. Like other recent studies, we found evidence that population structure can confound case-control studies by the clustering of rare variants in ancestry space; yet, unlike some recent studies, for these data we found that principal component-based analyses were sufficient to control for ancestry and produce test statistics with appropriate distributions. After using a variety of gene-based tests and both meta- and mega-analysis, we found no new risk genes for ASD in this sample. Our results suggest that standard gene-based tests will require much larger samples of cases and controls before being effective for gene discovery, even for a disorder like ASD.
Keywords: Case-Control Studies; Child; Child Development Disorders, Pervasive; Exome; Genetic Predisposition to Disease; Genetic Variation; Genome-Wide Association Study; Humans; Population Control; Sequence Analysis, DNA; Software

Combined sequence-based and genetic mapping analysis of complex traits in outbred rats. - Baud, Amelie; Hermsen, Roel; Guryev, Victor; Stridh, Pernilla; Graham, Delyth; McBride, Martin W; Foroud, Tatiana; Calderari, Sophie; Diez, Margarita; Ockinger, Johan; Beyeen, Amennai D; Gillett, Alan; et al. (Nat Genet, 2013)
Genetic mapping on fully sequenced individuals is transforming understanding of the relationship between molecular variation and variation in complex traits. Here we report a combined sequence and genetic mapping analysis in outbred rats that maps 355 quantitative trait loci for 122 phenotypes. We identify 35 causal genes involved in 31 phenotypes, implicating new genes in models of anxiety, heart disease and multiple sclerosis. The relationship between sequence and genetic variation is unexpectedly complex: at approximately 40% of quantitative trait loci, a single sequence variant cannot account for the phenotypic effect. Using comparable sequence and mapping data from mice, we show that the extent and spatial pattern of variation in inbred rats differ substantially from those of inbred mice and that the genetic variants in orthologous genes rarely contribute to the same phenotype in both species.
Keywords: Animals; Animals, Outbred Strains; Anxiety; Chromosome Mapping; Genetic Variation; Genotype; Heart Diseases; Humans; Mice; Mice, Inbred C57BL; Models, Molecular; Multiple Sclerosis; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Rats; Sequence Analysis, DNA

Complete Genome Sequence of Elephant Endotheliotropic Herpesvirus 1A. - Ling, Paul D; Reid, Jeffrey G; Qin, Xiang; Donna M Muzny; Richard A Gibbs; Petrosino, Joseph; Peng, Rongsheng; Zong, Jian-Chao; Heaggans, Sarah Y; Hayward, Gary S (Genome Announc, 2013)
Elephant endotheliotropic herpesvirus 1A is a member of the Proboscivirus genus and is a major cause of fatal hemorrhagic disease in endangered juvenile Asian elephants worldwide. Here, we report the first complete genome sequence from this genus, obtained directly from necropsy DNA, in which 60 of the 115 predicted genes are not found in any known herpesvirus.

CRHR1 genotypes, neural circuits and the diathesis for anxiety and depression. - Rogers, J; Raveendran, M; Fawcett, G L; Fox, A S; Shelton, S E; Oler, J A; Cheverud, J; Donna M Muzny; Richard A Gibbs; Davidson, R J; Kalin, N H (Mol Psychiatry, 2013)
The corticotrophin-releasing hormone (CRH) system integrates the stress response and is associated with stress-related psychopathology. Previous reports have identified interactions between childhood trauma and sequence variation in the CRH receptor 1 gene (CRHR1) that increase risk for affective disorders. However, the underlying mechanisms that connect variation in CRHR1 to psychopathology are unknown. To explore potential mechanisms, we used a validated rhesus macaque model to investigate association between genetic variation in CRHR1, anxious temperament (AT) and brain metabolic activity. In young rhesus monkeys, AT is analogous to the childhood risk phenotype that predicts the development of human anxiety and depressive disorders. Regional brain metabolism was assessed with (18)F-labeled fluoro-2-deoxyglucose (FDG) positron emission tomography in 236 young, normally reared macaques that were also characterized for AT. We show that single nucleotide polymorphisms (SNPs) affecting exon 6 of CRHR1 influence both AT and metabolic activity in the anterior hippocampus and amygdala, components of the neural circuit underlying AT. We also find evidence for association between SNPs in CRHR1 and metabolism in the intraparietal sulcus and precuneus. These translational data suggest that genetic variation in CRHR1 affects the risk for affective disorders by influencing the function of the neural circuit underlying AT and that differences in gene expression or the protein sequence involving exon 6 may be important. These results suggest that variation in CRHR1 may influence brain function before any childhood adversity and may be a diathesis for the interaction between CRHR1 genotypes and childhood trauma reported to affect human psychopathology.
Keywords: Animals; Anxiety; Brain; Depression; Disease Models, Animal; Female; Fluorodeoxyglucose F18; Genetic Association Studies; Genetic Predisposition to Disease; Genotype; Macaca mulatta; Male; Polymorphism, Single Nucleotide; Positron-Emission Tomography; Receptors, Corticotropin-Releasing Hormone

De novo truncating mutations in ASXL3 are associated with a novel clinical phenotype with similarities to Bohring-Opitz syndrome. - Bainbridge, Matthew N; Hu, Hao; Donna M Muzny; Musante, Luciana; Lupski, James R; Graham, Brett H; Chen, Wei; Gripp, Karen W; Jenny, Kim; Wienker, Thomas F; Yang, Yaping; Sutton, V Reid; et al. (Genome Med, 2013)
BACKGROUND: Molecular diagnostics can resolve locus heterogeneity underlying clinical phenotypes that may otherwise be co-assigned as a specific syndrome based on shared clinical features, and can associate phenotypically diverse diseases to a single locus through allelic affinity. Here we describe an apparently novel syndrome, likely caused by de novo truncating mutations in ASXL3, which shares characteristics with Bohring-Opitz syndrome, a disease associated with de novo truncating mutations in ASXL1. METHODS: We used whole-genome and whole-exome sequencing to interrogate the genomes of four subjects with an undiagnosed syndrome. RESULTS: Using genome-wide sequencing, we identified heterozygous, de novo truncating mutations in ASXL3, a transcriptional repressor related to ASXL1, in four unrelated probands. We found that these probands shared similar phenotypes, including severe feeding difficulties, failure to thrive, and neurologic abnormalities with significant developmental delay. Further, they showed less phenotypic overlap with patients who had de novo truncating mutations in ASXL1. CONCLUSION: We have identified truncating mutations in ASXL3 as the likely cause of a novel syndrome with phenotypic overlap with Bohring-Opitz syndrome.

Deep resequencing and association analysis of schizophrenia candidate genes. - Crowley, J J; Hilliard, C E; Kim, Y; Morgan, M B; Lewis, L R; Donna M Muzny; Hawes, A C; Aniko Sabo; Wheeler, D A; Lieberman, J A; Sullivan, P F; Richard A Gibbs (Mol Psychiatry, 2013)
Keywords: Adolescent; Adult; Aged; Female; Gene Frequency; Genetic Association Studies; Genetic Predisposition to Disease; Genotype; Humans; Logistic Models; Male; Middle Aged; Polymorphism, Single Nucleotide; Schizophrenia; Young Adult

Exome sequencing resolves apparent incidental findings and reveals further complexity of SH3TC2 variant alleles causing Charcot-Marie-Tooth neuropathy. - Lupski, James R; Gonzaga-Jauregui, Claudia; Yang, Yaping; Bainbridge, Matthew N; Jhangiani, Shalini; Buhay, Christian J; Kovar, Christie L; Wang, Min; Hawes, Alicia C; Reid, Jeffrey G; Eng, Christine; Donna M Muzny; et al. (Genome Med, 2013)
BACKGROUND: The debate regarding the relative merits of whole genome sequencing (WGS) versus exome sequencing (ES) centers around comparative cost, average depth of coverage for each interrogated base, and their relative efficiency in the identification of medically actionable variants from the myriad of variants identified by each approach. Nevertheless, few genomes have been subjected to both WGS and ES, using multiple next generation sequencing platforms. In addition, no personal genome has been so extensively analyzed using DNA derived from peripheral blood as opposed to DNA from transformed cell lines that may either accumulate mutations during propagation or clonally expand mosaic variants during cell transformation and propagation. METHODS: We investigated a genome that was studied previously by SOLiD chemistry using both ES and WGS, and now perform six independent ES assays (Illumina GAII (x2), Illumina HiSeq (x2), Life Technologies' Personal Genome Machine (PGM) and Proton), and one additional WGS (Illumina HiSeq). RESULTS: We compared the variants identified by the different methods and provide insights into the differences among variants identified between ES runs in the same technology platform and among different sequencing technologies. We resolved the true genotypes of medically actionable variants identified in the proband through orthogonal experimental approaches. Furthermore, ES identified an additional SH3TC2 variant (p.M1?) that likely contributes to the phenotype in the proband. CONCLUSIONS: ES identified additional medically actionable variant calls and helped resolve ambiguous single nucleotide variants (SNV) documenting the power of increased depth of coverage of the captured targeted regions. Comparative analyses of WGS and ES reveal that pseudogenes and segmental duplications may explain some instances of apparent disease mutations in unaffected individuals.

Exploring the utility of whole-exome sequencing as a diagnostic tool in a child with atypical episodic muscle weakness. - Hanchard, Neil A; David R Murdock; Magoulas, Pilar L; Matthew N Bainbridge; Donna M Muzny; Wu, Yuanqing; Wang, Min; James R Lupski; Richard A Gibbs; Brown, Chester W (Clin Genet, 2013)
The advent of whole-exome next-generation sequencing (WES) has been pivotal for the molecular characterization of Mendelian disease; however, the clinical applicability of WES has remained relatively unexplored. We describe our exploration of WES as a diagnostic tool in a 3½-year old female patient with a 2-year history of episodic muscle weakness and paroxysmal dystonia who presented following a previous extensive but unrevealing diagnostic work-up. WES was performed on the proband and her two parents. Parental exome data was used to filter potential de novo genomic events in the proband and suspected variants were confirmed using di-deoxy sequencing. WES revealed a de novo non-synonymous mutation in exon 21 of the calcium channel gene CACNA1S that has been previously reported in a single patient as a rare cause of atypical hypokalemic periodic paralysis. This was unexpected, as the proband's original differential diagnosis had included hypokalemic periodic paralysis, but clinical and laboratory features were equivocal, and standard clinical molecular testing for hypokalemic periodic paralysis and related disorders was negative. This report highlights the potential diagnostic utility of WES in clinical practice, with implications for the approach to similar diagnostic dilemmas in the future.
Keywords: Base Sequence; Calcium Channels; Child, Preschool; Exome; Exons; Female; Genotype; High-Throughput Nucleotide Sequencing; Humans; Male; Muscle Weakness; Mutation; NAV1.4 Voltage-Gated Sodium Channel; Pedigree; Phenotype

Identification of TP53 as an acute lymphocytic leukemia susceptibility gene through exome sequencing. - Powell, Bradford C; Jiang, Lichun; Donna M Muzny; Treviño, Lisa R; Dreyer, Zoann E; Strong, Louise C; Wheeler, David A; Richard A Gibbs; Plon, Sharon E (Pediatr Blood Cancer, 2013)
Although acute lymphocytic leukemia (ALL) is the most common childhood cancer, genetic predisposition to ALL remains poorly understood. Whole-exome sequencing was performed in an extended kindred in which five individuals had been diagnosed with leukemia. Analysis revealed a nonsense variant of TP53 which has been previously reported in families with sarcomas and other typical Li Fraumeni syndrome-associated cancers but never in a familial leukemia kindred. This unexpected finding enabled identification of an appropriate sibling bone marrow donor and illustrates that exome sequencing will reveal atypical clinical presentations of even well-studied genes.
Keywords: Exome; Female; Genetic Predisposition to Disease; Humans; Male; Pedigree; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Tumor Suppressor Protein p53

Integrative annotation of variants from 1092 humans: application to cancer genomics. - Khurana, Ekta; Fu, Yao; Colonna, Vincenza; Mu, Xinmeng Jasmine; Kang, Hyun Min; Lappalainen, Tuuli; Sboner, Andrea; Lochovsky, Lucas; Chen, Jieming; Harmanci, Arif; Das, Jishnu; Abyzov, Alexej; et al. (Science, 2013)
Interpreting variants, especially noncoding ones, in the increasing number of personal genomes is challenging. We used patterns of polymorphisms in functionally annotated regions in 1092 humans to identify deleterious variants; then we experimentally validated candidates. We analyzed both coding and noncoding regions, with the former corroborating the latter. We found regions particularly sensitive to mutations ("ultrasensitive") and variants that are disruptive because of mechanistic effects on transcription-factor binding (that is, "motif-breakers"). We also found variants in regions with higher network centrality tend to be deleterious. Insertions and deletions followed a similar pattern to single-nucleotide variants, with some notable exceptions (e.g., certain deletions and enhancers). On the basis of these patterns, we developed a computational tool (FunSeq), whose application to ~90 cancer genomes reveals nearly a hundred candidate noncoding drivers.
Keywords: Binding Sites; Genetic Variation; Genome, Human; Genomics; Humans; Kruppel-Like Transcription Factors; Molecular Sequence Annotation; Mutation; Neoplasms; Polymorphism, Single Nucleotide; Population; RNA, Untranslated; Selection, Genetic

Integrative genomic characterization of oral squamous cell carcinoma identifies frequent somatic drivers. - Pickering, Curtis R; Zhang, Jiexin; Yoo, Suk Young; Bengtsson, Linnea; Moorthy, Shhyam; Neskey, David M; Zhao, Mei; Ortega Alves, Marcus V; Chang, Kyle; Drummond, Jennifer; Cortez, Elsa; Xie, Tong-Xin; et al. (Cancer Discov, 2013)
The survival of patients with oral squamous cell carcinoma (OSCC) has not changed significantly in several decades, leading clinicians and investigators to search for promising molecular targets. To this end, we conducted comprehensive genomic analysis of gene expression, copy number, methylation, and point mutations in OSCC. Integrated analysis revealed more somatic events than previously reported, identifying four major driver pathways (mitogenic signaling, Notch, cell cycle, and TP53) and two additional key genes (FAT1, CASP8). The Notch pathway was defective in 66% of patients, and in follow-up studies of mechanism, functional NOTCH1 signaling inhibited proliferation of OSCC cell lines. Frequent mutation of caspase-8 (CASP8) defines a new molecular subtype of OSCC with few copy number changes. Although genomic alterations are dominated by loss of tumor suppressor genes, 80% of patients harbored at least one genomic alteration in a targetable gene, suggesting that novel approaches to treatment may be possible for this debilitating subset of head and neck cancers.
Keywords: Carcinoma, Squamous Cell; Caspase 8; Cell Line, Tumor; DNA Copy Number Variations; DNA Methylation; Gene Expression Regulation, Neoplastic; Genomics; Humans; Mouth Neoplasms; Point Mutation; Receptors, Notch

MLH1-silenced and non-silenced subgroups of hypermutated colorectal carcinomas have distinct mutational landscapes. - Donehower, Lawrence A; Creighton, Chad J; Schultz, Nikolaus; Shinbrot, Eve; Chang, Kyle; Gunaratne, Preethi H; Donna M Muzny; Sander, Chris; Hamilton, Stanley R; Richard A Gibbs; Wheeler, David (J Pathol, 2013)
Approximately 15% of colorectal carcinomas (CRCs) exhibit a hypermutated genotype accompanied by high levels of microsatellite instability (MSI-H) and defects in DNA mismatch repair. These tumours, unlike the majority of colorectal carcinomas, are often diploid, exhibit frequent epigenetic silencing of the MLH1 DNA mismatch repair gene, and have a better clinical prognosis. As an adjunct study to The Cancer Genome Atlas consortium that recently analysed 224 colorectal cancers by whole exome sequencing, we compared the 35 CRCs (15.6%) with a hypermutated genotype to those with a non-hypermutated genotype. We found that 22 (63%) of the hypermutated CRCs exhibited transcriptional silencing of the MLH1 gene, a high frequency of BRAF V600E gene mutations, and infrequent APC and KRAS mutations, a mutational pattern significantly different from their non-hypermutated counterparts. However, the remaining 13 (37%) hypermutated CRCs lacked MLH1 silencing, contained tumours with the highest mutation rates ('ultramutated' CRCs), and exhibited higher incidences of APC and KRAS mutations, but infrequent BRAF mutations. These patterns were confirmed in an independent validation set of 250 exome-sequenced CRCs. Analysis of mRNA and microRNA expression signatures revealed that hypermutated CRCs with MLH1 silencing had greatly reduced levels of WNT signalling and increased BRAF signalling relative to non-hypermutated CRCs. Our findings suggest that hypermutated CRCs include one subgroup with fundamentally different pathways to malignancy than the majority of CRCs. Examination of MLH1 expression status and frequencies of APC, KRAS, and BRAF mutation in CRC may provide a useful diagnostic tool that could supplement the standard microsatellite instability assays and influence therapeutic decisions.
Keywords: Adaptor Proteins, Signal Transducing; Adenomatous Polyposis Coli Protein; Carcinoma; Colorectal Neoplasms; Gene Expression Profiling; Gene Expression Regulation, Enzymologic; Gene Expression Regulation, Neoplastic; Gene Frequency; Gene Silencing; Genetic Predisposition to Disease; Humans; MicroRNAs; Microsatellite Instability; Mutation; MutL Protein Homolog 1; Nuclear Proteins; Oligonucleotide Array Sequence Analysis; Phenotype; Prognosis; Proto-Oncogene Proteins; Proto-Oncogene Proteins B-raf; Proto-Oncogene Proteins p21(ras); ras Proteins; RNA, Messenger; Wnt Signaling Pathway

Mutations in VRK1 associated with complex motor and sensory axonal neuropathy plus microcephaly. - Gonzaga-Jauregui, Claudia; Lotze, Timothy; Jamal, Leila; Penney, Samantha; Campbell, Ian M; Pehlivan, Davut; Hunter, Jill V; Woodbury, Suzanne L; Raymond, Gerald; Adesina, Adekunle M; Jhangiani, Shalini N; Reid, Jeffrey G; et al. (JAMA Neurol, 2013)
IMPORTANCE: Patients with rare diseases and complex clinical presentations represent a challenge for clinical diagnostics. Genomic approaches are allowing the identification of novel variants in genes for very rare disorders, enabling a molecular diagnosis. Genomics is also revealing a phenotypic expansion whereby the full spectrum of clinical expression conveyed by mutant alleles at a locus can be better appreciated. OBJECTIVE: To elucidate the molecular cause of a complex neuropathy phenotype in 3 patients by applying genomic sequencing strategies. DESIGN, SETTING, AND PARTICIPANTS: Three affected individuals from 2 unrelated families presented with a complex neuropathy phenotype characterized by axonal sensorimotor neuropathy and microcephaly. They were recruited into the Centers for Mendelian Genomics research program to identify the molecular cause of their phenotype. Whole-genome, targeted whole-exome sequencing, and high-resolution single-nucleotide polymorphism arrays were performed in genetics clinics of tertiary care pediatric hospitals and biomedical research institutions. MAIN OUTCOMES AND MEASURES: Whole-genome and whole-exome sequencing identified the variants responsible for the patients' clinical phenotype. RESULTS: We identified compound heterozygous alleles in 2 affected siblings from 1 family and a homozygous nonsense variant in the third unrelated patient in the vaccinia-related kinase 1 gene (VRK1). In the latter subject, we found a common haplotype on which the nonsense mutation occurred and that segregates in the Ashkenazi Jewish population. CONCLUSIONS AND RELEVANCE: We report the identification of disease-causing alleles in 3 children from 2 unrelated families with a previously uncharacterized complex axonal motor and sensory neuropathy accompanied by severe nonprogressive microcephaly and cerebral dysgenesis. Our data raise the question of whether VRK1 mutations disturb cell cycle progression and may result in apoptosis of cells in the nervous system. The application of unbiased genomic approaches allows the identification of potentially pathogenic mutations in unsuspected genes in highly genetically heterogeneous and uncharacterized neurological diseases.
Keywords: Child; Child, Preschool; DNA Mutational Analysis; Female; Genotype; Hereditary Sensory and Motor Neuropathy; Humans; Infant; Intracellular Signaling Peptides and Proteins; Magnetic Resonance Imaging; Male; Microcephaly; Mutation; Neural Conduction; Polymorphism, Single Nucleotide; Protein Serine-Threonine Kinases

Rare complete knockouts in humans: population distribution and significant role in autism spectrum disorders. - Lim, Elaine T; Raychaudhuri, Soumya; Sanders, Stephan J; Stevens, Christine; Aniko Sabo; MacArthur, Daniel G; Neale, Benjamin M; Kirby, Andrew; Ruderfer, Douglas M; Fromer, Menachem; Lek, Monkol; Liu, Li; et al. (Neuron, 2013)
To characterize the role of rare complete human knockouts in autism spectrum disorders (ASDs), we identify genes with homozygous or compound heterozygous loss-of-function (LoF) variants (defined as nonsense and essential splice sites) from exome sequencing of 933 cases and 869 controls. We identify a 2-fold increase in complete knockouts of autosomal genes with low rates of LoF variation (≤ 5% frequency) in cases and estimate a 3% contribution to ASD risk by these events, confirming this observation in an independent set of 563 probands and 4,605 controls. Outside the pseudoautosomal regions on the X chromosome, we similarly observe a significant 1.5-fold increase in rare hemizygous knockouts in males, contributing to another 2% of ASDs in males. Taken together, these results provide compelling evidence that rare autosomal and X chromosome complete gene knockouts are important inherited risk factors for ASD.
Keywords: Case-Control Studies; Child Development Disorders, Pervasive; Child, Preschool; Chromosomes, Human, X; Demography; Female; Gene Deletion; Genetic Variation; Homozygote; Humans; Linkage Disequilibrium; Loss of Heterozygosity; Male; Risk Factors

Whole Exome Sequencing and Analysis Of Mutations In Sézary Syndrome - Xi, Lui; koshalev, misha; Drummond, Jennifer; Donna M Muzny; Zhang, Xiang; Duvic, Madeleine (Blood, 2013)
Sézary Syndrome (SS), the leukemic variant of cutaneous T-cell lymphoma CTCL), is characterized by generalized erythroderma and >1000 circulating central memory T-cells with a CD4+CD26- phenotype, Other clinical features include reactive adenopathy, keratoderma, ectropion, pruritus, and colonization with Staphylococcus aureus. SS can arise de novo or emerge in patients with Mycosis Fungoides (MF). Morphologically, SS cells were first recognized by their convoluted nuclei and karyotype analysis has shown the presence of multiple chromosomal abnormalities and copy number variants, none of which are disease defining; however, the mutational landscape of SS has not been investigated systematically. Here we present initial findings from profiling somatic mutation by whole exome sequencing.

Whole-genome sequence-based analysis of high-density lipoprotein cholesterol. - Morrison, Alanna C; Voorman, Arend; Johnson, Andrew D; Liu, Xiaoming; Yu, Jin; Li, Alexander; Donna M Muzny; Fuli Yu; Rice, Kenneth; Zhu, Chengsong; Bis, Joshua; Heiss, Gerardo; et al. (Nat Genet, 2013)
We describe initial steps for interrogating whole-genome sequence data to characterize the genetic architecture of a complex trait, levels of high-density lipoprotein cholesterol (HDL-C). We report whole-genome sequencing and analysis of 962 individuals from the Cohorts for Heart and Aging Research in Genetic Epidemiology (CHARGE) studies. From this analysis, we estimate that common variation contributes more to heritability of HDL-C levels than rare variation, and screening for mendelian variants for dyslipidemia identified individuals with extreme HDL-C levels. Whole-genome sequencing analyses highlight the value of regulatory and non-protein-coding regions of the genome in addition to protein-coding regions.
Keywords: Cholesterol, HDL; Computational Biology; Databases, Genetic; Genetic Variation; Genome, Human; Genome-Wide Association Study; Genomics; Heterozygote; Humans; Open Reading Frames

Complete genome sequence of Enterococcus faecium strain TX16 and comparative genomic analysis of Enterococcus faecium genomes. - Qin, Xiang; Galloway-Peña, Jessica R; Sillanpaa, Jouko; Roh, Jung Hyeob; Nallapareddy, Sreedhar R; Chowdhury, Shahreen; Bourgogne, Agathe; Choudhury, Tina; Donna M Muzny; Buhay, Christian J; Ding, Yan; Dugan-Rocha, Shannon; et al. (BMC Microbiol, 2012)
BACKGROUND: Enterococci are among the leading causes of hospital-acquired infections in the United States and Europe, with Enterococcus faecalis and Enterococcus faecium being the two most common species isolated from enterococcal infections. In the last decade, the proportion of enterococcal infections caused by E. faecium has steadily increased compared to other Enterococcus species. Although the underlying mechanism for the gradual replacement of E. faecalis by E. faecium in the hospital environment is not yet understood, many studies using genotyping and phylogenetic analysis have shown the emergence of a globally dispersed polyclonal subcluster of E. faecium strains in clinical environments. Systematic study of the molecular epidemiology and pathogenesis of E. faecium has been hindered by the lack of closed, complete E. faecium genomes that can be used as references. RESULTS: In this study, we report the complete genome sequence of the E. faecium strain TX16, also known as DO, which belongs to multilocus sequence type (ST) 18, and was the first E. faecium strain ever sequenced. Whole genome comparison of the TX16 genome with 21 E. faecium draft genomes confirmed that most clinical, outbreak, and hospital-associated (HA) strains (including STs 16, 17, 18, and 78), in addition to strains of non-hospital origin, group in the same clade (referred to as the HA clade) and are evolutionally considerably more closely related to each other by phylogenetic and gene content similarity analyses than to isolates in the community-associated (CA) clade with approximately a 3-4% average nucleotide sequence difference between the two clades at the core genome level. Our study also revealed that many genomic loci in the TX16 genome are unique to the HA clade. 380 ORFs in TX16 are HA-clade specific and antibiotic resistance genes are enriched in HA-clade strains. Mobile elements such as IS16 and transposons were also found almost exclusively in HA strains, as previously reported. CONCLUSIONS: Our findings along with other studies show that HA clonal lineages harbor specific genetic elements as well as sequence differences in the core genome which may confer selection advantages over the more heterogeneous CA E. faecium isolates. Which of these differences are important for the success of specific E. faecium lineages in the hospital environment remain(s) to be determined.
Keywords: DNA, Bacterial; Enterococcus faecium; Genome, Bacterial; Humans; Molecular Sequence Data; Sequence Analysis, DNA

Deep sequencing of systematic combinatorial libraries reveals β-lactamase sequence constraints at high resolution. - Deng, Zhifeng; Huang, Wanzhi; Bakkalbasi, Erol; Brown, Nicholas G; Adamski, Carolyn J; Rice, Kacie; Donna M Muzny; Richard A Gibbs; Palzkill, Timothy (J Mol Biol, 2012)
In this study, combinatorial libraries were used in conjunction with ultrahigh-throughput sequencing to comprehensively determine the impact of each of the 19 possible amino acid substitutions at each residue position in the TEM-1 β-lactamase enzyme. The libraries were introduced into Escherichiacoli, and mutants were selected for ampicillin resistance. The selected colonies were pooled and subjected to ultrahigh-throughput sequencing to reveal the sequence preferences at each position. The depth of sequencing provided a clear, statistically significant picture of what amino acids are favored for ampicillin hydrolysis for all 263 positions of the enzyme in one experiment. Although the enzyme is generally tolerant of amino acid substitutions, several surface positions far from the active site are sensitive to substitutions suggesting a role for these residues in enzyme stability, solubility, or catalysis. In addition, information on the frequency of substitutions was used to identify mutations that increase enzyme thermodynamic stability. Finally, a comparison of sequence requirements based on the mutagenesis results versus those inferred from sequence conservation in an alignment of 156 class A β-lactamases reveals significant differences in that several residues in TEM-1 do not tolerate substitutions and yet extensive variation is observed in the alignment and vice versa. An analysis of the TEM-1 and other class A structures suggests that residues that vary in the alignment may nevertheless make unique, but important, interactions within individual enzymes.
Keywords: Amino Acid Sequence; Amino Acid Substitution; Ampicillin; Ampicillin Resistance; Base Sequence; beta-Lactamases; DNA Mutational Analysis; Enzyme Stability; Escherichia coli; Gene Library; High-Throughput Nucleotide Sequencing; Hydrolysis; Models, Molecular; Mutant Proteins; Mutation Rate; Selection, Genetic; Solubility; Thermodynamics

The Drosophila melanogaster Genetic Reference Panel. - Mackay, Trudy F C; Richards, Stephen; Stone, Eric A; Barbadilla, Antonio; Ayroles, Julien F; Zhu, Dianhui; Casillas, Sònia; Yi Han; Magwire, Michael M; Cridland, Julie M; Richardson, Mark F; Anholt, Robert R H; et al. (Nature, 2012)
A major challenge of biology is understanding the relationship between molecular genetic variation and variation in quantitative traits, including fitness. This relationship determines our ability to predict phenotypes from genotypes and to understand how evolutionary forces shape variation within and between species. Previous efforts to dissect the genotype-phenotype map were based on incomplete genotypic information. Here, we describe the Drosophila melanogaster Genetic Reference Panel (DGRP), a community resource for analysis of population genomics and quantitative traits. The DGRP consists of fully sequenced inbred lines derived from a natural population. Population genomic analyses reveal reduced polymorphism in centromeric autosomal regions and the X chromosome, evidence for positive and negative selection, and rapid evolution of the X chromosome. Many variants in novel genes, most at low frequency, are associated with quantitative traits and explain a large fraction of the phenotypic variance. The DGRP facilitates genotype-phenotype mapping using the power of Drosophila genetics.
Keywords: Alleles; Animals; Centromere; Chromosomes, Insect; Drosophila melanogaster; Genome-Wide Association Study; Genomics; Genotype; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Selection, Genetic; Starvation; Telomere; X Chromosome

Epistasis dominates the genetic architecture of Drosophila quantitative traits. - Huang, Wen; Richards, Stephen; Carbone, Mary Anna; Zhu, Dianhui; Anholt, Robert R H; Ayroles, Julien F; Duncan, Laura; Jordan, Katherine W; Lawrence, Faye; Magwire, Michael M; Warner, Crystal B; Blankenburg, Kerstin; et al. (Proc Natl Acad Sci U S A, 2012)
Epistasis-nonlinear genetic interactions between polymorphic loci-is the genetic basis of canalization and speciation, and epistatic interactions can be used to infer genetic networks affecting quantitative traits. However, the role that epistasis plays in the genetic architecture of quantitative traits is controversial. Here, we compared the genetic architecture of three Drosophila life history traits in the sequenced inbred lines of the Drosophila melanogaster Genetic Reference Panel (DGRP) and a large outbred, advanced intercross population derived from 40 DGRP lines (Flyland). We assessed allele frequency changes between pools of individuals at the extremes of the distribution for each trait in the Flyland population by deep DNA sequencing. The genetic architecture of all traits was highly polygenic in both analyses. Surprisingly, none of the SNPs associated with the traits in Flyland replicated in the DGRP and vice versa. However, the majority of these SNPs participated in at least one epistatic interaction in the DGRP. Despite apparent additive effects at largely distinct loci in the two populations, the epistatic interactions perturbed common, biologically plausible, and highly connected genetic networks. Our analysis underscores the importance of epistasis as a principal factor that determines variation for quantitative traits and provides a means to uncover genetic networks affecting these traits. Knowledge of epistatic networks will contribute to our understanding of the genetic basis of evolutionarily and clinically important traits and enhance predictive ability at an individualized level in medicine and agriculture.
Keywords: Animals; Drosophila melanogaster; Epistasis, Genetic; Genes, Insect; Polymorphism, Single Nucleotide; Quantitative Trait, Heritable

Gene therapy rescues cilia defects and restores olfactory function in a mammalian ciliopathy model. - McIntyre, Jeremy C; Davis, Erica E; Joiner, Ariell; Williams, Corey L; Tsai, I-Chun; Jenkins, Paul M; McEwen, Dyke P; Zhang, Lian; Escobado, John; Thomas, Sophie; Szymanska, Katarzyna; Johnson, Colin A; et al. (Nat Med, 2012)
Cilia are evolutionarily conserved microtubule-based organelles that are crucial for diverse biological functions, including motility, cell signaling and sensory perception. In humans, alterations in the formation and function of cilia manifest clinically as ciliopathies, a growing class of pleiotropic genetic disorders. Despite the substantial progress that has been made in identifying genes that cause ciliopathies, therapies for these disorders are not yet available to patients. Although mice with a hypomorphic mutation in the intraflagellar transport protein IFT88 (Ift88Tg737Rpw mice, also known as ORPK mice)5 have been well studied, the relevance of IFT88 mutations to human pathology is unknown. We show that a mutation in IFT88 causes a hitherto unknown human ciliopathy. In vivo complementation assays in zebrafish and mIMCD3 cells show the pathogenicity of this newly discovered allele. We further show that ORPK mice are functionally anosmic as a result of the loss of cilia on their olfactory sensory neurons (OSNs). Notably, adenoviral-mediated expression of IFT88 in mature, fully differentiated OSNs of ORPK mice is sufficient to restore ciliary structures and rescue olfactory function. These studies are the first to use in vivo therapeutic treatment to reestablish cilia in a mammalian ciliopathy. More broadly, our studies indicate that gene therapy is a viable option for cellular and functional rescue of the complex ciliary organelle in established differentiated cells.
Keywords: Adenoviridae; Animals; Cilia; Genetic Complementation Test; Genetic Diseases, Inborn; Genetic Therapy; Genetic Vectors; Humans; Mice; Microscopy, Fluorescence; Mutation; Olfactory Receptor Neurons; Smell; Tubulin; Tumor Suppressor Proteins; Zebrafish

Mind the gap: upgrading genomes with Pacific Biosciences RS long-read sequencing technology. - English, Adam C; Richards, Stephen; Yi Han; Wang, Min; Vee, Vanesa; Qu, Jiaxin; Qin, Xiang; Donna M Muzny; Reid, Jeffrey G; Worley, Kim C; Richard A Gibbs (PLoS One, 2012)
Many genomes have been sequenced to high-quality draft status using Sanger capillary electrophoresis and/or newer short-read sequence data and whole genome assembly techniques. However, even the best draft genomes contain gaps and other imperfections due to limitations in the input data and the techniques used to build draft assemblies. Sequencing biases, repetitive genomic features, genomic polymorphism, and other complicating factors all come together to make some regions difficult or impossible to assemble. Traditionally, draft genomes were upgraded to "phase 3 finished" status using time-consuming and expensive Sanger-based manual finishing processes. For more facile assembly and automated finishing of draft genomes, we present here an automated approach to finishing using long-reads from the Pacific Biosciences RS (PacBio) platform. Our algorithm and associated software tool, PBJelly, (publicly available at https://sourceforge.net/projects/pb-jelly/) automates the finishing process using long sequence reads in a reference-guided assembly process. PBJelly also provides "lift-over" co-ordinate tables to easily port existing annotations to the upgraded assembly. Using PBJelly and long PacBio reads, we upgraded the draft genome sequences of a simulated Drosophila melanogaster, the version 2 draft Drosophila pseudoobscura, an assembly of the Assemblathon 2.0 budgerigar dataset, and a preliminary assembly of the Sooty mangabey. With 24× mapped coverage of PacBio long-reads, we addressed 99% of gaps and were able to close 69% and improve 12% of all gaps in D. pseudoobscura. With 4× mapped coverage of PacBio long-reads we saw reads address 63% of gaps in our budgerigar assembly, of which 32% were closed and 63% improved. With 6.8× mapped coverage of mangabey PacBio long-reads we addressed 97% of gaps and closed 66% of addressed gaps and improved 19%. The accuracy of gap closure was validated by comparison to Sanger sequencing on gaps from the original D. pseudoobscura draft assembly and shown to be dependent on initial reference quality.
Keywords: Animals; Base Sequence; Cercocebus atys; Databases, Genetic; Decision Making; Drosophila; Genome; Melopsittacus; Reproducibility of Results; Sequence Analysis, DNA; Software

Pancreatic cancer genomes reveal aberrations in axon guidance pathway genes. - Biankin, Andrew V; Waddell, Nicola; Kassahn, Karin S; Marie-Claude Gingras; Muthuswamy, Lakshmi B; Johns, Amber L; Miller, David K; Wilson, Peter J; Patch, Ann-Marie; Wu, Jianmin; Chang, David K; Cowley, Mark J; et al. (Nature, 2012)
Pancreatic cancer is a highly lethal malignancy with few effective therapies. We performed exome sequencing and copy number analysis to define genomic aberrations in a prospectively accrued clinical cohort (n = 142) of early (stage I and II) sporadic pancreatic ductal adenocarcinoma. Detailed analysis of 99 informative tumours identified substantial heterogeneity with 2,016 non-silent mutations and 1,628 copy-number variations. We define 16 significantly mutated genes, reaffirming known mutations (KRAS, TP53, CDKN2A, SMAD4, MLL3, TGFBR2, ARID1A and SF3B1), and uncover novel mutated genes including additional genes involved in chromatin modification (EPC1 and ARID2), DNA damage repair (ATM) and other mechanisms (ZIM2, MAP2K4, NALCN, SLC16A4 and MAGEA6). Integrative analysis with in vitro functional data and animal models provided supportive evidence for potential roles for these genetic aberrations in carcinogenesis. Pathway-based analysis of recurrently mutated genes recapitulated clustering in core signalling pathways in pancreatic ductal adenocarcinoma, and identified new mutated genes in each pathway. We also identified frequent and diverse somatic aberrations in genes described traditionally as embryonic regulators of axon guidance, particularly SLIT/ROBO signalling, which was also evident in murine Sleeping Beauty transposon-mediated somatic mutagenesis models of pancreatic cancer, providing further supportive evidence for the potential involvement of axon guidance genes in pancreatic carcinogenesis.
Keywords: Animals; Axons; Carcinoma, Pancreatic Ductal; Gene Dosage; Gene Expression Regulation, Neoplastic; Genome; Humans; Kaplan-Meier Estimate; Mice; Mutation; Pancreatic Neoplasms; Proteins; Signal Transduction

Patterns and rates of exonic de novo mutations in autism spectrum disorders. - Neale, Benjamin M; Kou, Yan; Liu, Li; Ma'ayan, Avi; Samocha, Kaitlin E; Aniko Sabo; Lin, Chiao-Feng; Stevens, Christine; Wang, Li-San; Makarov, Vladimir; Polak, Paz; Yoon, Seungtai; et al. (Nature, 2012)
Autism spectrum disorders (ASD) are believed to have genetic and environmental origins, yet in only a modest fraction of individuals can specific causes be identified. To identify further genetic risk factors, here we assess the role of de novo mutations in ASD by sequencing the exomes of ASD cases and their parents (n = 175 trios). Fewer than half of the cases (46.3%) carry a missense or nonsense de novo variant, and the overall rate of mutation is only modestly higher than the expected rate. In contrast, the proteins encoded by genes that harboured de novo missense or nonsense mutations showed a higher degree of connectivity among themselves and to previous ASD genes as indexed by protein-protein interaction screens. The small increase in the rate of de novo events, when taken together with the protein interaction results, are consistent with an important but limited role for de novo point mutations in ASD, similar to that documented for de novo copy number variants. Genetic models incorporating these data indicate that most of the observed de novo events are unconnected to ASD; those that do confer risk are distributed across many genes and are incompletely penetrant (that is, not necessarily sufficient for disease). Our results support polygenic models in which spontaneous coding mutations in any of a large number of genes increases risk by 5- to 20-fold. Despite the challenge posed by such models, results from de novo events and a large parallel case-control study provide strong evidence in favour of CHD8 and KATNAL2 as genuine autism risk factors.
Keywords: Autistic Disorder; Case-Control Studies; DNA-Binding Proteins; Exome; Exons; Family Health; Genetic Predisposition to Disease; Humans; Models, Genetic; Multifactorial Inheritance; Mutation; Phenotype; Poisson Distribution; Protein Interaction Maps; Transcription Factors

Strict evolutionary conservation followed rapid gene loss on human and rhesus Y chromosomes. - Hughes, Jennifer F; Skaletsky, Helen; Brown, Laura G; Pyntikova, Tatyana; Graves, Tina; Fulton, Robert S; Dugan, Shannon; Ding, Yan; Buhay, Christian J; Kremitzki, Colin; Wang, Qiaoyan; Shen, Hua; et al. (Nature, 2012)
The human X and Y chromosomes evolved from an ordinary pair of autosomes during the past 200-300 million years. The human MSY (male-specific region of Y chromosome) retains only three percent of the ancestral autosomes' genes owing to genetic decay. This evolutionary decay was driven by a series of five 'stratification' events. Each event suppressed X-Y crossing over within a chromosome segment or 'stratum', incorporated that segment into the MSY and subjected its genes to the erosive forces that attend the absence of crossing over. The last of these events occurred 30 million years ago, 5 million years before the human and Old World monkey lineages diverged. Although speculation abounds regarding ongoing decay and looming extinction of the human Y chromosome, remarkably little is known about how many MSY genes were lost in the human lineage in the 25 million years that have followed its separation from the Old World monkey lineage. To investigate this question, we sequenced the MSY of the rhesus macaque, an Old World monkey, and compared it to the human MSY. We discovered that during the last 25 million years MSY gene loss in the human lineage was limited to the youngest stratum (stratum 5), which comprises three percent of the human MSY. In the older strata, which collectively comprise the bulk of the human MSY, gene loss evidently ceased more than 25 million years ago. Likewise, the rhesus MSY has not lost any older genes (from strata 1-4) during the past 25 million years, despite its major structural differences to the human MSY. The rhesus MSY is simpler, with few amplified gene families or palindromes that might enable intrachromosomal recombination and repair. We present an empirical reconstruction of human MSY evolution in which each stratum transitioned from rapid, exponential loss of ancestral genes to strict conservation through purifying selection.
Keywords: Animals; Chromosomes, Human, Y; Conserved Sequence; Crossing Over, Genetic; Evolution, Molecular; Gene Amplification; Gene Deletion; Humans; In Situ Hybridization, Fluorescence; Macaca mulatta; Male; Models, Genetic; Molecular Sequence Data; Pan troglodytes; Radiation Hybrid Mapping; Selection, Genetic; Time Factors; Y Chromosome

Whole genome sequence of Treponema pallidum ssp. pallidum, strain Mexico A, suggests recombination between yaws and syphilis strains. - Pětrošová, Helena; Zobaníková, Marie; Čejková, Darina; Mikalová, Lenka; Pospíšilová, Petra; Strouhal, Michal; Chen, Lei; Qin, Xiang; Donna M Muzny; Weinstock, George M; Smajs, David (PLoS Negl Trop Dis, 2012)
BACKGROUND: Treponema pallidum ssp. pallidum (TPA), the causative agent of syphilis, and Treponema pallidum ssp. pertenue (TPE), the causative agent of yaws, are closely related spirochetes causing diseases with distinct clinical manifestations. The TPA Mexico A strain was isolated in 1953 from male, with primary syphilis, living in Mexico. Attempts to cultivate TPA Mexico A strain under in vitro conditions have revealed lower growth potential compared to other tested TPA strains. METHODOLOGY/PRINCIPAL FINDINGS: The complete genome sequence of the TPA Mexico A strain was determined using the Illumina sequencing technique. The genome sequence assembly was verified using the whole genome fingerprinting technique and the final sequence was annotated. The genome size of the Mexico A strain was determined to be 1,140,038 bp with 1,035 predicted ORFs. The Mexico A genome sequence was compared to the whole genome sequences of three TPA (Nichols, SS14 and Chicago) and three TPE (CDC-2, Samoa D and Gauthier) strains. No large rearrangements in the Mexico A genome were found and the identified nucleotide changes occurred most frequently in genes encoding putative virulence factors. Nevertheless, the genome of the Mexico A strain, revealed two genes (TPAMA_0326 (tp92) and TPAMA_0488 (mcp2-1)) which combine TPA- and TPE- specific nucleotide sequences. Both genes were found to be under positive selection within TPA strains and also between TPA and TPE strains. CONCLUSIONS/SIGNIFICANCE: The observed mosaic character of the TPAMA_0326 and TPAMA_0488 loci is likely a result of inter-strain recombination between TPA and TPE strains during simultaneous infection of a single host suggesting horizontal gene transfer between treponemal subspecies.
Keywords: DNA, Bacterial; Genome, Bacterial; Humans; Male; Mexico; Molecular Sequence Data; Open Reading Frames; Recombination, Genetic; Sequence Analysis, DNA; Synteny; Syphilis; Treponema pallidum; Yaws

Whole genome sequences of three Treponema pallidum ssp. pertenue strains: yaws and syphilis treponemes differ in less than 0.2% of the genome sequence. - Čejková, Darina; Zobaníková, Marie; Chen, Lei; Pospíšilová, Petra; Strouhal, Michal; Qin, Xiang; Mikalová, Lenka; Norris, Steven J; Donna M Muzny; Richard A Gibbs; Fulton, Lucinda L; Sodergren, Erica; et al. (PLoS Negl Trop Dis, 2012)
BACKGROUND: The yaws treponemes, Treponema pallidum ssp. pertenue (TPE) strains, are closely related to syphilis causing strains of Treponema pallidum ssp. pallidum (TPA). Both yaws and syphilis are distinguished on the basis of epidemiological characteristics, clinical symptoms, and several genetic signatures of the corresponding causative agents. METHODOLOGY/PRINCIPAL FINDINGS: To precisely define genetic differences between TPA and TPE, high-quality whole genome sequences of three TPE strains (Samoa D, CDC-2, Gauthier) were determined using next-generation sequencing techniques. TPE genome sequences were compared to four genomes of TPA strains (Nichols, DAL-1, SS14, Chicago). The genome structure was identical in all three TPE strains with similar length ranging between 1,139,330 bp and 1,139,744 bp. No major genome rearrangements were found when compared to the four TPA genomes. The whole genome nucleotide divergence (d(A)) between TPA and TPE subspecies was 4.7 and 4.8 times higher than the observed nucleotide diversity (π) among TPA and TPE strains, respectively, corresponding to 99.8% identity between TPA and TPE genomes. A set of 97 (9.9%) TPE genes encoded proteins containing two or more amino acid replacements or other major sequence changes. The TPE divergent genes were mostly from the group encoding potential virulence factors and genes encoding proteins with unknown function. CONCLUSIONS/SIGNIFICANCE: Hypothetical genes, with genetic differences, consistently found between TPE and TPA strains are candidates for syphilitic treponemes virulence factors. Seventeen TPE genes were predicted under positive selection, and eleven of them coded either for predicted exported proteins or membrane proteins suggesting their possible association with the cell surface. Sequence changes between TPE and TPA strains and changes specific to individual strains represent suitable targets for subspecies- and strain-specific molecular diagnostics.
Keywords: DNA, Bacterial; Gene Order; Genetic Variation; Genome, Bacterial; Humans; Molecular Sequence Data; Sequence Analysis, DNA; Synteny; Syphilis; Treponema pallidum; Yaws

Activation of multiple proto-oncogenic tyrosine kinases in breast cancer via loss of the PTPN12 phosphatase. - Sun, Tingting; Aceto, Nicola; Meerbrey, Kristen L; Kessler, Jessica D; Zhou, Chunshui; Migliaccio, Ilenia; Nguyen, Don X; Pavlova, Natalya N; Botero, Maria; Huang, Jian; Bernardi, Ronald J; Schmitt, Earlene; et al. (Cell, 2011)
Among breast cancers, triple-negative breast cancer (TNBC) is the most poorly understood and is refractory to current targeted therapies. Using a genetic screen, we identify the PTPN12 tyrosine phosphatase as a tumor suppressor in TNBC. PTPN12 potently suppresses mammary epithelial cell proliferation and transformation. PTPN12 is frequently compromised in human TNBCs, and we identify an upstream tumor-suppressor network that posttranscriptionally controls PTPN12. PTPN12 suppresses transformation by interacting with and inhibiting multiple oncogenic tyrosine kinases, including HER2 and EGFR. The tumorigenic and metastatic potential of PTPN12-deficient TNBC cells is severely impaired upon restoration of PTPN12 function or combined inhibition of PTPN12-regulated tyrosine kinases, suggesting that TNBCs are dependent on the proto-oncogenic tyrosine kinases constrained by PTPN12. Collectively, these data identify PTPN12 as a commonly inactivated tumor suppressor and provide a rationale for combinatorially targeting proto-oncogenic tyrosine kinases in TNBC and other cancers based on their profile of tyrosine-phosphatase activity.
Keywords: Breast Neoplasms; Cell Line, Tumor; Cell Transformation, Neoplastic; ErbB Receptors; Female; Gene Expression Regulation, Neoplastic; Humans; MAP Kinase Signaling System; MicroRNAs; Mutation; Neoplasm Metastasis; Protein Processing, Post-Translational; Protein Tyrosine Phosphatase, Non-Receptor Type 12; Tumor Suppressor Proteins

Characterization of single-nucleotide variation in Indian-origin rhesus macaques (Macaca mulatta). - Fawcett, Gloria L; Raveendran, Muthuswamy; Deiros, David Rio; Chen, David; Fuli Yu; R. Alan Harris; Ren, Yanru; Donna M Muzny; Reid, Jeffrey G; Wheeler, David A; Worley, Kimberly C; Shelton, Steven E; et al. (BMC Genomics, 2011)
BACKGROUND: Rhesus macaques are the most widely utilized nonhuman primate model in biomedical research. Previous efforts have validated fewer than 900 single nucleotide polymorphisms (SNPs) in this species, which limits opportunities for genetic studies related to health and disease. Extensive information about SNPs and other genetic variation in rhesus macaques would facilitate valuable genetic analyses, as well as provide markers for genome-wide linkage analysis and the genetic management of captive breeding colonies. RESULTS: We used the available rhesus macaque draft genome sequence, new sequence data from unrelated individuals and existing published sequence data to create a genome-wide SNP resource for Indian-origin rhesus monkeys. The original reference animal and two additional Indian-origin individuals were resequenced to low coverage using SOLiD™ sequencing. We then used three strategies to validate SNPs: comparison of potential SNPs found in the same individual using two different sequencing chemistries, and comparison of potential SNPs in different individuals identified with either the same or different sequencing chemistries. Our approach validated approximately 3 million SNPs distributed across the genome. Preliminary analysis of SNP annotations suggests that a substantial number of these macaque SNPs may have functional effects. More than 700 non-synonymous SNPs were scored by Polyphen-2 as either possibly or probably damaging to protein function and these variants now constitute potential models for studying functional genetic variation relevant to human physiology and disease. CONCLUSIONS: Resequencing of a small number of animals identified greater than 3 million SNPs. This provides a significant new information resource for rhesus macaques, an important research animal. The data also suggests that overall genetic variation is high in this species. We identified many potentially damaging non-synonymous coding SNPs, providing new opportunities to identify rhesus models for human disease.
Keywords: Animals; Genetic Variation; India; Macaca mulatta; Polymorphism, Single Nucleotide; Sequence Analysis, DNA; Species Specificity

Comparative and demographic analysis of orang-utan genomes. - Locke, Devin P; Hillier, LaDeana W; Warren, Wesley C; Worley, Kim C; Nazareth, Lynne V; Donna M Muzny; Yang, Shiaw-Pyng; Wang, Zhengyuan; Chinwalla, Asif T; Minx, Pat; Mitreva, Makedonka; Cook, Lisa; et al. (Nature, 2011)
'Orang-utan' is derived from a Malay term meaning 'man of the forest' and aptly describes the southeast Asian great apes native to Sumatra and Borneo. The orang-utan species, Pongo abelii (Sumatran) and Pongo pygmaeus (Bornean), are the most phylogenetically distant great apes from humans, thereby providing an informative perspective on hominid evolution. Here we present a Sumatran orang-utan draft genome assembly and short read sequence data from five Sumatran and five Bornean orang-utan genomes. Our analyses reveal that, compared to other primates, the orang-utan genome has many unique features. Structural evolution of the orang-utan genome has proceeded much more slowly than other great apes, evidenced by fewer rearrangements, less segmental duplication, a lower rate of gene family turnover and surprisingly quiescent Alu repeats, which have played a major role in restructuring other primate genomes. We also describe a primate polymorphic neocentromere, found in both Pongo species, emphasizing the gradual evolution of orang-utan genome structure. Orang-utans have extremely low energy usage for a eutherian mammal, far lower than their hominid relatives. Adding their genome to the repertoire of sequenced primates illuminates new signals of positive selection in several pathways including glycolipid metabolism. From the population perspective, both Pongo species are deeply diverse; however, Sumatran individuals possess greater diversity than their Bornean counterparts, and more species-specific variation. Our estimate of Bornean/Sumatran speciation time, 400,000 years ago, is more recent than most previous studies and underscores the complexity of the orang-utan speciation process. Despite a smaller modern census population size, the Sumatran effective population size (N(e)) expanded exponentially relative to the ancestral N(e) after the split, while Bornean N(e) declined over the same period. Overall, the resources and analyses presented here offer new opportunities in evolutionary genomics, insights into hominid biology, and an extensive database of variation for conservation efforts.
Keywords: Animals; Centromere; Cerebrosides; Chromosomes; Evolution, Molecular; Female; Gene Rearrangement; Genetic Speciation; Genetic Variation; Genetics, Population; Genome; Humans; Male; Phylogeny; Pongo abelii; Pongo pygmaeus; Population Density; Population Dynamics; Species Specificity

Complete genome sequence of Treponema paraluiscuniculi, strain Cuniculi A: the loss of infectivity to humans is associated with genome decay. - Smajs, David; Zobaníková, Marie; Strouhal, Michal; Čejková, Darina; Dugan-Rocha, Shannon; Pospíšilová, Petra; Norris, Steven J; Albert, Tom; Qin, Xiang; Hallsworth-Pepin, Kym; Buhay, Christian; Donna M Muzny; et al. (PLoS One, 2011)
Treponema paraluiscuniculi is the causative agent of rabbit venereal spirochetosis. It is not infectious to humans, although its genome structure is very closely related to other pathogenic Treponema species including Treponema pallidum subspecies pallidum, the etiological agent of syphilis. In this study, the genome sequence of Treponema paraluiscuniculi, strain Cuniculi A, was determined by a combination of several high-throughput sequencing strategies. Whereas the overall size (1,133,390 bp), arrangement, and gene content of the Cuniculi A genome closely resembled those of the T. pallidum genome, the T. paraluiscuniculi genome contained a markedly higher number of pseudogenes and gene fragments (51). In addition to pseudogenes, 33 divergent genes were also found in the T. paraluiscuniculi genome. A set of 32 (out of 84) affected genes encoded proteins of known or predicted function in the Nichols genome. These proteins included virulence factors, gene regulators and components of DNA repair and recombination. The majority (52 or 61.9%) of the Cuniculi A pseudogenes and divergent genes were of unknown function. Our results indicate that T. paraluiscuniculi has evolved from a T. pallidum-like ancestor and adapted to a specialized host-associated niche (rabbits) during loss of infectivity to humans. The genes that are inactivated or altered in T. paraluiscuniculi are candidates for virulence factors important in the infectivity and pathogenesis of T. pallidum subspecies.
Keywords: Genome; Humans; Molecular Sequence Data; Sequence Analysis, DNA; Treponema

Copy number variation detection in whole-genome sequencing data using the Bayesian information criterion. - Xi, Ruibin; Hadjipanayis, Angela G; Luquette, Lovelace J; Kim, Tae-Min; Lee, Eunjung; Zhang, Jianhua; Johnson, Mark D; Donna M Muzny; Wheeler, David A; Richard A Gibbs; Kucherlapati, Raju; Park, Peter J (Proc Natl Acad Sci U S A, 2011)
DNA copy number variations (CNVs) play an important role in the pathogenesis and progression of cancer and confer susceptibility to a variety of human disorders. Array comparative genomic hybridization has been used widely to identify CNVs genome wide, but the next-generation sequencing technology provides an opportunity to characterize CNVs genome wide with unprecedented resolution. In this study, we developed an algorithm to detect CNVs from whole-genome sequencing data and applied it to a newly sequenced glioblastoma genome with a matched control. This read-depth algorithm, called BIC-seq, can accurately and efficiently identify CNVs via minimizing the Bayesian information criterion. Using BIC-seq, we identified hundreds of CNVs as small as 40 bp in the cancer genome sequenced at 10× coverage, whereas we could only detect large CNVs (> 15 kb) in the array comparative genomic hybridization profiles for the same genome. Eighty percent (14/16) of the small variants tested (110 bp to 14 kb) were experimentally validated by quantitative PCR, demonstrating high sensitivity and true positive rate of the algorithm. We also extended the algorithm to detect recurrent CNVs in multiple samples as well as deriving error bars for breakpoints using a Gibbs sampling approach. We propose this statistical approach as a principled yet practical and efficient method to estimate CNVs in whole-genome sequencing data.
Keywords: Algorithms; Bayes Theorem; Brain Neoplasms; Comparative Genomic Hybridization; Computer Simulation; DNA Copy Number Variations; Female; Gene Dosage; Genome; Genome, Human; Glioblastoma; Humans; Models, Genetic; Models, Statistical; Sequence Analysis, DNA

Exome sequencing of head and neck squamous cell carcinoma reveals inactivating mutations in NOTCH1. - Agrawal, Nishant; Frederick, Mitchell J; Pickering, Curtis R; Bettegowda, Chetan; Chang, Kyle; Li, Ryan J; Fakhry, Carole; Xie, Tong-Xin; Zhang, Jiexin; Wang, Jing; Zhang, Nianxiang; El-Naggar, Adel K; et al. (Science, 2011)
Head and neck squamous cell carcinoma (HNSCC) is the sixth most common cancer worldwide. To explore the genetic origins of this cancer, we used whole-exome sequencing and gene copy number analyses to study 32 primary tumors. Tumors from patients with a history of tobacco use had more mutations than did tumors from patients who did not use tobacco, and tumors that were negative for human papillomavirus (HPV) had more mutations than did HPV-positive tumors. Six of the genes that were mutated in multiple tumors were assessed in up to 88 additional HNSCCs. In addition to previously described mutations in TP53, CDKN2A, PIK3CA, and HRAS, we identified mutations in FBXW7 and NOTCH1. Nearly 40% of the 28 mutations identified in NOTCH1 were predicted to truncate the gene product, suggesting that NOTCH1 may function as a tumor suppressor gene rather than an oncogene in this tumor type.
Keywords: Carcinoma; Carcinoma, Squamous Cell; Cell Cycle Proteins; Codon, Nonsense; Exons; F-Box Proteins; F-Box-WD Repeat-Containing Protein 7; Gene Dosage; Genes, p53; Genes, Tumor Suppressor; Head and Neck Neoplasms; Humans; INDEL Mutation; Mutation; Mutation, Missense; Neoplasms, Squamous Cell; Nicotiana; Oligonucleotide Array Sequence Analysis; Oncogenes; Papillomaviridae; Papillomavirus Infections; Receptor, Notch1; Sequence Analysis, DNA; Smoking; Squamous Cell Carcinoma of Head and Neck; Ubiquitin-Protein Ligases

Exome sequencing of ion channel genes reveals complex profiles confounding personal risk assessment in epilepsy. - Klassen, Tara; Davis, Caleb; Goldman, Alica; Burgess, Dan; Chen, Tim; Wheeler, David; McPherson, John; Bourquin, Traci; Lewis, Lora; Villasana, Donna; Morgan, Margaret; Donna M Muzny; et al. (Cell, 2011)
Ion channel mutations are an important cause of rare Mendelian disorders affecting brain, heart, and other tissues. We performed parallel exome sequencing of 237 channel genes in a well-characterized human sample, comparing variant profiles of unaffected individuals to those with the most common neuronal excitability disorder, sporadic idiopathic epilepsy. Rare missense variation in known Mendelian disease genes is prevalent in both groups at similar complexity, revealing that even deleterious ion channel mutations confer uncertain risk to an individual depending on the other variants with which they are combined. Our findings indicate that variant discovery via large scale sequencing efforts is only a first step in illuminating the complex allelic architecture underlying personal disease risk. We propose that in silico modeling of channel variation in realistic cell and network models will be crucial to future strategies assessing mutation profile pathogenicity and drug response in individuals with a broad spectrum of excitability disorders.
Keywords: Computer Simulation; Epilepsy; Epistasis, Genetic; Gene Expression Profiling; Hippocampus; Humans; Ion Channels; Mutation, Missense; Neurons; Polymorphism, Single Nucleotide; Risk Assessment

Genome sequence of an Australian kangaroo, Macropus eugenii, provides insight into the evolution of mammalian reproduction and development. - Renfree, Marilyn B; Papenfuss, Anthony T; Deakin, Janine E; Lindsay, James; Heider, Thomas; Belov, Katherine; Rens, Willem; Waters, Paul D; Pharo, Elizabeth A; Shaw, Geoff; Wong, Emily S W; Lefèvre, Christophe M; et al. (Genome Biol, 2011)
BACKGROUND: We present the genome sequence of the tammar wallaby, Macropus eugenii, which is a member of the kangaroo family and the first representative of the iconic hopping mammals that symbolize Australia to be sequenced. The tammar has many unusual biological characteristics, including the longest period of embryonic diapause of any mammal, extremely synchronized seasonal breeding and prolonged and sophisticated lactation within a well-defined pouch. Like other marsupials, it gives birth to highly altricial young, and has a small number of very large chromosomes, making it a valuable model for genomics, reproduction and development. RESULTS: The genome has been sequenced to 2 × coverage using Sanger sequencing, enhanced with additional next generation sequencing and the integration of extensive physical and linkage maps to build the genome assembly. We also sequenced the tammar transcriptome across many tissues and developmental time points. Our analyses of these data shed light on mammalian reproduction, development and genome evolution: there is innovation in reproductive and lactational genes, rapid evolution of germ cell genes, and incomplete, locus-specific X inactivation. We also observe novel retrotransposons and a highly rearranged major histocompatibility complex, with many class I genes located outside the complex. Novel microRNAs in the tammar HOX clusters uncover new potential mammalian HOX regulatory elements. CONCLUSIONS: Analyses of these resources enhance our understanding of marsupial gene evolution, identify marsupial-specific conserved non-coding elements and critical genes across a range of biological systems, including reproduction, development and immunity, and provide new insight into marsupial and mammalian biology and genome evolution.
Keywords: Animals; Australia; Biological Evolution; Chromosome Mapping; Chromosomes, Mammalian; Female; Gene Expression Regulation; Genome; Genomic Imprinting; In Situ Hybridization, Fluorescence; Macropodidae; MicroRNAs; Molecular Sequence Data; Reproduction; Sequence Alignment; Sequence Analysis, DNA; Transcriptome

A high-resolution map of human evolutionary constraint using 29 mammals. - Lindblad-Toh, Kerstin; Garber, Manuel; Zuk, Or; Lin, Michael F; Parker, Brian J; Washietl, Stefan; Kheradpour, Pouya; Ernst, Jason; Jordan, Gregory; Mauceli, Evan; Ward, Lucas D; Lowe, Craig B; et al. (Nature, 2011)
The comparison of related genomes has emerged as a powerful lens for genome interpretation. Here we report the sequencing and comparative analysis of 29 eutherian genomes. We confirm that at least 5.5% of the human genome has undergone purifying selection, and locate constrained elements covering ∼4.2% of the genome. We use evolutionary signatures and comparisons with experimental data sets to suggest candidate functions for ∼60% of constrained bases. These elements reveal a small number of new coding exons, candidate stop codon readthrough events and over 10,000 regions of overlapping synonymous constraint within protein-coding exons. We find 220 candidate RNA structural families, and nearly a million elements overlapping potential promoter, enhancer and insulator regions. We report specific amino acid residues that have undergone positive selection, 280,000 non-coding elements exapted from mobile elements and more than 1,000 primate- and human-accelerated elements. Overlap with disease-associated variants indicates that our findings will be relevant for studies of human biology, health and disease.
Keywords: Animals; Disease; Evolution, Molecular; Exons; Genome; Genome, Human; Genomics; Health; Humans; Mammals; Molecular Sequence Annotation; Phylogeny; RNA; Selection, Genetic; Sequence Alignment; Sequence Analysis, DNA

Identification of genetic susceptibility to childhood cancer through analysis of genes in parallel. - Plon, Sharon E; Wheeler, David A; Strong, Louise C; Tomlinson, Gail E; Pirics, Michael; Meng, Qingchang; Cheung, Hannah C; Begin, Phyllis R; Donna M Muzny; Lewis, Lora; Biegel, Jaclyn A; Richard A Gibbs (Cancer Genet, 2011)
Clinical cancer genetic susceptibility analysis typically proceeds sequentially, beginning with the most likely causative gene. The process is time consuming and the yield is low, particularly for families with unusual patterns of cancer. We determined the results of in parallel mutation analysis of a large cancer-associated gene panel. We performed deletion analysis and sequenced the coding regions of 45 genes (8 oncogenes and 37 tumor suppressor or DNA repair genes) in 48 childhood cancer patients who also (i) were diagnosed with a second malignancy under age 30, (ii) have a sibling diagnosed with cancer under age 30, and/or (iii) have a major congenital anomaly or developmental delay. Deleterious mutations were identified in 6 of 48 (13%) families, 4 of which met the sibling criteria. Mutations were identified in genes previously implicated in both dominant and recessive childhood syndromes, including SMARCB1, PMS2, and TP53. No pathogenic deletions were identified. This approach has provided efficient identification of childhood cancer susceptibility mutations and will have greater utility as additional cancer susceptibility genes are identified. Integrating parallel analysis of large gene panels into clinical testing will speed results and increase diagnostic yield. The failure to detect mutations in 87% of families highlights that a number of childhood cancer susceptibility genes remain to be discovered.
Keywords: Adolescent; Adult; Algorithms; Child; DNA Mutational Analysis; DNA Repair; Gene Dosage; Genes, Dominant; Genes, Recessive; Genes, Tumor Suppressor; Genetic Predisposition to Disease; Humans; Immunoprecipitation; Models, Genetic; Mutation; Neoplasms; Oncogenes; Reverse Transcriptase Polymerase Chain Reaction; Rhabdoid Tumor

Oligogenic heterozygosity in individuals with high-functioning autism spectrum disorders. - Schaaf, Christian P; Aniko Sabo; Sakai, Yasunari; Crosby, Jacy; Donna M Muzny; Hawes, Alicia; Lewis, Lora; Akbar, Humeira; Varghese, Robin; Eric Boerwinkle; Richard A Gibbs; Zoghbi, Huda Y (Hum Mol Genet, 2011)
Autism spectrum disorders (ASDs) are a heterogeneous group of neuro-developmental disorders. While significant progress has been made in the identification of genes and copy number variants associated with syndromic autism, little is known to date about the etiology of idiopathic non-syndromic autism. Sanger sequencing of 21 known autism susceptibility genes in 339 individuals with high-functioning, idiopathic ASD revealed de novo mutations in at least one of these genes in 6 of 339 probands (1.8%). Additionally, multiple events of oligogenic heterozygosity were seen, affecting 23 of 339 probands (6.8%). Screening of a control population for novel coding variants in CACNA1C, CDKL5, HOXA1, SHANK3, TSC1, TSC2 and UBE3A by the same sequencing technology revealed that controls were carriers of oligogenic heterozygous events at significantly (P < 0.01) lower rate, suggesting oligogenic heterozygosity as a new potential mechanism in the pathogenesis of ASDs.
Keywords: Adolescent; Child; Child Development Disorders, Pervasive; Child, Preschool; Genetic Predisposition to Disease; Heterozygote; Humans; Male; Mutation

Resequencing of IRS2 reveals rare variants for obesity but not fasting glucose homeostasis in Hispanic children. - Butte, Nancy F; Voruganti, V Saroja; Cole, Shelley A; Haack, Karin; Comuzzie, Anthony G; Donna M Muzny; Wheeler, David A; Chang, Kyle; Hawes, Alicia; Richard A Gibbs (Physiol Genomics, 2011)
Our objective was to resequence insulin receptor substrate 2 (IRS2) to identify variants associated with obesity- and diabetes-related traits in Hispanic children. Exonic and intronic segments, 5' and 3' flanking regions of IRS2 (∼14.5 kb), were bidirectionally sequenced for single nucleotide polymorphism (SNP) discovery in 934 Hispanic children using 3730XL DNA Sequencers. Additionally, 15 SNPs derived from Illumina HumanOmni1-Quad BeadChips were analyzed. Measured genotype analysis tested associations between SNPs and obesity and diabetes-related traits. Bayesian quantitative trait nucleotide analysis was used to statistically infer the most likely functional polymorphisms. A total of 140 SNPs were identified with minor allele frequencies (MAF) ranging from 0.001 to 0.47. Forty-two of the 70 coding SNPs result in nonsynonymous amino acid substitutions relative to the consensus sequence; 28 SNPs were detected in the promoter, 12 in introns, 28 in the 3'-UTR, and 2 in the 5'-UTR. Two insertion/deletions (indels) were detected. Ten independent rare SNPs (MAF = 0.001-0.009) were associated with obesity-related traits (P = 0.01-0.00002). SNP 10510452_139 in the promoter region was shown to have a high posterior probability (P = 0.77-0.86) of influencing BMI, fat mass, and waist circumference in Hispanic children. SNP 10510452_139 contributed between 2 and 4% of the population variance in body weight and composition. None of the SNPs or indels were associated with diabetes-related traits or accounted for a previously identified quantitative trait locus on chromosome 13 for fasting serum glucose. Rare but not common IRS2 variants may play a role in the regulation of body weight but not an essential role in fasting glucose homeostasis in Hispanic children.
Keywords: Bayes Theorem; Child; Diabetes Mellitus; Fasting; Genetic Predisposition to Disease; Genotyping Techniques; Glucose; Hispanic or Latino; Homeostasis; Humans; Insulin Receptor Substrate Proteins; Linkage Disequilibrium; Obesity; Polymorphism, Single Nucleotide; Quantitative Trait, Heritable; Sequence Analysis, DNA

Targeted enrichment beyond the consensus coding DNA sequence exome reveals exons with higher variant densities. - Bainbridge, Matthew N; Wang, Min; Wu, Yuanqing; Newsham, Irene; Donna M Muzny; Jefferies, John L; Albert, Thomas J; Burgess, Daniel L; Richard A Gibbs (Genome Biol, 2011)
BACKGROUND: Enrichment of loci by DNA hybridization-capture, followed by high-throughput sequencing, is an important tool in modern genetics. Currently, the most common targets for enrichment are the protein coding exons represented by the consensus coding DNA sequence (CCDS). The CCDS, however, excludes many actual or computationally predicted coding exons present in other databases, such as RefSeq and Vega, and non-coding functional elements such as untranslated and regulatory regions. The number of variants per base pair (variant density) and our ability to interrogate regions outside of the CCDS regions is consequently less well understood. RESULTS: We examine capture sequence data from outside of the CCDS regions and find that extremes of GC content that are present in different subregions of the genome can reduce the local capture sequence coverage to less than 50% relative to the CCDS. This effect is due to biases inherent in both the Illumina and SOLiD sequencing platforms that are exacerbated by the capture process. Interestingly, for two subregion types, microRNA and predicted exons, the capture process yields higher than expected coverage when compared to whole genome sequencing. Lastly, we examine the variation present in non-CCDS regions and find that predicted exons, as well as exonic regions specific to RefSeq and Vega, show much higher variant densities than the CCDS. CONCLUSIONS: We show that regions outside of the CCDS perform less efficiently in capture sequence experiments. Further, we show that the variant density in computationally predicted exons is more than 2.5-times higher than that observed in the CCDS.
Keywords: Alleles; Computational Biology; Consensus Sequence; Exome; Exons; Gene Frequency; Genome, Human; Humans; Introns; Mutation Rate; Open Reading Frames; Polymorphism, Single Nucleotide; Sequence Analysis, DNA

TTC21B contributes both causal and modifying alleles across the ciliopathy spectrum. - Davis, Erica E; Zhang, Qi; Liu, Qin; Diplas, Bill H; Davey, Lisa M; Hartley, Jane; Stoetzel, Corinne; Szymanska, Katarzyna; Ramaswami, Gokul; Logan, Clare V; Donna M Muzny; Young, Alice C; et al. (Nat Genet, 2011)
Ciliary dysfunction leads to a broad range of overlapping phenotypes, collectively termed ciliopathies. This grouping is underscored by genetic overlap, where causal genes can also contribute modifier alleles to clinically distinct disorders. Here we show that mutations in TTC21B, which encodes the retrograde intraflagellar transport protein IFT139, cause both isolated nephronophthisis and syndromic Jeune asphyxiating thoracic dystrophy. Moreover, although resequencing of TTC21B in a large, clinically diverse ciliopathy cohort and matched controls showed a similar frequency of rare changes, in vivo and in vitro evaluations showed a significant enrichment of pathogenic alleles in cases (P < 0.003), suggesting that TTC21B contributes pathogenic alleles to ∼5% of ciliopathy cases. Our data illustrate how genetic lesions can be both causally associated with diverse ciliopathies and interact in trans with other disease-causing genes and highlight how saturated resequencing followed by functional analysis of all variants informs the genetic architecture of inherited disorders.
Keywords: Adaptor Proteins, Signal Transducing; Alleles; Animals; Ciliary Motility Disorders; Genetic Variation; Humans; Mice; Mutation; Pedigree; Photoreceptor Cells; Zebrafish

Whole-exome sequencing identifies ALMS1, IQCB1, CNGA3, and MYO7A mutations in patients with Leber congenital amaurosis. - Wang, Xia; Wang, Hui; Cao, Ming; Li, Zhe; Chen, Xianfeng; Patenia, Claire; Gore, Athurva; Abboud, Emad B; Al-Rajhi, Ali A; Lewis, Richard A; Lupski, James R; Mardon, Graeme; et al. (Hum Mutat, 2011)
It has been well documented that mutations in the same retinal disease gene can result in different clinical phenotypes due to difference in the mutant allele and/or genetic background. To evaluate this, a set of consanguineous patient families with Leber congenital amaurosis (LCA) that do not carry mutations in known LCA disease genes was characterized through homozygosity mapping followed by targeted exon/whole-exome sequencing to identify genetic variations. Among these families, a total of five putative disease-causing mutations, including four novel alleles, were found for six families. These five mutations are located in four genes, ALMS1, IQCB1, CNGA3, and MYO7A. Therefore, in our LCA collection from Saudi Arabia, three of the 37 unassigned families carry mutations in retinal disease genes ALMS1, CNGA3, and MYO7A, which have not been previously associated with LCA, and 3 of the 37 carry novel mutations in IQCB1, which has been recently associated with LCA. Together with other reports, our results emphasize that the molecular heterogeneity underlying LCA, and likely other retinal diseases, may be highly complex. Thus, to obtain accurate diagnosis and gain a complete picture of the disease, it is essential to sequence a larger set of retinal disease genes and combine the clinical phenotype with molecular diagnosis.
Keywords: Calmodulin-Binding Proteins; Cell Cycle Proteins; Child, Preschool; Chromosome Mapping; Consanguinity; Cyclic Nucleotide-Gated Cation Channels; DNA Mutational Analysis; Exome; Family; Homozygote; Humans; Leber Congenital Amaurosis; Mutation; Myosin VIIa; Myosins; Pedigree; Proteins; Saudi Arabia; Sequence Analysis, DNA

Whole-exome sequencing identifies compound heterozygous mutations in WDR62 in siblings with recurrent polymicrogyria. - Murdock, David R; Clark, Gary D; Bainbridge, Matthew N; Newsham, Irene; Wu, Yuan-Qing; Donna M Muzny; Cheung, Sau Wai; Richard A Gibbs; Ramocki, Melissa B (Am J Med Genet A, 2011)
Polymicrogyria is a disorder of neuronal development resulting in structurally abnormal cerebral hemispheres characterized by over-folding and abnormal lamination of the cerebral cortex. Polymicrogyria is frequently associated with severe neurologic deficits including intellectual disability, motor problems, and epilepsy. There are acquired and genetic causes of polymicrogyria, but most patients with a presumed genetic etiology lack a specific diagnosis. Here we report using whole-exome sequencing to identify compound heterozygous mutations in the WD repeat domain 62 (WDR62) gene as the cause of recurrent polymicrogyria in a sibling pair. Sanger sequencing confirmed that the siblings both inherited 1-bp (maternal allele) and 2-bp (paternal allele) frameshift deletions, which predict premature truncation of WDR62, a protein that has a role in early cortical development. The probands are from a non-consanguineous family of Northern European descent, suggesting that autosomal recessive PMG due to compound heterozygous mutation of WDR62 might be a relatively common cause of PMG in the population. Further studies to identify mutation frequency in the population are needed.
Keywords: Abnormalities, Multiple; Adult; Base Sequence; Cell Cycle Proteins; Child; Craniofacial Abnormalities; Exome; Female; Frameshift Mutation; Genetic Testing; Heterozygote; High-Throughput Nucleotide Sequencing; Humans; Magnetic Resonance Imaging; Male; Malformations of Cortical Development; Mutation; Nerve Tissue Proteins; Sequence Analysis, DNA; Sequence Deletion; Siblings

Whole-genome sequencing for optimized patient management. - Bainbridge, Matthew N; Wiszniewski, Wojciech; Murdock, David R; Friedman, Jennifer; Gonzaga-Jauregui, Claudia; Newsham, Irene; Reid, Jeffrey G; Fink, John K; Morgan, Margaret B; Marie-Claude Gingras; Donna M Muzny; Hoang, Linh D; et al. (Sci Transl Med, 2011)
Whole-genome sequencing of patient DNA can facilitate diagnosis of a disease, but its potential for guiding treatment has been under-realized. We interrogated the complete genome sequences of a 14-year-old fraternal twin pair diagnosed with dopa (3,4-dihydroxyphenylalanine)-responsive dystonia (DRD; Mendelian Inheritance in Man #128230). DRD is a genetically heterogeneous and clinically complex movement disorder that is usually treated with l-dopa, a precursor of the neurotransmitter dopamine. Whole-genome sequencing identified compound heterozygous mutations in the SPR gene encoding sepiapterin reductase. Disruption of SPR causes a decrease in tetrahydrobiopterin, a cofactor required for the hydroxylase enzymes that synthesize the neurotransmitters dopamine and serotonin. Supplementation of l-dopa therapy with 5-hydroxytryptophan, a serotonin precursor, resulted in clinical improvements in both twins.
Keywords: Adolescent; Decision Making; Dystonic Disorders; Female; Genome, Human; Humans; Levodopa; Male; Patient Care; Pedigree; Sequence Analysis, DNA; Treatment Outcome; Twins, Dizygotic

A catalog of reference genomes from the human microbiome. - Nelson, Karen E; Weinstock, George M; Highlander, Sarah K; Worley, Kim C; Creasy, Heather Huot; Wortman, Jennifer Russo; Rusch, Douglas B; Mitreva, Makedonka; Sodergren, Erica; Chinwalla, Asif T; Feldgarden, Michael; Gevers, Dirk; et al. (Science, 2010)
The human microbiome refers to the community of microorganisms, including prokaryotes, viruses, and microbial eukaryotes, that populate the human body. The National Institutes of Health launched an initiative that focuses on describing the diversity of microbial species that are associated with health and disease. The first phase of this initiative includes the sequencing of hundreds of microbial reference genomes, coupled to metagenomic sequencing from multiple body sites. Here we present results from an initial reference genome sequencing of 178 microbial genomes. From 547,968 predicted polypeptides that correspond to the gene complement of these strains, previously unidentified ("novel") polypeptides that had both unmasked sequence length greater than 100 amino acids and no BLASTP match to any nonreference entry in the nonredundant subset were defined. This analysis resulted in a set of 30,867 polypeptides, of which 29,987 (approximately 97%) were unique. In addition, this set of microbial genomes allows for approximately 40% of random sequences from the microbiome of the gastrointestinal tract to be associated with organisms based on the match criteria used. Insights into pan-genome analysis suggest that we are still far from saturating microbial species genetic data sets. In addition, the associated metrics and standards used by our group for quality assurance are presented.
Keywords: Bacteria; Bacterial Proteins; Biodiversity; Computational Biology; Databases, Genetic; Gastrointestinal Tract; Genes, Bacterial; Genetic Variation; Genome, Archaeal; Genome, Bacterial; Humans; Metagenome; Metagenomics; Mouth; Peptides; Phylogeny; Respiratory System; Sequence Analysis, DNA; Skin; Urogenital System

Comparative genomics of Gardnerella vaginalis strains reveals substantial differences in metabolic and virulence potential. - Yeoman, Carl J; Yildirim, Suleyman; Thomas, Susan M; Durkin, A Scott; Torralba, Manolito; Sutton, Granger; Buhay, Christian J; Ding, Yan; Dugan-Rocha, Shannon P; Donna M Muzny; Qin, Xiang; Richard A Gibbs; et al. (PLoS One, 2010)
BACKGROUND: Gardnerella vaginalis is described as a common vaginal bacterial species whose presence correlates strongly with bacterial vaginosis (BV). Here we report the genome sequencing and comparative analyses of three strains of G. vaginalis. Strains 317 (ATCC 14019) and 594 (ATCC 14018) were isolated from the vaginal tracts of women with symptomatic BV, while Strain 409-05 was isolated from a healthy, asymptomatic individual with a Nugent score of 9. PRINCIPAL FINDINGS: Substantial genomic rearrangement and heterogeneity were observed that appeared to have resulted from both mobile elements and substantial lateral gene transfer. These genomic differences translated to differences in metabolic potential. All strains are equipped with significant virulence potential, including genes encoding the previously described vaginolysin, pili for cytoadhesion, EPS biosynthetic genes for biofilm formation, and antimicrobial resistance systems, We also observed systems promoting multi-drug and lantibiotic extrusion. All G. vaginalis strains possess a large number of genes that may enhance their ability to compete with and exclude other vaginal colonists. These include up to six toxin-antitoxin systems and up to nine additional antitoxins lacking cognate toxins, several of which are clustered within each genome. All strains encode bacteriocidal toxins, including two lysozyme-like toxins produced uniquely by strain 409-05. Interestingly, the BV isolates encode numerous proteins not found in strain 409-05 that likely increase their pathogenic potential. These include enzymes enabling mucin degradation, a trait previously described to strongly correlate with BV, although commonly attributed to non-G. vaginalis species. CONCLUSIONS: Collectively, our results indicate that all three strains are able to thrive in vaginal environments, and therein the BV isolates are capable of occupying a niche that is unique from 409-05. Each strain has significant virulence potential, although genomic and metabolic differences, such as the ability to degrade mucin, indicate that the detection of G. vaginalis in the vaginal tract provides only partial information on the physiological potential of the organism.
Keywords: Bacterial Proteins; Female; Gardnerella vaginalis; Genomics; Humans; Male; Molecular Sequence Data; Phylogeny; Vagina; Vaginosis, Bacterial; Virulence

Complete Khoisan and Bantu genomes from southern Africa. - Schuster, Stephan C; Miller, Webb; Ratan, Aakrosh; Tomsho, Lynn P; Giardine, Belinda; Kasson, Lindsay R; Harris, Robert S; Petersen, Desiree C; Zhao, Fangqing; Qi, Ji; Alkan, Can; Kidd, Jeffrey M; et al. (Nature, 2010)
The genetic structure of the indigenous hunter-gatherer peoples of southern Africa, the oldest known lineage of modern human, is important for understanding human diversity. Studies based on mitochondrial and small sets of nuclear markers have shown that these hunter-gatherers, known as Khoisan, San, or Bushmen, are genetically divergent from other humans. However, until now, fully sequenced human genomes have been limited to recently diverged populations. Here we present the complete genome sequences of an indigenous hunter-gatherer from the Kalahari Desert and a Bantu from southern Africa, as well as protein-coding regions from an additional three hunter-gatherers from disparate regions of the Kalahari. We characterize the extent of whole-genome and exome diversity among the five men, reporting 1.3 million novel DNA differences genome-wide, including 13,146 novel amino acid variants. In terms of nucleotide substitutions, the Bushmen seem to be, on average, more different from each other than, for example, a European and an Asian. Observed genomic differences between the hunter-gatherers and others may help to pinpoint genetic adaptations to an agricultural lifestyle. Adding the described variants to current databases will facilitate inclusion of southern Africans in medical research efforts, particularly when family and medical histories can be correlated with genome-wide data.
Keywords: Asian People; Black People; Ethnicity; Exons; Genetics, Medical; Genome, Human; Humans; Phylogeny; Polymorphism, Single Nucleotide; South Africa; White People

Deep resequencing reveals excess rare recent variants consistent with explosive population growth. - Coventry, Alex; Bull-Otterson, Lara M; Liu, Xiaoming; Clark, Andrew G; Maxwell, Taylor J; Crosby, Jacy; Hixson, James E; Rea, Thomas J; Donna M Muzny; Lewis, Lora R; David A Wheeler; Aniko Sabo; et al. (Nat Commun, 2010)
Accurately determining the distribution of rare variants is an important goal of human genetics, but resequencing of a sample large enough for this purpose has been unfeasible until now. Here, we applied Sanger sequencing of genomic PCR amplicons to resequence the diabetes-associated genes KCNJ11 and HHEX in 13,715 people (10,422 European Americans and 3,293 African Americans) and validated amplicons potentially harbouring rare variants using 454 pyrosequencing. We observed far more variation (expected variant-site count ∼578) than would have been predicted on the basis of earlier surveys, which could only capture the distribution of common variants. By comparison with earlier estimates based on common variants, our model shows a clear genetic signal of accelerating population growth, suggesting that humanity harbours a myriad of rare, deleterious variants, and that disease risk and the burden of disease in contemporary populations may be heavily influenced by the distribution of rare variants.

Functional and evolutionary insights from the genomes of three parasitoid Nasonia species. - Werren, John H; Richards, Stephen; Desjardins, Christopher A; Niehuis, Oliver; Gadau, Jürgen; Colbourne, John K; Werren, John H; Richards, Stephen; Desjardins, Christopher A; Niehuis, Oliver; Gadau, Jürgen; Colbourne, John K; et al. (Science, 2010)
We report here genome sequences and comparative analyses of three closely related parasitoid wasps: Nasonia vitripennis, N. giraulti, and N. longicornis. Parasitoids are important regulators of arthropod populations, including major agricultural pests and disease vectors, and Nasonia is an emerging genetic model, particularly for evolutionary and developmental genetics. Key findings include the identification of a functional DNA methylation tool kit; hymenopteran-specific genes including diverse venoms; lateral gene transfers among Pox viruses, Wolbachia, and Nasonia; and the rapid evolution of genes involved in nuclear-mitochondrial interactions that are implicated in speciation. Newly developed genome resources advance Nasonia for genetic research, accelerate mapping and cloning of quantitative trait loci, and will ultimately provide tools and knowledge for further increasing the utility of parasitoids as pest insect-control agents.
Keywords: Animals; Arthropods; Biological Evolution; DNA Methylation; DNA Transposable Elements; Female; Gene Transfer, Horizontal; Genes, Insect; Genetic Speciation; Genetic Variation; Genome, Insect; Host-Parasite Interactions; Insect Proteins; Insect Viruses; Insecta; Male; Molecular Sequence Data; Quantitative Trait Loci; Recombination, Genetic; Sequence Analysis, DNA; Wasp Venoms; Wasps; Wolbachia

Genetic diversity in India and the inference of Eurasian population expansion. - Xing, Jinchuan; Watkins, W Scott; Hu, Ya; Huff, Chad D; Aniko Sabo; Donna M Muzny; Bamshad, Michael J; Richard A Gibbs; Jorde, Lynn B; Fuli Yu (Genome Biol, 2010)
BACKGROUND: Genetic studies of populations from the Indian subcontinent are of great interest because of India's large population size, complex demographic history, and unique social structure. Despite recent large-scale efforts in discovering human genetic variation, India's vast reservoir of genetic diversity remains largely unexplored. RESULTS: To analyze an unbiased sample of genetic diversity in India and to investigate human migration history in Eurasia, we resequenced one 100-kb ENCODE region in 92 samples collected from three castes and one tribal group from the state of Andhra Pradesh in south India. Analyses of the four Indian populations, along with eight HapMap populations (692 samples), showed that 30% of all SNPs in the south Indian populations are not seen in HapMap populations. Several Indian populations, such as the Yadava, Mala/Madiga, and Irula, have nucleotide diversity levels as high as those of HapMap African populations. Using unbiased allele-frequency spectra, we investigated the expansion of human populations into Eurasia. The divergence time estimates among the major population groups suggest that Eurasian populations in this study diverged from Africans during the same time frame (approximately 90 to 110 thousand years ago). The divergence among different Eurasian populations occurred more than 40,000 years after their divergence with Africans. CONCLUSIONS: Our results show that Indian populations harbor large amounts of genetic variation that have not been surveyed adequately by public SNP discovery efforts. Our data also support a delayed expansion hypothesis in which an ancestral Eurasian founding population remained isolated long after the out-of-Africa diaspora, before expanding throughout Eurasia.
Keywords: DNA, Mitochondrial; Ethnicity; Gene Frequency; Genetic Variation; Genetics, Population; Geography; Humans; India; Polymorphism, Single Nucleotide; Population Density; Population Dynamics; Sequence Analysis, DNA

Integrating common and rare genetic variation in diverse human populations. - Altshuler, David M; Richard A Gibbs; Peltonen, Leena; Altshuler, David M; Richard A Gibbs; Peltonen, Leena; Dermitzakis, Emmanouil; Schaffner, Stephen F; Fuli Yu; Peltonen, Leena; Dermitzakis, Emmanouil; Bonnen, Penelope E; et al. (Nature, 2010)
Despite great progress in identifying genetic variants that influence human disease, most inherited risk remains unexplained. A more complete understanding requires genome-wide studies that fully examine less common alleles in populations with a wide range of ancestry. To inform the design and interpretation of such studies, we genotyped 1.6 million common single nucleotide polymorphisms (SNPs) in 1,184 reference individuals from 11 global populations, and sequenced ten 100-kilobase regions in 692 of these individuals. This integrated data set of common and rare alleles, called 'HapMap 3', includes both SNPs and copy number polymorphisms (CNPs). We characterized population-specific differences among low-frequency variants, measured the improvement in imputation accuracy afforded by the larger reference panel, especially in imputing SNPs with a minor allele frequency of <or=5%, and demonstrated the feasibility of imputing newly discovered CNPs and SNPs. This expanded public resource of genome variants in global populations supports deeper interrogation of genomic variation and its role in human disease, and serves as a step towards a high-resolution map of the landscape of human genetic variation.
Keywords: DNA Copy Number Variations; Genome, Human; Human Genome Project; Humans; Polymorphism, Single Nucleotide; Population Groups

Whole exome capture in solution with 3 Gbp of data. - Bainbridge, Matthew N; Wang, Min; Burgess, Daniel L; Kovar, Christie; Rodesch, Matthew J; D'Ascenzo, Mark; Kitzman, Jacob; Wu, Yuan-Qing; Newsham, Irene; Richmond, Todd A; Jeddeloh, Jeffrey A; Donna M Muzny; et al. (Genome Biol, 2010)
We have developed a solution-based method for targeted DNA capture-sequencing that is directed to the complete human exome. Using this approach allows the discovery of greater than 95% of all expected heterozygous singe base variants, requires as little as 3 Gbp of raw sequence data and constitutes an effective tool for identifying rare coding alleles in large scale genomic studies.
Keywords: Base Pairing; Databases, Nucleic Acid; Exons; Gene Library; Haplotypes; Humans; Polymorphism, Single Nucleotide; Reproducibility of Results; Sequence Alignment; Sequence Analysis, DNA; Solutions

Whole-genome sequencing in a patient with Charcot-Marie-Tooth neuropathy. - Lupski, James R; Reid, Jeffrey G; Gonzaga-Jauregui, Claudia; Rio Deiros, David; Chen, David C Y; Nazareth, Lynne; Bainbridge, Matthew; Dinh, Huyen; Jing, Chyn; Wheeler, David A; McGuire, Amy L; Zhang, Feng; et al. (N Engl J Med, 2010)
BACKGROUND: Whole-genome sequencing may revolutionize medical diagnostics through rapid identification of alleles that cause disease. However, even in cases with simple patterns of inheritance and unambiguous diagnoses, the relationship between disease phenotypes and their corresponding genetic changes can be complicated. Comprehensive diagnostic assays must therefore identify all possible DNA changes in each haplotype and determine which are responsible for the underlying disorder. The high number of rare, heterogeneous mutations present in all humans and the paucity of known functional variants in more than 90% of annotated genes make this challenge particularly difficult. Thus, the identification of the molecular basis of a genetic disease by means of whole-genome sequencing has remained elusive. We therefore aimed to assess the usefulness of human whole-genome sequencing for genetic diagnosis in a patient with Charcot-Marie-Tooth disease. METHODS: We identified a family with a recessive form of Charcot-Marie-Tooth disease for which the genetic basis had not been identified. We sequenced the whole genome of the proband, identified all potential functional variants in genes likely to be related to the disease, and genotyped these variants in the affected family members. RESULTS: We identified and validated compound, heterozygous, causative alleles in SH3TC2 (the SH3 domain and tetratricopeptide repeats 2 gene), involving two mutations, in the proband and in family members affected by Charcot-Marie-Tooth disease. Separate subclinical phenotypes segregated independently with each of the two mutations; heterozygous mutations confer susceptibility to neuropathy, including the carpal tunnel syndrome. CONCLUSIONS: As shown in this study of a family with Charcot-Marie-Tooth disease, whole-genome sequencing can identify clinically relevant variants and provide diagnostic information to inform the care of patients.
Keywords: Adult; Aged; Aged, 80 and over; Charcot-Marie-Tooth Disease; Codon, Nonsense; Female; Genes, Recessive; Genetic Association Studies; Genome, Human; Genotype; Humans; Male; Middle Aged; Mutation, Missense; Pedigree; Phenotype; Polymorphism, Single Nucleotide; Sequence Analysis, DNA

A collagen-binding adhesin, Acb, and ten other putative MSCRAMM and pilus family proteins of Streptococcus gallolyticus subsp. gallolyticus (Streptococcus bovis Group, biotype I). - Sillanpaa, Jouko; Nallapareddy, Sreedhar R; Qin, Xiang; Singh, Kavindra V; Donna M Muzny; Kovar, Christie L; Nazareth, Lynne V; Richard A Gibbs; Ferraro, Mary J; Steckelberg, James M; Weinstock, George M; Murray, Barbara E (J Bacteriol, 2009)
Members of the Streptococcus bovis group are important causes of endocarditis. However, factors associated with their pathogenicity, such as adhesins, remain uncharacterized. We recently demonstrated that endocarditis-derived Streptococcus gallolyticus subsp. gallolyticus isolates frequently adhere to extracellular matrix (ECM) proteins. Here, we generated a draft genome sequence of an ECM protein-adherent S. gallolyticus subsp. gallolyticus strain and found, by genome-wide analyses, 11 predicted LPXTG-type cell wall-anchored proteins with characteristics of MSCRAMMs, including a modular architecture of domains predicted to adopt immunoglobulin (Ig)-like folding. A recombinant segment of one of these, Acb, showed high-affinity binding to immobilized collagen, and cell surface expression of Acb correlated with the presence of acb and collagen adherence of isolates. Three of the 11 proteins have similarities to major pilus subunits and are organized in separate clusters, each including a second Ig-fold-containing MSCRAMM and a class C sortase, suggesting that the sequenced strain encodes three distinct types of pili. Reverse transcription-PCR demonstrated that all three genes of one cluster, acb-sbs7-srtC1, are cotranscribed, consistent with pilus operons of other gram-positive bacteria. Further analysis detected expression of all 11 genes in cells grown to mid to late exponential growth phases. Wide distribution of 9 of the 11 genes was observed among S. gallolyticus subsp. gallolyticus isolates with fewer genes present in other S. bovis group species/subspecies. The high prevalence of genes encoding putative MSCRAMMs and pili, including a collagen-binding MSCRAMM, among S. gallolyticus subsp. gallolyticus isolates may play an important role in the predominance of this subspecies in S. bovis endocarditis.
Keywords: Adhesins, Bacterial; Fimbriae, Bacterial; Gene Expression Profiling; Gene Expression Regulation, Bacterial; Genome, Bacterial; Multigene Family; Streptococcus

A common allele in RPGRIP1L is a modifier of retinal degeneration in ciliopathies. - Khanna, Hemant; Davis, Erica E; Murga-Zamalloa, Carlos A; Estrada-Cuzcano, Alejandro; Lopez, Irma; den Hollander, Anneke I; Zonneveld, Marijke N; Othman, Mohammad I; Waseem, Naushin; Chakarova, Christina F; Maubaret, Cecilia; Diaz-Font, Anna; et al. (Nat Genet, 2009)
Despite rapid advances in the identification of genes involved in disease, the predictive power of the genotype remains limited, in part owing to poorly understood effects of second-site modifiers. Here we demonstrate that a polymorphic coding variant of RPGRIP1L (retinitis pigmentosa GTPase regulator-interacting protein-1 like), a ciliary gene mutated in Meckel-Gruber (MKS) and Joubert (JBTS) syndromes, is associated with the development of retinal degeneration in individuals with ciliopathies caused by mutations in other genes. As part of our resequencing efforts of the ciliary proteome, we identified several putative loss-of-function RPGRIP1L mutations, including one common variant, A229T. Multiple genetic lines of evidence showed this allele to be associated with photoreceptor loss in ciliopathies. Moreover, we show that RPGRIP1L interacts biochemically with RPGR, loss of which causes retinal degeneration, and that the Thr229-encoded protein significantly compromises this interaction. Our data represent an example of modification of a discrete phenotype of syndromic disease and highlight the importance of a multifaceted approach for the discovery of modifier alleles of intermediate frequency and effect.
Keywords: Adaptor Proteins, Signal Transducing; Alleles; Animals; Bardet-Biedl Syndrome; Ciliary Body; Europe; Genetic Variation; GTP Phosphohydrolases; Humans; Mutation; Polymorphism, Single Nucleotide; Retinal Degeneration; Retinitis Pigmentosa; RNA, Messenger; Uveitis; Zebrafish

Common and rare variants of DAOA in bipolar disorder. - Maheshwari, Manjula; Shi, Jiajun; Badner, Judith A; Skol, Andrew; Willour, Virginia L; Donna M Muzny; Wheeler, David A; Gerald, Fowler R; Detera-Wadleigh, Sevilla; McMahon, Francis J; Potash, James B; Gershon, Elliot S; et al. (Am J Med Genet B Neuropsychiatr Genet, 2009)
The D-amino acid oxidase activator (DAOA, previously known as G72) gene, mapped on 13q33, has been reported to be genetically associated with bipolar disorder (BP) in several populations. The consistency of associated variants is unclear and rare variants in exons of the DAOA gene have not been investigated in psychiatric diseases. We employed a conditional linkage method-STatistical Explanation for Positional Cloning (STEPC) to evaluate whether any associated single nucleotide polymorphisms (SNPs) account for the evidence of linkage in a pedigree series that previously has been linked to marker D13S779 at 13q33. We also performed an association study in a sample of 376 Caucasian BP parent-proband trios by genotyping 38 common SNPs in the gene region. Besides, we resequenced coding regions and flanking intronic sequences of DAOA in 555 Caucasian unrelated BP patients and 564 mentally healthy controls, to identify putative functional rare variants that may contribute to disease. One SNP rs1935058 could "explain" the linkage signal in the family sample set (P = 0.055) using STEPC analysis. No significant allelic association was detected in an association study by genotyping 38 common SNPs in 376 Caucasian BP trios. Resequencing identified 53 SNPs, of which 46 were novel SNPs. There was no significant excess of rare variants in cases relative to controls. Our results suggest that DAOA does not have a major effect on BP susceptibility. However, DAOA may contribute to bipolar susceptibility in some specific families as evidenced by the STEPC analysis.
Keywords: Bipolar Disorder; Carrier Proteins; Cloning, Molecular; Exons; Female; Genetic Predisposition to Disease; Humans; Intracellular Signaling Peptides and Proteins; Male; Polymorphism, Single Nucleotide; Sequence Analysis, DNA

The completion of the Mammalian Gene Collection (MGC). - Temple, Gary; Gerhard, Daniela S; Rasooly, Rebekah; Feingold, Elise A; Good, Peter J; Robinson, Cristen; Mandich, Allison; Derge, Jeffrey G; Lewis, Jeanne; Shoaf, Debonny; Collins, Francis S; Jang, Wonhee; et al. (Genome Res, 2009)
Since its start, the Mammalian Gene Collection (MGC) has sought to provide at least one full-protein-coding sequence cDNA clone for every human and mouse gene with a RefSeq transcript, and at least 6200 rat genes. The MGC cloning effort initially relied on random expressed sequence tag screening of cDNA libraries. Here, we summarize our recent progress using directed RT-PCR cloning and DNA synthesis. The MGC now contains clones with the entire protein-coding sequence for 92% of human and 89% of mouse genes with curated RefSeq (NM-accession) transcripts, and for 97% of human and 96% of mouse genes with curated RefSeq transcripts that have one or more PubMed publications, in addition to clones for more than 6300 rat genes. These high-quality MGC clones and their sequences are accessible without restriction to researchers worldwide.
Keywords: Animals; Cloning, Molecular; Computational Biology; DNA; DNA, Complementary; Gene Library; Genes; Humans; Mammals; Mice; National Institutes of Health (U.S.); Rats; Reverse Transcriptase Polymerase Chain Reaction; United States

The genome sequence of taurine cattle: a window to ruminant biology and evolution. - Elsik, Christine G; Tellam, Ross L; Worley, Kim C; Richard A Gibbs; Donna M Muzny; Weinstock, George M; Adelson, David L; Eichler, Evan E; Elnitski, Laura; Guigó, Roderic; Hamernik, Debora L; Kappes, Steve M; et al. (Science, 2009)
To understand the biology and evolution of ruminants, the cattle genome was sequenced to about sevenfold coverage. The cattle genome contains a minimum of 22,000 genes, with a core set of 14,345 orthologs shared among seven mammalian species of which 1217 are absent or undetected in noneutherian (marsupial or monotreme) genomes. Cattle-specific evolutionary breakpoint regions in chromosomes have a higher density of segmental duplications, enrichment of repetitive elements, and species-specific variations in genes associated with lactation and immune responsiveness. Genes involved in metabolism are generally highly conserved, although five metabolic genes are deleted or extensively diverged from their human orthologs. The cattle genome sequence thus provides a resource for understanding mammalian evolution and accelerating livestock genetic improvement for milk and meat production.
Keywords: Alternative Splicing; Animals; Animals, Domestic; Biological Evolution; Cattle; Evolution, Molecular; Female; Genetic Variation; Genome; Humans; Male; MicroRNAs; Molecular Sequence Data; Proteins; Sequence Analysis, DNA; Species Specificity; Synteny

Genome-wide survey of SNP variation uncovers the genetic structure of cattle breeds. - Richard A Gibbs; Taylor, Jeremy F; Van Tassell, Curtis P; Barendse, William; Eversole, Kellye A; Gill, Clare A; Green, Ronnie D; Hamernik, Debora L; Kappes, Steven M; Lien, Sigbjørn; Matukumalli, Lakshmi K; McEwan, John C; et al. (Science, 2009)
The imprints of domestication and breed development on the genomes of livestock likely differ from those of companion animals. A deep draft sequence assembly of shotgun reads from a single Hereford female and comparative sequences sampled from six additional breeds were used to develop probes to interrogate 37,470 single-nucleotide polymorphisms (SNPs) in 497 cattle from 19 geographically and biologically diverse breeds. These data show that cattle have undergone a rapid recent decrease in effective population size from a very large ancestral population, possibly due to bottlenecks associated with domestication, selection, and breed formation. Domestication and artificial selection appear to have left detectable signatures of selection within the cattle genome, yet the current levels of diversity within breeds are at least as great as exists within humans.
Keywords: Animals; Breeding; Cattle; Female; Gene Frequency; Genetic Variation; Genome; Male; Molecular Sequence Data; Mutation; Polymorphism, Single Nucleotide; Population Density

Genomics. Genome project standards in a new era of sequencing. - Chain, P S G; Grafham, D V; Fulton, R S; Fitzgerald, M G; Hostetler, J; Donna M Muzny; Ali, J; Birren, B; Bruce, D C; Buhay, C; Cole, J R; Ding, Y; et al. (Science, 2009)
More detailed sequence standards that keep up with revolutionary sequencing technologies will aid the research community in evaluating data.
Keywords: Computational Biology; Databases, Nucleic Acid; Genome; Genomics; Sequence Analysis, DNA

Mutations in smooth muscle alpha-actin (ACTA2) cause coronary artery disease, stroke, and Moyamoya disease, along with thoracic aortic disease. - Guo, Dong-chuan; Papke, Christina L; Tran-Fadulu, Van; Regalado, Ellen S; Avidan, Nili; Johnson, Ralph Jay; Kim, Dong H; Pannu, Hariyadarshi; Willing, Marcia C; Sparks, Elizabeth; Pyeritz, Reed E; Singh, Michael N; et al. (Am J Hum Genet, 2009)
The vascular smooth muscle cell (SMC)-specific isoform of alpha-actin (ACTA2) is a major component of the contractile apparatus in SMCs located throughout the arterial system. Heterozygous ACTA2 mutations cause familial thoracic aortic aneurysms and dissections (TAAD), but only half of mutation carriers have aortic disease. Linkage analysis and association studies of individuals in 20 families with ACTA2 mutations indicate that mutation carriers can have a diversity of vascular diseases, including premature onset of coronary artery disease (CAD) and premature ischemic strokes (including Moyamoya disease [MMD]), as well as previously defined TAAD. Sequencing of DNA from patients with nonfamilial TAAD and from premature-onset CAD patients independently identified ACTA2 mutations in these patients and premature onset strokes in family members with ACTA2 mutations. Vascular pathology and analysis of explanted SMCs and myofibroblasts from patients harboring ACTA2 suggested that increased proliferation of SMCs contributed to occlusive diseases. These results indicate that heterozygous ACTA2 mutations predispose patients to a variety of diffuse and diverse vascular diseases, including TAAD, premature CAD, ischemic strokes, and MMD. These data demonstrate that diffuse vascular diseases resulting from either occluded or enlarged arteries can be caused by mutations in a single gene and have direct implications for clinical management and research on familial vascular diseases.
Keywords: Actins; Adolescent; Adult; Aortic Aneurysm, Thoracic; Aortic Dissection; Cell Proliferation; Cells, Cultured; Coronary Artery Disease; Female; Genetic Predisposition to Disease; Humans; Male; Middle Aged; Models, Molecular; Moyamoya Disease; Mutation; Myocytes, Smooth Muscle; Protein Isoforms; Stroke; Young Adult

A sequence-level map of chromosomal breakpoints in the MCF-7 breast cancer cell line yields insights into the evolution of a cancer genome. - Hampton, Oliver A; Den Hollander, Petra; Miller, Christopher A; Delgado, David A; Li, Jian; Coarfa, Cristian; R. Alan Harris; Richards, Stephen; Scherer, Steven E; Donna M Muzny; Richard A Gibbs; Lee, Adrian V; et al. (Genome Res, 2009)
By applying a method that combines end-sequence profiling and massively parallel sequencing, we obtained a sequence-level map of chromosomal aberrations in the genome of the MCF-7 breast cancer cell line. A total of 157 distinct somatic breakpoints of two distinct types, dispersed and clustered, were identified. A total of 89 breakpoints are evenly dispersed across the genome. A majority of dispersed breakpoints are in regions of low copy repeats (LCRs), indicating a possible role for LCRs in chromosome breakage. The remaining 68 breakpoints form four distinct clusters of closely spaced breakpoints that coincide with the four highly amplified regions in MCF-7 detected by array CGH located in the 1p13.1-p21.1, 3p14.1-p14.2, 17q22-q24.3, and 20q12-q13.33 chromosomal cytobands. The clustered breakpoints are not significantly associated with LCRs. Sequences flanking most (95%) breakpoint junctions are consistent with double-stranded DNA break repair by nonhomologous end-joining or template switching. A total of 79 known or predicted genes are involved in rearrangement events, including 10 fusions of coding exons from different genes and 77 other rearrangements. Four fusions result in novel expressed chimeric mRNA transcripts. One of the four expressed fusion products (RAD51C-ATXN7) and one gene truncation (BRIP1 or BACH1) involve genes coding for members of protein complexes responsible for homology-driven repair of double-stranded DNA breaks. Another one of the four expressed fusion products (ARFGEF2-SULF2) involves SULF2, a regulator of cell growth and angiogenesis. We show that knock-down of SULF2 in cell lines causes tumorigenic phenotypes, including increased proliferation, enhanced survival, and increased anchorage-independent growth.
Keywords: Breast Neoplasms; Cell Line, Tumor; Chromosome Breakage; Chromosome Mapping; Chromosomes, Artificial, Bacterial; DNA Repair; Evolution, Molecular; Gene Expression Profiling; Genes, Neoplasm; Genome, Human; Humans; Locus Control Region; Models, Biological; Mutant Chimeric Proteins; Sequence Analysis, DNA

Single nucleotide polymorphism in RECQL and survival in resectable pancreatic adenocarcinoma. - Cotton, Ronald T; Li, Donghui; Scherer, Steven E; Donna M Muzny; Hodges, Sally E; Catania, Robbi L; Witkiewicz, Agnieszka K; Brody, Jonathan R; Kennedy, Eugene P; Yeo, Charles J; Brunicardi, F Charles; Richard A Gibbs; et al. (HPB (Oxford), 2009)
BACKGROUND: RECQL is a DNA helicase involved in DNA mismatch repair. The RECQL polymorphism, 3' untranslated region (UTR) A159C, was previously associated with overall survival of patients with resectable pancreatic adenocarcinoma treated with neoadjuvant chemoradiation. In the present study, we examined RECQL for somatic mutations and other polymorphisms and compared these findings with the outcome in patients who received adjuvant or neoadjuvant chemoradiation. We hypothesized that RECQL (i) would be mutated in cancer, (ii) would have polymorphisms linked to the 3'UTR A159C and that either or both events would affect function. We also hypothesized that (iii) these changes would be associated with survival in both cohorts of patients. MATERIAL AND METHODS: We sequenced RECQL's 15 exons and surrounding sequences in paired blood and tumour DNA of 39 patients. The 3'UTR A159C genotype was determined in blood DNA samples from 176 patients with resectable pancreatic adenocarcinoma treated with adjuvant (53) or neoadjuvant (123) chemoradiation. Survival was calculated using the Kaplan-Meier method, with log rank comparisons between groups. The relative impact of genotype on time to overall survival was performed using the Cox proportional hazards model. RESULTS: Somatic mutations were found in UTRs and intronic regions but not in exonic coding regions of the RECQL gene. Two single nucleotide polymorphisms (SNPs), located in introns 2 and 11, were found to be part of the same haplotype block as the RECQL A159C SNP and showed a similar association with overall survival. No short-term difference in survival between treatment strategies was found. We identified a subgroup of patients responsive to neoadjuvant therapy in which the 159 A allele conferred strikingly improved long-term survival. DISCUSSION: The RECQL 3'UTR A159C SNP is not linked with other functional SNPs within RECQL but may function as a site for regulatory molecules. The mechanism of action needs to be clarified further.

The complete genome of an individual by massively parallel DNA sequencing. - Wheeler, David A; Srinivasan, Maithreyan; Egholm, Michael; Shen, Yufeng; Chen, Lei; McGuire, Amy; He, Wen; Chen, Yi-Ju; Makhijani, Vinod; Roth, G Thomas; Gomes, Xavier; Tartaro, Karrie; et al. (Nature, 2008)
The association of genetic variation with disease and drug response, and improvements in nucleic acid technologies, have given great optimism for the impact of 'genomic medicine'. However, the formidable size of the diploid human genome, approximately 6 gigabases, has prevented the routine application of sequencing methods to deciphering complete individual human genomes. To realize the full potential of genomics for human health, this limitation must be overcome. Here we report the DNA sequence of a diploid genome of a single individual, James D. Watson, sequenced to 7.4-fold redundancy in two months using massively parallel sequencing in picolitre-size reaction vessels. This sequence was completed in two months at approximately one-hundredth of the cost of traditional capillary electrophoresis methods. Comparison of the sequence to the reference genome led to the identification of 3.3 million single nucleotide polymorphisms, of which 10,654 cause amino-acid substitution within the coding sequence. In addition, we accurately identified small-scale (2-40,000 base pair (bp)) insertion and deletion polymorphism as well as copy number variation resulting in the large-scale gain and loss of chromosomal segments ranging from 26,000 to 1.5 million base pairs. Overall, these results agree well with recent results of sequencing of a single individual by traditional methods. However, in addition to being faster and significantly less expensive, this sequencing technology avoids the arbitrary loss of genomic sequences inherent in random shotgun sequencing by bacterial cloning because it amplifies DNA in a cell-free system. As a result, we further demonstrate the acquisition of novel human sequence, including novel genes not previously identified by traditional genomic sequencing. This is the first genome sequenced by next-generation technologies. Therefore it is a pilot for the future challenges of 'personalized genome sequencing'.
Keywords: Alleles; Computational Biology; Genetic Predisposition to Disease; Genetic Variation; Genome, Human; Genomics; Genotype; Humans; Individuality; Male; Oligonucleotide Array Sequence Analysis; Polymorphism, Single Nucleotide; Reproducibility of Results; Sensitivity and Specificity; Sequence Alignment; Sequence Analysis, DNA; Software

The complete genome sequence of Escherichia coli DH10B: insights into the biology of a laboratory workhorse. - Durfee, Tim; Nelson, Richard; Baldwin, Schuyler; Plunkett, Guy; Burland, Valerie; Mau, Bob; Petrosino, Joseph F; Qin, Xiang; Donna M Muzny; Ayele, Mulu; Richard A Gibbs; Csörgo, Bálint; et al. (J Bacteriol, 2008)
Escherichia coli DH10B was designed for the propagation of large insert DNA library clones. It is used extensively, taking advantage of properties such as high DNA transformation efficiency and maintenance of large plasmids. The strain was constructed by serial genetic recombination steps, but the underlying sequence changes remained unverified. We report the complete genomic sequence of DH10B by using reads accumulated from the bovine sequencing project at Baylor College of Medicine and assembled with DNAStar's SeqMan genome assembler. The DH10B genome is largely colinear with that of the wild-type K-12 strain MG1655, although it is substantially more complex than previously appreciated, allowing DH10B biology to be further explored. The 226 mutated genes in DH10B relative to MG1655 are mostly attributable to the extensive genetic manipulations the strain has undergone. However, we demonstrate that DH10B has a 13.5-fold higher mutation rate than MG1655, resulting from a dramatic increase in insertion sequence (IS) transposition, especially IS150. IS elements appear to have remodeled genome architecture, providing homologous recombination sites for a 113,260-bp tandem duplication and an inversion. DH10B requires leucine for growth on minimal medium due to the deletion of leuLABCD and harbors both the relA1 and spoT1 alleles causing both sensitivity to nutritional downshifts and slightly lower growth rates relative to the wild type. Finally, while the sequence confirms most of the reported alleles, the sequence of deoR is wild type, necessitating reexamination of the assumed basis for the high transformability of DH10B.
Keywords: Escherichia coli; Genes, Bacterial; Genome, Bacterial; Models, Genetic; Mutation; Sequence Analysis, DNA

The genome of the model beetle and pest Tribolium castaneum. - Stephen Richards; Richard A Gibbs; Weinstock, George M; Brown, Susan J; Denell, Robin; Beeman, Richard W; Richard A Gibbs; Beeman, Richard W; Brown, Susan J; Bucher, Gregor; Friedrich, Markus; Grimmelikhuijzen, Cornelis J P; et al. (Nature, 2008)
Tribolium castaneum is a member of the most species-rich eukaryotic order, a powerful model organism for the study of generalized insect development, and an important pest of stored agricultural products. We describe its genome sequence here. This omnivorous beetle has evolved the ability to interact with a diverse chemical environment, as shown by large expansions in odorant and gustatory receptors, as well as P450 and other detoxification enzymes. Development in Tribolium is more representative of other insects than is Drosophila, a fact reflected in gene content and function. For example, Tribolium has retained more ancestral genes involved in cell-cell communication than Drosophila, some being expressed in the growth zone crucial for axial elongation in short-germ development. Systemic RNA interference in T. castaneum functions differently from that in Caenorhabditis elegans, but nevertheless offers similar power for the elucidation of gene function and identification of targets for selective insect control.
Keywords: Animals; Base Composition; Body Patterning; Cytochrome P-450 Enzyme System; DNA Transposable Elements; Genes, Insect; Genome, Insect; Growth and Development; Humans; Insecticides; Neurotransmitter Agents; Oogenesis; Phylogeny; Proteome; Receptors, G-Protein-Coupled; Receptors, Odorant; Repetitive Sequences, Nucleic Acid; RNA Interference; Taste; Telomere; Tribolium; Vision, Ocular

Large scale variation in Enterococcus faecalis illustrated by the genome analysis of strain OG1RF. - Bourgogne, Agathe; Garsin, Danielle A; Qin, Xiang; Singh, Kavindra V; Sillanpaa, Jouko; Yerrapragada, Shailaja; Ding, Yan; Dugan-Rocha, Shannon; Buhay, Christian; Shen, Hua; Chen, Guan; Williams, Gabrielle; et al. (Genome Biol, 2008)
BACKGROUND: Enterococcus faecalis has emerged as a major hospital pathogen. To explore its diversity, we sequenced E. faecalis strain OG1RF, which is commonly used for molecular manipulation and virulence studies. RESULTS: The 2,739,625 base pair chromosome of OG1RF was found to contain approximately 232 kilobases unique to this strain compared to V583, the only publicly available sequenced strain. Almost no mobile genetic elements were found in OG1RF. The 64 areas of divergence were classified into three categories. First, OG1RF carries 39 unique regions, including 2 CRISPR loci and a new WxL locus. Second, we found nine replacements where a sequence specific to V583 was substituted by a sequence specific to OG1RF. For example, the iol operon of OG1RF replaces a possible prophage and the vanB transposon in V583. Finally, we found 16 regions that were present in V583 but missing from OG1RF, including the proposed pathogenicity island, several probable prophages, and the cpsCDEFGHIJK capsular polysaccharide operon. OG1RF was more rapidly but less frequently lethal than V583 in the mouse peritonitis model and considerably outcompeted V583 in a murine model of urinary tract infections. CONCLUSION: E. faecalis OG1RF carries a number of unique loci compared to V583, but the almost complete lack of mobile genetic elements demonstrates that this is not a defining feature of the species. Additionally, OG1RF's effects in experimental models suggest that mediators of virulence may be diverse between different E. faecalis strains and that virulence is not dependent on the presence of mobile genetic elements.
Keywords: Animals; Anti-Bacterial Agents; Bacterial Proteins; Biofilms; DNA, Bacterial; Drug Resistance, Bacterial; Enterococcus faecalis; Fusidic Acid; Genetic Variation; Genome, Bacterial; Genomics; Interspersed Repetitive Sequences; Membrane Proteins; Mice; Operon; Repetitive Sequences, Nucleic Acid; Rifampin; Sequence Homology, Nucleic Acid

Mouse let-7 miRNA populations exhibit RNA editing that is constrained in the 5'-seed/ cleavage/anchor regions and stabilize predicted mmu-let-7a:mRNA duplexes. - Reid, Jeffrey G; Nagaraja, Ankur K; Lynn, Francis C; Drabek, Rafal B; Donna M Muzny; Shaw, Chad A; Weiss, Michelle K; Naghavi, Arash O; Khan, Mahjabeen; Zhu, Huifeng; Tennakoon, Jayantha; Gunaratne, Gemunu H; et al. (Genome Res, 2008)
Massively parallel sequencing of millions of < 30-nt RNAs expressed in mouse ovary, embryonic pancreas (E14.5), and insulin-secreting beta-cells (betaTC-3) reveals that approximately 50% of the mature miRNAs representing mostly the mmu-let-7 family display internal insertion/deletions and substitutions when compared to precursor miRNA and the mouse genome reference sequences. Approximately, 12%-20% of species associated with mmu-let-7 populations exhibit sequence discrepancies that are dramatically reduced in nucleotides 3-7 (5'-seed) and 10-15 (cleavage and anchor sites). This observation is inconsistent with sequencing error and leads us to propose that the changes arise predominantly from post-transcriptional RNA-editing activity operating on miRNA:target mRNA complexes. Internal nucleotide modifications are most enriched at the ninth nucleotide position. A common ninth base edit of U-to-G results in a significant increase in stability of down-regulated let-7a targets in inhibin-deficient mice (Inha-/-). An excess of U-insertions (14.8%) over U-deletions (1.5%) and the presence of cleaved intermediates suggest that a mammalian TUTase (terminal uridylyl transferase) mediated dUTP-dependent U-insertion/U-deletion cycle may be a possible mechanism. We speculate that mRNA target site-directed editing of mmu-let-7a duplex-bulges stabilizes "loose" miRNA:mRNA target associations and functions to expand the target repertoire and/or enhance mRNA decay over translational repression. Our results also demonstrate that the systematic study of sequence variation within specific RNA classes in a given cell type from millions of sequences generated by next-generation sequencing (NGS) technologies ("intranomics") can be used broadly to infer functional constraints on specific parts of completely uncharacterized RNAs.
Keywords: Animals; Base Sequence; Cells, Cultured; Deoxyuracil Nucleotides; Embryo, Mammalian; Female; Mice; MicroRNAs; Molecular Sequence Data; Nucleic Acid Conformation; RNA Editing; RNA Nucleotidyltransferases; RNA Stability; RNA, Messenger; RNA, Small Untranslated

Pulmonary alveolar proteinosis caused by deletion of the GM-CSFRalpha gene in the X chromosome pseudoautosomal region 1. - Martinez-Moczygemba, Margarita; Doan, Minh L; Elidemir, Okan; Fan, Leland L; Cheung, Sau Wai; Lei, Jonathan T; Moore, James P; Tavana, Ghamartaj; Lewis, Lora R; Zhu, Yiming; Donna M Muzny; Richard A Gibbs; et al. (J Exp Med, 2008)
Pulmonary alveolar proteinosis (PAP) is a rare lung disorder in which surfactant-derived lipoproteins accumulate excessively within pulmonary alveoli, causing severe respiratory distress. The importance of granulocyte/macrophage colony-stimulating factor (GM-CSF) in the pathogenesis of PAP has been confirmed in humans and mice, wherein GM-CSF signaling is required for pulmonary alveolar macrophage catabolism of surfactant. PAP is caused by disruption of GM-CSF signaling in these cells, and is usually caused by neutralizing autoantibodies to GM-CSF or is secondary to other underlying diseases. Rarely, genetic defects in surfactant proteins or the common beta chain for the GM-CSF receptor (GM-CSFR) are causal. Using a combination of cellular, molecular, and genomic approaches, we provide the first evidence that PAP can result from a genetic deficiency of the GM-CSFR alpha chain, encoded in the X-chromosome pseudoautosomal region 1.
Keywords: Animals; CD11b Antigen; Child, Preschool; Chromosomes, Human, X; Exons; Female; Genotype; Granulocyte-Macrophage Colony-Stimulating Factor; Humans; In Situ Hybridization, Fluorescence; Karyotyping; Male; Mice; Monocytes; Pulmonary Alveolar Proteinosis; Pulmonary Surfactants; Receptors, Granulocyte-Macrophage Colony-Stimulating Factor; Signal Transduction; Turner Syndrome

Somatic mutations affect key pathways in lung adenocarcinoma. - Ding, Li; Getz, Gad; Wheeler, David A; Mardis, Elaine R; McLellan, Michael D; Cibulskis, Kristian; Sougnez, Carrie; Greulich, Heidi; Donna M Muzny; Morgan, Margaret B; Fulton, Lucinda; Fulton, Robert S; et al. (Nature, 2008)
Determining the genetic basis of cancer requires comprehensive analyses of large collections of histopathologically well-classified primary tumours. Here we report the results of a collaborative study to discover somatic mutations in 188 human lung adenocarcinomas. DNA sequencing of 623 genes with known or potential relationships to cancer revealed more than 1,000 somatic mutations across the samples. Our analysis identified 26 genes that are mutated at significantly high frequencies and thus are probably involved in carcinogenesis. The frequently mutated genes include tyrosine kinases, among them the EGFR homologue ERBB4; multiple ephrin receptor genes, notably EPHA3; vascular endothelial growth factor receptor KDR; and NTRK genes. These data provide evidence of somatic mutations in primary lung adenocarcinoma for several tumour suppressor genes involved in other cancers--including NF1, APC, RB1 and ATM--and for sequence changes in PTPRD as well as the frequently deleted gene LRP1B. The observed mutational profiles correlate with clinical features, smoking status and DNA repair defects. These results are reinforced by data integration including single nucleotide polymorphism array and gene expression array. Our findings shed further light on several important signalling pathways involved in lung adenocarcinoma, and suggest new molecular targets for treatment.
Keywords: Adenocarcinoma, Bronchiolo-Alveolar; Female; Gene Dosage; Gene Expression Regulation, Neoplastic; Genes, Tumor Suppressor; Humans; Lung Neoplasms; Male; Mutation; Proto-Oncogenes

Analyses of deep mammalian sequence alignments and constraint predictions for 1% of the human genome. - Margulies, Elliott H; Cooper, Gregory M; Asimenos, George; Thomas, Daryl J; Dewey, Colin N; Siepel, Adam; Birney, Ewan; Keefe, Damian; Schwartz, Ariel S; Hou, Minmei; Taylor, James; Nikolaev, Sergey; et al. (Genome Res, 2007)
A key component of the ongoing ENCODE project involves rigorous comparative sequence analyses for the initially targeted 1% of the human genome. Here, we present orthologous sequence generation, alignment, and evolutionary constraint analyses of 23 mammalian species for all ENCODE targets. Alignments were generated using four different methods; comparisons of these methods reveal large-scale consistency but substantial differences in terms of small genomic rearrangements, sensitivity (sequence coverage), and specificity (alignment accuracy). We describe the quantitative and qualitative trade-offs concomitant with alignment method choice and the levels of technical error that need to be accounted for in applications that require multisequence alignments. Using the generated alignments, we identified constrained regions using three different methods. While the different constraint-detecting methods are in general agreement, there are important discrepancies relating to both the underlying alignments and the specific algorithms. However, by integrating the results across the alignments and constraint-detecting methods, we produced constraint annotations that were found to be robust based on multiple independent measures. Analyses of these annotations illustrate that most classes of experimentally annotated functional elements are enriched for constrained sequences; however, large portions of each class (with the exception of protein-coding sequences) do not overlap constrained regions. The latter elements might not be under primary sequence constraint, might not be constrained across all mammals, or might have expendable molecular functions. Conversely, 40% of the constrained sequences do not overlap any of the functional elements that have been experimentally identified. Together, these findings demonstrate and quantify how many genomic functional elements await basic molecular characterization.
Keywords: Animals; Evolution, Molecular; Genome, Human; Human Genome Project; Humans; Mammals; Open Reading Frames; Phylogeny; Sequence Alignment

Demographic histories and patterns of linkage disequilibrium in Chinese and Indian rhesus macaques. - Hernandez, Ryan D; Hubisz, Melissa J; David A Wheeler; Smith, David G; Ferguson, Betsy; Jeffrey Rogers; Nazareth, Lynne; Indap, Amit; Bourquin, Traci; McPherson, John; Donna M Muzny; Richard A Gibbs; et al. (Science, 2007)
To understand the demographic history of rhesus macaques (Macaca mulatta) and document the extent of linkage disequilibrium (LD) in the genome, we partially resequenced five Encyclopedia of DNA Elements regions in 9 Chinese and 38 captive-born Indian rhesus macaques. Population genetic analyses of the 1467 single-nucleotide polymorphisms discovered suggest that the two populations separated about 162,000 years ago, with the Chinese population tripling in size since then and the Indian population eventually shrinking by a factor of four. Using coalescent simulations, we confirmed that these inferred demographic events explain a much faster decay of LD in Chinese (r(2) approximately 0.15 at 10 kilobases) versus Indian (r(2) approximately 0.52 at 10 kilobases) macaque populations.
Keywords: Animals; China; Demography; DNA, Mitochondrial; Genetics, Medical; Humans; India; Linkage Disequilibrium; Macaca mulatta; Polymorphism, Single Nucleotide

Direct selection of human genomic loci by microarray hybridization. - Albert, Thomas J; Molla, Michael N; Donna M Muzny; Nazareth, Lynne; Wheeler, David; Song, Xingzhi; Richmond, Todd A; Middle, Chris M; Rodesch, Matthew J; Packard, Charles J; Weinstock, George M; Richard A Gibbs (Nat Methods, 2007)
We applied high-density microarrays to the enrichment of specific sequences from the human genome for high-throughput sequencing. After capture of 6,726 approximately 500-base 'exon' segments, and of 'locus-specific' regions ranging in size from 200 kb to 5 Mb, followed by sequencing on a 454 Life Sciences FLX sequencer, most sequence reads represented selection targets. These direct selection methods supersede multiplex PCR for the large-scale analysis of genomic regions.
Keywords: BRCA1 Protein; Cell Line, Tumor; Gene Library; Genome, Human; Humans; Nucleic Acid Hybridization; Oligodeoxyribonucleotides; Oligonucleotide Array Sequence Analysis; Polymerase Chain Reaction; Polymorphism, Single Nucleotide; Sequence Analysis, DNA

Evolutionary and biomedical insights from the rhesus macaque genome. - Richard A Gibbs; Jeffrey Rogers; Katze, Michael G; Bumgarner, Roger; Weinstock, George M; Mardis, Elaine R; Remington, Karin A; Strausberg, Robert L; Venter, J Craig; Wilson, Richard K; Batzer, Mark A; Bustamante, Carlos D; et al. (Science, 2007)
The rhesus macaque (Macaca mulatta) is an abundant primate species that diverged from the ancestors of Homo sapiens about 25 million years ago. Because they are genetically and physiologically similar to humans, rhesus monkeys are the most widely used nonhuman primate in basic and applied biomedical research. We determined the genome sequence of an Indian-origin Macaca mulatta female and compared the data with chimpanzees and humans to reveal the structure of ancestral primate genomes and to identify evidence for positive selection and lineage-specific expansions and contractions of gene families. A comparison of sequences from individual animals was used to investigate their underlying genetic diversity. The complete description of the macaque genome blueprint enhances the utility of this animal model for biomedical research and improves our understanding of the basic biology of the species.
Keywords: Animals; Biomedical Research; Evolution, Molecular; Female; Gene Duplication; Gene Rearrangement; Genetic Diseases, Inborn; Genetic Variation; Genome; Humans; Macaca mulatta; Male; Multigene Family; Mutation; Pan troglodytes; Sequence Analysis, DNA; Species Specificity

Genome-wide detection and characterization of positive selection in human populations. - Sabeti, Pardis C; Varilly, Patrick; Fry, Ben; Lohmueller, Jason; Hostetter, Elizabeth; Cotsapas, Chris; Xie, Xiaohui; Byrne, Elizabeth H; McCarroll, Steven A; Gaudet, Rachelle; Schaffner, Stephen F; Lander, Eric S; et al. (Nature, 2007)
With the advent of dense maps of human genetic variation, it is now possible to detect positive natural selection across the human genome. Here we report an analysis of over 3 million polymorphisms from the International HapMap Project Phase 2 (HapMap2). We used 'long-range haplotype' methods, which were developed to identify alleles segregating in a population that have undergone recent selection, and we also developed new methods that are based on cross-population comparisons to discover alleles that have swept to near-fixation within a population. The analysis reveals more than 300 strong candidate regions. Focusing on the strongest 22 regions, we develop a heuristic for scrutinizing these regions to identify candidate targets of selection. In a complementary analysis, we identify 26 non-synonymous, coding, single nucleotide polymorphisms showing regional evidence of positive selection. Examination of these candidates highlights three cases in which two genes in a common biological process have apparently undergone positive selection in the same population:LARGE and DMD, both related to infection by the Lassa virus, in West Africa;SLC24A5 and SLC45A2, both involved in skin pigmentation, in Europe; and EDAR and EDA2R, both involved in development of hair follicles, in Asia.
Keywords: Antiporters; Edar Receptor; Gene Frequency; Genetics, Population; Genome, Human; Geography; Haplotypes; Humans; Models, Molecular; Polymorphism, Single Nucleotide; Protein Structure, Tertiary; Selection, Genetic

Identification and analysis of functional elements in 1% of the human genome by the ENCODE pilot project. - Birney, Ewan; Stamatoyannopoulos, John A; Dutta, Anindya; Guigó, Roderic; Gingeras, Thomas R; Margulies, Elliott H; Weng, Zhiping; Snyder, Michael; Dermitzakis, Emmanouil T; Thurman, Robert E; Kuehn, Michael S; Taylor, Christopher M; et al. (Nature, 2007)
We report the generation and analysis of functional data from multiple, diverse experiments performed on a targeted 1% of the human genome as part of the pilot phase of the ENCODE Project. These data have been further integrated and augmented by a number of evolutionary and computational analyses. Together, our results advance the collective knowledge about human genome function in several major areas. First, our studies provide convincing evidence that the genome is pervasively transcribed, such that the majority of its bases can be found in primary transcripts, including non-protein-coding transcripts, and those that extensively overlap one another. Second, systematic examination of transcriptional regulation has yielded new understanding about transcription start sites, including their relationship to specific regulatory sequences and features of chromatin accessibility and histone modification. Third, a more sophisticated view of chromatin structure has emerged, including its inter-relationship with DNA replication and transcriptional regulation. Finally, integration of these new sources of information, in particular with respect to mammalian evolution based on inter- and intra-species sequence comparisons, has yielded new mechanistic and evolutionary insights concerning the functional landscape of the human genome. Together, these studies are defining a path for pursuit of a more comprehensive characterization of human genome function.
Keywords: Chromatin; Chromatin Immunoprecipitation; Conserved Sequence; DNA Replication; Evolution, Molecular; Exons; Genetic Variation; Genome, Human; Genomics; Heterozygote; Histones; Humans; Pilot Projects; Protein Binding; Regulatory Sequences, Nucleic Acid; RNA, Messenger; RNA, Untranslated; Transcription Factors; Transcription Initiation Site; Transcription, Genetic

Paradoxical DNA repair and peroxide resistance gene conservation in Bacillus pumilus SAFR-032. - Gioia, Jason; Yerrapragada, Shailaja; Qin, Xiang; Jiang, Huaiyang; Igboeli, Okezie C; Donna M Muzny; Dugan-Rocha, Shannon; Ding, Yan; Hawes, Alicia; Liu, Wen; Perez, Lesette; Kovar, Christie; et al. (PLoS One, 2007)
BACKGROUND: Bacillus spores are notoriously resistant to unfavorable conditions such as UV radiation, gamma-radiation, H2O2, desiccation, chemical disinfection, or starvation. Bacillus pumilus SAFR-032 survives standard decontamination procedures of the Jet Propulsion Lab spacecraft assembly facility, and both spores and vegetative cells of this strain exhibit elevated resistance to UV radiation and H2O2 compared to other Bacillus species. PRINCIPAL FINDINGS: The genome of B. pumilus SAFR-032 was sequenced and annotated. Lists of genes relevant to DNA repair and the oxidative stress response were generated and compared to B. subtilis and B. licheniformis. Differences in conservation of genes, gene order, and protein sequences are highlighted because they potentially explain the extreme resistance phenotype of B. pumilus. The B. pumilus genome includes genes not found in B. subtilis or B. licheniformis and conserved genes with sequence divergence, but paradoxically lacks several genes that function in UV or H2O2 resistance in other Bacillus species. SIGNIFICANCE: This study identifies several candidate genes for further research into UV and H2O2 resistance. These findings will help explain the resistance of B. pumilus and are applicable to understanding sterilization survival strategies of microbes.
Keywords: Bacillus; DNA Repair; Drug Resistance, Bacterial; Gamma Rays; Genes, Bacterial; Genome, Bacterial; Hydrogen Peroxide; Oxidative Stress; Sequence Analysis, DNA; Spores, Bacterial; Ultraviolet Rays

A second generation human haplotype map of over 3.1 million SNPs. - Frazer, Kelly A; Ballinger, Dennis G; Cox, David R; Hinds, David A; Stuve, Laura L; Richard A Gibbs; Belmont, John W; Boudreau, Andrew; Hardenbol, Paul; Leal, Suzanne M; Pasternak, Shiran; Wheeler, David A; et al. (Nature, 2007)
We describe the Phase II HapMap, which characterizes over 3.1 million human single nucleotide polymorphisms (SNPs) genotyped in 270 individuals from four geographically diverse populations and includes 25-35% of common SNP variation in the populations surveyed. The map is estimated to capture untyped common variation with an average maximum r2 of between 0.9 and 0.96 depending on population. We demonstrate that the current generation of commercial genome-wide genotyping products captures common Phase II SNPs with an average maximum r2 of up to 0.8 in African and up to 0.95 in non-African populations, and that potential gains in power in association studies can be obtained through imputation. These data also reveal novel aspects of the structure of linkage disequilibrium. We show that 10-30% of pairs of individuals within a population share at least one region of extended genetic identity arising from recent ancestry and that up to 1% of all common variants are untaggable, primarily because they lie within recombination hotspots. We show that recombination rates vary systematically around genes and between genes of different function. Finally, we demonstrate increased differentiation at non-synonymous, compared to synonymous, SNPs, resulting from systematic differences in the strength or efficacy of natural selection between populations.
Keywords: Female; Haplotypes; Homozygote; Humans; Linkage Disequilibrium; Male; Polymorphism, Single Nucleotide; Racial Groups; Recombination, Genetic; Selection, Genetic

Subtle genetic changes enhance virulence of methicillin resistant and sensitive Staphylococcus aureus. - Highlander, Sarah K; Hultén, Kristina G; Qin, Xiang; Jiang, Huaiyang; Yerrapragada, Shailaja; Mason, Edward O; Shang, Yue; Williams, Tiffany M; Fortunov, Régine M; Liu, Yamei; Igboeli, Okezie; Petrosino, Joseph; et al. (BMC Microbiol, 2007)
BACKGROUND: Community acquired (CA) methicillin-resistant Staphylococcus aureus (MRSA) increasingly causes disease worldwide. USA300 has emerged as the predominant clone causing superficial and invasive infections in children and adults in the USA. Epidemiological studies suggest that USA300 is more virulent than other CA-MRSA. The genetic determinants that render virulence and dominance to USA300 remain unclear. RESULTS: We sequenced the genomes of two pediatric USA300 isolates: one CA-MRSA and one CA-methicillin susceptible (MSSA), isolated at Texas Children's Hospital in Houston. DNA sequencing was performed by Sanger dideoxy whole genome shotgun (WGS) and 454 Life Sciences pyrosequencing strategies. The sequence of the USA300 MRSA strain was rigorously annotated. In USA300-MRSA 2658 chromosomal open reading frames were predicted and 3.1 and 27 kilobase (kb) plasmids were identified. USA300-MSSA contained a 20 kb plasmid with some homology to the 27 kb plasmid found in USA300-MRSA. Two regions found in US300-MRSA were absent in USA300-MSSA. One of these carried the arginine deiminase operon that appears to have been acquired from S. epidermidis. The USA300 sequence was aligned with other sequenced S. aureus genomes and regions unique to USA300 MRSA were identified. CONCLUSION: USA300-MRSA is highly similar to other MRSA strains based on whole genome alignments and gene content, indicating that the differences in pathogenesis are due to subtle changes rather than to large-scale acquisition of virulence factor genes. The USA300 Houston isolate differs from another sequenced USA300 strain isolate, derived from a patient in San Francisco, in plasmid content and a number of sequence polymorphisms. Such differences will provide new insights into the evolution of pathogens.
Keywords: Adolescent; Anti-Bacterial Agents; Base Sequence; Genomic Islands; Humans; Hydrolases; Methicillin Resistance; Molecular Epidemiology; Molecular Sequence Data; Open Reading Frames; Plasmids; Polymorphism, Genetic; Staphylococcal Infections; Staphylococcus aureus; United States

Comparative analysis of the bovine MHC class IIb sequence identifies inversion breakpoints and three unexpected genes. - Childers, C P; Newkirk, H L; Honeycutt, D A; Ramlachan, N; Donna M Muzny; Sodergren, E; Richard A Gibbs; Weinstock, G M; Womack, J E; Skow, L C (Anim Genet, 2006)
The bovine major histocompatibility complex (MHC) or BoLA is organized differently from typical mammalian MHCs in that a large portion of the class II region, called class IIb, has been transposed to a position near the centromere on bovine chromosome 23. Gene mapping indicated that the rearrangement resulted from a single inversion, but the boundaries and gene content of the inverted segment have not been fully determined. Here, we report the genomic sequence of BoLA IIb. Comparative sequence analysis with the human MHC revealed that the proximal inversion breakpoint occurred approximately 2.5 kb from the 3' end of the glutamate-cysteine ligase, catalytic subunit (GCLC) locus and that the distal breakpoint occurred about 2 kb from the 5' end from a divergent class IIDRbeta-like sequence designated DSB. Gene content, order and orientation of BoLA IIb are consistent with the single inversion hypothesis when compared with the corresponding region of the human class II MHC (HLA class II). Differences with HLA include the presence of a single histone H2B gene located between the proteasome subunit, beta type, 9 (PSMB9) and DMB loci and a duplicated TAP2 with a variant splice site. BoLA IIb spans approximately 450 kb DNA, with 20 apparently intact genes and no obvious pseudogenes. The region contains 227 simple sequence repeats (SSRs) and approximately 167 kb of retroviral-related repetitive DNA. Nineteen of the 20 genes identified in silico are supported by bovine EST data indicating that the functional gene content of BoLA IIb has not been diminished because it has been transposed from the remainder of BoLA genes.
Keywords: Animals; Cattle; Chromosome Inversion; Chromosomes, Mammalian; Contig Mapping; Evolution, Molecular; Genes, MHC Class II; Histones; Humans; Molecular Sequence Data; Sequence Analysis, DNA

The DNA sequence, annotation and analysis of human chromosome 3. - Donna M Muzny; Steven E Scherer; Kaul, Rajinder; Wang, Jing; Yu, Jun; Sudbrak, Ralf; Buhay, Christian J; Rui Chen; Cree, Andrew; Ding, Yan; Dugan-Rocha, Shannon; Gill, Rachel; et al. (Nature, 2006)
After the completion of a draft human genome sequence, the International Human Genome Sequencing Consortium has proceeded to finish and annotate each of the 24 chromosomes comprising the human genome. Here we describe the sequencing and analysis of human chromosome 3, one of the largest human chromosomes. Chromosome 3 comprises just four contigs, one of which currently represents the longest unbroken stretch of finished DNA sequence known so far. The chromosome is remarkable in having the lowest rate of segmental duplication in the genome. It also includes a chemokine receptor gene cluster as well as numerous loci involved in multiple human cancers such as the gene encoding FHIT, which contains the most common constitutive fragile site in the genome, FRA3B. Using genomic sequence from chimpanzee and rhesus macaque, we were able to characterize the breakpoints defining a large pericentric inversion that occurred some time after the split of Homininae from Ponginae, and propose an evolutionary history of the inversion.
Keywords: Animals; Base Sequence; Chromosome Breakage; Chromosome Inversion; Chromosomes, Human, Pair 3; Contig Mapping; CpG Islands; DNA, Complementary; Evolution, Molecular; Expressed Sequence Tags; Human Genome Project; Humans; Macaca mulatta; Molecular Sequence Data; Pan troglodytes; Sequence Analysis, DNA; Synteny

The finished DNA sequence of human chromosome 12. - Scherer, Steven E; Donna M Muzny; Buhay, Christian J; Rui Chen; Cree, Andrew; Ding, Yan; Dugan-Rocha, Shannon; Gill, Rachel; Gunaratne, Preethi; R. Alan Harris; Hawes, Alicia C; Hernandez, Judith; et al. (Nature, 2006)
Human chromosome 12 contains more than 1,400 coding genes and 487 loci that have been directly implicated in human disease. The q arm of chromosome 12 contains one of the largest blocks of linkage disequilibrium found in the human genome. Here we present the finished sequence of human chromosome 12, which has been finished to high quality and spans approximately 132 megabases, representing approximately 4.5% of the human genome. Alignment of the human chromosome 12 sequence across vertebrates reveals the origin of individual segments in chicken, and a unique history of rearrangement through rodent and primate lineages. The rate of base substitutions in recent evolutionary history shows an overall slowing in hominids compared with primates and rodents.
Keywords: Animals; Base Composition; Chromosomes, Human, Pair 12; CpG Islands; Evolution, Molecular; Expressed Sequence Tags; Genes; Humans; Linkage Disequilibrium; Microsatellite Repeats; Molecular Sequence Data; Mutagenesis, Insertional; Pan troglodytes; Sequence Analysis, DNA; Sequence Deletion; Short Interspersed Nucleotide Elements; Synteny

The genome of the sea urchin Strongylocentrotus purpuratus. - Sodergren, Erica; Weinstock, George M; Davidson, Eric H; Cameron, R Andrew; Richard A Gibbs; Angerer, Robert C; Angerer, Lynne M; Arnone, Maria Ina; Burgess, David R; Burke, Robert D; Coffman, James A; Dean, Michael; et al. (Science, 2006)
We report the sequence and analysis of the 814-megabase genome of the sea urchin Strongylocentrotus purpuratus, a model for developmental and systems biology. The sequencing strategy combined whole-genome shotgun and bacterial artificial chromosome (BAC) sequences. This use of BAC clones, aided by a pooling strategy, overcame difficulties associated with high heterozygosity of the genome. The genome encodes about 23,300 genes, including many previously thought to be vertebrate innovations or known only outside the deuterostomes. This echinoderm genome provides an evolutionary outgroup for the chordates and yields insights into the evolution of deuterostomes.
Keywords: Animals; Calcification, Physiologic; Cell Adhesion Molecules; Complement Activation; Computational Biology; Embryonic Development; Evolution, Molecular; Gene Expression Regulation, Developmental; Genes; Genome; Immunity, Innate; Immunologic Factors; Male; Nervous System Physiological Phenomena; Proteins; Sequence Analysis, DNA; Signal Transduction; Strongylocentrotus purpuratus; Transcription Factors

The genome sequence of Mannheimia haemolytica A1: insights into virulence, natural competence, and Pasteurellaceae phylogeny. - Gioia, Jason; Qin, Xiang; Jiang, Huaiyang; Clinkenbeard, Kenneth; Lo, Reggie; Liu, Yamei; Fox, George E; Yerrapragada, Shailaja; McLeod, Michael P; McNeill, Thomas Z; Hemphill, Lisa; Sodergren, Erica; et al. (J Bacteriol, 2006)
The draft genome sequence of Mannheimia haemolytica A1, the causative agent of bovine respiratory disease complex (BRDC), is presented. Strain ATCC BAA-410, isolated from the lung of a calf with BRDC, was the DNA source. The annotated genome includes 2,839 coding sequences, 1,966 of which were assigned a function and 436 of which are unique to M. haemolytica. Through genome annotation many features of interest were identified, including bacteriophages and genes related to virulence, natural competence, and transcriptional regulation. In addition to previously described virulence factors, M. haemolytica encodes adhesins, including the filamentous hemagglutinin FhaB and two trimeric autotransporter adhesins. Two dual-function immunoglobulin-protease/adhesins are also present, as is a third immunoglobulin protease. Genes related to iron acquisition and drug resistance were identified and are likely important for survival in the host and virulence. Analysis of the genome indicates that M. haemolytica is naturally competent, as genes for natural competence and DNA uptake signal sequences (USS) are present. Comparison of competence loci and USS in other species in the family Pasteurellaceae indicates that M. haemolytica, Actinobacillus pleuropneumoniae, and Haemophilus ducreyi form a lineage distinct from other Pasteurellaceae. This observation was supported by a phylogenetic analysis using sequences of predicted housekeeping genes.
Keywords: Actinobacillus pleuropneumoniae; Adhesins, Bacterial; DNA, Bacterial; Gene Expression Regulation, Bacterial; Genome, Bacterial; Haemophilus ducreyi; Mannheimia haemolytica; Phylogeny; Prophages; Sequence Analysis, DNA; Transcription, Genetic; Transformation, Bacterial; Virulence

Comparative genome sequencing of Drosophila pseudoobscura: chromosomal, gene, and cis-element evolution. - Richards, Stephen; Liu, Yue; Bettencourt, Brian R; Hradecky, Pavel; Letovsky, Stan; Nielsen, Rasmus; Thornton, Kevin; Hubisz, Melissa J; Rui Chen; Meisel, Richard P; Couronne, Olivier; Hua, Sujun; et al. (Genome Res, 2005)
We have sequenced the genome of a second Drosophila species, Drosophila pseudoobscura, and compared this to the genome sequence of Drosophila melanogaster, a primary model organism. Throughout evolution the vast majority of Drosophila genes have remained on the same chromosome arm, but within each arm gene order has been extensively reshuffled, leading to a minimum of 921 syntenic blocks shared between the species. A repetitive sequence is found in the D. pseudoobscura genome at many junctions between adjacent syntenic blocks. Analysis of this novel repetitive element family suggests that recombination between offset elements may have given rise to many paracentric inversions, thereby contributing to the shuffling of gene order in the D. pseudoobscura lineage. Based on sequence similarity and synteny, 10,516 putative orthologs have been identified as a core gene set conserved over 25-55 million years (Myr) since the pseudoobscura/melanogaster divergence. Genes expressed in the testes had higher amino acid sequence divergence than the genome-wide average, consistent with the rapid evolution of sex-specific proteins. Cis-regulatory sequences are more conserved than random and nearby sequences between the species--but the difference is slight, suggesting that the evolution of cis-regulatory elements is flexible. Overall, a pattern of repeat-mediated chromosomal rearrangement, and high coadaptation of both male genes and cis-regulatory sequences emerges as important themes of genome divergence between these species of Drosophila.
Keywords: Animals; Chromosome Breakage; Chromosome Inversion; Chromosome Mapping; Chromosomes; Conserved Sequence; Drosophila; Drosophila melanogaster; Enhancer Elements, Genetic; Evolution, Molecular; Gene Rearrangement; Genes, Insect; Genetic Variation; Genome; Molecular Sequence Data; Predictive Value of Tests; Repetitive Sequences, Nucleic Acid; Sequence Analysis, DNA

The DNA sequence of the human X chromosome. - Ross, Mark T; Grafham, Darren V; Coffey, Alison J; Scherer, Steven; McLay, Kirsten; Donna M Muzny; Platzer, Matthias; Howell, Gareth R; Burrows, Christine; Bird, Christine P; Frankish, Adam; Lovell, Frances L; et al. (Nature, 2005)
The human X chromosome has a unique biology that was shaped by its evolution as the sex chromosome shared by males and females. We have determined 99.3% of the euchromatic sequence of the X chromosome. Our analysis illustrates the autosomal origin of the mammalian sex chromosomes, the stepwise process that led to the progressive loss of recombination between X and Y, and the extent of subsequent degradation of the Y chromosome. LINE1 repeat elements cover one-third of the X chromosome, with a distribution that is consistent with their proposed role as way stations in the process of X-chromosome inactivation. We found 1,098 genes in the sequence, of which 99 encode proteins expressed in testis and in various tumour types. A disproportionately high number of mendelian diseases are documented for the X chromosome. Of this number, 168 have been explained by mutations in 113 X-linked genes, which in many cases were characterized with the aid of the DNA sequence.
Keywords: Animals; Antigens, Neoplasm; Centromere; Chromosomes, Human, X; Chromosomes, Human, Y; Contig Mapping; Crossing Over, Genetic; Dosage Compensation, Genetic; Evolution, Molecular; Female; Genetic Linkage; Genetics, Medical; Genomics; Humans; Male; Polymorphism, Single Nucleotide; Repetitive Sequences, Nucleic Acid; RNA; Sequence Analysis, DNA; Sequence Homology, Nucleic Acid; Testis

The genome of the social amoeba Dictyostelium discoideum. - Eichinger, L; Pachebat, J A; Glöckner, G; Rajandream, M-A; Sucgang, R; Berriman, M; Song, J; Olsen, R; Szafranski, K; Xu, Q; Tunggal, B; Kummerfeld, S; et al. (Nature, 2005)
The social amoebae are exceptional in their ability to alternate between unicellular and multicellular forms. Here we describe the genome of the best-studied member of this group, Dictyostelium discoideum. The gene-dense chromosomes of this organism encode approximately 12,500 predicted proteins, a high proportion of which have long, repetitive amino acid tracts. There are many genes for polyketide synthases and ABC transporters, suggesting an extensive secondary metabolism for producing and exporting small molecules. The genome is rich in complex repeats, one class of which is clustered and may serve as centromeres. Partial copies of the extrachromosomal ribosomal DNA (rDNA) element are found at the ends of each chromosome, suggesting a novel telomere structure and the use of a common mechanism to maintain both the rDNA and chromosomal termini. A proteome-based phylogeny shows that the amoebozoa diverged from the animal-fungal lineage after the plant-animal split, but Dictyostelium seems to have retained more of the diversity of the ancestral genome than have plants, animals or fungi.
Keywords: Animals; ATP-Binding Cassette Transporters; Base Composition; Cell Adhesion; Cell Movement; Centromere; Conserved Sequence; Dictyostelium; DNA Transposable Elements; DNA, Ribosomal; Eukaryotic Cells; Gene Duplication; Gene Transfer, Horizontal; Genome; Genomics; Humans; Molecular Sequence Data; Phylogeny; Proteome; Protozoan Proteins; Repetitive Sequences, Nucleic Acid; RNA, Transfer; Sequence Analysis, DNA; Signal Transduction; Social Behavior; Telomere

Complete genome sequence of Rickettsia typhi and comparison with sequences of other rickettsiae. - McLeod, Michael P; Qin, Xiang; Karpathy, Sandor E; Gioia, Jason; Highlander, Sarah K; Fox, George E; McNeill, Thomas Z; Jiang, Huaiyang; Donna M Muzny; Jacob, Leni S; Hawes, Alicia C; Sodergren, Erica; et al. (J Bacteriol, 2004)
Rickettsia typhi, the causative agent of murine typhus, is an obligate intracellular bacterium with a life cycle involving both vertebrate and invertebrate hosts. Here we present the complete genome sequence of R. typhi (1,111,496 bp) and compare it to the two published rickettsial genome sequences: R. prowazekii and R. conorii. We identified 877 genes in R. typhi encoding 3 rRNAs, 33 tRNAs, 3 noncoding RNAs, and 838 proteins, 3 of which are frameshifts. In addition, we discovered more than 40 pseudogenes, including the entire cytochrome c oxidase system. The three rickettsial genomes share 775 genes: 23 are found only in R. prowazekii and R. typhi, 15 are found only in R. conorii and R. typhi, and 24 are unique to R. typhi. Although most of the genes are colinear, there is a 35-kb inversion in gene order, which is close to the replication terminus, in R. typhi, compared to R. prowazekii and R. conorii. In addition, we found a 124-kb R. typhi-specific inversion, starting 19 kb from the origin of replication, compared to R. prowazekii and R. conorii. Inversions in this region are also seen in the unpublished genome sequences of R. sibirica and R. rickettsii, indicating that this region is a hot spot for rearrangements. Genome comparisons also revealed a 12-kb insertion in the R. prowazekii genome, relative to R. typhi and R. conorii, which appears to have occurred after the typhus (R. prowazekii and R. typhi) and spotted fever (R. conorii) groups diverged. The three-way comparison allowed further in silico analysis of the SpoT split genes, leading us to propose that the stringent response system is still functional in these rickettsiae.
Keywords: Chromosome Inversion; DNA, Bacterial; Electron Transport Complex IV; Frameshifting, Ribosomal; Gene Expression Regulation, Bacterial; Gene Rearrangement; Genes, Bacterial; Genes, rRNA; Genome, Bacterial; Genomics; Molecular Sequence Data; Pseudogenes; Rickettsia; Rickettsia conorii; Rickettsia typhi; RNA, Transfer; RNA, Untranslated; Sequence Analysis, DNA; Sequence Homology; Synteny

Genome sequence of the Brown Norway rat yields insights into mammalian evolution. - Richard A Gibbs; Weinstock, George M; Metzker, Michael L; Donna M Muzny; Sodergren, Erica J; Scherer, Steven; Scott, Graham; Steffen, David; Worley, Kim C; Burch, Paula E; Okwuonu, Geoffrey; Hines, Sandra; et al. (Nature, 2004)
The laboratory rat (Rattus norvegicus) is an indispensable tool in experimental medicine and drug development, having made inestimable contributions to human health. We report here the genome sequence of the Brown Norway (BN) rat strain. The sequence represents a high-quality 'draft' covering over 90% of the genome. The BN rat sequence is the third complete mammalian genome to be deciphered, and three-way comparisons with the human and mouse genomes resolve details of mammalian evolution. This first comprehensive analysis includes genes and proteins and their relation to human disease, repeated sequences, comparative genome-wide studies of mammalian orthologous chromosomal regions and rearrangement breakpoints, reconstruction of ancestral karyotypes and the events leading to existing species, rates of variation, and lineage-specific and lineage-independent evolutionary events such as expansion of gene families, orthology relations and protein evolution.
Keywords: Animals; Base Composition; Centromere; Chromosomes, Mammalian; CpG Islands; DNA Transposable Elements; DNA, Mitochondrial; Evolution, Molecular; Gene Duplication; Genome; Genomics; Humans; Introns; Male; Mice; Models, Molecular; Mutagenesis; Polymorphism, Single Nucleotide; Rats; Rats, Inbred BN; Regulatory Sequences, Nucleic Acid; Retroelements; RNA Splice Sites; RNA, Untranslated; Sequence Analysis, DNA; Telomere

The status, quality, and expansion of the NIH full-length cDNA project: the Mammalian Gene Collection (MGC). - Gerhard, Daniela S; Wagner, Lukas; Feingold, Elise A; Shenmen, Carolyn M; Grouse, Lynette H; Schuler, Greg; Klein, Steven L; Old, Susan; Rasooly, Rebekah; Good, Peter; Guyer, Mark; Peck, Allison M; et al. (Genome Res, 2004)
The National Institutes of Health's Mammalian Gene Collection (MGC) project was designed to generate and sequence a publicly accessible cDNA resource containing a complete open reading frame (ORF) for every human and mouse gene. The project initially used a random strategy to select clones from a large number of cDNA libraries from diverse tissues. Candidate clones were chosen based on 5'-EST sequences, and then fully sequenced to high accuracy and analyzed by algorithms developed for this project. Currently, more than 11,000 human and 10,000 mouse genes are represented in MGC by at least one clone with a full ORF. The random selection approach is now reaching a saturation point, and a transition to protocols targeted at the missing transcripts is now required to complete the mouse and human collections. Comparison of the sequence of the MGC clones to reference genome sequences reveals that most cDNA clones are of very high sequence quality, although it is likely that some cDNAs may carry missense variants as a consequence of experimental artifact, such as PCR, cloning, or reverse transcriptase errors. Recently, a rat cDNA component was added to the project, and ongoing frog (Xenopus) and zebrafish (Danio) cDNA projects were expanded to take advantage of the high-throughput MGC pipeline.
Keywords: Animals; Cloning, Molecular; Computational Biology; DNA Primers; DNA, Complementary; Gene Library; Humans; Mice; National Institutes of Health (U.S.); Open Reading Frames; Rats; United States; Xenopus laevis; Zebrafish

Sequence and structure of the extrachromosomal palindrome encoding the ribosomal RNA genes in Dictyostelium. - Sucgang, Richard; Chen, Guokai; Liu, Wen; Lindsay, Ryan; Lu, Jing; Donna M Muzny; Shaulsky, Gad; Loomis, William; Richard A Gibbs; Kuspa, Adam (Nucleic Acids Res, 2003)
Ribosomal RNAs (rRNAs) are encoded by multicopy families of identical genes. In Dictyostelium and other protists, the rDNA is carried on extrachromosomal palindromic elements that comprise up to 20% of the nuclear DNA. We present the sequence of the 88 kb Dictyostelium rDNA element, noting that the rRNA genes are likely to be the only transcribed regions. By interrogating a library of ordered YAC clones, we provide evidence for a chromosomal copy of the rDNA on chromosome 4. This locus may provide master copies for the stable transmission of the extrachromosomal elements. The extrachromosomal elements were also found to form chromosome-sized clusters of DNA within nuclei of nocodazole-treated cells arrested in mitosis. These clusters resemble true chromosomes and may allow the efficient segregation of the rDNA during mitosis. These rDNA clusters may also explain the cytological observations of a seventh chromosome in this organism.
Keywords: Animals; Chromosome Mapping; Dictyostelium; DNA, Protozoan; In Situ Hybridization, Fluorescence; Molecular Sequence Data; Plasmids; RNA, Ribosomal; Sequence Analysis, DNA

Finishing a whole-genome shotgun: release 3 of the Drosophila melanogaster euchromatic genome sequence. - Celniker, Susan E; Wheeler, David A; Kronmiller, Brent; Carlson, Joseph W; Halpern, Aaron; Patel, Sandeep; Adams, Mark; Champe, Mark; Dugan, Shannon P; Frise, Erwin; Hodgson, Ann; George, Reed A; et al. (Genome Biol, 2002)
BACKGROUND: The Drosophila melanogaster genome was the first metazoan genome to have been sequenced by the whole-genome shotgun (WGS) method. Two issues relating to this achievement were widely debated in the genomics community: how correct is the sequence with respect to base-pair (bp) accuracy and frequency of assembly errors? And, how difficult is it to bring a WGS sequence to the accepted standard for finished sequence? We are now in a position to answer these questions. RESULTS: Our finishing process was designed to close gaps, improve sequence quality and validate the assembly. Sequence traces derived from the WGS and draft sequencing of individual bacterial artificial chromosomes (BACs) were assembled into BAC-sized segments. These segments were brought to high quality, and then joined to constitute the sequence of each chromosome arm. Overall assembly was verified by comparison to a physical map of fingerprinted BAC clones. In the current version of the 116.9 Mb euchromatic genome, called Release 3, the six euchromatic chromosome arms are represented by 13 scaffolds with a total of 37 sequence gaps. We compared Release 3 to Release 2; in autosomal regions of unique sequence, the error rate of Release 2 was one in 20,000 bp. CONCLUSIONS: The WGS strategy can efficiently produce a high-quality sequence of a metazoan genome while generating the reagents required for sequence finishing. However, the initial method of repeat assembly was flawed. The sequence we report here, Release 3, is a reliable resource for molecular genetic experimentation and computational analysis.
Keywords: Animals; Drosophila melanogaster; Euchromatin; Genome; Physical Chromosome Mapping; Research Design; Sequence Analysis, DNA; X Chromosome

Generation and initial analysis of more than 15,000 full-length human and mouse cDNA sequences. - Strausberg, Robert L; Feingold, Elise A; Grouse, Lynette H; Derge, Jeffery G; Klausner, Richard D; Collins, Francis S; Wagner, Lukas; Shenmen, Carolyn M; Schuler, Gregory D; Altschul, Stephen F; Zeeberg, Barry; Buetow, Kenneth H; et al. (Proc Natl Acad Sci U S A, 2002)
The National Institutes of Health Mammalian Gene Collection (MGC) Program is a multiinstitutional effort to identify and sequence a cDNA clone containing a complete ORF for each human and mouse gene. ESTs were generated from libraries enriched for full-length cDNAs and analyzed to identify candidate full-ORF clones, which then were sequenced to high accuracy. The MGC has currently sequenced and verified the full ORF for a nonredundant set of >9,000 human and >6,000 mouse genes. Candidate full-ORF clones for an additional 7,800 human and 3,500 mouse genes also have been identified. All MGC sequences and clones are available without restriction through public databases and clone distribution networks (see http:mgc.nci.nih.gov).
Keywords: Algorithms; Animals; DNA, Complementary; Gene Library; Humans; Mice; Open Reading Frames; Sequence Analysis, DNA

Glass bead purification of plasmid template DNA for high throughput sequencing of mammalian genomes. - Dederich, Debra A; Okwuonu, Geoffrey; Garner, Toni; Denn, Amanda; Sutton, Angelica; Escotto, Michael; Martindale, Ashley; Delgado, Oliver; Donna M Muzny; Richard A Gibbs; Metzker, Michael L (Nucleic Acids Res, 2002)
To meet the new challenge of generating the draft sequences of mammalian genomes, we describe the development of a novel high throughput 96-well method for the purification of plasmid DNA template using size-fractionated, acid-washed glass beads. Unlike most previously described approaches, the current method has been designed and optimized to facilitate the direct binding of alcohol-precipitated plasmid DNA to glass beads from alkaline lysed bacterial cells containing the insoluble cellular aggregate material. Eliminating the tedious step of separating the cleared lysate significantly simplifies the method and improves throughput and reliability. During a 4 month period of 96-capillary DNA sequencing of the Rattus norvegicus genome at the Baylor College of Medicine Human Genome Sequencing Center, the average success rate and read length derived from >1 800 000 plasmid DNA templates prepared by the direct lysis/glass bead method were 82.2% and 516 bases, respectively. The cost of this direct lysis/glass bead method in September 2001 was approximately 10 cents per clone, which is a significant cost saving in high throughput genomic sequencing efforts.
Keywords: Animals; DNA; Genome; Glass; Microspheres; Plasmids; Rats; Reproducibility of Results; Sequence Analysis, DNA

Initial sequencing and comparative analysis of the mouse genome. - Waterston, Robert H; Lindblad-Toh, Kerstin; Birney, Ewan; Rogers, Jane; Abril, Josep F; Agarwal, Pankaj; Agarwala, Richa; Ainscough, Rachel; Alexandersson, Marina; An, Peter; Antonarakis, Stylianos E; Attwood, John; et al. (Nature, 2002)
The sequence of the mouse genome is a key informational tool for understanding the contents of the human genome and a key experimental tool for biomedical research. Here, we report the results of an international collaboration to produce a high-quality draft sequence of the mouse genome. We also present an initial comparative analysis of the mouse and human genomes, describing some of the insights that can be gleaned from the two sequences. We discuss topics including the analysis of the evolutionary forces shaping the size, structure and sequence of the genomes; the conservation of large-scale synteny across most of the genomes; the much lower extent of sequence orthology covering less than half of the genomes; the proportions of the genomes under selection; the number of protein-coding genes; the expansion of gene families related to reproduction and immunity; the evolution of proteins; and the identification of intraspecies polymorphism.
Keywords: Animals; Base Composition; Chromosomes, Mammalian; Conserved Sequence; CpG Islands; Evolution, Molecular; Gene Expression Regulation; Genes; Genetic Variation; Genome; Genome, Human; Genomics; Humans; Mice; Mice, Knockout; Mice, Transgenic; Models, Animal; Multigene Family; Mutagenesis; Neoplasms; Physical Chromosome Mapping; Proteome; Pseudogenes; Quantitative Trait Loci; Repetitive Sequences, Nucleic Acid; RNA, Untranslated; Selection, Genetic; Sequence Analysis, DNA; Sex Chromosomes; Species Specificity; Synteny

Initial sequencing and analysis of the human genome. - Lander, E S; Linton, L M; Birren, B; Nusbaum, C; Zody, M C; Baldwin, J; Devon, K; Dewar, K; Doyle, M; FitzHugh, W; Funke, R; Gage, D; et al. (Nature, 2001)
The human genome holds an extraordinary trove of information about human development, physiology, medicine and evolution. Here we report the results of an international collaboration to produce and make freely available a draft sequence of the human genome. We also present an initial analysis of the data, describing some of the insights that can be gleaned from the sequence.
Keywords: Animals; Chromosome Mapping; Conserved Sequence; CpG Islands; Databases, Factual; DNA Transposable Elements; Drug Industry; Evolution, Molecular; Forecasting; GC Rich Sequence; Gene Duplication; Genes; Genetic Diseases, Inborn; Genetics, Medical; Genome, Human; Human Genome Project; Humans; Mutation; Private Sector; Proteins; Proteome; Public Sector; Repetitive Sequences, Nucleic Acid; RNA; Sequence Analysis, DNA; Species Specificity

The genome sequence of Drosophila melanogaster. - Adams, M D; Celniker, S E; Holt, R A; Evans, C A; Gocayne, J D; Amanatides, P G; Steven E Scherer; Li, P W; Hoskins, R A; Galle, R F; George, R A; Lewis, S E; et al. (Science, 2000)
The fly Drosophila melanogaster is one of the most intensively studied organisms in biology and serves as a model system for the investigation of many developmental and cellular processes common to higher eukaryotes, including humans. We have determined the nucleotide sequence of nearly all of the approximately 120-megabase euchromatic portion of the Drosophila genome using a whole-genome shotgun sequencing strategy supported by extensive clone-based sequence and a high-quality bacterial artificial chromosome physical map. Efforts are under way to close the remaining gaps; however, the sequence is of sufficient accuracy and contiguity to be declared substantially complete and to support an initial analysis of genome structure and preliminary gene annotation and interpretation. The genome encodes approximately 13,600 genes, somewhat fewer than the smaller Caenorhabditis elegans genome, but with comparable functional diversity.
Keywords: Animals; Biological Transport; Chromatin; Cloning, Molecular; Computational Biology; Contig Mapping; Cytochrome P-450 Enzyme System; DNA Repair; DNA Replication; Drosophila melanogaster; Euchromatin; Gene Library; Genes, Insect; Genome; Heterochromatin; Insect Proteins; Nuclear Proteins; Protein Biosynthesis; Sequence Analysis, DNA; Transcription, Genetic

Analysis of the quality and utility of random shotgun sequencing at low redundancies. - Bouck, J; Miller, W; Gorrell, J H; Donna M Muzny; Richard A Gibbs (Genome Res, 1998)
The currently favored approach for sequencing the human genome involves selecting representative large-insert clones (100-200 kb), randomly shearing this DNA to construct shotgun libraries, and then sequencing many different isolates from the library. This method, entitled directed random shotgun sequencing, requires highly redundant sequencing to obtain a complete and accurate finished consensus sequence. Recently it has been suggested that a rapidly generated lower redundancy sequence might be of use to the scientific community. Low-redundancy sequencing has been examined previously using simulated data sets. Here we utilize trace data from a number of projects submitted to GenBank to perform reconstruction experiments that mimic low-redundancy sequencing. These low-redundancy sequences have been examined for the completeness and quality of the consensus product, information content, and usefulness for interspecies comparisons. The data presented here suggest three different sequencing strategies, each with different utilities. (1) Nearly complete sequence data can be obtained by sequencing a random shotgun library at sixfold redundancy. This may therefore represent a good point to switch from a random to directed approach. (2) Sequencing can be performed with as little as twofold redundancy to find most of the information about exons, EST hits, and putative exon similarity matches. (3) To obtain contiguity of coding regions, sequencing at three- to fourfold redundancy would be appropriate. From these results, we suggest that a useful intermediate product for genome sequencing might be obtained by three- to fourfold redundancy. Such a product would allow a large amount of biologically useful data to be extracted while postponing the majority of work involved in producing a high quality consensus sequence.
Keywords: Animals; Contig Mapping; Expressed Sequence Tags; Gene Library; Genome, Human; Humans; Mice; Quality Control; Retrospective Studies; Sequence Analysis, DNA

Comparative sequence analysis of a gene-rich cluster at human chromosome 12p13 and its syntenic region in mouse chromosome 6. - Ansari-Lari, M A; Oeltjen, J C; Schwartz, S; Zhang, Z; Donna M Muzny; Lu, J; Gorrell, J H; Chinault, A C; Belmont, J W; Miller, W; Richard A Gibbs (Genome Res, 1998)
The Human Genome Project has created a formidable challenge: the extraction of biological information from extensive amounts of raw sequence. With the increasing availability of genomic sequence from other species, one approach to extracting coding and regulatory element information is through cross-species sequence comparison. To assess the strengths and weaknesses of this methodology for large-scale sequence analysis, 227 kb of mouse sequence syntenic to a gene-rich cluster on human chromosome 12p13 was obtained. Primarily through percent identity plots (PIPs) of SIM comparative sequence alignments, the sequence of coding regions, putative alternative exons, conserved noncoding regions, and correlation in repetitive element insertions were easily determined. The analysis demonstrated that the number, order, and orientation of all 17 genes are conserved between the two species, whereas two human pseudogenes are absent in mouse. In addition, apart from MIRs, no direct correlation of distribution or position of the majority of repetitive elements between the two species is seen. Finally, in examining the synonymous and nonsynonymous substitution rates in the conserved genes, a large variation in nonsynonymous rates is observed indicating that the genes in this region are diverging at different rates. This study indicates the utility and strength of large-scale cross-species sequence comparisons in the extraction of biological information from raw sequence, especially when combined with other computational tools such as GRAIL and BLAST.
Keywords: Amino Acid Sequence; Animals; Chromosome Mapping; Chromosomes; Chromosomes, Human, Pair 12; Conserved Sequence; Humans; Mice; Molecular Sequence Data; Multigene Family; Repetitive Sequences, Nucleic Acid; Sequence Alignment; Sequence Analysis, DNA

Using BODIPY dye-primer chemistry in large-scale sequencing. - Donna M Muzny; Metzker, M L; Bouck, J; Gorrell, J H; Ding, Y; Maxim, E; Richard A Gibbs (IEEE Eng Med Biol Mag, 1998)
Keywords: Boron Compounds; Chromosome Mapping; DNA Primers; Drug Storage; Fluorescent Dyes; Humans; Quality Control; Reproducibility of Results; Robotics; Sequence Analysis, DNA

Large-scale comparative sequence analysis of the human and murine Bruton's tyrosine kinase loci reveals conserved regulatory domains. - Oeltjen, J C; Malley, T M; Donna M Muzny; Miller, W; Richard A Gibbs; Belmont, J W (Genome Res, 1997)
Large-scale genomic DNA sequencing of orthologous and paralogous loci in different species should contribute to a basic understanding of the evolution of both the protein-coding regions and noncoding regulatory elements. We compared 93 kb of human sequence to 89 kb of mouse sequence in the Bruton's tyrosine kinase (BTK) region. In addition to showing the conservation of both position and orientation of the five functionally unrelated genes in the region (BTK, alpha-D-galactosidase A, L44L, FTP-3, and FCI-12), the comparison revealed conservation of clusters of noncoding sequence flanking the first exon of each gene. Furthermore, in the sequence comparison at the BTK locus, the conservation of clusters of noncoding sequence extends throughout the locus; the noncoding sequence is more highly conserved in the BTK locus in comparison to the flanking loci. This suggests a correlation with the complex developmental regulation of expression of btk. To determine whether a highly conserved 3.5-kb segment flanking the first exon of BTK contains transcriptional regulatory signals, we tested various portions of the segment for promoter and expression activity in several appropriate cell lines. The results demonstrate the contribution of the conserved region flanking the first exon to the cell lineage-specific expression pattern of btk. These data show the usefulness of large scale sequence comparisons to focus investigation on regions of noncoding sequence that play essential roles in complex gene regulation.
Keywords: Agammaglobulinaemia Tyrosine Kinase; alpha-Galactosidase; Animals; Base Sequence; Conserved Sequence; Enhancer Elements, Genetic; Genetic Variation; Humans; Mice; Models, Genetic; Molecular Sequence Data; Promoter Regions, Genetic; Protein-Tyrosine Kinases; Recombinant Proteins; Regulatory Sequences, Nucleic Acid; Repetitive Sequences, Nucleic Acid; Sequence Alignment; Sequence Analysis, DNA; Sequence Homology, Nucleic Acid; Transcription Factors; Transcription, Genetic; Transfection

Large-scale sequencing in human chromosome 12p13: experimental and computational gene structure determination. - Ansari-Lari, M A; Shen, Y; Donna M Muzny; Lee, W; Richard A Gibbs (Genome Res, 1997)
The detailed genomic organization of a gene-dense region at human chromosome 12p13, spanning 223 kb of contiguous sequence, was determined. This region is composed of 20 genes and several other expressed sequences. Experimental tools including RT-PCR and cDNA sequencing, combined with gene prediction programs, were utilized in the analysis of the sequence. Various computer software programs were employed for sequence similarity searches and functional predictions. The high number of genes with diverse functions and complex transcriptional patterns make this region ideal for addressing challenges of gene discovery and genomic characterization amenable to large-scale sequence analysis.
Keywords: Alternative Splicing; Amino Acid Sequence; Chromosome Mapping; Chromosomes, Human, Pair 12; Computational Biology; DNA, Complementary; Exons; Gene Expression; Genomic Library; Glycolysis; Humans; Introns; Molecular Sequence Data; Multigene Family; Nerve Tissue Proteins; Polymerase Chain Reaction; RNA-Directed DNA Polymerase; Sequence Analysis, DNA; Sequence Homology, Amino Acid; Signal Transduction; Software

Molecular and phenotypic variation in patients with severe Hunter syndrome. - Timms, K M; Bondeson, M L; Ansari-Lari, M A; Lagerstedt, K; Donna M Muzny; Dugan-Rocha, S P; Nelson, D L; Pettersson, U; Richard A Gibbs (Hum Mol Genet, 1997)
Severe Hunter syndrome is a fatal X-linked lysosomal storage disorder caused by iduronate-2-sulphatase (IDS) deficiency. Patients with complete deletion of the IDS locus often have atypical phenotypes including ptosis, obstructive sleep apnoea, and the occurrence of seizures. We have used genomic DNA sequencing to identify several new genes in the IDS region. DNA deletion patients with atypical symptoms have been analysed to determine whether these atypical symptoms could be due to involvement of these other loci. The occurrence of seizures in two individuals correlated with a deletion extending proximal of IDS, up to and including part of the FMR2 locus. Other (non-seizure) symptoms were associated with distal deletions. In addition, a group of patients with no variant symptoms, and a characteristic rearrangement involving a recombination between the IDS gene and an adjacent IDS pseudogene (IDS psi), showed normal expression of loci distal to IDS. Together, these results identify FMR2 as a candidate gene for seizures, when mutated along with IDS.
Keywords: Chromosome Mapping; Cloning, Molecular; Electrophoresis, Agar Gel; Gene Deletion; Gene Expression; Gene Rearrangement; Humans; Iduronate Sulfatase; Male; Molecular Sequence Data; Mucopolysaccharidosis II; Nuclear Proteins; Phenotype; Polymerase Chain Reaction; Proteins; Pseudogenes; Recombination, Genetic; Seizures; Trans-Activators; X Chromosome

A gene-rich cluster between the CD4 and triosephosphate isomerase genes at human chromosome 12p13. - Ansari-Lari, M A; Donna M Muzny; Lu, J; Lu, F; Lilley, C E; Spanos, S; Malley, T; Richard A Gibbs (Genome Res, 1996)
The genomic sequence of the human CD4 gene and its neighboring region, located at chromosome 12p13, was generated using the large-scale shotgun sequencing strategy. A total of 117 kb of genomic sequence and approximately 11 kb of cDNA sequence were obtained. Six genes, including CD4, triosephosphate isomerase, B3 subunit of G proteins (GNB3), and ubiquitin isopeptidase T (ISOT), with known functions, and two new genes with unknown functions were identified. Using a battery of strategies, the exon/intron boundaries, splice variants, and tissue expression patterns of the genes were determined. Various computer software was utilized for analyses of the DNA and amino acid sequences. The results of the analyses and sequence-based strategies for gene identification are discussed.
Keywords: Alternative Splicing; Amino Acid Sequence; Base Sequence; CD4 Antigens; Chromosome Mapping; Chromosomes, Human, Pair 12; DNA, Complementary; Humans; Molecular Sequence Data; Multigene Family; Sequence Homology, Amino Acid; Triose-Phosphate Isomerase

Method for 96-well M13 DNA template preparations for large-scale sequencing. - Andersson, B; Lu, J; Edwards, K E; Donna M Muzny; Richard A Gibbs (Biotechniques, 1996)
Efficient preparation of DNA templates is an important step in large-scale DNA sequencing. The ensure high-quality sequence data, we have prepared M13 phage DNA templates using a glass fiber-filtration method. We present the adaptation of this protocol to a 96-well format using commercially available filter plates. Two variations are described: one using polyethylene glycol precipitation and a second where the phage particles are disrupted before filtration, thus eliminating the need for precipitation. Using either of these protocols, 96 templates can be prepared in less than 2 h. Sufficient DNA for 1-2 dye primer sequencing reactions is routinely obtained from 1 mL of culture, and the resulting sequence data are of high quality.
Keywords: Bacteriophage M13; DNA, Viral; Genetic Vectors; Polyethylene Glycols; Polymerase Chain Reaction; Sequence Analysis, DNA; Templates, Genetic

A recombination hotspot responsible for two inherited peripheral neuropathies is located near a mariner transposon-like element. - Reiter, L T; Murakami, T; Koeuth, T; Pentao, L; Donna M Muzny; Richard A Gibbs; James R Lupski (Nat Genet, 1996)
The Charcot-Marie Tooth disease type 1A (CMT1A) duplication and hereditary neuropathy with liability to pressure palsies (HNPP) deletion are reciprocal products of an unequal crossing-over event between misaligned flanking CMT1A-REP repeats. The molecular aetiology of this apparently homologous recombination event was examined by sequencing the crossover region. Through the detection of novel junction fragments from the recombinant CMT1A-REPs in both CMT1A and HNPP patients, a 1.7-kb recombination hotspot within the approximately 30-kb CMT1A-REPs was identified. This hotspot is 98% identical between CMT1A-REPs indicating that sequence identity is not likely the sole factor involved in promoting crossover events. Sequence analysis revealed a mariner transposon-like element (MITE) near the hotspot which we hypothesize could mediate strand exchange events via cleavage by a transposase at or near the 3' end of the element.
Keywords: Amino Acid Sequence; Base Sequence; Charcot-Marie-Tooth Disease; DNA; DNA Transposable Elements; Gene Deletion; Humans; Molecular Sequence Data; Multigene Family; Peripheral Nervous System Diseases; Recombination, Genetic; Repetitive Sequences, Nucleic Acid; Restriction Mapping; Sequence Homology, Amino Acid

130 kb of DNA sequence reveals two new genes and a regional duplication distal to the human iduronate-2-sulfate sulfatase locus. - Timms, K M; Lu, F; Shen, Y; Pierson, C A; Donna M Muzny; Gu, Y; Nelson, D L; Richard A Gibbs (Genome Res, 1995)
Deficiency of IDs activity results in Hunter Syndrome (mucopolysaccharidosis type II), a fatal X-linked recessive disorder. We report characterization of 28 cosmids around the IDS locus in Xq28. Four overlapping cosmids have been sequenced in their entirety generating a 130-kb contig. These studies show the fine structure of the IDS gene and identify an IDS pseudogene-like structure located 20 kb distal to the active gene. Two novel genes have also been identified in this sequence, and one of these genes is also locally duplicated. Both homologs are expressed, and a number of alternative transcript products have been characterized. The presence of a highly conserved pseudogene-like structure within a larger duplicated region close to the IDS gene has significant implications for the study of mutations at this locus.
Keywords: Base Sequence; Chromosome Walking; Chromosomes, Artificial, Yeast; Cosmids; Gene Expression; Genes; Genetic Markers; Humans; Iduronate Sulfatase; Male; Mucopolysaccharidosis II; Multigene Family; Polymerase Chain Reaction; Pseudogenes; Repetitive Sequences, Nucleic Acid; RNA, Messenger; Sequence Alignment; Transcription, Genetic; X Chromosome

Complete sequence of a 38.4-kb human cosmid insert containing the polymorphic marker DXS455 from Xq28. - Andersson, B; Lu, F; Donna M Muzny; Warren, S T; Richard A Gibbs (DNA Seq, 1995)
The complete DNA sequence of a cosmid mapping to human Xq28 (DXS455) has been determined using a shotgun approach (genbank accession number: L31948). The cosmid insert is 38.4 kb in length, and contains several repetitive sequences, including a highly repetitive region located in a fragment previously shown to contain a polymorphic VNTR locus, as well as short di- and tri-nucleotide repeats. In addition to the previously known VNTR locus, a CA-repeat and an unusual 800-bp repetitive region have been found to be polymorphic. The repeated sequence mapping to the site of the VNTR locus spans 480 bp in the cosmid. In addition to several AT-dinucleotide stretches, this repeat has four copies of a 25 bp repeat unit and flanking sequences similar to this 25-mer. No expressed sequences have so far been identified in this cosmid.
Keywords: Bacteriophage M13; Base Sequence; Cosmids; DNA; Gene Library; Genetic Markers; Humans; Minisatellite Repeats; Molecular Sequence Data; Repetitive Sequences, Nucleic Acid; X Chromosome

Sixty-nine kilobases of contiguous human genomic sequence containing the alpha-galactosidase A and Bruton's tyrosine kinase loci. - Oeltjen, J C; Liu, X; Lu, J; Allen, R C; Donna M Muzny; Belmont, J W; Richard A Gibbs (Mamm Genome, 1995)
Several disease loci have been mapped to the Xq21.3-Xq22 region of the human X Chromosome (Chr) including X-linked agammaglobulinemia (XLA), Fabry disease, Alport syndrome, and Pelizaeus Merzbacher disease. Upon cloning of the XLA gene, Bruton's tyrosine kinase (btk), both Fabry disease and XLA were mapped within the same 50- to 70-kb interval. In order to investigate the genomic organization of the region surrounding btk and the Fabry disease gene, alpha-galactosidase A (gla), we constructed a 6-cosmid contig spanning the region from 5' of gla to 3' of btk. Two of these cosmids spanning most of the coding sequence and the upstream region of btk and gla, U237D10 and U230D1, were sequenced by a random shotgun strategy combined with automated sequencing, resulting in 69 kb of contiguous genomic sequence. Sequencing of U237D10 showed btk to be comprised of 19 exons spanning over 35 kb. Sequencing of U230D1 showed that the 3' end of gla is 9 kb from the 5' end of btk and also demonstrated the presence of two additional genes in the region immediately 5' to btk. The surprisingly high gene density is similar to that seen previously only in the human major histocompatibility locus.
Keywords: Agammaglobulinaemia Tyrosine Kinase; alpha-Galactosidase; Amino Acid Sequence; Base Sequence; Cosmids; Fabry Disease; Gene Library; Humans; Introns; Molecular Sequence Data; Protein-Tyrosine Kinases; Repetitive Sequences, Nucleic Acid; X Chromosome

Adaptor-based uracil DNA glycosylase cloning simplifies shotgun library construction for large-scale sequencing. - Andersson, B; Povinelli, C M; Wentland, M A; Shen, Y; Donna M Muzny; Richard A Gibbs (Anal Biochem, 1994)
An improved strategy for the preparation of libraries for the random sequencing of DNA is reported. The protocol is a modification of a previous adaptor-based strategy, and utilizes long (11 base) overhangs, which eliminates the unreliable step of vector-insert ligation. The random inserts are prepared by adaptor ligation, while the M13 vector is prepared as described for uracil DNA glycosylase (UDG) cloning of polymerase chain reaction (PCR) products, using PCR with uracil-containing primers, followed by UDG treatment to produce overhangs. This method has been found to reliably yield large numbers of clones. There is no background due to religation of the vector, and all clones contain inserts. In addition, the method is simple and suitable for export to other investigators. Libraries were constructed from cosmids containing human DNA and from human cDNAs in order to characterize a strategy for shotgun sequencing of multiple shorter fragments.
Keywords: Base Sequence; Cloning, Molecular; DNA Glycosylases; DNA Primers; DNA, Complementary; Genomic Library; Humans; Molecular Sequence Data; N-Glycosyl Hydrolases; Polymerase Chain Reaction; Sequence Analysis, DNA; Uracil-DNA Glycosidase

Expression of the murine Duchenne muscular dystrophy gene in muscle and brain. - Chamberlain, J S; Pearlman, J A; Donna M Muzny; Richard A Gibbs; Ranier, J E; Caskey, C T; Reeves, A A (Science, 1988)
Complementary DNA clones were isolated that represent the 5' terminal 2.5 kilobases of the murine Duchenne muscular dystrophy (Dmd) messenger RNA (mRNA). Mouse Dmd mRNA was detectable in skeletal and cardiac muscle and at a level approximately 90 percent lower in brain. Dmd mRNA is also present, but at much lower than normal levels, in both the muscle and brain of three different strains of dystrophic mdx mice. The identification of Dmd mRNA in brain raises the possibility of a relation between human Duchenne muscular dystrophy (DMD) gene expression and the mental retardation found in some DMD males. These results also provide evidence that the mdx mutations are allelic variants of mouse Dmd gene mutations.
Keywords: Animals; Brain; DNA; DNA, Recombinant; Gene Expression Regulation; Intellectual Disability; Mice; Mice, Inbred ICR; Mice, Mutant Strains; Muscles; Muscular Dystrophy, Animal; Mutation; Nucleic Acid Hybridization; Ribonuclease, Pancreatic; RNA, Messenger

Generation of cDNA probes directed by amino acid sequence: cloning of urate oxidase. - Lee, C C; Wu, X W; Richard A Gibbs; Cook, R G; Donna M Muzny; Caskey, C T (Science, 1988)
Urate oxidase (E.C. 1.7.3.3) catalyzes the oxidation of uric acid to allantoin in most mammals except humans and certain primates. The amino-terminal amino acid sequence for porcine urate oxidase was determined and used in a novel procedure for generating complementary DNA (cDNA) probes to this amino acid sequence. The procedure is based on the polymerase chain reaction and utilizes mixed oligonucleotide primers complementary to the reverse translation products of an amino acid sequence. This rapid and simple cDNA cloning procedure is generally applicable and requires only a partial amino acid sequence. A cDNA probe developed by this procedure was used to isolate a full-length porcine urate oxidase cDNA and to demonstrate the presence of homologous genomic sequences in humans.
Keywords: Amino Acid Sequence; Animals; Base Sequence; Cloning, Molecular; DNA; Gene Amplification; Liver; Mice; Molecular Sequence Data; Nucleic Acid Hybridization; Swine; Urate Oxidase